The Rejection Sensitivity Model as a Framework for Understanding Sexual Minority Mental Health. - Feinstein, Brian A. (Archives of Sexual Behavior, 2020)
Sexual minorities are disproportionately affected by mental health problems (e.g., depression, anxiety, substance use disorders, suicidality). Minority stress theory and the psychological mediation framework have become the predominant conceptual models used to explain these disparities, and they have led to substantial advances in research on stigma-related stress and mental health. However, the field's reliance on these models has limited the extent to which other theories have been considered as potential frameworks for further advancing our understanding of sexual minority mental health. In this article, I discuss how the rejection sensitivity (RS) model can be used to complement and extend minority stress theory and the psychological mediation framework by: (1) emphasizing the role of perception in stigma-related experiences; (2) acknowledging the unique consequences of different anticipatory emotions; (3) describing additional mechanisms linking proximal minority stressors to mental health; and (4) further specifying the temporal order of these processes. I conclude by discussing the importance of attending to developmental processes in research on sexual orientation-related RS and describing important directions for future research. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minorities; Minority stress; Sexual orientation; Gay people; Lesbians; Bisexuals; Gay, lesbian, and bisexual; Rejection sensitivity; Sexual minority

Suicidality risk among adult sexual minorities: Results from a cross-sectional population-based survey. - Haney, Jolynn L. (Journal of Gay & Lesbian Social Services, 2021)
Suicide among sexual minority adults is a serious public health issue. Data from the National Survey of Drug Use and Health (2015–2018) were analyzed to evaluate factors associated with past-year suicidality risk (thoughts, plans, or attempts) and self-reported sexual identity. Findings support previous research that sexual minority groups have a higher risk of suicidality compared to heterosexuals. Additionally, significant within-group gender differences were found for bisexuals with reported past-year suicide attempts. The risk ratio trajectory from suicidal ideation to suicidal attempt was the most striking for the gay and lesbian group compared to other populations. Implications and recommendations for future research are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minorities; Suicidal ideation; Adults; Minorities; Attempted suicide; NSDUH; sexual identity; sexual minority; sexual orientation; suicidality; suicide attempts; suicide plans; suicide thoughts

Sexual violence among men who have sex with men and two-spirit peoples: A scoping review. - Dame, Jessy; Oliffe, John L.; Hill, Nolan; Carrier, Leah; Evans-Amalu, Kelsey (Canadian Journal of Human Sexuality, 2020)
Sexual violence (SV) is a human rights and public health issue that impacts people from all communities. Men who have sex with men/Two-Spirit (MSM/2S) peoples are up to six times more likely to experience SV compared to heterosexual men. In addition, MSM/2S people are less likely to report SV. Reasons for this lack of reporting include male rape myths, fear of judgment, stigma, shame, homophobia, and/or lack of access to supportive services. The current scoping review offers a synthesis of the recent literature regarding SV among MSM/2S peoples in order to make research, practice, and policy recommendations. Findings indicated consistent SV risk factors, associated negative health outcomes, and barriers to accessing services. Risk factors included being younger, inexperience in MSM/2S communities, and having a history of sexual abuse or violence. Negative health outcomes included increased risk for HIV, depression, anxiety, heart disease, fear, eating disorders, substance use, social isolation, PTSD, and suicide. Help-seeking barriers included limited support services, lack of reporting, and male rape myths. Policy recommendations include targeted efforts to raise awareness of SV among MSM/2S peoples, and affirming the legitimacy of reporting SV through specialized healthcare services and trained professionals. [ABSTRACT FROM AUTHOR]
Keywords: Masculinity; Medical care; Sex crimes; LGBTQ+ people; Men who have sex with men; Evaluation of medical care; Systematic reviews (Medical research); Literature reviews; men who have sex with men (MSM); sexual violence; two-spirit (2S)

High Burden of Mental Health Problems, Substance Use, Violence, and Related Psychosocial Factors in Transgender, Non-Binary, and Gender Diverse Youth and Young Adults. - Newcomb, Michael E.; Hill, Ricky; Buehler, Kathleen; Ryan, Daniel T.; Whitton, Sarah W.; Mustanski, Brian (Archives of Sexual Behavior, 2020)
Transgender and gender diverse (TGD) people are disproportionately impacted by various health issues and associated risk factors, but little is known about differences in these outcomes between gender identities within the TGD population. This study characterized the health of a diverse sample of TGD youth and young adults. Data were taken from the baseline visit of two longitudinal studies in the Chicago area, RADAR (N = 1079, M age = 20.8 years) and FAB 400 (N = 488, M age = 19.57 years), which are cohorts of young sexual and gender minorities assigned male at birth (AMAB) and assigned female at birth (AFAB), respectively. There was a combined sample of 214 TGD (128 AFAB, 86 AMAB) individuals across cohorts. We examined differences between gender identities in self-reported health and related psychosocial variables, and compared TGD youth and their cisgender sexual minority peers from their cohort of origin on all variables. Among TGD youth, we found high rates of depression and suicidality (ideation, plan, attempt), violence (trauma, victimization, childhood sexual abuse), and substance use (cigarette, alcohol, illicit drug use). With the exception of depression, transgender women and non-binary AMAB youth reported worse health outcomes than transgender men and non-binary AFAB youth. Non-binary AMAB youth reported the highest rates of certain outcomes, including traumatic experiences and suicidal ideation. TGD youth generally reported worse outcomes than cisgender sexual minority youth; these differences were less pronounced among AFAB youth. Findings point to the diversity of experiences within the TGD population and critical needs for intervention approaches to mitigate health disparities. [ABSTRACT FROM AUTHOR]
Keywords: Transgender youth; Transgender young adults; Gender-nonconforming people; LGBTQ+ people -- Alcohol use; Mental health of LGBTQ people; Suicide; Mental depression; Gender identity; Mental health; Non-binary; Substance use; Transgender; Violence

Logging Out: The Inadequacies of Current Cyberbullying Remedies and Their Impact on LGBTQ+ Youth. - Zhang, Elizabeth (Law & Sexuality: A Review of Lesbian, Gay, Bisexual & Transgender Legal Issues, 2020)
The article discusses the effects of cyberbullying on lesbian, gay, bisexual, transgender, and queer (LGBTQ+) youth and the legality of regulating youth-on-youth cyberbullying by schools. Also cited are the challenges faced by schools in disciplining students for speech online or electronic communication without violating their First Amendment rights to freedom of speech, LGBTQ+ suicide, and the remedies against cyberbullying for secondary and college students and schools.
Keywords: Cyberbullying; LGBTQ+ youth; Suicide; Freedom of speech; Cyberbullying laws; Prevention of cyberbullying; School discipline

Interpersonal Psychotherapy for Gender Dysphoria in a Transgender Woman. - Barbisan, Guilherme Kirsten; Moura, Daniel Heidemman; Lobato, Maria Inês Rodrigues; da Rocha, Neusa Sica (Archives of Sexual Behavior, 2020)
We present a case of a 32-year-old natal male seeking medical follow-up care, due to gender dysphoria (GD) along with other complaints (depressive symptoms, anxiety, and suicidal ideation). The attending team chose interpersonal psychotherapy (IPT), with a focus on role transition in order to help her. The patient presented a favorable trajectory throughout treatment and demonstrated personal growth one year after treatment. To our knowledge, little was found in the literature on the use of IPT in the treatment of those with GD; we also did not find any other publication or case report using IPT exclusively to treat the problems accompanying role transition. Psychotherapy was not intended to change the gender identity of this individual. However, further studies will be required to explore possible benefits of IPT for GD treatment. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Gender dysphoria; Gender identity; Anxiety; Suicidal ideation; Interpersonal psychotherapy; Mental depression; Psychotherapy; Role transition

A Post-Hoc Comparison of Two Sexual Health Curricula on Sexual Health Knowledge, Perception, and Attitudes. - Son, Juyeon; Draws, Cindy (American Journal of Sexuality Education, 2021)
A post-hoc study was conducted to ascertain the effect of comprehensive sex education on of 7th graders' knowledge, perceptions, and attitudes regarding sexual health and sexual identities in a small city school district in the Midwest USA. All five middle schools in the district participated, three of which used a comprehensive curriculum and two taught their existing curriculum. A total of 260 online surveys were completed by the 7th graders through Qualtrics. Chi-square tests were conducted, and the outcome showed a statistically significant difference in student perception and attitudes regarding sexual identity and orientation between the two curriculum groups. The comprehensive curriculum group scored higher than the existing curriculum group on items that indicate openness and respect regarding diversity in sexual identities and orientation. Given that LGBTQ+ students are at a greater risk to engage in self-harm and suicidal attempts, the outcome potentially suggests that a more open and accepting school atmosphere can be created by the implementation of a comprehensive sexual health curriculum. It implies that a purposive, systematic, and longitudinal effort to provide comprehensive sexual health education could also help reduce the challenges LGBTQ+ youth face outside of school. [ABSTRACT FROM AUTHOR]
Keywords: Gay community; Sexual health; LGBTQ+ youth; LGBTQ+ students; Bisexuality; Health literacy; Student attitudes; Middle school student attitudes; Midwest (U.S.); Adolescent health; and plus (LGBTQ+) health; bisexual; community-based participatory research; comprehensive sexual health curriculum; gay; lesbian; questioning; sexuality; transgender

Social and Medical Gender Affirmation Experiences Are Inversely Associated with Mental Health Problems in a U.S. Non-Probability Sample of Transgender Adults. - Hughto, Jaclyn M. W.; Gunn, Hamish A.; Rood, Brian A.; Pantalone, David W. (Archives of Sexual Behavior, 2020)
A dearth of research has explored concurrently the associations between multiple forms of gender affirmation (or transitioning) and the mental health of transgender adults. In 2015, 288 U.S. transgender adults completed a cross-sectional, online survey assessing demographics, gender affirmation experiences, and mental health. Adjusting for age and discrimination experiences, we used mixed-effect logistic regression analyses to examine changes in self-reported suicidal ideation, suicide attempts, and non-suicidal self-injury (NSSI) before and after initiating the gender affirmation process, and linear regression analyses to examine associations between gender affirmation experiences and self-reported depressive, anxiety, and stress symptoms. Overall, 81.3% of participants identified along the female-to-male, trans masculine gender spectrum (of which 20.9% identified as non-binary) and 18.8% identified along the male-to-female, trans feminine gender spectrum (of which 7.4% identified as non-binary). Nearly all participants (98.6%) reported disclosing their gender identity to family or a coworker; 67.4% endorsed recently using hormones, and 31.3% endorsed a gender-affirming medical procedure. In multivariable models, participants were at greater odds of NSSI, contemplating suicide, and attempting suicide before initiating the gender affirmation process compared to after. In additional models, gender identity disclosure and medical procedure engagement were inversely associated with depressive and anxiety symptoms, whereas gender identity disclosure, hormone use, and medical procedure engagement were inversely associated with stress symptoms. Finally, the number of gender affirmation experiences endorsed was inversely associated with depressive, anxiety, and stress symptoms. Findings support the possibility that social and medical gender affirmation experiences may be protective against mental health problems in transgender adults. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Mental health; Suicide; Self-mutilation; Gender identity; Gender affirmation; Self-harm; Transgender

Using Photovoice to Understand Suicidality Among Gay, Bisexual, and Two-Spirit Men. - Ferlatte, Olivier; Oliffe, John L.; Salway, Travis; Broom, Alex; Bungay, Victoria; Rice, Simon (Archives of Sexual Behavior, 2019)
This study explored the drivers of suicidality from the perspectives of gay, bisexual, and two-spirit men (GB2SM) with a history of suicidality. Twenty-one GB2SM participated in this photovoice study taking photographs to depict and discuss their previous suicidality. Data were collected from in-depth individual interviews in which participants discussed their photographs and in turn offered verbal/narrative accounts of suicidality. Drawing on intersectionality, analyses of the photographs and interview data revealed three interconnected themes. First, adverse childhood events and negative adolescent experiences were described as the root causes of mental health struggles and suicidality. Second, violence and homophobia had disrupted these men's education and employment opportunities and some participants detailed how their lack of capital and challenges for maintaining employment shaped their suicidality. Third, a sociality of stigma and sense of isolation compounded experiences of suicidality. The three themes overlapped and were shaped by multiple intersectional axes including sexuality, class, ethnicity, and mental health status. The findings have implications for services and health professionals working with GB2SM who need to thoughtfully consider life-course trajectories and multiple social axes when assessing and treating GB2SM experiencing suicidality. More so, because these factors relate to social inequities, structural and policy changes warrant targeted attention. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Two-spirit people; Psychology of gay people; Psychology of lesbians; Bisexuals; Photovoice (Social action programs); Gay and bisexual men's health; Intersectionality; Male suicide; Photovoice; Sexual orientation

Suicidal Tendencies: Notes toward a Queer Narratology. - Seitler, Dana (GLQ: A Journal of Lesbian & Gay Studies, 2019)
This essay concentrates on a series of suicide plots in which the risk of one's undoing does not indicate a refusal of one's existing life as much as it performs a fantastic desire to live a different one. Willa Cather's short story "Paul's Case" (1905), Ridley Scott's Thelma and Louise (1991), and Alejandro G. Iñárritu's Birdman (2014) help us think about how suicide functions as a sustaining fantasy and a queer narrative strategy. In each, the main character's retreat into suicidal fantasy is not limiting but productive: it creates a space of protection for otherwise damaged individuals, allowing them to imagine an alternative configuration as/at the end of their world. This essay thus makes the counterintuitive claim that the suicide plot should be read non-tragically. It considers how acts of self-annihilation force us to think about the binding narratives of gendered and sexualized person-hood. If these narratives most readily seem to forward a critique of the hetero and sexist norms for life, they also offer a compelling argument about how the use of death works to imagine new forms, narratives, and possibilities of living. [ABSTRACT FROM AUTHOR]
Keywords: Suicide; LGBTQ+ people; Fantasy; Narration (Rhetoric); Tragedy (Trauma); Life; death drive; narrative closure; queer form; queer narratology; suicide plots

An Intersectional Analysis of LGBTQ Online Media Coverage of the Pulse Nightclub Shooting Victims. - Meyer, Doug (Journal of Homosexuality, 2020)
This study illustrates the radical potential of intersectionality to offer a more deeply critical analysis of hierarchies in lesbian, gay, bisexual, transgender, and queer (LGBTQ) communities. The author examines how 377 reports from the five most-trafficked LGBTQ Web sites represented victims of the Pulse nightclub shooting in Orlando, FL. Findings support previous scholarship that has emphasized Latinx exclusion, as the articles generally failed to present the victims in an intersectional way, focusing on their LGBTQ status and excluding their Latinx identities. At the same time, a significant minority of the reports emphasized Latinx queer people, most frequently in a way that continued to prioritize LGBTQ identification, sometimes even advancing stereotypical representations of Latinx communities as extraordinarily focused on faith, family, or "machismo." Moreover, none of the articles considered xenophobia as a potential motivating factor in the shooting, and the reports typically presented policing agencies in a neutral, and sometimes even positive, way. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ communities; Orlando Nightclub Massacre, Orlando, Fla., 2016; Intersectionality; Racism; Online social networks; Shootings (Crime); Massacre survivors; Hierarchies; anti-transgender violence; immigration; intersectionality theory; Latina; Latino; Latinx; mass shootings; Pulse nightclub shooting; race/ethnicity; racism in LGBTQ communities

"Alone in the Rain(bow)": Existential Therapy for Loneliness in LGBTQ + Clients. - Ratanashevorn, Rattanakorn; Brown, Emily C. (Journal of LGBT Issues in Counseling, 2021)
Loneliness and isolation are major concerns for LGBTQ + clients who experience marginalization, discrimination and alienation in society and social networks. These experiences of increased loneliness and isolation can lead to other detrimental mental health outcomes, such as substance abuse, HIV, and suicide. Loneliness and isolation are central concerns of existential therapy which makes this a compatible approach for addressing these issues among LGBTQ + clients. This article uses an existential therapy lens to examine the issue of loneliness among LGBTQ + clients and provides a case illustration to demonstrate its application. [ABSTRACT FROM AUTHOR]
Keywords: Psychology of LGBTQ+ people; Social networks; Mental health; Social isolation; Loneliness; Psychotherapy; Mental illness treatment; existential isolation; existential therapy; LGBTQ+

Examining the Association between Weapon Carrying on School Property and Suicide Attempt among Adolescents in the United States. - Baiden, Philip; Tadeo, Savarra K.; Graaf, Genevieve; Respress, Brandon N. (Social Work in Public Health, 2019)
Suicidal behaviors among adolescents in the United States are the second leading cause of death and has been steadily increasing over the years. Although access to and possession of a weapon may facilitate the transition from suicidal ideation to a suicide attempt, few studies have examined the association between weapon carrying and suicide attempts among adolescents. The objective of this study was to examine the association between weapon carrying on school property and suicide attempt among adolescents. Data for this study came from the 2017 Youth Risk Behavior Surveillance System. A sample of 14,547 adolescents aged 14-18 years old (50.5% female) was analyzed using logistic regression. Of the 14,547 adolescents, 4% carried a weapon on school property, and 7.7% attempted suicide during the past 12 months. In the multivariate logistic regression, adolescents who reported carrying a weapon on school property had more than double the odds of attempting suicide when compared to their counterparts who did not carry a weapon on school property. Other significant predictors of suicide attempt include sexual minority, history of forced sexual intercourse, school bullying and cyberbullying victimization, feeling sad or hopeless, and substance use. Examining the association between weapon carrying and suicide attempt among adolescents would contribute to early identification of adolescents who are likely to engage in suicidal behaviors. [ABSTRACT FROM AUTHOR]
Keywords: Suicide victims; Suicidal behavior; Teenagers; Sexual minorities; Suicidal ideation; School bullying; At-risk youth; United States; adolescents; suicide attempt; victimization; Weapon carrying

Extending a Rejection Sensitivity Model to Suicidal Thoughts and Behaviors in Sexual Minority Groups and to Transgender Mental Health. - Wells, Tony T.; Tucker, Raymond P.; Kraines, Morganne A. (Archives of Sexual Behavior, 2020)
The authors comment on an article by B. A. Feinstein on how a rejection sensitivity (RS) model contributes to the understanding of the etiology and maintenance of mental health issues in sexual minorities. Topics include areas deserving of additional consideration in the context of developing RS model, RS sensitivity application to transgender and gender diverse individuals, and the potential for the RS model proposed by Feinstein to contribute to understanding of sexual minority mental health.
Keywords: Rejection (Psychology); Sexual minorities; Transgender people; Mental health; Sensitivity (Personality trait)

Responsible journalism, imitative suicide, and transgender populations: A systematic review of UK newspapers. - Bolzern, Jaime E.; Mnyama, Nandi L.; McMillan, Dean (Journal of Gay & Lesbian Mental Health, 2019)
Purpose: The risk of suicide is high in the transgender population. Imitative suicide occurs when excess suicidal behavior is observed following news media coverage of suicide. The purpose of this study is to evaluate how often UK newspapers adhere to suicide reporting guidelines designed to minimize imitative suicide when they report the suicides of transgender individuals. Methods: A newspaper archive was searched for articles about the suicides of transgender people published between 2007 and 2017. Two reviewers applied a checklist of responsible reporting practices to assess adherence to guidelines. Results: There were 79 articles meeting inclusion criteria. The mean number of guideline breaches was 3.9 (of a maximum 10), with the most commonly breached guidelines an inappropriate headline (70.9%) and failure to provide sources of support (60.8%). Every article breached at least one guideline. There was not a significant difference between the different newspapers in mean number of guideline breaches (p = 0.24). Conclusion: There is generally poor adherence to responsible reporting guidelines in UK newspapers when reporting the suicides of transgender people. [ABSTRACT FROM AUTHOR]
Keywords: Suicide; Suicidal behavior; Newspapers; Press; Meta-analysis; Great Britain; Journalism; LGBT; mental illness; suicide; transgender

Non-binary and binary transgender youth: Comparison of mental health, self-harm, suicidality, substance use and victimization experiences. - Rimes, Katharine A.; Goodship, Nicola; Ussher, Greg; Baker, Dan; West, Elizabeth (International Journal of Transgenderism, 2019)
Background: Little research has compared the mental health and victimization experiences of non-binary youth depending on their sex assigned at birth (SAAB), or compared these two groups with binary transgender youth. Aims: To compare mental health, self-harm and suicidality, substance use and victimization experiences between non-binary and binary transgender young adults, both male assigned at birth (MAAB) and female assigned at birth (FAAB). Methods: Online survey data from 677 participants from the "Youth Chances" community study of 16 to 25 year olds in the United Kingdom was analyzed, comparing across binary participants (transgender females (n = 105) and transgender males (n = 210)) and non-binary participants (MAAB (n = 93) and FAAB (n = 269)). Results: Female SAAB participants (binary and non-binary) were more likely to report a current mental health condition and history of self-harm than male SAAB participants (binary and non-binary). Similarly, female SAAB participants (binary and non-binary) were more likely to report childhood sexual abuse than male SAAB participants (binary and non-binary); the reverse pattern was found for lifetime physical assault relating to being LGBTQ. Non-binary MAAB participants were less likely than the other groups to report past suicide attempts and previous help-seeking for depression/anxiety. Binary participants reported lower life satisfaction than non-binary participants. For all four groups, mental health problems, self-harm, suicidality, alcohol use and victimization experiences were generally higher than that of youth in general population studies. Conclusions: These findings highlight the importance of considering both non-binary versus binary gender identity and SAAB in relation to mental health problems, self-harm, suicidality and substance use in transgender youth. The roles of sexual abuse, other abuse and discrimination in contributing to increased rates of mental illness and self-harm in non-binary and binary transgender individuals, particularly those who were assigned female at birth, relative to those assigned male, require investigation. [ABSTRACT FROM AUTHOR]
Keywords: Alcoholism; Anxiety; Child sexual abuse; Discrimination; Gender identity; Mental illness; Satisfaction; Self-mutilation; Substance abuse; Suicidal behavior; Crime victims; LGBTQ+ people; Transgender people; Suicidal ideation; Assault & battery; Mental depression; Health status indicators; Help-seeking behavior; Surveys; Psychosocial factors; Great Britain; Abuse; discrimination; gender identity; gender-nonconformity; genderqueer; mental illness

Late-Onset Transgender Identity Development of Adolescents in Psychotherapy for Mood and Anxiety Problems: Approach to Assessment and Treatment. - Sevlever, Melina; Meyer-Bahlburg, Heino F. L. (Archives of Sexual Behavior, 2019)
The rate of adolescents with gender-nonconforming behavior and/or gender dysphoria seeking mental health care has dramatically increased in the past decade. Many of these youths also present with co-occurring psychiatric problems, including depression, anxiety, suicidality, substance use, and others. This combination may generate a complex clinical picture that challenges the ability of clinicians to accurately diagnose gender distress and develop suitable treatment recommendations. This article illustrates those challenges with two adolescent patients who developed late-onset gender dysphoria in the course of long-term mental health care for diverse psychiatric problems preceding the emergence of gender dysphoria. One underwent full progression from gender dysphoria as a male through social and medical transition to female, the other a less definitive progression from gender dysphoria as female through social transition to male without deciding for any medical treatment. The report provides details on the assessment procedures and the resulting findings, the rationale for treatment recommendations, and short-term follow-up information. [ABSTRACT FROM AUTHOR]
Keywords: Transgender identity; Transgender teenagers; Psychotherapy; Gender dysphoria; Transgender people; Mental health of teenagers; Adolescence; Transgender

Suicidal and Help-Seeking Behaviors Among Youth in an Online Lesbian, Gay, Bisexual, Transgender, Queer, and Questioning Social Network. - Lytle, Megan C.; Silenzio, Vincent M. B.; Homan, Christopher M.; Schneider, Phoenix; Caine, Eric D. (Journal of Homosexuality, 2018)
LGBTQ youth have a great burden for suicidal ideation/behavior compared to their non-LGBTQ peers. While scholars have explored risk factors for suicidal behaviors, little is known about protective factors among LGBTQ youth, let alone within group differences in terms of help-seeking. Data were collected from 203 TrevorSpace (e.g., a social network for LGBTQ youth) users via online survey to examine suicidal and help-seeking behaviors among LGBTQ individuals. Among participants who reported suicidal ideation/behavior, a large proportion did not seek help (73.1% of gay men, 33.3% of bisexual men, 42.9% of bisexual women, 14.3% of lesbian women, 41.2% of queer individuals) when they considered or attempted suicide. Among those who sought support, reaching out to a friend was most common. However, family support was associated with fewer suicidal behaviors. Our findings underscore the need to examine the effectiveness of specific sources of help and the impact of exposure to social connectedness. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ youth; Suicidal behavior; Suicidal ideation; Families of LGBTQ+ people; Friendship; Help-seeking behavior; Online social networks; LGBTQ youth; protective factors; Risk factors; suicidal ideation; suicide attempt

LGBQ+ Self-Acceptance and Its Relationship with Minority Stressors and Mental Health: A Systematic Literature Review. - Camp, Jake; Vitoratou, Silia; Rimes, Katharine A. (Archives of Sexual Behavior, 2020)
Many individuals who identify as lesbian, gay, bisexual, queer, and with other non-heterosexual orientations (LGBQ+) experience stigma, prejudice, and/or discrimination because of their sexuality. According to minority stress and identity development theories, these experiences can contribute to difficulties with self-acceptance of sexuality. Lower self-acceptance is considered a risk factor for adverse mental health outcomes. The current review aims to investigate whether self-acceptance of sexuality is associated with minority stressors or difficulties with mental health in LGBQ+ individuals, as well as whether there are differences in self-acceptance between different sexual orientations. Five bibliographic databases were searched. Thirteen studies were identified which used quantitative methodology to investigate associations between self-acceptance, minority stressors, and/or mental health within LGBQ+ samples, or differences in self-acceptance between different sexual orientations. The results from these cross-sectional studies suggested that lower self-acceptance of sexuality was associated with higher levels of self-reported minority stressors, including a lack of acceptance from friends and family, a lack of disclosure to others, and internalized heterosexism. Lower self-acceptance of sexuality was associated with poorer mental health outcomes, including greater global distress, depression symptoms, and lower psychological well-being. There was no significant relationship with suicidality. Studies also found that LGBQ+ individuals had lower general self-acceptance compared to heterosexual participants, bisexual individuals had lower sexuality self-acceptance compared to lesbian/gay individuals, and lesbian women had lower sexuality self-acceptance compared to gay men. Given the potential importance of self-acceptance for LGBQ+ populations, further research is required with more robust methodology. Self-acceptance could be a potential target in clinical interventions for LGBQ+ individuals. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Self-acceptance; Minority stress; Mental health; Sexual orientation; Human sexuality; Sexuality

Sexual identity modifies the association between bullying and suicide planning among adolescents with same-sex sexual partners. - Turpin, Rodman; Boekeloo, Bradley; Dyer, Typhanye (Journal of LGBT Youth, 2019)
Heterosexual adolescents with same-sex sexual partners may be at increased risk for psychological distress from victimization; this may lead to suicidality. We tested if sexual identity modified the association between bullying at school and suicide planning among adolescents with the same-sex sexual partners. We sampled 924 youth with same-sex sexual partners from the 2015 Youth Risk Behavior Survey, testing the association between bullying and suicide planning using log-binomial regression with sexual identity interactions. Sexual identity modified this association, with the greatest association among heterosexual participants (PR = 4.01, 95% CI 2.60–6.18). Anti-homophobia messaging and intervention programs that target these youth may be needed. [ABSTRACT FROM AUTHOR]
Keywords: Heterosexuals; Psychology of gay people; Suicidal ideation; Sexual orientation identity; Sexual partners; Adolescence; Bullying & psychology; School violence & psychology; Risk factors in suicidal behavior; Confidence intervals; Questionnaires; Regression analysis; Surveys; Teenagers' conduct of life; Psychosocial factors; Bullying; identity; LGB; sexuality; suicide

The association between HIV/AIDS and childhood sexual abuse: An exploratory case study. - Diao, Xavier Y.; Albert, Madeline; Forstein, Marshall (Journal of Gay & Lesbian Mental Health, 2019)
The effects of sexual abuse in childhood are serious and far-reaching, and include a number of short- and long-term sequelae, including depression, anxiety, disordered eating, post-traumatic stress disorder (PTSD), substance abuse disorders, suicidal ideation and self-injurious behavior, sexual dysfunction, borderline personality traits, high-risk sexual behavior, and dissociative disorders. MSM (men who have sex with men) with a history of childhood sexual abuse are more likely to engage in high-risk sexual behavior, trade sex for substances and/or money, experience intimate partner violence, and report as being HIV-positive. In this case study, we aim to explore the association between sexual abuse in childhood and HIV/AIDS. We identify a HIV-positive gay man with a history of sexual abuse and review the existing literature on the subject of HIV and sexual abuse, with a focus on victims who are MSM. Early childhood traumas, especially sexual abuse, can have immense and long-lasting psychological sequelae. Here, we report a victim of childhood sexual abuse who suffers from PTSD, selective amnesia, and episodes of dissociation during sex who was diagnosed as being HIV-positive at the height of the HIV/AIDS epidemic in the United States. More research needs to be done to investigate the complex relationship between childhood trauma and HIV infection, with insights into racial, gender, and socioeconomic differences. Counseling and risk-reduction strategies need to be explored with patients with a history of sexual trauma, in tandem with long-term pharmacologic and therapeutic interventions. [ABSTRACT FROM AUTHOR]
Keywords: Child sexual abuse; Men's sexual behavior; AIDS; Human sexuality; Intimate partner violence; HIV infections; Self-injurious behavior; United States; HIV; LGBT; sexual abuse

Peer victimization and suicidality among LGBTQ youth: the roles of school belonging, self-compassion, and parental support. - Hatchel, Tyler; Espelage, and Dorothy; Merrin, Gabriel J. (Journal of LGBT Youth, 2019)
Research on lesbian, gay, bisexual, transgender and questioning (LGBTQ) youth's experiences at school has largely focused on stigma, adversity, disparities, and peer victimization. Factors like school climate, individual differences, and social support have also garnered significant attention. However, there has been a dearth of research examining how they relate to both suicidal ideation and suicide attempts. Our goal was to bolster the extant literature by examining the protective role of parental support and psychological mechanisms like school belonging and self-compassion among LGBTQ youth struggling with peer victimization and suicidality. A cross-sectional study was completed with a sample of 934 LGBTQ high school students. Structural equation modeling was employed to analyze direct and indirect effects. Peer victimization was positively associated with both forms of suicidality and negatively associated with school belonging and self-compassion. Psychological processes varied in their in prediction of suicidal ideation and attempts. Parental support did not moderate pathways between victimization and processes, but was associated with diminished suicidality and improved school belonging. Our findings illustrate the critical nature of further developing our understanding of the complexities of suicidality. School programs and interventions that are designed to cultivate belonging, self-compassion, and parental support may prove to be especially beneficial for victimized LGBTQ youth who struggle with suicidality. [ABSTRACT FROM AUTHOR]
Keywords: Self-perception; Suicidal behavior; Suicide; Crime victims; Social support; Suicidal ideation; Parent attitudes; Psychology of LGBTQ+ people; Adolescence; High school students; School environment; Compassion; Structural equation modeling; Cross-sectional method; bullying; LGBTQ youth; mental health; school connectedness; social support; suicide

Psychotherapeutic depression interventions adapted for sexual and gender minority youth: A systematic review of an emerging literature. - Sheinfil, Alan Z.; Foley, Jacklyn D.; Ramos, Jeremy; Antshel, Kevin M.; Woolf-King, Sarah E. (Journal of Gay & Lesbian Mental Health, 2019)
Sexual and gender minority youth (SGMY) are disproportionately affected by mental health problems, including depression and suicidality. Recently, there has been increased interest in developing and adapting evidence-based treatments for depressive symptoms tailored to address the unique issues facing SGMY. This is the first systematic review of interventions targeting depressive symptoms that have been adapted for SGMY populations. Findings from these studies provide evidence in support of the feasibility, acceptability, and preliminary efficacy for SGM-informed interventions for the treatment of depressive symptoms. Fully powered randomized controlled trials are needed to determine the efficacy of these adapted treatments prior to dissemination. [ABSTRACT FROM AUTHOR]
Keywords: Youths' sexual behavior; Sexual minorities; Meta-analysis; Literature reviews; Randomized controlled trials; Vulvodynia; Depressive symptoms; intervention; sexual minority; systematic review; youth

Parental reactions to transgender and gender diverse children: A literature review. - Abreu, Roberto L.; Rosenkrantz, Dani E.; Ryser-Oatman, Jonathan T.; Rostosky, Sharon S.; Riggle, Ellen D. B. (Journal of GLBT Family Studies, 2019)
Transgender and gender diverse (TGD) individuals face stigmatization from family members and peers, placing this group at high risk of adverse outcomes including suicidality, substance abuse, and compromised mental health. This article uses a literature review approach to explore the common experiences of parents of TGD individuals as they navigate their relationship with their TGD children. Across 32 identified studies, the experiences of parental reactions include: (a) initial experiences (including noticing gender atypical behavior, diverse emotional reactions, cognitive dissonance and behavioral avoidance, and lack of knowledge); (b) transformation processes (including seeking informative resources and developing cognitive flexibility, seeking support and making TGD connections, facing barriers and isolation, developing awareness of discrimination and building empathy, and acknowledging the toll on mental health); (c) positive outcomes (including relational benefits, affirmation of values and activism, and new personal narratives); and (d) influences on the process (including time, gender, and attribution of the cause of TGD identity). Recommendations for health service providers include acknowledging diverse emotional reactions and cognitive dissonance, cultivating hope, honoring systemic barriers, and helping parents of TGD individuals create new positive narratives. [ABSTRACT FROM AUTHOR]
Keywords: Parents of transgender people; Parent-child relationships; Literature reviews; Experience; Cognitive dissonance; literature review; Parental figures; parental reactions; TGD children

A Systematic Review and Meta-Analysis of Disparities in the Prevalence of Suicide Ideation and Attempt Among Bisexual Populations. - Salway, Travis; Ross, Lori E.; Fehr, Charles P.; Burley, Joseph; Asadi, Shayan; Hawkins, Blake; Tarasoff, Lesley A. (Archives of Sexual Behavior, 2019)
Sexual minorities are at increased risk of suicide; however, it is unclear whether there are within-sexual minority differences in risk across specific sexual identities-notably between bisexual and lesbian/gay subgroups. We therefore conducted a systematic review and meta-analysis to quantify associations between bisexual identity and self-reported suicide ideation and attempt and the moderation of these associations by gender/sex, age, sampling strategy, and measurement of sexuality. Abstracts and full texts were independently screened by two reviewers, resulting in a total of 46 studies that met inclusion criteria and reported 12-month or lifetime prevalence estimates for suicide ideation or attempt. A consistent gradient was observed across all four outcomes, whereby bisexual respondents reported the highest proportion of suicide ideation or attempt, lesbian/gay respondents the next highest proportion, and heterosexual respondents the lowest proportion. Random-effects meta-analysis comparing bisexual individuals with lesbian/gay individuals yielded odds ratios (ORs) ranging between 1.22-1.52 across the four outcomes examined. Between-study variability in ORs was large. Thirty-one percent of heterogeneity was explained by sample type (e.g., probability vs. non-probability) and 17% by gender/sex. ORs were consistently larger for women (range: 1.48-1.95, all statistically significant at p < .05) than for men (range: 1.00-1.48, all p > .05), suggesting that gender/sex moderates the association between bisexual identity and suicide risk. Within-sexual minority differences in suicide risk may be attributed to structural and interpersonal experiences of monosexism, bisexual erasure and invisibility, or lack of bisexual-affirming social support, each of which may be experienced differently across gender/sex identities. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minorities; Suicidal ideation; Bisexual identity; Heterosexuals; Suicide risk factors; Bisexual; Mental health; Meta-analysis; Sexual orientation; Suicide

Adolescents with Gender Dysphoria: Reflections on Some Contemporary Clinical and Research Issues. - Zucker, Kenneth J. (Archives of Sexual Behavior, 2019)
This article provides an overview of five contemporary clinical and research issues pertaining to adolescents with a diagnosis of gender dysphoria: (1) increased referrals to specialized gender identity clinics; (2) alteration in the sex ratio; (3) suicidality; (4) "rapid-onset gender dysphoria" (ROGD) as a new developmental pathway; (5) and best practice clinical care for adolescents who may have ROGD. [ABSTRACT FROM AUTHOR]
Keywords: Gender dysphoria in adolescence; Gender identity; Mental health of teenagers; Sex ratio; DSM-5; Gender dysphoria; Rapid-onset gender dysphoria; Suicidality

Recent Suicide Attempts Across Multiple Social Identities Among Gay and Bisexual Men: An Intersectionality Analysis. - Ferlatte, Olivier; Salway, Travis; Hankivsky, Olena; Trussler, Terry; Oliffe, John L.; Marchand, Rick (Journal of Homosexuality, 2018)
This study draws from intersectionality to describe variations in recent suicide attempts (RSA) among gay and bisexual men (GBM) across sociodemographics. Using survey data, logistic regression modeling explored RSA in two analytical stages: (1) the individual effects of each sociodemographic were measured; (2) two-way interaction terms between sociodemographics were tested and added to the models created in stage A. In stage A, only education and income achieved significance. In stage B, the study found that (a) education and income interacted significantly such that the odds of RSA increased for those with a lower income and a lower education; (b) sexual orientation and partnership status interacted, resulting in decreased odds among bisexual men in heterosexual partnerships; and (c) income and education interacted with geography; the effects of these variables were significant only among urban men. These findings suggest that GBM are at unequal risk of RSA according to intersecting sociodemographics. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Homosexuality; Suicide; Gay men; Bisexual men; Intersectionality; Risk factors in suicidal behavior; bisexuality; gay; homosexuality; intersectionality; risk factors; suicide attempts

Looking beyond the lesbian: The intersectionality of death on Netflix's Orange is the New Black. - Ruderman-Looff, Ashley (Journal of Lesbian Studies, 2019)
In 2016, GLAAD's "Where We Are On TV" report noted a significant rise in lesbian death. This article addresses this perpetual trend as it manifests within Netflix's Orange is the New Black by considering the deaths of Tricia Miller and Poussey Washington. I use a narrative form of intersectional analysis to argue that lesbian death initiates a powerful critique of the criminal legal system and the prison industrial complex. Specifically, lesbian death points to the way multiple modes of marginalization intersect with homophobia to buttress a system designed to administer social and premature death. My analysis of Tricia's death demonstrates how the school-to-prison pipeline prepares children to take responsibility for their behaviors, but neglects to address how their futures in the justice system are systematically produced and beyond their control. This message corresponds to Tricia's flashbacks and her suicide, which demonstrate how, under neoliberalism, Tricia's failure to "pull herself up" leads to her incarceration. In turning to Poussey, I argue that reading her death as an accident not only dismisses the "one bad apple" myth typically used to account for police brutality, it demonstrates how "accidental death" is systematically and deliberately produced within the prison industrial complex. I analyze flashbacks of both Poussey and her killer, Baxter Bayley, to draw attention to the fact that they have committed the same crimes. I demonstrate how power and criminalization are assigned on the basis of gender, race, sexuality, and class. [ABSTRACT FROM AUTHOR]
Keywords: Intersectionality; Lesbians; Justice administration; School-to-prison pipeline; Death; intersectionality; lesbian representation; mass incarceration; Orange is the New Black; prison industrial complex; Orange Is the New Black (TV program)

The gender affirmative lifespan approach (GALA): A framework for competent clinical care with nonbinary clients. - Rider, G. Nic; Vencill, Jennifer A.; Berg, Dianne R.; Becker-Warner, Rachel; Candelario-Pérez, Leonardo; Spencer, Katherine G. (International Journal of Transgenderism, 2019)
Background: The limited research on nonbinary individuals suggests that this community experiences significant health disparities. Compared to binary transgender individuals, research suggests that nonbinary individuals are at elevated risk for discrimination and negative mental health outcomes, including depression, anxiety, traumatic stress, and suicidality. Even mental health providers who work with binary transgender individuals often lack knowledge of and training to work competently with nonbinary individuals. Methods: The authors of this conceptual article present the Gender Affirmative Lifespan Approach (GALA), a psychotherapy framework based in health disparities theory and research, which asserts that therapeutic interventions combating internalized oppression have the potential to improve mental health symptomatology resulting in improved overall health and well-being for gender diverse clients. GALA's therapeutic interventions are designed to promote positive gender identity development through five core components: (1) building resiliency; (2) developing gender literacy; (3) moving beyond the binary; 4) promoting positive sexuality; and (5) facilitating empowering connections to medical interventions (if desired). Results: The core components of the GALA model are individualized to each client's unique needs, while taking into consideration age and acknowledging developmental shifts in, or fluidity of, gender across the lifespan. This model represents an inclusive, trans-affirmative approach to competent clinical care with nonbinary individuals. Discussion: Application of the GALA model with nonbinary clients is discussed, including one clinical case vignette. [ABSTRACT FROM AUTHOR]
Keywords: Gender identity; Mental illness; Psychotherapy; Human sexuality; Well-being; Conceptual structures; Case studies; Resilience (Personality trait); Self-efficacy; Health disparities; gender affirming psychotherapy; Genderqueer; LGBT health; nonbinary; transgender; transgender health

Coming out in Mainland China: A national survey of LGBTQ students. - Wei, Chongzheng; Liu, Wenli (Journal of LGBT Youth, 2019)
This study examined the school experience and its association with the mental health of lesbian, gay, bisexual, transgender, and questioning (LGBTQ) students in Mainland China. From 29 Chinese provinces/municipalities, 732 LGBTQ students (Mage = 20.7 ± 2.5) completed an online survey based on the Supporting LGBT Lives study. The findings revealed that most Chinese schools were not inclusive for LGBTQ students. Despite the lack of support of very few LGBTQ-specific school policy, teacher training, and curriculum reported by students, the majority of LGBTQ youth felt safe living and learning at school. As well, most LGBTQ students felt comfortable about their sexual orientation and had come out to someone; however, the majority remained closeted with their siblings, parents, or teachers. Furthermore, Chinese LGBTQ students were at great risk for psychological distresses—about 85% of them felt depressed and around 40% had suicidal thoughts. Having a more inclusive school climate and more school resources, especially a positive LGBTQ role model, were significantly associated with the reduction of LGBTQ students' suicidal ideation. Given these findings, the authors strongly recommend further research, development, and implementation of robust LGBTQ-specific policy, training, and counseling be implemented immediately to improve the lives of Chinese LGBTQ youth. [ABSTRACT FROM AUTHOR]
Keywords: Mental health; Bisexuals; Psychology of lesbians; Parent-child relationships; Social support; Psychology of gay people; Suicidal ideation; Psychology of LGBTQ+ people; Transgender people; Sexual orientation identity; Psychology; Psychological stress -- Risk factors; Chinese students; Siblings; Chinese; Mental depression; Curriculum; Experience; School environment; School administration; Surveys; Teacher-student relationships; China; 中国大陆; 关键词 校园氛围; 出柜; 心理健康; coming out; LGBTQ 学生; LGBTQ students; Mainland China; mental health; School climate; 中国大陆; 关键词 校园氛围; 出柜; 心理健康; LGBTQ 学生

Coming-Out Experiences of Irish Gay Fathers Who Have Been Heterosexually Married: An Interpretative Phenomenological Analysis. - Daly, Siobhán C.; MacNeela, Pádraig; Sarma, Kiran M. (Journal of Homosexuality, 2020)
This study explores how Irish gay fathers, who married heterosexually in a heteronormative culture, assumed a settled gay identity in the Republic of Ireland. A purposive sample of nine men reflected on their experiences of marriage and separation, assuming a gay identity, and social and familial connectivity. Interpretative phenomenological analysis (IPA) indicated the suppression of gay sexual desires before marriage as a result of cultural homophobia. The coming-out process continued during the participants' marriage. Extramarital same-gender sexual desires and/or transgressions co-occurred with existential conflict (remorse) and resulted in marital separation. The marital and family loss was experienced as traumatic, and suicidal ideation occurred for most. All the men assumed an openly gay identity after separating. Many established a family-orientated same-gender repartnership. Results highlight the individuality and significance of the marital and family loss for those who separate after coming out as gay. [ABSTRACT FROM AUTHOR]
Keywords: Gay fathers; Marriage; Homophobia; Gay men; Separation (Law); coming out; heterosexual marriage; interpretative phenomenological analysis (IPA); Ireland; marital separation

Stigma and suicide risk among the LGBTQ population: Are anxiety and depression to blame and can connectedness to the LGBTQ community help? - Kaniuka, Andrea; Pugh, Kelley C.; Jordan, Megan; Brooks, Byron; Dodd, Julia; Mann, Abbey K.; Williams, Stacey L.; Hirsch, Jameson K. (Journal of Gay & Lesbian Mental Health, 2019)
LGBTQ individuals may be at risk for suicidal behavior due to perceived stigma and psychopathology. However, protective factors, such as community connectedness, may reduce risk. We examined depression and anxiety as mediators of the linkage between perceived stigma and suicidal behavior, and the moderating role of LGBTQ community connectedness. Among our sample of LGBTQ persons (N = 496), psychopathology mediated the association between perceived stigma and suicidal behavior. Connectedness moderated the relation between perceived stigma and depression, and between perceived stigma and suicidal behavior in the anxiety model. Therapeutically addressing stigma and promoting LGBTQ community connectedness may reduce risk for suicidal behavior. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Suicidal behavior; Suicide; Social stigma; Anxiety; Social belonging; Suicide risk factors; Mental depression; Connectedness; LGBTQ; perceived stigma; psychopathology; suicide

A comparison of mental health symptomatology and levels of social support in young treatment seeking transgender individuals who identify as binary and non-binary. - Thorne, Nat; Witcomb, Gemma L.; Nieder, Timo; Nixon, Elena; Yip, Andrew; Arcelus, Jon (International Journal of Transgenderism, 2019)
Background: Previous research has consistently reported high rates of mental health symptomatology and lower social support in young treatment seeking transgender individuals. However, these studies have failed to distinguish between transgender people who identify within the gender binary and those who identify as non-binary. Aims: This study aimed to compare levels of mental health symptomatology (anxiety, depression, and non-suicidal self-injury behavior) and social support of treatment seeking non-binary transgender young individuals with those self-identified as binary transgender young individuals. All participants attended a national transgender health service in the UK during a 2-year period. Measures: Age and gender identity descriptors were collected, as well as clinical measures of anxiety and depression (Hospital Anxiety and Depression Scale), self-esteem (The Rosenberg Self-Esteem Scale), non-suicidal self-injury (Non-Suicidal Self-Injury: Treatment Related), and social support (Multidimensional Scale of Perceived Social Support). Results: A total of 388 young people, aged 16–25 years, agreed participation; 331 (85.3%) identified as binary and 57 (14.7%) as non-binary. Analysis of the data showed the non-binary group experienced significantly more anxiety and depression and had significantly lower self-esteem than the binary group. There were no significant differences between groups in the likelihood of engaging in non-suicidal self-injury behavior or levels of social support.Conclusions: Non-binary identifying treatment seeking transgender youth are at increased risk of developing anxiety, depression, and low self-esteem compared to binary transgender youth. This may reflect the even greater barriers and feelings of discrimination that may be faced by those whose identity does not fit the notion of binary gender that is pervasive in how society views both cis- and transgender populations. [ABSTRACT FROM AUTHOR]
Keywords: Discrimination; Emotions; Gender identity; Health services accessibility; Medical care; Self-perception; Transgender people; Social support; Anxiety diagnosis; Anxiety treatment; Diagnosis of mental depression; Mental depression risk factors; Anxiety risk factors; Age distribution; Mental depression; Help-seeking behavior; Psychological tests; Self-esteem testing; Self-injurious behavior; Psychosocial factors; Great Britain; Anxiety; depression; gender dysphoria; non-binary; non-suicidal self-injury; self-esteem; social support; trans; transgender; youth

The Suicide of Leelah Alcorn: Whiteness in the Cultural Wake of Dying Queers. - Schares, Evan Mitchell (QED: A Journal in GLBTQ Worldmaking, 2019)
In this article, I examine public discourse in the wake of transgender teenager Leelah Alcorn's suicide. I argue that Alcorn's politicized suicide beckoned a national tragedy whereas the slew of queer and transgender people of color murdered did not because of the repeated deployments of a whiteness-derived innocence. Performances of hegemonic grief evinced Alcorn's posthumous rhetorical agency in ways that caused responsible adults to take action against the violence of conversion therapy on U.S. queer youth. In this article, I analyze how the rhetorics and performances of white grief functioned as an exigence for a queer of color critique that used the wake of Alcorn to unhinge logics of white supremacy and white grievability. As queers of color labored in Alcorn's wake to grieve their own dead in more public ways, they demonstrated how queers of color shoulder the burden of evincing their own trauma more so than their white counterparts. The cultural wake of Alcorn suggests that hegemonic grief functions as a modality of white supremacy while determining whose life is worthy of remembrance and a place in the queer imaginary. [ABSTRACT FROM AUTHOR]
Keywords: Suicide; Transgender teenagers; Violence; Racial identity of whites; Alcorn, Leelah, 1997-2014

Erections Exploding in Midair: The Obscenity of War Discussion of Chaim Shatan's "Happiness Is a Warm Gun". - Botticelli, Steven (Studies in Gender & Sexuality, 2020)
Building on earlier work that aimed to understand the traumatogenic effects of war experiences on soldiers, Chaim Shatan (1989) introduces in "Happiness Is a Warm Gun" his conception of "eroticized violence." He provides examples from his work with soldiers that are at once lurid and disturbing, yet also elliptical. These examples by their excess reflect the (micro)traumatic impact of Shatan's years of listening to soldiers' accounts of their war experiences, now inflicted on the reader. A reflection of his era, Shatan's difficulty conceiving of homosexuality and its interimplication with gender limits his understanding of the material he presents, a lack I attempt to remediate by recourse to Laplanche's work on enigmatic transfer. [ABSTRACT FROM AUTHOR]
Keywords: Homosexuality; Gender; Happiness; Firearms; Military personnel

Minority Stress and Suicidal Behavior: Investigating a Protective Model Through Resilience in a Bisexual Sample. - Miceli, Matt; Klibert, Jeff; Yancey, C. Thresa (Journal of Bisexuality, 2019)
Suicidal behaviors are a serious public health concern in the bisexual community. Protective models are needed to guide culturally informed methods of prevention. The current study evaluated the moderating effects of resilience and mental health status on the relationship between minority stress and suicidal behaviors. Data were collected from a convenience sample of bisexuals (N = 200). Results reveal a complex pattern of findings. Resilience moderates the relationship between minority stress and suicidal behaviors for bisexual community members with a reported mental health diagnosis; at moderate levels of resilience, a score of 15 on the Brief Resilience Scale, the relationship between minority stress and suicidal behaviors is nullified. Alternatively, resilience was not revealed as a significant moderator among bisexual community members without a mental health diagnosis. These findings provide preliminary evidence for resilience as a buffer against suicide for bisexual community members with mental health difficulties. [ABSTRACT FROM AUTHOR]
Keywords: Bisexuals; Bisexuality; Minority stress; Suicidal behavior; Mental health of bisexuals; Mental health; Resilience (Personality trait); Public health research; Bisexual; mental health status; minority stress; resilience; suicidal behavior

Agents and Objects of Death: Gay Murder, Boyfriend Twins, and Queer of Color Negativity. - Benedicto, Bobby (GLQ: A Journal of Lesbian & Gay Studies, 2019)
Drawing on the writings of Georges Bataille and Leo Bersani, this essay reexamines the long-held association of homosexuality with a radical erotics of death from the vantage of queer of color critique. While notions of suicidal ecstasy, self-shattering, and masochistic jouissance have played a central role in the theorization of homosexuality's transgressive potential, accounts that center homosexuality's desubjectivizing negativity have often been charged with a failure to attend to questions of racial difference and the limits they pose for an erotics and ethics grounded in risk and violence. This essay sets philosophical and psychoanalytic readings of (homo)sexuality's thanatology against the necropolitical realities of racist violence in order to think through, while refusing to abandon, the possibility of a nonwhite erotics of self-shattering. To do so, it analyzes the case of Luka Magnotta, the so-called Montreal gay cannibal killer, who murdered, decapitated, and committed acts of cannibalism and necrophilia on the corpse of Jun Lin, an Asian international student. In reading this case, however, the essay aims not only to demonstrate the racialized distribution of risk but also to show how racist violence itself might stem from the disavowal of the urge to dissolution that homosexuality is said to represent. The essay suggests, in turn, that this disavowal might be read as part of the ongoing conversion of homosexuality into a form of life, a process usefully illuminated by the phenomenon of gay twinning, in which gay men pursue sexual relations with what appear to be their mirror images made flesh. Grounded in notions of sameness and self-duplication, twinning dramatizes the abnegation of homosexuality's suicidal erotics and demonstrates the relations of complicity that bind the work of self-preservation to the reproduction of orders of racial difference that threaten to erupt into murderous violence. [ABSTRACT FROM AUTHOR]
Keywords: Homosexuality; Death; Crimes against gay people; Murder; Negativism; Thanatology; death; Georges Bataille; Leo Bersani; narcissism; negativity; queer of color; self-shattering; Bersani, Leo

Identity Affirmation and Mental Health among Sexual Minorities: A Raised-Mormon Sample. - Bridges, James G.; Tyler Lefevor, G.; Schow, Ronald L.; Rosik, Christopher H. (Journal of GLBT Family Studies, 2020)
How can someone successfully integrate a lesbian, gay, or bisexual (LGB) identity and a Mormon identity? Using a sample of 530 LGB-identified individuals raised in the Later-Day Saints (LDS) church, this study asks how factors of empowerment are associated with sexual identity affirmation and mental health outcomes. We found that sexual identity support, connection needs support, LGBT community support, and educational attainment were significantly associated with more positive mental health outcomes. LGB women who were raised Mormon appear to fair worse than men, on average. We also found that those raised Mormon who had disaffiliated with the LDS church reported significantly lower levels of internalized homonegativity than those still affiliated. Clinicians working with LGB Mormons and post-Mormons should consider the effect that affirming sources of support may have on positive mental health outcomes. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minorities; Mental health; Sexual health; Homophobia; Bisexuality; LGBTQ+ people; Educational attainment; Mormons; empowerment; LDS; mental health; Mormon; Sexual minority; suicidality

Introduction to the Special Section on Bisexual Health: Can You See Us Now? - Bostwick, Wendy B.; Dodge, Brian (Archives of Sexual Behavior, 2019)
Despite comprising the largest proportion of the "lesbian, gay, and bisexual" population, research focusing on the unique health concerns and needs of bisexual individuals is relatively scarce. While health disparities are increasingly well documented among lesbian, gay, bisexual, and transgender individuals relative to their heterosexual and cisgender counterparts, gaps remain in our basic understanding of how health status, behaviors, and outcomes vary within these groups, especially bisexual individuals. The lack of specified research on bisexual health is even more curious given that, when separated from both heterosexual and gay/lesbian individuals, bisexual individuals consistently report higher rates of a wide range of negative health outcomes, including mood and anxiety disorders, substance use, suicidality, as well as disparities related to healthcare access and utilization. Indeed, in scientific research, mass media, and in public health interventions, bisexual individuals remain relatively invisible. This Special Section represents an effort to shed light on a new generation of quantitative, qualitative, and mixed methods research studies that examine health-related concerns, outcomes, and intervention opportunities specifically among diverse samples of bisexual individuals from a variety of social and cultural contexts. The research herein focuses on intersections of multiple identities, the development of new measures, the use of large national data sets, and diverse groups of self-identified bisexual men (who tend to be least visible in health research). Findings from these studies will significantly advance our knowledge of factors associated with health disparities, as well as health and well-being more generally, among bisexual individuals and will help to inform directions for future health promotion research and intervention efforts. [ABSTRACT FROM AUTHOR]
Keywords: Bisexual men; Health disparities; Health promotion; Bisexual health; Bisexuality; LGBT; Sexual and gender minority (SGM); Sexual identity; Sexual orientation

Puberty Blockers and Suicidality in Adolescents Suffering from Gender Dysphoria. - Biggs, Michael (Archives of Sexual Behavior, 2020)
The author comments on a study by J. L. Turban and colleagues which showed that suicidal ideation is lower in transgender adults who as adolescents had been prescribed puberty blockers gonadotropin-releasing hormone analogs (GnRHa). He discusses the low-quality survey used in the study, psychological problems as a confounding factor that will create a spurious link between suicidality and treatment, and the acknowledgement made the researchers on the study's cross-sectional design.
Keywords: Suicidal ideation; Suicidal behavior; Transgender people; Gonadotropin releasing hormone; Teenage suicide

Association between risky sexual behavior and a psychosocial syndemic among Nigerian men who have sex with men. - Oginni, Olakunle A.; Mapayi, Boladale M.; Afolabi, Olusegun T.; Ebuenyi, Ikenna D.; Akinsulore, Adesanmi; Mosaku, Kolawole S. (Journal of Gay & Lesbian Mental Health, 2019)
Background: The HIV epidemic among men who have sex with men (MSM) is reinforced by a psychosocial syndemic, but this has not been investigated in sub-Saharan Africa. This study investigated the psychosocial syndemic and its relationship with risky sexual behavior among Nigeria MSM. Methods: Eighty-one MSM and 81 heterosexual men were compared for risky sexual behavior and psychosocial adversity variables—childhood adversity, intimate partner violence, depressive symptoms, suicidal ideation, substance use, and a derived psychosocial syndemic score. The association between syndemic scores and risky sexual behavior was examined among MSM. Results: MSM had significantly higher rates of individual psychosocial adversities except substance use. There were significant interrelationships between the variables, and syndemic scores were associated with higher-risk sexual behavior. Conclusion: This is the first study to investigate the psychosocial syndemic and its relationship with HIV risk among African MSM. The findings highlight the role of psychosocial adversities in exacerbating the HIV epidemic among MSM in developing countries. [ABSTRACT FROM AUTHOR]
Keywords: Men's sexual behavior; Human sexuality; Risk-taking behavior; Intimate partner violence; Heterosexual men; Suicidal ideation; Sub-Saharan Africa; Nigeria; MSM; psychosocial adversity; risky sexual behavior; syndemic

"Savoring" buffers the association between negative emotions and suicidal behaviors in the GSM community. - Klibert, Jeffrey J.; Luna, Amy; Miceli, Matthew (Journal of Gay & Lesbian Mental Health, 2019)
This study examined the effects of "savoring the moment" (the ability to generate, maintain, and extend positive emotions) on the relationship between negative emotions and suicidal behavior in a sample of gender and sexual minorities (GSM). Savoring the moment moderated the associated effects of negative emotions on suicidal behavior; the relationship between negative emotions and suicidal behaviors ceased at higher levels of savoring the moment. Our finding offers preliminary evidence for savoring as a buffer to suicide among subpopulations of GSM individuals. Our findings also provide some insights into the use of positive psychological interventions in GSM suicide prevention efforts. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Emotions; Gender and sexual minorities; negative emotions; positive psychology; savoring; suicidal behavior

Increased mental health and psychosocial risks in LGBQ youth accessing Australian youth AOD services. - Wishart, Madeline; Davis, Cassandra; Pavlis, Alexia; Hallam, Karen T (Journal of LGBT Youth, 2020)
Research has consistently demonstrated that young people who identify as lesbian, gay, bisexual, or queer (LGBQ) show greater levels of psychosocial risk than general cohorts of young people. Young people engaged with youth alcohol and other drug (AOD) services are some of the most marginalized of all young people. Hitherto research is yet to investigate if young people identifying as LGBQ fare worse in these psychosocial domains than their non-LGBQ co-clients within AOD services. This study compared outcomes for 103 matched pairs of LGBQ identified and non-LGBQ identified young people (N = 206) using youth AOD services in Australia from a youth needs census. The results indicated that youth identifying as LGBQ reported more family dysfunction; and had experienced more violent crime, sexual, physical, and emotional abuse; and accumulated trauma than the non-LGBQ group. They had significantly more substance related harms, greater polysubstance use, and greater severity in their substance use. The LGBQ group also demonstrated poorer psychological health, quality of life, and were more likely to report a history of mental illness, and non-suicidal self-injury according to their youth worker. Overall these data indicate a need to direct more support to this particularly at risk group of young people. [ABSTRACT FROM AUTHOR]
Keywords: Emotions; Quality of life; Sex crimes; Family relations; Psychology of LGBTQ+ people; Mental illness risk factors; Violence -- Psychological aspects; Substance abuse -- Risk factors; Pharmacy -- Information services; Emotional trauma; Risk assessment; Self-injurious behavior; Australia; adolescence; Alcohol and other drug; LGBQ; mental health; services; substance use

“May Her Memory Be a Revolution”: Rethinking Queer Kinships through Mourning and Trans Necropolitics. - ISRAELI-NEVO, ATALIA (Lambda Nordica, 2019)
This essay explores the ways in which queer kinships are manifold through mourning. Using an autoethnographic methodology accounting the suicide of DanVeg, a transwoman and queer activist from Israel/Palestine and a member of the author’s chosen family, the article aims to question the different affects of queer kinships as they unravel through mourning, as well as the challenges trans death pose to them. Examining different mourning practices and subversive political actions following DanVeg’s death, through the lens of critical kinship studies, queer and trans theories of necropolitics, and spectrality theories, it is claimed that eventually queer kinships are a precarious haunting ghost on the nuclear, biological heterosexual family, always in danger of being deconstructed but nevertheless always lingers and posing a threat to the normative kinship matrix. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ activists; Political participation; Bereavement; Accounting methods; Revolutions; Kinship; Palestine; Israel; autoethnography; Israel/Palestine; mourning; necropolitics; queer kinship; suicide; trans death

Mental Health of Transgender People in Hong Kong: A Community-Driven, Large-Scale Quantitative Study Documenting Demographics and Correlates of Quality of Life and Suicidality. - Suen, Yiu Tung; Chan, Randolph Chun Ho; Wong, Eliz Miu Yin (Journal of Homosexuality, 2018)
A community-driven survey of 106 transgender people (the first such survey in Hong Kong) showed that: (1) more than half the sample (50.9%) had a university degree or higher qualification; (2) despite this, 43.4% had a monthly income below HK$6,000 (about USD$775); (3) 66% reported “fair” or “poor” quality of life; (4) 67% of the sample (87.1% of respondents aged 15-24 years) had contemplated suicide; and (5) 20.8% of the sample (35.5% of respondents aged 15-24 years) had attempted suicide. It was found that (1) those who were single, had a lower monthly income, and identified as transgender women reported lower quality of life; and (2) those who were younger and on a lower income expressed higher suicidality. The findings suggest that service providers and policy makers urgently need to address the mental health needs of transgender people, particular younger transgender people. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Quality of life; Suicidal ideation; Trans women; Mental health; Hong Kong (China) -- Social conditions; Hong Kong; LGBT; mental health; quality of life; suicide attempt; suicide ideation; transgender

Violence as Mediating Variable in Mental Health Disparities Associated to Sexual Orientation Among Mexican Youths. - Mendoza-Pérez, Juan Carlos; Ortiz-Hernández, Luis (Journal of Homosexuality, 2019)
In this study, we explored the role of sex as an effect-modifying variable in the association between sexual orientation and mental health in Mexican youth. In addition, we tested if violent experiences in the family and the school and attitudes toward homosexuality could act as mediating variables in such association. Data from three representative surveys performed in 2007, 2009, and 2013 among Mexican high school students were analyzed. Two dimensions of sexual orientation were evaluated: romantic partnership and sexual behavior. The outcomes were negative and positive mood, suicidal ideation and intent, self-concept, and self-esteem. There were differences by gender because in males, there were more disparities in mental health associated with sexual orientation (suicidal ideation and attempt, negative and positive mood, negative self-concept, and family-related self-esteem) than in females (suicidal ideation and negative mood). Experiences of school violence were mediators in the relationship between sexual orientation and most health outcomes in males. [ABSTRACT FROM AUTHOR]
Keywords: Violence; Mental health; Sexual orientation; Attitudes toward homosexuality; Suicidal ideation; Youths' sexual behavior; Health disparities; High school students; disparities; gender; mental health; mood; self-esteem; teenagers; violence sexual abuse

Trajectories of Suicidal Ideation from Adolescence to Adulthood: Does the History of Same-Sex Experience Matter? - Oi, Katsuya; Wilkinson, Lindsey (Archives of Sexual Behavior, 2018)
The fluidity of same-sex experience (SSE) can be conceptualized as both a risk and a resource that impacts suicidal ideation over time. Considering whether SSE occurs in adolescence, adulthood, or both, this study suggests that SSE in both adolescence and adulthood is associated with depression and low self-esteem throughout the life course, resulting in chronic susceptibility to suicidal ideation. Yet due to variation in both accumulation of risk and resources over time, trajectories of suicidal ideation during the transition to adulthood likely vary by timing of SSE. To test these hypotheses, we fit latent growth curve models to a gender-stratified sample taken from the National Longitudinal Study of Adolescent to Adult Health (7608 men, 8070 women). We created four groups of SSE: no SSE (6322 men, 5981 women), SSE in adolescence only (634 men, 480 women), SSE in adulthood only (372 men, 1081 women), and SSE in adolescence and adulthood (280 men, 528 women). Men and women with SSE in both life stages had the greatest risk of suicidal ideation in adolescence and in adulthood. Yet women with first SSE in adulthood had less of a decline in suicidal ideation over time, relative to those with no SSE and those with SSE in adolescence only, and this was partially due to higher depression and lower self-esteem. Results suggest greater support is needed for adolescents expressing non-normative sexualities and for those with first SSE in adulthood, a group that is more difficult to identify in schools. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal ideation; Self-destructive behavior; Suicidal behavior; Sexual orientation; Adolescent psychology; Adolescence; Coping; Non-heterosexuality; Suicidality

Omar Mateen as US citizen, not foreign threat: Homonationalism and LGBTQ online representations of the Pulse nightclub shooting. - Meyer, Doug (Sexualities, 2020)
This article focuses on how 377 reports from popular lesbian, gay, bisexual, transgender, and queer (LGBTQ) websites represented Omar Mateen, the shooter of the 2016 Pulse nightclub shooting in Orlando, Florida, drawing particular attention to the exclusion of Mateen's native-born status. Based on a grounded theory analysis of the five most-trafficked LGBTQ websites, results demonstrate that the reports generally decontextualized Mateen from his country of birth, the USA, and excluded any emphasis on xenophobia or anti-Latinx prejudice as a potential motivating factor in the shooting. Instead, Mateen was usually associated with "terrorism" and sometimes implicitly positioned as a "foreign threat." These results, building on Jasbir Puar's concept of homonationalism, have implications for LGBTQ positions on the US political left, as the reports typically constructed themselves as anti-Republican and opposed to Islamophobia, while simultaneously reinforcing homonationalist, and relatively conservative, positions. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Nightclubs; Grounded theory; Islamophobia; Citizens; Xenophobia; Mass shootings; Orlando (Fla.); Homonationalism; mass shootings; Muslims; Pulse nightclub

Evidence of Multiple Mediating Pathways in Associations Between Constructs of Stigma and Self-Reported Suicide Attempts in a Cross-Sectional Study of Gay and Bisexual Men. - Salway, Travis; Gesink, Dionne; Ibrahim, Selahadin; Ferlatte, Olivier; Rhodes, Anne E.; Brennan, David J.; Marchand, Rick; Trussler, Terry (Archives of Sexual Behavior, 2018)
Gay and bisexual men (GBM) are more likely to attempt suicide than heterosexual men. This disparity is commonly interpreted using minority stress theory; however, specific pathways from antigay stigma to suicidal behavior are poorly understood. We aimed to estimate associations between multiple constructs of stigma and suicide attempts among adult GBM, and to measure the proportion of these associations mediated by distinct suicide risk factors, thus identifying proximal points of intervention. Data were drawn from a Canadian community-based survey of adult GBM. Structural equation modeling was used to compare associations between three latent constructs-enacted stigma (e.g., discrimination, harassment), anticipated prejudice (worry about encountering antigay/bisexual prejudice), and sexuality concealment-and self-reported suicide attempts (last 12 months). Coefficients were estimated for direct, indirect, and total pathways and evaluated based on magnitude and statistical significance. The proportion of associations mediated by depression, drug/alcohol use, and social isolation was calculated using indirect paths. Among 7872 respondents, 3.4% reported a suicide attempt in the past 12 months. The largest total association was observed for enacted stigma, and this association was partially mediated by depression and drug/alcohol use. The total association of anticipated prejudice was relatively smaller and mediated by depression and social isolation. Concealment had an inverse association with suicide attempts as mediated by depression but was also positively associated with suicide attempts when mediated through social isolation. Multiple constructs of antigay stigma were associated with suicide attempts; however, mediating pathways differed by construct, suggesting that a combination of strategies is required to prevent suicide in adult GBM. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Mental health of gay men; Bisexual men; Minority stress; Sexual orientation; Psychology; Gay and bisexual men; Mental health; Sexual stigma; Suicide

The Relationship Between Queer Identity, Social Connection, School Bullying, and Suicidal Ideations Among Youth of Color. - Lardier, David T.; Pinto, Stacy A.; Brammer, Mary Kathryn; Garcia-Reid, Pauline; Reid, Robert J. (Journal of LGBT Issues in Counseling, 2020)
Queer youth, and specifically queer youth of color (YOC), identified in this study as Hispanic/Latinx and African American/Black youth, disproportionately experience suicidal ideations (SI). The nexus of limited social support and school bullying exacerbates the effect on SI among these youth. Using data from a larger Drug-Free Communities grant initiative among YOC (N = 687; 65.6% youth aged 16–18 years; 53% female; 16% queer [i.e., lesbian, gay, bisexual and queer]) this study examined: (1) the mediating role of school bullying between queer identity status and SI and (2) both the mediating and moderating roles of family, social supports, and school importance on the initial mediating model. Findings from this study provide implications that may help prepare counselors to intervene across contexts. [ABSTRACT FROM AUTHOR]
Keywords: Bullying; Families; Gender identity; Minorities; Social networks; Social support; Suicidal ideation; Psychology of LGBTQ+ people; Black people; High schools; Hispanic Americans; bullying; Queer; social connection; suicidal ideation; youth of color

BDSM Role Fluidity: A Mixed-Methods Approach to Investigating Switches Within Dominant/Submissive Binaries. - Martinez, Katherine (Journal of Homosexuality, 2018)
This mixed-methods study of BDSM investigates the nuances of BDSM participants’ role identities, role frequencies, and role fluidities—shifts in identities and play across time, location, scene, and play partner. Data were gathered from 202 online surveys and 25 semistructured interviews about participants’ roles given their gender and sexual identities. These data reveal that men tend to self-identify as Dominant, Master, Top, or Sadist (DMTS) and always perform dominant roles, while women tend to self-identify as Submissive, Slave, Bottom, or Masochist (SSBM) and always perform submissive roles. Although this would seem to support the theory that BDSM reinforces gendered dominant/submissive binaries, further analyses indicate that women and queer/pansexual individuals disrupt this binary through their Switch identities and roles. Switching and queer identities, thus, offer the possibility for transforming dominant/submissive and other binaries. [ABSTRACT FROM AUTHOR]
Keywords: BDSM; Sexual dominance & submission; Sadomasochism; Suicidal ideation; Suicidal behavior; Gender role; Sexual role playing; Suicide risk factors; dominance; Dualism; fluidity; gender identity; sadomasochism; sexual identity; submission

Out of the darkness and into the shadows: The evolution of contemporary bisexuality. - Taylor, Julia (Canadian Journal of Human Sexuality, 2018)
Bisexuality, as we currently understand it, has evolved over the past 150 years both shaped by and shaping cultural change, scholarly endeavour and individual experience. To understand bisexuality in contemporary Western society it is essential to understand its past. This article explores the history of bisexuality within scholarly literature and social conversation by examining its progression from a largely silent past to a contemporary topic of scholarly investigation, a socio-political concept and a lived experience. With the growing awareness of poor mental health and suicidality among bisexual people in Western society, there has never been a more pressing time to examine bisexuality from its roots to its current existence with the aim of building a foundation from which academics, activists, health professionals and bisexual individuals can work together toward a more positive future where bisexuality can emerge from the shadows and be explored, understood, accepted and celebrated. [ABSTRACT FROM AUTHOR]
Keywords: Bisexuality; Bisexuals; Interpersonal relations; Mental health; Suicidal ideation; Psychology; Associations, institutions, etc.; Medical personnel; Bisexual history; bisexual theory; bisexuality; LGBTI; sexuality

Conditioning of Sexual Interests and Paraphilias in Humans Is Difficult to See, Virtually Impossible to Test, and Probably Exactly How It Happens: A Comment on Hsu and Bailey (2020). - Pfaus, James G.; Quintana, Gonzalo R.; Mac Cionnaith, Conall E.; Gerson, Christine A.; Dubé, Simon; Coria-Avila, Genaro A. (Archives of Sexual Behavior, 2020)
The authors comment on a study by B. T. Grey on the role of conditioning explanations for sexual interests. Topics discussed include factor that makes sexual interest extremely difficult to study, comparison of heterosexual men's and women's genital arousal to a picture of an opposite sex abdomen to a gun that were either paired or unpaired, and an explanation for the weak effects reported in adult human participants.
Keywords: Sexual excitement; Heterosexual men; Heterosexual women; Human sexuality; Sex customs

“Invisible During My Own Crisis”: Responses of LGBT People of Color to the Orlando Shooting. - Ramirez, Johanna L.; Gonzalez, Kirsten A.; Galupo, M. Paz (Journal of Homosexuality, 2018)
On June 12, 2016, the Pulse nightclub in Orlando, Florida was the target of one of the country’s deadliest mass shootings. Pulse, a gay nightclub, was hosting a Latin Pride Night the evening of the tragedy, which resulted in the death of 49 victims and 53 casualties, over 90% of whom were lesbian, gay, bisexual, and transgender (LGBT) Latinx people, specifically. The present research investigates the narrative responses from LGBT people of color (LGBT-POC) following the tragedy. Results included an analysis of 94 participant narrative responses. Results were collected online from a sample of LGBT-POC with varying sexual, gender, and racial identities. Thematic analysis revealed four major themes: (1) Violence is Not New for LGBT-POC; (2) Personal Identification with Victims; (3) Lack of Intersectionality in Others’ Responses to Orlando; and (4) Acknowledgment of Intersectionality across LGBT-POC. Discussion focuses on describing the ways in which LGBT-POC responded to the shooting regarding their multiple minority identities. Implications of this research reinforce the need for continued intersectional research with LGBT-POC. [ABSTRACT FROM PUBLISHER]
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; Attitudes of LGBTQ+ people; LGBTQ+ people of color; Social history; Latin Americans; Hate crimes -- United States; LGBTQ+ Americans; Hate crime; intersectionality; Latinx; LGBT-POC; minority stress; Orlando

Supporting sexual and gender minority health: Research priorities from mental health professionals. - Clark, Kristen D.; Capriotti, Matthew R.; Obedin-Maliver, Juno; Lunn, Mitchell R.; Lubensky, Micah E.; Flentje, Annesa (Journal of Gay & Lesbian Mental Health, 2020)
Sexual and gender minority (SGM) people experience significant disparities in mental health and substances use disorders. This study reached out to mental health professionals (MHPs) who treat SGM people to determine mental health priorities for research that would better inform their clinical practice. MHPs were surveyed and asked to rate items based on a likert-type scale. Open-ended questions were also queried and analyzed qualitatively. Five items had the highest mean scores: "stressors related to SGM status," "lifestyle factors that support emotional resilience and wellbeing," "depression," "intimate relationships," and "suicide." Intersecting identities and sexual relationships emerged as qualitative themes. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minorities; Minority stress; Mental health personnel; Health of minorities; Public health research; Psychiatric research; Resilience (Personality trait); disparities; family therapy; LGBTQ; Mental health

The Role of Distal Minority Stress and Internalized Transnegativity in Suicidal Ideation and Nonsuicidal Self-Injury Among Transgender Adults. - Staples, Jennifer M.; Neilson, Elizabeth C.; Bryan, Amanda E. B.; George, William H. (Journal of Sex Research, 2018)
Transgender people are at elevated risk for nonsuicidal self-injury (NSSI) and suicidal ideation compared to the general population. Transgender (trans) refers to a diverse group of people who experience incongruence between their gender identity and sex assigned at birth. The present study is guided by the minority stress model and the psychological mediation framework, which postulate that sexual minority groups experience elevated stress as a result of anti-minority prejudice, contributing to negative mental health outcomes. This study utilized these theories to investigate the role of internalized transnegativity—internalization of negative societal attitudes about one’s trans identity—in the relationships of distal trans stress to suicidal ideation and NSSI. A U.S. national sample of trans adults (N = 237) completed a battery of online measures. Structural equation modeling (SEM) was used to compare models with mediation and moderation effects. Results suggested that internalized transnegativity acts as both a mediator and a moderator in the relationship between distal trans stress and suicidal ideation. Log likelihood comparisons suggested moderation models had the superior fit for these data. Results suggest that clinical interventions should directly target individuals’ internalized transnegativity as well as societal-level transnegativity. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Minority stress; Suicidal ideation; Psychology; Internalization; Self-injurious behavior; Psychology of adults

Depression and Associated Factors Among Gay and Heterosexual Male University Students in Nigeria. - Oginni, Olakunle A.; Mosaku, Kolawole S.; Mapayi, Boladale M.; Akinsulore, Adesanmi; Afolabi, Temitope O. (Archives of Sexual Behavior, 2018)
Homosexuality is a recognized risk factor for depression in high-income countries; however, there is little research investigating the relationship between depression and sexual orientation in developing countries, especially in Africa. In this first study to investigate psychopathology in sexual minority men in Nigeria, the prevalence rates of depression in Nigerian gay and heterosexual individuals were compared as well as the explanatory power of risk and resilience factors in both groups. Eighty-one gay and 81 heterosexual male university students were, respectively, recruited from the Obafemi Awolowo University. Both groups were assessed for depression and other clinical factors, including alcohol and other substance use, suicidal ideation, and resilience. Gay students were further assessed for sexuality-related variables, including minority stress factors such as internalized homophobia and perceived stigma. The prevalence rates of depression among gay and heterosexual students were, respectively, 16 and 4.9% (OR 3.7; 95% CI 1.15-11.82), and this increased likelihood for depression was significantly attenuated by resilience. Clinical factors correlated significantly with depression in both groups, explaining 31% of the variance in depression in gay and heterosexual students, respectively. Sexuality-related variables including internalized homophobia and perceived stigma were further associated with depression in gay students-accounting for a further 14% of the variance of depression in gay students. The findings highlight the importance of minority stress factors in understanding depression among non-heterosexual individuals in a developing country, and the need for further research to investigate the mechanisms of these relationships in such settings. [ABSTRACT FROM AUTHOR]
Keywords: Heterosexuals; Gay men; Homosexuality; Sexual orientation; Pathological psychology; Human sexuality; Mental depression; Depression; Nigeria

Have Mischievous Responders Misidentified Sexual Minority Youth Disparities in the National Longitudinal Study of Adolescent to Adult Health? - Fish, Jessica N.; Russell, Stephen T. (Archives of Sexual Behavior, 2018)
The National Longitudinal Study of Adolescent to Adult Health (Add Health) has been instrumental in identifying sexual minority youth health disparities. Recent commentary suggested that some Wave 1 youth responders, especially males, intentionally mismarked same-sex attraction and, as a result, published reports of health disparities from these data may be suspect. We use two recently developed approaches to identify "jokesters" and mischievous responding and apply them to the Add Health data. First, we show that Wave 1 same-sex attracted youth, including those who later reported completely heterosexual identities in adulthood, were no more likely than different-sex attracted youth and consistently heterosexual participants to be "jokesters." Second, after accounting for mischievous responses, we replicated six previously established disparities: depressive symptoms, suicidal ideation and behaviors, alcohol use, cocaine use, parental satisfaction, and school connectedness. Accounting for mischievousness resulted in the elimination of one observed disparity between heterosexual and sexual minority youth: suicidal ideation for males who reported romantic attraction to both sexes. Results also showed that accounting for mischievous responding may underestimate disparities for sexual minority youth, particularly females. Overall, results presented here support previous studies that identified health disparities among sexual minority youth using these data. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minorities; Same-sex relationships; Sexual orientation; Suicidal ideation; Health disparities; Mental depression; Add Health; Adolescence; Alcohol; LGB; Mental health; National Longitudinal Study of Adolescent Health (Organization)

Differences in well-being between sexual minority and heterosexual college students. - Crawford, Timothy N.; Ridner, S. Lee (Journal of LGBT Youth, 2018)
This study examines differences in well-being between sexual minority and heterosexual college students and identifies factors associated with well-being among sexual minority college students. A secondary analysis of cross-sectional web-based survey data was conducted. Using propensity score matching, 43 sexual minority students were matched to 43 heterosexual students on age, race, sex, and year in school. Sexual minorities had significantly lower well-being scores compared to heterosexual college students. Among sexual minorities, physical activity, depression, thoughts of suicide, and sleep quality were all predictive of well-being. Understanding issues related to well-being among sexual minorities is important and strategies need to be developed to improve well-being. [ABSTRACT FROM AUTHOR]
Keywords: Heterosexuals; PSYCHOLOGY; Well-being; Suicidal ideation; Psychology of LGBTQ+ people; Psychology; Age distribution; Psychology of college students; Mental depression; Minorities; Probability theory; Race; Sleep; Surveys; World Wide Web; Secondary analysis; Educational attainment; Cross-sectional method; Physical activity; College Students; Sexual Minority; Well-Being

Family Functioning and Mental Health of Transgender and Gender-Nonconforming Youth in the Trans Teen and Family Narratives Project. - Katz-Wise, Sabra L.; Ehrensaft, Diane; Vetters, Ralph; Forcier, Michelle; Austin, S. Bryn (Journal of Sex Research, 2018)
Transgender and gender-nonconforming (TGN) youth are at increased risk for adverse mental health outcomes, but better family functioning may be protective. This study describes TGN youth’s mental health and associations with family functioning in a community-based sample. Participants were from 33 families (96 family members) and included 33 TGN youth, ages 13 to 17 years; 48 cisgender (non-transgender) caregivers; and 15 cisgender siblings. Participants completed a survey with measures of family functioning (family communication, family satisfaction) and mental health of TGN youth (suicidality, self-harm, depression, anxiety, self-esteem, resilience). TGN youth reported a high risk of mental health concerns: suicidality (15% to 30%), self-harm (49%), clinically significant depressive symptoms (61%); and moderate self-esteem (M = 27.55, SD = 7.15) and resiliency (M = 3.67, SD = 0.53). In adjusted models, better family functioning from the TGN youth’s perspective was associated with better mental health outcomes among TGN youth (β ranged from −0.40 to −0.65 for self-harm, depressive symptoms, and anxious symptoms, and 0.58 to 0.70 for self-esteem and resiliency). Findings from this study highlight the importance of considering TGN youth’s perspectives on the family to inform interventions to improve family functioning in families with TGN youth. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Gender-nonconforming people; Public health; Mental health; Youth psychology; Caregivers

Suicidality and Associated Factors Among Men Who Have Sex With Men in Estonia. - Rüütel, Kristi; Valk, Anti; Lõhmus, Liilia (Journal of Homosexuality, 2017)
Many studies over the last decade provide strong evidence of elevated rates of suicidality among lesbian, gay, bisexual, and transgender populations compared to heterosexual populations. The aim of the current study was to investigate suicidal ideation and attempts and related factors among men who have sex with men (MSM) in Estonia. We conducted a nationwide Internet-based study among MSM with 265 eligible participants. Our results reveal high rates of self-reported suicidal ideation (lifetime prevalence 45%) and attempts (lifetime prevalence 11%) as well as a high rate of problem drinking (33%) and depressive symptoms (32%) among MSM. Recent suicidal ideation (14% had thought about suicide in the last 12 months) was related to depressive symptoms and lower socioeconomic situation. There is a need to develop specific interventions to address these issues among MSM and to provide gay-friendly mental health services. [ABSTRACT FROM PUBLISHER]
Keywords: Men who have sex with men; Suicidal behavior; HIV infection risk factors; Mental depression; Estonia; Depression; HIV; internalized homonegativity; men who have sex with men; outness; problem drinking; suicide

Relationship among gender-related stress, resilience factors, and mental health in a Midwestern U.S. transgender and gender-nonconforming population. - Brennan, Stephanie L.; Irwin, Jay; Drincic, Andjela; Amoura, N. Jean; Randall, Amanda; Smith-Sallans, Megan (International Journal of Transgenderism, 2017)
Background: Transgender and gender-nonconforming individuals experience more discrimination than their cisgender peers, and this discrimination can be associated with poorer mental health. This study used the gender minority stress model as a framework to examine the relationship among gender-related stressors and resilience factors and mental health outcomes. The study particularly aimed to increase knowledge of the gender-nonconforming population. Methods: A community sample of 83 individuals that identify as a gender different than the sex assigned to them at birth completed an online survey. Depression and anxiety were assessed using the Center for Epidemiological Studies Depression Scale (CES-D) and Beck Anxiety Inventory (BAI), respectively. The Gender Minority Stress and Resilience measure was used to assess distal and proximal stressors and resilience factors. Results: The median CES-D and BAI scores were 16 and 13, respectively. Forty percent had a history of non-suicidal self-injury (NSSI), 75% had experienced suicidal ideation, and 45% had attempted suicide. Proximal stress was found to be a positive predictor of depressive symptoms. Resilience was a weak negative predictor of anxiety symptoms. Distal stress was a positive predictor of suicide attempts, and resilience factors and hormone use were marginal negative predictors of suicide attempt. Trans women were significantly less likely to have engaged in NSSI, but had a significantly higher proximal stress score than trans men and gender-nonconforming individuals. Conclusion: Our study found high rates of mental health problems in the trans and gender-nonconforming sample. Our findings in part support the gender minority stress model, with gender-related stress predicting certain mental health problems and resilience being a negative predictor. Overall, gender-nonconforming individuals have had similar experiences and mental health findings as transgender individuals. [ABSTRACT FROM PUBLISHER]
Keywords: Anxiety; Discrimination; Mental health; Self-mutilation; Suicidal behavior; Suicidal ideation; Transgender people; Minority stress; Psychology; Mental depression; Psychological tests; Resilience (Personality trait); Surveys; Sample size (Statistics); Data analysis software; Descriptive statistics; Midwest (U.S.); Gender-nonconforming; gender-related stress; mental health; non-suicidal self-injury; resilience; transgender

Depression and suicidality among bisexual youth: A nationally representative sample. - Taliaferro, Lindsay A.; Gloppen, Kari M.; Muehlenkamp, Jennifer J.; Eisenberg, Marla E. (Journal of LGBT Youth, 2018)
To address gaps in the literature on bisexual youth, we used the first nationally representative sample of high school students from the United States to determine profiles of behaviors related to depressive symptoms, a suicide attempt, and a medically-serious attempt. We examined the data from 922 bisexual students in grades 9–12 who completed the Centers for Disease Control and Prevention's 2015 National Youth Risk Behavior Survey. Latent class analysis derived three classes reflecting unique patterns of 10 risk and protective behaviors. For both the sexes: one group was high on all the risk behaviors and demonstrated the greatest risk of depression, a suicide attempt, and a medically-serious attempt; another was below average on all the risk and protective behaviors and demonstrated average/moderate risk of the outcomes; and the last demonstrated the highest levels of protective behaviors and the lowest risk of depression and suicidal behavior. Bisexual students are not homogenous with regard to the risk of mental health problems. Greater involvement in several risk behaviors and less involvement in protective behaviors, rather than merely a bisexual identity, might contribute to bisexual adolescents' increased risk of depression and suicidal behavior. Findings have implications for prevention programming, clinical interventions, and future research. [ABSTRACT FROM PUBLISHER]
Keywords: Bisexuals; Suicidal behavior; Suicidal ideation; Adolescence; Psychology; High school students -- United States; Mental depression; Student attitudes; United States; Adolescents; bisexual; depression; suicide

Predictors of Sexual Minority Youth’s Reported Suicide Attempts and Mental Health. - Puckett, Jae A.; Horne, Sharon G.; Surace, Francisco; Carter, Alice; Noffsinger-Frazier, Nicole; Shulman, Julie; Detrie, Pam; Ervin, Audrey; Mosher, Chad (Journal of Homosexuality, 2017)
Lesbian, gay, and bisexual youth (LGBY) report higher rates of mental health concerns compared to heterosexual youth due to minority stressors. This study examined the interpersonal and intrapersonal variables that predict psychological distress and self-reported suicide attempts in a sample of 61 LGBY in the Mid-South, which is a highly overlooked regional area for LGBY research. Youth who lost friends when coming out were 29 times more likely to report suicide attempts, and those who experienced psychological maltreatment from caregivers were 9.5 times more likely to report a suicide attempt. Internalized heterosexism, feelings of guilt or shame, and psychological maltreatment from caregivers were significant predictors of depression and anxiety symptoms. This study highlights the importance of creating affirming spaces for LGBY, particularly in areas of the country that experience greater political oppression of sexual minorities, such as the Mid-South. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority youth; Mental health of LGBTQ people; Heterosexism; Mental health; Suicidal behavior in youth; Anxiety -- Psychological aspects; Anxiety; depression; harassment; internalized heterosexism; LGB youth; sexual minority youth; suicide

Persecution Experiences and Mental Health of LGBT Asylum Seekers. - Hopkinson, Rebecca A.; Keatley, Eva; Glaeser, Elizabeth; Erickson-Schroth, Laura; Fattal, Omar; Nicholson Sullivan, Melba (Journal of Homosexuality, 2017)
Asylum seekers are a unique population, particularly those who have endured persecution for their sexual orientation or gender identity. Little data exist about the specific experiences and needs of asylum seekers persecuted due to lesbian, gay, bisexual, or transgender (LGBT) identity. Quantitative data were gathered regarding demographics, persecution histories, and mental health of 61 clients from a torture survivors program in New York City who reported persecution due to LGBT identity. Thirty-five clients persecuted due to their LGBT identity were matched by country of origin and sex with clients persecuted for other reasons to explore how persecution and symptoms may differ for LGBT clients. LGBT asylum seekers have a higher incidence of sexual violence, persecution occurring during childhood, persecution by family members, and suicidal ideation. Understanding the type of persecution experiences and how these influence mental health outcomes is an essential step toward designing and delivering effective treatments. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ political refugees; Post-traumatic stress disorder; Torture victims; Health; Mental health of refugees; Political refugees; Refugees -- United States; Asylum; bisexual; gay; lesbian; LGBT; posttraumatic stress disorder; refugee; survivor of torture; transgender; trauma

The Moderating Role of Community Resiliency on Suicide Risk in the Transgender Population. - Cogan, Chelsea M.; Scholl, James A.; Cole, Hannah E.; Davis, Joanne L. (Journal of LGBT Issues in Counseling, 2020)
Transgender individuals are disproportionately impacted by negative mental and physical health outcomes, including increased suicide risk. The gender minority stress theory proposes a potential pathway to suicide risk through distal and proximal stressors. However, little research has examined how resiliency impacts this relationship. The present study explored the moderating role of resiliency in the relationship between stressors, trauma exposure, and suicide risk. Stressors and trauma exposure were significantly associated with suicide risk, but community resilience was not found to moderate this relationship. The clinical implications of these findings are discussed in depth. [ABSTRACT FROM AUTHOR]
Keywords: Communities; Sexual minorities; Minority stress; Suicide risk factors; Injury complications; Resilience (Personality trait); Community resilience; minority stress; PTSD; suicide; transgender; trauma

Concealment of Sexual Minority Identities in Interviewer-Administered Government Surveys and Its Impact on Estimates of Suicide Ideation Among Bisexual and Gay Men. - Hottes, Travis Salway; Gesink, Dionne; Ferlatte, Olivier; Brennan, David J.; Rhodes, Anne E.; Marchand, Rick; Trussler, Terry (Journal of Bisexuality, 2016)
Bisexual and gay men are at increased risk of suicide ideation. Characterizing this risk requires self-disclosure of sexual identities; however, many will conceal their identity when interviewed. The authors investigated the impact of the resulting information bias within the Canadian Community Health Survey (CCHS). Expected probabilities of disclosure were derived from a community-based survey of bisexual and gay men, stratified by sexual identity and other social characteristics. Forty percent of bisexual men and 86% of gay men were willing to disclose to CCHS interviewers. The odds of suicide ideation were higher for bisexual (odds ratio [OR] = 4.91) and gay (OR = 3.63) men compared to heterosexual men. After bias analysis these disparities remained significant but were attenuated, with greater attenuation for bisexual (adjusted OR = 3.53) than for gay (adjusted OR = 3.52) men. The authors recommend that researchers continue exploring bias in estimated sexual minority health disparities, and that population surveys be more inclusive of bisexual-identified individuals. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Sexual minorities; Suicidal behavior; Bisexual men; Gay men; Self-disclosure; disclosure; LGB; men; research methods; sampling; sexual identity

Continuing Education Credits and Questions: CE Questions for 14(1). (Journal of LGBT Issues in Counseling, 2020)
A Continuing Education Unit (CEU) from the National Board for Certified Counselors on the topics including Moderating Role of Community Resiliency on Suicide Risk in the Transgender Population; and Clinical Issues among Chinese Gay Males in Counseling is presented.
Keywords: Counseling; Gay men; Gender dysphoria; Femininity; Sexual minorities; Suicide risk factors; Experience; Continuing education units

Cultural heterosexism and silencing sexual diversity: Anoka-Hennepin School District. - Grozelle, Renee S. (Journal of LGBT Youth, 2017)
In less than 2 years, nine young people within one Minnesota school district committed suicide. As such, the bullying of lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth in the Anoka-Hennepin School District continues to be an example of how embedded ideologies of some individuals can substantially impact the treatment of marginalized groups. Using the theory of cultural heterosexism, this paper will look at the ways in which the Anoka-Hennepin School District in Minnesota became a breeding ground for homophobic violence and discrimination. Furthermore, attention will be directed toward how discourses of sexuality, mobilized by conservative Christian groups in the Anoka-Hennepin School District, were used in order to maintain a heteronormative social order. [ABSTRACT FROM PUBLISHER]
Keywords: Bullying; Christianity; Homophobia; Social control; Suicide; Violence; Psychology of LGBTQ+ people; Attitudes toward sex; Psychology; School environment; Schools; Minnesota; bullying; Cultural heterosexism; LGBTQ rights; schools; sexuality; suicide

Parent-Initiated Sexual Orientation Change Efforts With LGBT Adolescents: Implications for Young Adult Mental Health and Adjustment. - Ryan, Caitlin; Toomey, Russell B.; Diaz, Rafael M.; Russell, Stephen T. (Journal of Homosexuality, 2020)
Studies of adults who experienced sexual orientation change efforts (SOCE) have documented a range of health risks. To date, there is little research on SOCE among adolescents and no known studies of parents' role related to SOCE with adolescents. In a cross-sectional study of 245 LGBT White and Latino young adults (ages 21–25), we measured parent-initiated SOCE during adolescence and its relationship to mental health and adjustment in young adulthood. Measures include being sent to therapists and religious leaders for conversion interventions as well as parental/caregiver efforts to change their child's sexual orientation during adolescence. Attempts by parents/caregivers and being sent to therapists and religious leaders for conversion interventions were associated with depression, suicidal thoughts, suicidal attempts, less educational attainment, and less weekly income. Associations between SOCE, health, and adjustment were much stronger and more frequent for those reporting both attempts by parents and being sent to therapists and religious leaders, underscoring the need for parental education and guidance. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; LGBTQ+ youth; Parenting; Suicidal ideation; Mental health of young adults; Mental depression; conversion therapy; depression; LGBT youth; reparative therapy; sexual orientation change efforts; suicidality

Transgender Adults’ Access to College Bathrooms and Housing and the Relationship to Suicidality. - Seelman, Kristie L. (Journal of Homosexuality, 2016)
Transgender and gender non-conforming people frequently experience discrimination, harassment, and marginalization across college and university campuses (Bilodeau, 2007; Finger, 2010; Rankin et al., 2010; Seelman et al., 2012). The minority stress model (Meyer, 2007) posits that experiences of discrimination often negatively impact the psychological wellbeing of minority groups. However, few scholars have examined whether college institutional climate factors—such as being denied access to bathrooms or gender-appropriate campus housing—are significantly associated with detrimental psychological outcomes for transgender people. Using the National Transgender Discrimination Survey, this study analyzes whether being denied access to these spaces is associated with lifetime suicide attempts, after controlling for interpersonal victimization by students or teachers. Findings from sequential logistic regression (N = 2,316) indicate that denial of access to either space had a significant relationship to suicidality, even after controlling for interpersonal victimization. This article discusses implications for higher education professionals and researchers. [ABSTRACT FROM PUBLISHER]
Keywords: Transgender people; Suicidal behavior; PSYCHOLOGY; Gender nonconformity; Psychological stress; Transphobia; Social conditions of LGBTQ people; Minorities; Bathrooms; Universities & colleges -- United States; campus housing; harassment; higher education; minority stress model; suicidality; transgender

Syndemic indicators predict poor medication adherence and increased healthcare utilization for urban HIV-positive men who have sex with men. - Pantalone, David W.; Valentine, Sarah E.; Woodward, Eva N.; O'Cleirigh, Conall (Journal of Gay & Lesbian Mental Health, 2018)
Research on men who have sex with men (MSM) has uncovered psychosocial factors (syndemic indicators) that are associated additively with poor health. To test these relations in a sample of HIV-positive MSM, we enrolled 166 patients from two HIV clinics. We investigated relations between syndemic indicators and outcomes, including medication nonadherence, condomless anal sex (CAS), and healthcare utilization. A large proportion of participants reported each syndemic indicator: polysubstance use 43%, suicide attempt 28%, childhood sexual abuse 39%, partner abuse 64%. Analyses confirmed an additive effect, whereby endorsing 1+ indicator was associated with increased odds of medication nonadherence and medical hospitalization. [ABSTRACT FROM AUTHOR]
Keywords: HIV-positive men; Men who have sex with men; Anal sex; Medical care; Suicidal behavior; Child sexual abuse; Patient compliance; Healthcare utilization; HIV; medication adherence; MSM; syndemics

Transgender youth and suicidal behaviors: Applying the interpersonal psychological theory of suicide. - Grossman, Arnold H.; Park, Jung Yeon; Russell, Stephen T. (Journal of Gay & Lesbian Mental Health, 2016)
The interpersonal psychological theory of suicide (IPTS) was used to examine suicidal thoughts and behaviors among 129 transgender and gender nonconforming (TGNC) youth. Youth were categorized according to their gender identities: female to male (FTM), male to female (MTF), female to different gender (FTDG), and male to different gender (MTDG). Higher percentages of suicidal ideation were reported by FTDG and FTM youth; higher percentages of suicide attempts were reported by FTDG and MTDG youth. Perceived burdensomeness and thwarted belongingness were significantly related to suicidal ideation and/or suicide attempts. Experiences of painful, provocative, and harmful events and acquired capability significantly predicted suicide attempts. The findings support IPTS in explaining suicidal behaviors among TGNC youth. Implications for prevention and intervention efforts are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Transgender youth; Suicidal behavior; Suicidal ideation; Gender identity; Psychological stress; Psychology; Female to different gender (FTDG); female to male (FTM); gender nonconforming; interpersonal psychological theory of suicide (IPTS); male to different gender (MTDG); male to female (MTF); suicidal ideation; suicide attempt; thwarted belongingness; transgender; youth

IMAGINING QUEER LIFE AFTER DEATH. - Young, Thelathia "Nikki" (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author reflects on the aftermath of the June 12, 2016 shooting at the Pulse gay nightclub in Orlando, Florida in which Omar Mateen killed 49 people and injured 58. She comments on how failure to acknowledge Mateen's homosexuality and instead emphasize his connections to Islamic terror organization takes focus away from the queerness of the victims and the sociopolitical factors associated with the massacre.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; LGBTQ+ communities -- Social aspects; Massacres; Terrorism -- United States; Mateen, Omar, 1986-2016

WHY WE FORGET THE PULSE NIGHTCLUB MURDERS: Bodies That (Never) Matter and a Call for Coalitional Models of Queer and Trans Social Justice. - Edelman, Elijah Adiv (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author reflects on how the 2016 Pulse nightclub massacre in Orlando, Florida has faded from public memory in a similar way that LGBT communities are considered by the broader public. He argues against a model of LGBT activism that groups multiple gender identities together and instead calls for coalition models of queer and transgender social justice.
Keywords: Social conditions of LGBTQ people; Orlando Nightclub Massacre, Orlando, Fla., 2016; Social justice; LGBTQ+ activists; Collective memory

Building Bridges, Not Walls: Intersectional Analysis and the Next Frontier in the Corporate Equality Movement. - Quartey, Nii-Quartelai; Fraizer, Lani; Miramontes, Gabby (LGBTQ Policy Journal, 2018)
In recent years, we have seen a backlash to what had become a more LGBTQ-affirming America. The current national climate includes heightened support for laws that essentially give government and private businesses a license to discriminate based on sexual orientation; repeal of healthcare and employment nondiscrimination protections; and increase in hate crimes, including the then-largest mass shooting in US history at an LGBTQ nightclub in Orlando, Florida.1 Each of these issues has inherent effects on employee recruitment, retention, and performance and on individual and collective efforts to create an organizational culture where all employees can thrive without fear of retaliation, retribution, or being unaffirmed in the workplace. While "executive culture" has traditionally focused on returns for stockholders at the expense of their broader stakeholders, complicating social responsibility efforts, corporate America's LGBTQ engagement has helped to create a paradigm shift2 through company-supported LGBTQ employee resource groups, business resource groups, volunteerism, philanthropy, and public policy advocacy efforts, that together have helped to make corporate America a critical ally in the movement for LGBTQ equality. The social unrest in the United States on issues related to race, ethnicity, age, gender, sexual orientation, and immigration status are challenging corporate leaders to demonstrate solidarity and be a lifeline to traditionally marginalized communities. At the same time, corporate activism on LGBTQ rights is being elevated as a civil rights issue among others all at once, causing a demand for increased competencies in intersectional analysis. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; LGBTQ+ rights; Corporate culture

"You can't break... when you're already broken": The importance of school climate to suicidality among LGBTQ youth. - Peter, Tracey; Taylor, Catherine; Campbell, Christopher (Journal of Gay & Lesbian Mental Health, 2016)
Suicide has been a longstanding problem among sexual and gender minority youth in Canada. The goal of the article is to examine the link between suicidality and school climate within a theoretically informed framework and a mixed methods approach. Qualitative and quantitative findings are presented using data from more than 3,700 secondary students from the National Climate Survey of Homophobia and Transphobia in Canadian Schools (Taylor & Peter, 2011a). The findings show that even modest efforts to shift the balance of heteronormative discourse on behalf of lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) students can have profound effects on the experiences and perceptions of sexual and gender minority youth, which we argue would go a long way in reducing incidents of suicidality among LGBTQ youth. In many jurisdictions across Canada, LGBTQ-inclusive policies have attempted to improve school climates and reduce the effects of homophobia and transphobia in schools. These initiatives, along with the work done by Egale Canada to create a National Youth Suicide Prevention Strategy, are important steps in addressing the needs of LGBTQ youth. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Youth centers; Youth -- Dwellings; Preaching to youth; Youths' attitudes; Discrimination; suicide; youth

preface. - Ahmad, Attiya; Gardiner, Judith (Feminist Studies, 2018)
An introduction is presented in which the editor discusses articles in the issue on topics including historical inhibitions which shaped the autobiographical writings of labor activist Elizabeth Gurley Flynn's that omitted her bisexuality, an examination of "The Autobiography of Alice B. Toklas" by Gertrude Stein, and a short story on suicide by Olga Zilberbourg.
Keywords: Flynn, Elizabeth Gurley, 1890-1964; Zilberbourg, Olga; Autobiography of Alice B. Toklas, The (Book)

Self-Reported Changes in Attractions and Social Determinants of Mental Health in Transgender Adults. - Katz-Wise, Sabra; Reisner, Sari; White Hughto, Jaclyn; Budge, Stephanie; Katz-Wise, Sabra L; Reisner, Sari L; White Hughto, Jaclyn M; Budge, Stephanie L (Archives of Sexual Behavior, 2017)
This study examined associations between changes in self-reported attractions and mental health in a community-based sample of self-identified transgender adults. Participants were purposively recruited in 2013 using bimodal sampling methods and completed a one-time survey. Multivariable logistic regression models estimated adjusted risk ratios and 95 % confidence intervals to examine associations between changes in attractions and mental health outcomes (lifetime self-harm, suicide attempts, depression diagnosis; past-week clinically significant depressive distress assessed via CES-D 10) among the entire sample (N = 452; 285 female-to-male spectrum, 167 male-to-female spectrum) and after gender transition among those who had socially transitioned (n = 205; 156 female-to-male spectrum, 49 male-to-female spectrum). Models were adjusted for known population social determinants (age, race/ethnicity, gender identity, socioeconomic status, sexual orientation identity), transgender-specific determinants (age of transgender realization, social transition, medical transition, visual gender nonconformity, non-binary gender identification), and survey mode (online vs. in-person sampling). Lifetime changes in attractions were significantly associated with increased probability of all mental health outcomes; individuals reporting any change in attractions were more likely than individuals not reporting changes to indicate lifetime self-harm, suicide attempts, depression diagnosis, and current depressive distress (all ps < .05). Changes in attractions post-social transition were not significantly associated with mental health outcomes. Many, but not all, population and transgender-specific social determinants were significantly associated with mental health in the full sample and among those who had socially transitioned. Clinical implications of findings about changes in attractions and mental health are discussed for transgender individuals. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Sexual orientation; Mental health; Psychology; Transsexualism; Gender identity; Human sexuality; Diagnosis of mental depression; Physiology; Mental depression; Psychological tests; Research funding; Self-evaluation; Logistic regression analysis; Odds ratio; Gender minority; Sexual fluidity; Transgender

Prevalence and Correlates of Lifetime Suicide Attempts Among Transgender Persons in Argentina. - Marshall, Brandon D. L.; Socías, María Eugenia; Kerr, Thomas; Zalazar, Virginia; Sued, Omar; Arístegui, Inés (Journal of Homosexuality, 2016)
This study examined the lifetime prevalence and correlates of attempted suicide among transgender persons in Argentina. Data were derived from a nation-wide, cross-sectional survey conducted in 2013. We assessed individual, social, and structural correlates of reporting a history of attempting suicide using logistic regression. Among 482 participants, the median age was 30, 91% identified as transwomen, and 32% resided in the Buenos Aires metropolitan area. A lifetime suicide attempt was reported by 159 (33%), among whom the median age at first attempt was 17. In a multivariate model, internalized stigma was positively associated with a history of suicidal behavior, while participants with stable housing had reduced odds of prior suicide attempt(s). These findings suggest that reducing stigma and mitigating structural vulnerabilities (through, for example, the enactment and enforcement of laws that prohibit discrimination based on gender identity to ensure equitable access to housing) could be effective targets for intervention to reduce suicide attempts among transgender individuals in Argentina. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Suicidal behavior; Social stigma; Mental health; Logistic regression analysis; Argentina; mental health; stigma; suicide; transgender; violence

Clinician competencies: Strengths and limitations for work with transgender and gender non-conforming (TGNC) clients. - Whitman, Chassitty N.; Han, Heather (International Journal of Transgenderism, 2017)
Individuals who identify as transgender or gender nonconforming (TGNC) face a number of health disparities compared to individuals who identify as cisgender (those who self-identify with the sex they were assigned at birth). For example, TGNC individuals experience heightened rates of clinical depression, anxiety, general psychological distress, suicidal ideation, and suicide attempts. Despite these troubling disparities, many TGNC individuals report hesitance to seek mental health services due to concerns regarding culturally insensitive or even overtly discriminatory services from providers. In addition to decreasing service utilization among TGNC populations, discriminatory services impair intervention effectiveness even when TGNC individuals persist in seeking mental health services. The American Psychological Association (APA) and the World Professional Association for Transgender Health (WPATH) provide guidelines for culturally competent work with TGNC clients; however, research indicates a profound lack of TGNC-specific training and resources among mental health care providers. To address this gap, the present investigation utilized a mixed-method design to assess training experiences, understanding of terminology, and TGNC competence among mental health care providers at various training levels. Participants were current mental health clinicians across the United States. Implications for improving reported and demonstrated weaknesses are discussed. [ABSTRACT FROM PUBLISHER]
Keywords: Mental health services; Transgender people; Attitudes toward sex; Psychology; Mental illness treatment; Clinical competence; Help-seeking behavior; Patient-professional relations; Transcultural medical care; competence; gender nonconforming; mental health; TGNC; Transgender

NUNCA OLVIDAR/TO NEVER FORGET: Pulse Orlando. - Fountain-Stokes, Lawrence La (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author reflects on the June 12, 2016 massacre at the gay nightclub Pulse in Orlando, Florida by Omar Mateen in which 49 individuals were killed. He comments on the effect the massacre has had on the LGBT community in Orlando as well as on similar nightclubs across the U.S. He goes on to profile several individuals killed in the shooting including Brenda Lee Marquez McCool, Luis Daniel Wilson Leon, and Jean Carlos Mendez Perez.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; LGBTQ+ communities -- Social aspects; Violence against LGBTQ+ people; Massacres; Mateen, Omar, 1986-2016

Suicidal Ideation, Resilience, and Healthcare Implications for Newly Diagnosed HIV-Positive Men Who Have Sex with Men in China: A Qualitative Study. - Li, Haochu; Holroyd, Eleanor; Zhang, Jie; Tucker, Joseph; Jiang, Baofa (Archives of Sexual Behavior, 2017)
Globally, suicidal ideation and behavior have been widely reported among people living with human immunodeficiency virus (HIV). Knowledge gaps exist regarding the longer life and resilience-related experiences of people living with HIV (PLWH). Specifically, there is a dearth of data about the interaction of perceived risk and resilient factors resulting in a wide spectrum of intentional suicidal ideation outcomes in a Chinese cultural context. This qualitative research drew from a larger ethnographic study of newly diagnosed HIV-positive men who have sex with men (MSM) in Mainland China. Interviews were conducted with 31 MSM within 6 months of diagnosis of HIV infection. Initial suicidal ideation was commonly reported with participants subsequently feeling more resilient to these thoughts through gaining a greater understanding of their prognosis and treatment. Post-HIV diagnosis, some participants reported forming new relationships and receiving increased support from their partners, friends, peers, families, and community-based organizations. At follow-up, these participants generally reported suicidal ideation had declined. However, participants who continued to express suicidal ideation perceived extended pressure from their families' expectations for them to engage in heterosexual marriages and parenthood. Furthermore, these men reported ongoing hardships in their daily life, unemployment, lack of social support, and isolation. Among this Mainland Chinese cohort of HIV-positive MSM, suicidal ideation may be a transient phenomenon experienced initially following HIV diagnosis that resolves with increased and specific familial, social, and service-based support. It is crucial to identify the causes of stress and social suffering associated with HIV diagnosis in order to reduce suicidal ideation. In China, action is needed to develop routine mental health screening and to increase services that support PLWH. Important services mechanism to accomplish this are promoting resilience through intentional activities as well as continued public health campaigns to reduce stigma toward HIV-positive MSM. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal ideation; HIV-positive men; Sexual orientation; Men who have sex with men; Men; HIV-positive persons; Human sexuality; HIV infections; Homosexuality; Resilience (Personality trait); PSYCHOLOGICAL aspects; HIV infection epidemiology; Qualitative research; China; HIV; Resilience

The buffering role of social support on the associations among discrimination, mental health, and suicidality in a transgender sample. - Trujillo, Michael A.; Perrin, Paul B.; Sutter, Megan; Tabaac, Ariella; Benotsch, Eric G. (International Journal of Transgenderism, 2017)
Introduction: Per the minority stress framework, trans individuals often experience psychological distress given the unique stress engendered by gender identity–related discrimination. Prior research has identified social support as particularly important for psychological distress and has suggested that social support may moderate this relationship. The purpose of the current study was to explore the patterns of connections among discrimination, mental health, and suicidal ideation in trans individuals and whether social support moderates these relationships. Methods: Participants (N = 78) completed measures of these constructs as part of a national online survey. Results: A series of simultaneous multiple regressions found that harassment/rejection discrimination was a unique positive predictor of mental health symptoms and suicidal ideation, with depression positively predicting suicidal ideation. A mediational model indicated that the association between harassment/rejection discrimination and suicidal ideation was fully mediated by depression. Three moderated meditational models were run, and one yielded a significant interaction, such that discrimination predicted suicidal ideation most strongly when participants had low social support from a significant other in comparison to participants who had moderate or high support. Further, conditional direct effects identified that discrimination led to ideation only for individuals with low support from friends or a significant other but not for those with moderate or high support. Conclusions: Helping trans individuals cope with harassment and rejection, particularly by drawing on social support, may promote better mental health, which could help reduce suicidality in this population. [ABSTRACT FROM AUTHOR]
Keywords: Discrimination; Mental health; Social support; Suicidal ideation; Transgender people; Minority stress; Psychology; Mental depression; Surveys; Multiple regression analysis; Data analysis software; Descriptive statistics; mental health; social support; suicide

Are LGBT Populations at a Higher Risk for Suicidal Behaviors in Australia? Research Findings and Implications. - Skerrett, Delaney M.; Kõlves, Kairi; De Leo, Diego (Journal of Homosexuality, 2015)
The aim of this article is to review the Australian literature about suicidality in minority sexual identity and/or behavior groups in order to determine the evidence base for their reported higher vulnerability to suicidal behaviors than heterosexual and non-transgendered individuals in the Australian context, as well as to identify the factors that are predictive of suicidal behaviors in these groups in Australia. A literature search for all available years (until the end of 2012) was conducted using the databases Scopus, Medline, and Proquest for articles published in English in peer-reviewed academic journals. All peer-reviewed publications that provided empirical evidence for prevalence and predictive factors of suicidal behaviors among LGBT individuals (or a subset thereof) in Australia were included. Reference lists were also scrutinized to identify “gray” literature for inclusion. The results revealed that there is only limited research from Australia. Nevertheless, although no population-based studies have been published, research indicates that sexual minorities are indeed at a higher risk for suicidal behaviors. In order to further the understanding of suicidal behaviors and potential prevention among LGBT groups in the Australia, further research is needed, particularly on fatal suicidal behaviors. [ABSTRACT FROM PUBLISHER]
Keywords: Suicidal behavior; Suicidal ideation; Psychology of LGBTQ+ people; Intersex people; Self-mutilation; Suicide prevention; Australia; bisexual; gay; intersex; lesbian; self-harm; suicide; transgender

LGBTQ adolescents of color: Considerations for working with youth and their families. - Murphy, James; Hardaway, Rashad (Journal of Gay & Lesbian Mental Health, 2017)
Adolescence is a period during which youth are tasked with self-discovery and formation of their identity. This may be more challenging for youths of minority backgrounds. LGBTQ individuals have the additional task of understanding who they are in comparison to heterosexual peers. For LGBTQ youth of color, however, a multiple minority status can lead to particular psychosocial vulnerabilities. These vulnerabilities are noted in family and social life, and may occur in both online and in-person settings. A review of literature as it pertains to a clinical vignette was performed, highlighting risk factors and protective factors for LGBTQ youth of color during adolescence. Cross-sectional data and longitudinal studies have been noted to show that sexual minority youth of color are at increased risk of relationships with adult individuals, substance use, suicidal ideation and suicide attempts, and trauma. In light of this, minority status may be a protective factor in these youths' lives. It is important for clinicians to be aware of the intersectionality of LGBTQ status and racial/ethnic identity, as this may yield to increased risk for psychosocial stressors and comorbidities. Furthermore, clinicians should be aware of resources for patient referral to mitigate these factors. Further research is needed to understand the complex dynamics that occur in the lives of LGBTQ youth of color. [ABSTRACT FROM PUBLISHER]
Keywords: Black LGBTQ+ people; LGBTQ+ young adults; Heterosexuals; Work environment; Suicidal ideation; Adolescent; intersectionality; LGBTQ; racial minority; sexual minority

I JUST CAN'T EVEN. - McGlotten, Shaka (GLQ: A Journal of Lesbian & Gay Studies, 2018)
A personal narrative is presented in which the author reflects on how social and political conditions since 2014 have depressed her, citing incidents such as police shootings of black men, the election of U.S. President Donald Trump, and the massacre at the gay nightclub Pulse in Orlando, Florida.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; Sadness

Pathways to Suicide in Lesbian and Gay Populations in Australia: A Life Chart Analysis. - Skerrett, Delaney; Kõlves, Kairi; Leo, Diego; Kõlves, Kairi; De Leo, Diego; Skerrett, Delaney M (Archives of Sexual Behavior, 2017)
Given the continued paucity of research into suicide in lesbian and gay (LG) people, there is a need to investigate the characteristics of those LG suicides that are able to be identified. The aim of this article was to analyze pathways to suicide in lesbian and gay individuals by way of life charts. Data were gathered through of 24 psychological autopsy interviews with next-of-kin of an LG person who had died by suicide. The female (n = 5) and male (n = 19) cases in this study clustered into younger and older suicides. The defining feature of the younger suicides was lack of acceptance by family and, to a lesser extent, self, and that of the older suicides was romantic relationship conflict, although this was also common in younger suicides. There appears to have been, furthermore, an accumulation of risk factors, particularly in the period prior to death where these specific risk factors combined with other life stressors, such as work problems. Initiatives to reduce stigma around diversity in sexuality and to support families and young people through the "coming out" process as well as services designed to assist those experiencing problems in same-sex relationships, in particular, would appear to be the most relevant within the trajectories presented. [ABSTRACT FROM AUTHOR]
Keywords: Psychology of lesbians; Suicide victims; Psychology of gay people; Sexual orientation; Psychology; Gay; Lesbian; Psychological autopsy; Risk factors; Suicide

Health Status and Risk Behaviors of Sexual Minorities Among Chinese Adolescents: A School-Based Survey. - Zhang, Huiping; Wong, William C. W.; Ip, Patrick; Fan, Susan; Yip, Paul S. F. (Journal of Homosexuality, 2017)
This study aimed to examine the association between sexual orientation and health disparities among a stratified random sample of 3776 secondary students in Hong Kong. The prevalence of homosexuality and bisexuality were 1.5% and 2.6% in boys and 1.8% and 3.7% in girls, respectively. A total of 10.7% of boys and 8.8% of girls were unsure of their sexual orientation. Homosexual and bisexual boys reported poorer physical and mental health than their heterosexual peers. Homosexual and bisexual boys were more likely to engage in smoking, frequent drinking, and vaginal sex and be subjected to sexually transmitted disease and sexual victimization. However, lesbian and bisexual girls were less likely to engage in risky health behaviors except for smoking and being subjected to sexual victimization. There is a gender-specific problem that may warrant prevention and intervention programs to address the unique health issues facing homosexual and bisexual adolescents in Hong Kong. [ABSTRACT FROM AUTHOR]
Keywords: Health of LGBTQ+ people; LGBTQ+ youth; LGBTQ+ history; LGBTQ+ people's sexual behavior; Social conditions of LGBTQ people; Health; Hong Kong (China) -- Social conditions; Twenty-first century; Hong Kong Chinese adolescents; mental health; physical health; risky behaviors; school survey; sexual minority; sexual orientation

Effects of state nondiscrimination laws on transgender and gender-nonconforming individuals' perceived community stigma and mental health. - Gleason, Hillary A.; Livingston, Nicholas A.; Peters, Marianne M.; Oost, Kathryn M.; Reely, Evan; Cochran, Bryan N. (Journal of Gay & Lesbian Mental Health, 2016)
In this study, we investigated the potential effects of statewide nondiscrimination laws on community stigma, as well as its relationship with psychosocial stressors and mental health outcomes. Gender minority individuals (N= 120) completed an online survey containing psychosocial and mental health outcome measures. The experiences of participants who resided in stateswithandwithoutnondiscrimination laws were compared in regard to perceived community stigma. Hierarchical and logistic regression were used to test the hypothesized relationships between community stigma and lifetime discrimination and victimization; current depression, anxiety, and substance use; and lifetime suicide attempts. Approximately 60% of participants reported residing in a state without nondiscrimination laws (n= 74). These participants reported higher levels of perceived community stigma, and stigma was positively associated with reports of lifetime discrimination and victimization. The observed relationship between stigma and current anxiety symptoms was marginally significant. Logistic regression results indicate that stigma was positively related to the odds of reporting a lifetime suicide attempt. Analyses suggest that statewide nondiscrimination laws are associated with lower rates of perceived stigma at the community level, which, in turn, is associated with lower rates of discrimination, victimization, anxiety, and risk for attempted suicide. [ABSTRACT FROM AUTHOR]
Keywords: Anti-discrimination laws; Transgender people; Social stigma; Mental health; Psychological stress; Sexual minorities; Psychology; Law; mental health; stigma; TGNC; transgender

IN SECURITY. - Beauchamp, Toby (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author reflects on how increased security following the 2016 massacre at the Pulse gay nightclub in Orlando, Florida demonstrates the social conditions of LGBT individuals as well as U.S. surveillance policies. He discusses how security provided at both the state and private levels were not widely accepted in some LGBT communities already concerned about police tactics, incarceration rates, law enforcement administration.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; Social conditions of LGBTQ people; Violence against LGBTQ+ people; National security -- United States; Nightclubs -- Security measures; Video surveillance

Systematic review of the psychometric properties of transphobia scales. - Morrison, Melanie A.; Bishop, CJ; Gazzola, Stephanie B.; McCutcheon, Jessica M.; Parker, Kandice; Morrison, Todd G. (International Journal of Transgenderism, 2017)
Introduction: Prejudice and discrimination against transgender individuals (i.e., transphobia) is pervasive and has been shown to have pernicious effects on the physical (e.g., substance abuse and other self-harm behaviors) and psychological (e.g., depression and suicidal ideation) well-being of those targeted. Aims: To date, a review of the psychometric properties of scales assessing transphobia has not been conducted; this gap compromises researchers' ability to make informed measurement decisions. Methods: In the current study, 61 articles that contained 83 scales were identified, and their adherence to best practices in psychometric testing was evaluated. Results: Most of the transphobia scales included in the current review did not provide sufficient information about item generation and refinement, scale dimensionality, scale score reliability, or validity. Each scale was entered into a table and was ranked on the basis of its total score. A score of 1 was issued for each psychometric feature that adhered to best practice guidelines, with total scores ranging from 0 to 5 (i.e., higher scores denote greater psychometric soundness). Discussion: Properties of the reviewed scales are summarized and recommendations are made for future transphobia scale development and validation. The measures that emerged as possessing the highest scores and, subsequently, the greatest utility are identified. [ABSTRACT FROM AUTHOR]
Keywords: Discrimination; Prejudices; Transgender people; Psychology; Psychometrics; Experimental design; Research methodology; Medical protocols; Research evaluation; Systematic reviews (Medical research); Research methodology evaluation; Psychometric; trans; transgender; transnegativity; transphobia; transprejudice; validity

MONSTROUS CHILDREN OF PREGNANT ANDROIDS: Latinx Futures after Orlando. - cárdenas, micha (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author presents her thoughts on the future of social conditions for Hispanic Americans (Latinx) and Hispanic American LGBT people in the aftermath of the 2016 massacre at the gay nightclub Pulse in Orlando, Florida. She criticizes the depiction of people of color and mixed-race people as "monstrous" in nationalist immigration narratives. She goes on to discuss how trans Latinx kinship can be created through solidarity and acts of acceptance.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; Hispanic American LGBTQ people; LGBTQ+ communities; Social history; Hispanic Americans -- Social conditions; Racially mixed people -- United States; Twenty-first century

Help-seeking for nonsuicidal self-injury in sexual minority adolescent and young adult females. - Zaki, Landon F.; Gross, Madeline; Pachankis, John E. (Journal of Gay & Lesbian Mental Health, 2017)
Subgroups of sexual minority adolescent and young adult females (e.g., lesbian, bisexual, questioning) have been underrepresented in youth health research. However, evidence suggests they experience compromised coping strategies compared to heterosexual female peers and may be reluctant to seek professional help due to stigma. An Internet survey (N = 482) examined nonsuicidal self-injury (NSSI), suicidal ideation, and help-seeking for NSSI in sexual minority and heterosexual adolescent and young adult females with histories of NSSI. Compared to heterosexual female youth, lesbian youth reported lower rates of NSSI and greater help-seeking from professionals, whereas bisexual youth reported greater suicidal ideation and a reluctance to seek professional help, favoring the help of romantic partners instead. Results extend research on help-seeking for risk behaviors in sexual minority female youth subgroups, while echoing the need to reduce sexual minority stigma in healthcare. [ABSTRACT FROM AUTHOR]
Keywords: Self-mutilation; Sexual minorities; Teenagers; Young women; Help-seeking behavior; Help-seeking; nonsuicidal self-injury; sexual minority; youth

Differences in Parental Monitoring Components and Their Associated Health Indicators Between Sexual-Minority and Heterosexual Girls. - Montano, Gerald T.; McCauley, Heather L.; Miller, Elizabeth; Chisolm, Deena J.; Marshal, Michael P. (Journal of GLBT Family Studies, 2017)
Our study sought to assess whether parental monitoring and their associations with health behaviors differed for heterosexual girls compared to sexual-minority girls (girls who identified as lesbian or bisexual, endorsed same-sex attraction, or had same-sex romantic or sexual partners). We analyzed three components of parental monitoring—adolescent disclosure, parental solicitation, and parental knowledge—between heterosexual and sexual-minority girls. We also tested if the associations between these three constructs and adolescent relationship abuse, suicidality, heavy drinking, binge drinking, anxiety symptoms, and depressive symptoms were different for heterosexual girls compared to sexual-minority girls. Sexual-minority girls were less likely to disclose accurately to their parents their location and activities and perceived their parents asked less and knew less about their location and activities than did heterosexual girls. Heterosexual girls who reported higher levels of adolescent disclosure were less likely than were sexual-minority girls to report suicidality and anxiety symptoms. Additionally, heterosexual girls who reported higher levels of parental knowledge were also less likely than were sexual-minority girls to report anxiety and depressive symptoms. These findings suggest that parental monitoring may not be as protective for sexual-minority girls as it is for heterosexual girls. [ABSTRACT FROM PUBLISHER]
Keywords: Parents; Heterosexual women; Health behavior; Teenage girls; Health status indicators; Familial relationships; mental health; parental monitoring; sexual-minority girls; substance use

The Bromance: Undergraduate Male Friendships and the Expansion of Contemporary Homosocial Boundaries. - Robinson, Stefan; Anderson, Eric; White, Adam (Sex Roles, 2018)
The present study provides the first known qualitative examination of heterosexual undergraduate men's conceptualization and experiences of the bromance, outside research on cinematic representations. Drawing on semi-structured interviews with 30 undergraduate men enrolled in one of four undergraduate sport-degree programs at one university in the United Kingdom, we find these heterosexual men to be less reliant on traditional homosocial boundaries, which have previously limited male same-sex friendships. Contrary to the repressive homosociality of the 1980s and 1990s, these men embrace a significantly more inclusive, tactile, and emotionally diverse approach to their homosocial relationships. All participants provided comparable definitions of what a bromance is and how it operates, all had at least one bromantic friend, and all suggested that bromances had more to offer than a standard friendship. Participants described a bromance as being more emotionally intimate, physically demonstrative, and based upon unrivalled trust and cohesion compared to their other friendships. Participants used their experiences with romances and familial relations as a reference point for considering the conditions of a bromance. Results support the view that declining homophobia and its internalization has had significantly positive implications for male expression and intimacy. Conclusions are made about the bromance's potential to improve men's mental health and social well-being because participants indicate these relationships provide a space for emotional disclosure and the discussion of potentially traumatic and sensitive issues. [ABSTRACT FROM AUTHOR]
Keywords: Male friendship; Heterosexual men; Romantic friendship; Male college students; Psychology of men; Men's mental health; Bromance; Homohysteria; Homosocial; Masculinity; Men; Stoicism; Suicide

THE ORLANDO(S)CENE. - Lim, Eng-Beng (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author contrasts the political and social climate under U.S. President Donald Trump to the atmosphere of social acceptance at the gay nightclub Pulse in Orlando, Florida, the site of a 2016 massacre that killed 49 people. He criticizes the racism and misogyny perpetuated by Trump and other Far Right Republicans, suggesting that toxic masculinity can be combated by the sense of belonging created in spaces like Pulse.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; LGBTQ+ communities -- Social aspects; Social acceptance; Masculinity -- Social aspects; Trump, Donald, 1946- -- Political & social views

Bisexuality, Mental Health, and Media Representation. - Johnson, Hannah J. (Journal of Bisexuality, 2016)
There is a mental health crisis in the bisexual community, and though the issues of mental health and media representation are analyzed separately in bisexual literature, they are rarely put side by side. Media such as television, film, and music often contribute to the perpetuation of negative stereotypes and stigmas about people who are bisexual. How do these issues contribute to the high rates of depression, anxiety, and suicide among individuals who are bisexual? What issues do individuals who are bisexual face when they choose to seek help? This research project contributes to bisexual literature by drawing connections between media representation and mental health by firstly examining existing literature on bisexual issues such as biphobia, bisexual erasure, media representation, and mental health, and secondly discussing the results of an online survey to determine how other people who identify as bisexual feel about media representation and its relationship to the mental health crisis in the bisexual community. [ABSTRACT FROM AUTHOR]
Keywords: Bisexuality; Bisexuals in mass media; Mental illness; Mental health of LGBTQ people; LGBTQ+ literature; Biphobia; Bisexual communities; Mental depression; biphobia; bisexuality; film; mental health; mental illness; music; television

The relationship between social support and suicide risk in a national sample of ethnically diverse sexual minority women. - Tabaac, Ariella R.; Perrin, Paul B.; Rabinovitch, Annie E. (Journal of Gay & Lesbian Mental Health, 2016)
This study examined the relationship between three types of social support and suicidal ideation and lifetime attempts among a national sample of ethnically diverse sexual minority women (SMW). Participants (N= 150) completed measures of social support and suicidal ideation/attempts. After controlling for socioeconomic status, social support explained 12.3% of the variance in past suicidal ideation and 10.7% in lifetime suicide attempts. Social support from family and significant other were both inversely associated with suicidal ideation, and social support from family inversely with lifetime attempts. Interventions that strengthen family relationships could be a buffer of suicidality in this population. [ABSTRACT FROM AUTHOR]
Keywords: Bisexual women; Families; Lesbians' social life & customs; Suicidal behavior; Quality of life; LGBTQ+ people's sexual behavior; Bisexual; family; lesbian; suicide

A comparison of health disparities among transgender adults in Colorado (USA) by race and income. - Seelman, Kristie L.; Young, Sarah R.; Tesene, Megan; Alvarez-Hernandez, Luis R.; Kattari, Leo (International Journal of Transgenderism, 2017)
Transgender individuals face heightened risks for discrimination, harassment, and violence that impact their psychosocial well-being and physical health. However, few studies have thoroughly examined the general physical and mental health of transgender adults or within-group health differences by race/ethnicity and income. To that end, after controlling for health insurance status, age, and engagement in exercise, this study asks: (a) Are transgender people of color more likely than White transgender individuals to experience poor health outcomes? and (b) Is lower annual household income among transgender adults associated with poorer health outcomes? The study analyzes secondary data from a survey of transgender adults (N= 417) in one state in the western United States using multiple linear regression and logistic regression models. Results showed that transgender people of color had significantly greater odds than their White counterparts of having arthritis/rheumatoid arthritis/gout/lupus/fibromyalgia, or asthma but lower odds of being told by a provider that they had depression. Having a lower income was significantly associated with worse general health as well as multiple indicators of poor physical and mental health, including depression, anxiety, and suicidal ideation. We discuss implications for health care delivery for transgender people and for future research. [ABSTRACT FROM PUBLISHER]
Keywords: Transgender people; Psychology; Chronic disease risk factors; Age distribution; Evaluation of medical care; Race; Regression analysis; Surveys; Logistic regression analysis; Socioeconomic factors; Health disparities; Colorado; health; income; mental health; race; Transgender

The Interrelations Between Internalized Homophobia, Depressive Symptoms, and Suicidal Ideation Among Australian Gay Men, Lesbians, and Bisexual Women. - McLaren, Suzanne (Journal of Homosexuality, 2016)
Internalized homophobia has been linked to depression among gay men, lesbians, and bisexuals. Relatively little research has investigated the link between internalized homophobia and suicidal thoughts and behaviors. The current research investigated the interrelations among internalized homophobia, depressive symptoms, and suicidal ideation by testing additive, mediation, and moderation models. Self-identified Australian gay men (n = 360), lesbians (n = 444), and bisexual women (n = 114) completed the Internalized Homophobia Scale, the Center for Epidemiological Studies Depression Scale, and the suicide subscale of the General Health Questionnaire. Results supported the additive and partial mediation models for gay men and the mediation and moderation models for lesbians. None of the models were supported for bisexual women. The findings imply that clinicians should focus on reducing internalized homophobia and depressive symptoms among gay men and lesbians, and depressive symptoms among bisexual women, to reduce suicidal ideation. [ABSTRACT FROM PUBLISHER]
Keywords: Internalized homophobia; Suicidal ideation; Mental health of LGBTQ people; Mental depression; Symptoms; Australians; Moderation (Statistics); Mediation (Statistics); Depressive symptoms; internalized homophobia; suicidal ideation

Mostly Heterosexual and Lesbian/Gay Young Adults: Differences in Mental Health and Substance Use and the Role of Minority Stress. - Kuyper, Lisette; Bos, Henny (Journal of Sex Research, 2016)
Individuals mostly attracted to other-sex but also to same-sex partners are a distinct and common sexual orientation group with possibly increased levels of health problems. The current study examined whether mostly heterosexual individuals differed in mental health and substance use from lesbian/gay individuals and whether sexual minority risk and protective factors offer an explanation in a sample of 528 Dutch young adults (16 to 25 years old, M = 21.2 years). Mostly heterosexual participants reported higher levels of psychological distress, suicidality, drug use, and smoking than lesbian/gay participants and equal levels of binge drinking. They also reported higher levels of internalized negativity to same-sex attractions, less openness to family members and others, less community involvement, and lower numbers of lesbian/gay/bisexual friends. However, bootstrapped mediation analysis showed that the differences in minority stress risk and protective factors did not mediate most of the differences in mental health and substance use with one exception: higher levels of psychological distress were mediated by the higher levels of internalized negativity to same-sex attractions. The limited explanatory power of the minority stress factors combined with the elevated level of problems of mostly heterosexual individuals call for future studies examining other risk and protective factors. [ABSTRACT FROM AUTHOR]
Keywords: Heterosexuals; Mental health of gay men; Lesbians; Substance abuse; Minority stress; Mental health

A Comparative Analysis of a Community and General Sample of Lesbian, Gay, and Bisexual Individuals. - Kuyper, Lisette; Fernee, Henk; Keuzenkamp, Saskia (Archives of Sexual Behavior, 2016)
Samples recruited at lesbian, gay, and bisexual (LGB) venues have certain benefits, but a major drawback is that these samples are prone to bias as they only contain LGB participants who visit such venues. Empirical data with regard to the potential differences between LGB community samples and LGB general samples may shed some light on the generalizability of research findings from convenience samples recruited through LGB venues. The current study attempted to contribute to existing knowledge by examining differences in social demographics, sexual orientation, minority stress, and mental health between a convenience sample recruited at LGB venues ("community sample," N = 3,403) and an LGB sample recruited from a general research panel in the Netherlands ("panel sample," N = 1,000). Various differences were found. In general, community participants were younger, reported a more exclusive same-sex sexual orientation, were more open about their sexual orientation, had lower levels of internalized homonegativity, and encountered more negative social reactions on their LGB status. They also reported higher levels of psychological distress and suicidality. The Nagelkerke R (2) of the analyses (which were adjusted for sociodemographic differences) ranged from .08 (suicide plans among men) to .27 (sexual attraction among women). However, while the estimates of sociodemographics, sexual orientation, minority stress, and mental well-being differed, the relationships between these constructs were comparable in both samples. Implications and suggestions for future studies are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Mental health of LGBTQ people; Sexual orientation; Homosexuality; Minority stress; Bisexuality; Lesbians; Psychology of lesbians; Mental health; PSYCHOLOGY; Psychological stress; Sociodemographic factors; Statistics on minorities; Minorities; Residential patterns; Psychological factors; Netherlands; Gay men

Rethinking queer failure: Trans youth embodiments of distress. - Roen, Katrina (Sexualities, 2019)
This article examines trans youth embodied distress in relation to the workings of normativity. I consider the normative cruelties that structure the embodied and gendered experiences of trans youth, and I locate trans youth embodied distress in relation to a notion of queer failure. Central to this analysis is the way emotion is implicated in normativity. I focus on the idea that happiness norms are implicated in keeping gendered subjects in line, and I consider the specific emotions that are bound up in queer failure and embodied distress, such as shame, hatred, and fear. Trans youth frequently respond to the challenges of embodied distress by embarking on a significant emotional, relational project that can involve reworking the relationship to the body and reworking the relationship to norms. In the context of this emotional, relational project, some trans youth self-harm and/or become suicidal. I work with empirical data from trans and gender questioning youth who write online about their self-harming and suicidal feelings, and I use this analysis to locate self-harm in relation to the ways in which some trans youth are crafting embodied and gendered ways of being that break with norms. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Youth; Suicidal behavior; Distress (Psychology); Normativity (Ethics); Emotion; gender queer; normativity; self-harm; transgender youth

Consequences of runaway and thrownaway experiences for sexual minority health during the transition to adulthood. - Pearson, Jennifer; Thrane, Lisa; Wilkinson, Lindsey (Journal of LGBT Youth, 2017)
Sexual minority youth are more likely to run away from home or experience homelessness, leaving them at increased risk of victimization and negative health outcomes. In this study, the authors use a developmental perspective that considers both vulnerable beginnings in families and the risky trajectories that follow to explore the connections between running away or being thrown out by parents and sexual minority women's and men's health in adulthood. Using four waves of data from the National Longitudinal Study of Adolescent to Adult Health (Add Health), the authors consider multiple dimensions of health and several potential intervening mechanisms. Findings suggest that runaway and thrownaway experiences have persistent negative effects on health into adulthood, in part because of their association with sexual victimization, educational attainment, and relationships with parents. Sexual minority men who have been thrown out by parents report a greater likelihood of suicidal ideation, smoking, and substance use into adulthood. Sexual minority women with runaway experiences have poorer health and increased depressive symptoms, while women with thrownaway experiences engage in more health risk behaviors. Sexual victimization stands out as a key mechanism for sexual minority women's health, as more than half of these young women report experiences of sexual victimization. [ABSTRACT FROM AUTHOR]
Keywords: Health; Homelessness; Risk-taking behavior; Family relations; Psychology of LGBTQ+ people; Adolescence; Psychology; Sex crimes -- Risk factors; Mental depression; Runaways (People); health; homelessness; runaway youth; Sexual minorities; transition to adulthood

Cyberbullying and health: A preliminary investigation of the experiences of Canadian gay and bisexual adult men. - Lam, Simon; Ferlatte, Olivier; Salway, Travis (Journal of Gay & Lesbian Social Services, 2019)
The majority of cyberbullying studies are within the school environment. This quantitative study investigates cyberbullying among Canadian gay and bisexual men outside of the educational setting through a cross-sectional survey. Of the 7,430 respondents, 4.6% reported cyberbullying in the past year, with younger, Aboriginal, lower-educated, lower-income respondents reporting higher odds of experiencing cyberbullying. Victimization from cyberbullying was significantly associated with experiences of antigay discrimination as well as worry about antigay prejudice. A variety of negative health outcomes were also associated with cyberbullying, including intimate partner violence and suicidality. Implications for social service providers and future research are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Cyberbullying; Gay community; Bisexual men; Intimate partner violence; Social services; Gay men; Social impact; School environment; bisexual men; cyberbullying; gay men; homophobia

Sociodemographic Characteristics and Psychological Adjustment Among Transsexuals in Spain. - Guzmán-Parra, José; Sánchez-Álvarez, Nicolás; Diego-Otero, Yolanda; Pérez-Costillas, Lucía; Esteva de Antonio, Isabel; Navais-Barranco, Miriam; Castro-Zamudio, Serafina; Bergero-Miguel, Trinidad; Guzmán-Parra, José; Sánchez-Álvarez, Nicolás; de Diego-Otero, Yolanda; Pérez-Costillas, Lucía (Archives of Sexual Behavior, 2016)
This study examined the sociodemographic characteristics and the psychological adjustment of transsexuals in Andalusia (Spain), and also analyzed the differences between female-to-male (FtM) and male-to-female (MtF) transsexuals. The sample included 197 transsexuals (101 MtF and 96 FtM) selected from those who visited the Transsexual and Gender Identity Unit at the Carlos Haya Hospital in Malaga between 2011 and 2012. Our analyses indicated that MtF transsexuals were more likely to have lower educational levels, live alone, have worked less frequently throughout their lifetime, and have engaged in prostitution. For FtM transsexuals, there were more frequent references to the mother's psychiatric history and more social avoidance and distress. Multivariate analysis showed that the number of personality dysfunctional traits and unemployment status were associated with depression in the entire sample. The following three conclusions can be made: there are significant differences between MtF and FtM transsexuals (mainly related to sociodemographic variables), depression was high in both groups, and a remarkable percentage of transsexuals have attempted suicide (22.8 %) or have had suicidal thoughts (52.3 %). [ABSTRACT FROM AUTHOR]
Keywords: Psychological adaptation; Transsexuals; Gender dysphoria; Transsexualism; Adaptability (Psychology); Gender identity; Human sexuality; Psychology; Sociodemographic factors; Andalusia (Spain); Spain; Psychosocial adjustment; Sociodemographic characteristics; Transgender

Suicide risk factors among trans feminine individuals in Lebanon. - Kaplan, Rachel L.; Nehme, Simon; Aunon, Frances; de Vries, David; Wagner, Glenn (International Journal of Transgenderism, 2016)
Transgender women are disproportionately affected by high rates of depression and suicide attempts. It is therefore important to identify factors that influence suicidal risk, particularly in the Middle East, where little research has examined the mental health of transgender women. We examined risk factors associated with suicide attempts among 54 trans feminine individuals in Beirut, Lebanon. Data were collected using interviewer-administered questionnaires and were analyzed using bivariate statistics. Twenty-five (46%) participants reported having ever attempted suicide. Among them, only one participant had received some kind of counseling in response to the attempted suicide. Low general social support, low social integration, and low support from peers were significantly associated with a history of attempted suicide, as were being more open about transgender identity in public and any hormone use (past or current). These findings suggest that progression in gender transition can have unintended consequences related to mental health and suicide risk, while social support systems can mitigate the impact of mental health problems. Some of these findings mirror other contexts around the globe and can inform mental health services for trans feminine individuals in Lebanon, the greater Middle East region, and other international settings. [ABSTRACT FROM AUTHOR]
Keywords: Femininity; Suicidal ideation; Transgender people; Psychology; Mental depression risk factors; Questionnaires; Statistics; Descriptive statistics; Psychological factors; Middle East; Lebanon; MENA; mental health; suicide; trans feminine

Letters. - Philbrook, Craig Gingrich; Pérez, Kimberlee (QED: A Journal in GLBTQ Worldmaking, 2017)
Keywords: Heteronormativity; Violence against LGBTQ+ people; Orlando Nightclub Massacre, Orlando, Fla., 2016

Sex Education Inclusivity and Sexual Minority Health: The Perceived Inclusivity of Sex Education Scale. - Keiser, Gregory H.; Kwon, Paul; Hobaica, Steven (American Journal of Sexuality Education, 2019)
Minority stress research has demonstrated negative health outcomes in sexual minority populations. However, the influence of sex education on these outcomes remains unclear. In the current study, the Perceived Inclusivity of Sex Education Scale (PISES) was developed and administered to sexual minorities (N = 263) to assess the associations between sex education climate and health outcomes. Greater perceived inclusivity was associated with lower anxiety, depression, and suicidality, but was not associated with sexual risk-taking and substance use. We hypothesized that a number of resilience factors would moderate these relationships, but no interactions were found. These findings may help guide further research on sex education among sexual minorities. [ABSTRACT FROM AUTHOR]
Keywords: Minority stress; Sex education; Sexual minorities; Sexual health; Health of minorities; Educational outcomes; health outcomes; inclusivity; LGB

Orlando: Observances. (Feminist Studies, 2016)
The article presents first person accounts from vigils organized all over the U.S. to mark the June 12, 2016 massacre at the Pulse Night Club in Orlando, Florida. The accounts highlight the complex interplay between racism and homophobia and how people of color express their solidarities with multiple struggles. Accounts presented include that of Joseph Allen Ruanto-Ramirez, Harjant Gill, Lucas Bulgarelli and Aniqa Raihan.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; Racism; Homophobia; Mass shootings -- Florida; Solidarity

Correlates of Suicide Ideation Among LGBT Nebraskans. - Irwin, Jay A.; Coleman, Jason D.; Fisher, Christopher M.; Marasco, Vincent M. (Journal of Homosexuality, 2014)
The aim of this investigation is to outline correlates of suicide ideation among LGBT individuals living in Nebraska. A community-based participatory research approach was utilized to develop a 30-minute, online anonymous survey. Almost half of the sample had seriously considered suicide at some point in their lives. Significant correlates of increased likelihood of suicide ideation are age, gender, transgender identity, income, depression, and discrimination. Suicide ideation is a serious concern for the health of LGBT Nebraskans. Steps should be taken to incorporate individuals who fall into these high-risk categories in suicide outreach programs. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal ideation; Rural LGBTQ people; Mental health of LGBTQ people; Correlation (Statistics); Internet surveys; Sociological research methods; Nebraska; bisexual; gay; lesbian; mental health; suicide; transgender

Prevalence and Mental Health Correlates of Illegal Cannabis Use Among Bisexual Women. - Robinson, Margaret; Sanches, Marcos; MacLeod, Melissa A. (Journal of Bisexuality, 2016)
This study reports the prevalence of cannabis use among bisexual women in Ontario, Canada, and identifies correlations among levels of cannabis use (no use, some use, active use) and measures of mental health and social support. Analysis focused on 262 bisexual women from a bisexual mental health study using respondent-driven sampling. Among networked bisexual women in Ontario, Canada, the weighted prevalence of past-year cannabis use was 33.6%, with 13.8% of bisexual women using cannabis twice or more per week. Cannabis use was positively associated with social support, gay community involvement, outness to family, and depression. There was no significant association between cannabis use and anxiety, posttraumatic stress disorder, antibisexual experiences, or suicidal ideation. Bisexual women's rate of past-year cannabis use is more than 5 times that for Canadian women in general, and is consistent with rates for bisexual women found in U.S. studies. [ABSTRACT FROM PUBLISHER]
Keywords: Bisexual women; Mental health of LGBTQ people; Bisexuality; Biphobia; Social support; Post-traumatic stress disorder; Substance abuse; Marijuana abuse; Ontario; biphobia; bisexuality; cannabis; discrimination; internalized biphobia; mental health; sampling

Suicide Protective Factors Among Trans Adults. - Moody, Chérie; Smith, Nathan (Archives of Sexual Behavior, 2013)
A recent study indicated a suicide attempt rate of 41 % among trans (e.g., trans, transgender, transexual/transsexual, genderqueer, two-spirit) individuals. Although this rate is alarming, there is a dearth of literature regarding suicide prevention for trans individuals. A vital step in developing suicide prevention models is the identification of protective factors. It was hypothesized that social support from friends, social support from family, optimism, reasons for living, and suicide resilience, which are known to protect cis (non-trans) individuals, also protect trans individuals. A sample of self-identified trans Canadian adults ( N = 133) was recruited from LGBT and trans LISTSERVs. Data were collected online using a secure survey platform. A three block hierarchical multiple regression model was used to predict suicidal behavior from protective factors. Social support from friends, social support from family, and optimism significantly and negatively predicted 33 % of variance in participants' suicidal behavior after controlling for age. Reasons for living and suicide resilience accounted for an additional 19 % of the variance in participants' suicidal behavior after controlling for age, social support from friends, social support from family, and optimism. Of the factors mentioned above, perceived social support from family, one of three suicide resilience factors (emotional stability), and one of six reasons for living (child-related concerns) significantly and negatively predicted participants' suicidal behavior. Overall, these findings can be used to inform the practices of mental health workers, medical doctors, and suicide prevention workers working with trans clients. [ABSTRACT FROM AUTHOR]
Keywords: Suicide prevention; Suicidal behavior; Transgender people; Transsexuals; Social support; Protective factors; Suicide; Trans; Transgender; Transsexual

Homophobic bullying in Mexico: Results of a national survey. - Baruch-Dominguez, Ricardo; Infante-Xibille, Cesar; Saloma-Zuñiga, Claudio E. (Journal of LGBT Youth, 2016)
Homophobic and transphobic bullying, through teasing, physical violence, and other forms of aggression, is a problem that affects lesbian, gay, bisexual, and transgender students at all levels of education. Even though there have been legal changes in Mexico to protect human rights of lesbian, gay, bisexual, and transgender people, schools are spaces where discrimination and violence toward them are still common. In 2012, using an online survey asking participants about their experiences with bullying, its consequences, and responses from adults, the authors collected responses from 912 participants younger than 30 years of age who self-identified as lesbian, gay, bisexual, or transgender and who lived in the 32 states of Mexico. Two thirds of participants said that they were victims of bullying during their school years; the majority of these students indicated that they did not have support from teachers or parents to avoid or stop the violence. The consequences of bullying were truancy, dropouts, depression, and suicide attempts. Attitudes that normalize bullying may impede the effective prevention of or response to homophobic and transphobic bullying by teachers and parents. To eliminate homophobic bullying in school, there is a need for sexual diversity trainings for teachers and media campaigns for the general public. [ABSTRACT FROM AUTHOR]
Keywords: Bullying prevention; Bullying; Homophobia; Human rights; Social networks; Stereotypes; LGBTQ+ people; Parent attitudes; School administrators; Schools; Self-evaluation; Surveys; Teachers; Mathematical variables; Victims; Cross-sectional method; College teacher attitudes; Mexico; bullying; LGBT; teachers

Reshaping Time: Recommendations for Suicide Prevention in LBGT Populations. - Mullaney, Clare (Journal of Homosexuality, 2016)
This article serves as one of the supplementary pieces of this special issue on “Mapping Queer Bioethics,” in which we take a solipsistic turn to “map” the Journal of Homosexuality itself. Here, the author examines the journal’s 2011 consensus recommendations for the prevention of LGBT suicide. Invoking the axiom approach of Eve Kosovsky Sedgwick’s seminal Epistemology of the Closet, the author argues that merely offering practical guidelines at the level of the demonstrative and the instructive may not be sufficient models to address the urgency of suicide rates in LGBTQ youth populations. [ABSTRACT FROM PUBLISHER]
Keywords: LGBTQ+ youth; Suicide prevention; Sexual minority community; LGBTQ+ identity; Bioethics; Suicide risk factors; childhood sexuality; gender identity; LGBT education; LGBT youth; psychiatry; suicide; suicide prevention; suicide risk; the closet; Sedgwick, Eve Kosovksy; Journal of Homosexuality (Periodical)

Sexuality and Suicidality: Matched-Pairs Analyses Reveal Unique Characteristics in Non-Heterosexual Suicidal Behaviors. - Harris, Keith (Archives of Sexual Behavior, 2013)
The present findings offer new perspectives on differences between suicide-risk heterosexuals and non-heterosexuals (lesbian, gay, bisexual, and questioning: LGBQ). Results from an anonymous online survey, employing standardized scales, showed that LGBQ participants reported significantly greater suicide-risk than heterosexuals. Seventy-nine matched pairs of suicide-risk LGBQ and heterosexuals were examined by individual suicide risk factors. Results showed no significant differences on separate measures of suicidal ideation; however, LGBQ participants were more likely to report suicide attempts, disclosure of suicidal intentions, and prediction of future suicide attempts. The LGBQ group also indicated greater likelihood of going online to develop new personal relationships. Multiple regression modeling was conducted to guide outreach and support efforts, revealing unique factors predicting help-seeking denial of suicide-risk LGBQ. Implications include the importance of online support and considering sexual minorities not just as a potential high-risk group, but also as a population with unique suicide risks and behaviors. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minorities; Psychology of LGBTQ+ people; Sexual orientation; Risk factors in suicidal behavior; Regression analysis; Gay; Internet; Social support; Suicide

Effects of Minority Stress Processes on the Mental Health of Latino Men Who Have Sex with Men and Women: A Qualitative Study. - Holloway, Ian; Padilla, Mark; Willner, Lauren; Guilamo-Ramos, Vincent (Archives of Sexual Behavior, 2015)
Emerging literature on minority stress among sexual minority populations has described the negative consequences that multiple minority statuses may exert on mental health and well-being. This literature has tended to focus on individuals whose self-identifications reflect sexual minority sexual categories, such as gay or bisexual, and has explored the intersection of these definitions with ethnic, racial, and class statuses. Few such studies have explored mental health among men who actively deny a sexual minority sexual identity label while engaging in same-sex sexual behaviors. The present study used ethnographic interview data from 20 non-gay-identified bisexually behaving Dominican and Puerto Rican men in New York City. Participants described discovery of same sex sexual behavior as a threat to their intimate relationships, community affiliation, and counter to expectations of Latino masculinity. Recounting a wide range of information management strategies used to avoid open disclosure about their sexual lives, participants experienced the potential consequences of disclosure as extreme and even life threatening. Men anticipated social isolation, depression, self-injury, and suicidality as possible outcomes from disclosing sexual behavior with other men to their female romantic partners. This analysis provides direction for future research on minority stress processes and mental health service delivery among Latino men who have sex with men and women. [ABSTRACT FROM AUTHOR]
Keywords: Minority stress; Bisexual men; Men who have sex with men; Well-being; Puerto Ricans; New York (N.Y.); Bisexual; Latino; Men Who Have Sex with Men; Mental health; Sexual orientation; Stress; Dominicans

Minority Stress in Lesbian, Gay, and Bisexual Young Adults in Australia: Associations with Psychological Distress, Suicidality, and Substance Use. - Lea, Toby; Wit, John; Reynolds, Robert (Archives of Sexual Behavior, 2014)
Lesbian, gay, bisexual, and other same-sex attracted young people have been shown to be at a higher risk of mental health problems, including depression, anxiety, suicidality, and substance abuse, compared to their heterosexual peers. Homophobic prejudice and stigma are often thought to underlie these disparities. In this study, the relationship between such experiences of social derogation and mental health and substance use in same-sex attracted young people was examined using Meyer's minority stress theory. An online survey recruited 254 young women and 318 young men who identified as same-sex attracted, were aged 18-25 years, and lived in Sydney, Australia. Multivariate logistic regression analyses showed that internalized homophobia, perceived stigma, and experienced homophobic physical abuse were associated with higher levels of psychological distress and self-reported suicidal thoughts in the previous month. Furthermore, perceived stigma and homophobic physical abuse were associated with reporting a lifetime suicide attempt. The association between minority stress and substance use was inconsistent. While, as expected, higher levels of perceived stigma were associated with club drug dependence, there was an inverse association between internalized homophobia and club drug use, and between perceived stigma and hazardous alcohol use. The findings of this study provide support for the minority stress theory proposition that chronic social stress due to sexual orientation is associated with poorer mental health. The high rates of mental health and substance use problems in the current study suggest that same-sex attracted young people should continue to be a priority population for mental health and substance use intervention and prevention. [ABSTRACT FROM AUTHOR]
Keywords: Minority stress; LGBTQ+ people; Sexual orientation; Mental health; Alcohol; Drugs; Substance use

Buried Above Ground: A University-Based Study of Risk/Protective Factors for Suicidality Among Sexual Minority Youth in Canada. - Peter, Tracey; Taylor, Catherine (Journal of LGBT Youth, 2014)
This study examined differences in suicidal behavior between lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) and non-LGBTQ university students as well as investigated the importance of risk and protective factors in the prediction of suicidality between these two groups. A total of 1,205 university students participated in the survey. Findings show, compared to non-LGBTQ respondents, sexual minority youth are at a greater risk for serious suicidal ideation (8.9% versus 23%, respectively) and suicide attempt (3.5% versus 26.2%). Among LGBTQ respondents, significant risk covariates for suicidality were depressive symptoms, socioeconomic status, being bullied, age, and childhood trauma. The only significant protective factor was self-esteem. [ABSTRACT FROM AUTHOR]
Keywords: Suicide prevention; Bullying; Suicidal ideation; Psychology of LGBTQ+ people; Risk factors in suicidal behavior; Psychology of college students; Multivariate analysis; Psychological tests; Questionnaires; Self-esteem testing; Self-evaluation; Statistics; T-test (Statistics); Data analysis software; Prevention; Canada; At-risk youth; bullying; higher education; mental health; minority stress theory; protective factors; sexual minority youth; students; suicidality; Suicide Behavior Questionnaire

Explaining the Suicide Risk of Sexual Minority Individuals by Contrasting the Minority Stress Model with Suicide Models. - Plöderl, Martin; Sellmeier, Maximilian; Fartacek, Clemens; Pichler, Eva-Maria; Fartacek, Reinhold; Kralovec, Karl (Archives of Sexual Behavior, 2014)
Many studies have found elevated levels of suicide ideation and attempts among sexual minority (homosexual and bisexual) individuals as compared to heterosexual individuals. The suicide risk difference has mainly been explained by minority stress models (MSTM), but the application of established suicidological models and testing their interrelations with the MSTM has been lacking so far. Therefore, we have contrasted two established models explaining suicide risk, the Interpersonal Psychological Theory (IPT) (Joiner, ) and the Clinical Model (CM) (Mann et al., ), with the MSTM (Meyer, ) in a Bavarian online-sample of 255 adult sexual minority participants and 183 heterosexual participants. The results suggested that the CM and the IPT model can well explain suicide ideation among sexual minorities according to the factors depression, hopelessness, perceived burdensomeness, and failed belongingness. The CM and the IPT were intertwined with the MSTM via internalized homophobia, social support, and early age of coming out. Early coming out was associated with an increased suicide attempt risk, perhaps through violent experiences that enhanced the capability for suicide; however, coming out likely changed to a protective factor for suicide ideation by enhanced social support and reduced internalized homophobia. These results give more insight into the development of suicide risk among sexual minority individuals and may be helpful to tailor minority-specific suicide prevention strategies. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority community; Minority stress; Suicide; Homosexuality; Sexual orientation; Bisexual; Gay; Lesbian

A Retrospective Examination of Completed Sexual and Gender Minority Youth Suicides in the United States: What Can Be Learned from Written Online Media? - Wolff, JoshuaR.; Allen, KennethD.; Himes, HeatherL.; Fish, AshleyE.; Losardo, JenniferR. (Journal of Gay & Lesbian Mental Health, 2014)
Due to several high profile suicides and increased social acceptance of lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) persons in the United States, significant media attention has focused on the occurrence of and factors that contribute to sexual and gender minority youth (SGMY) suicide. Although previous research has established an increased likelihood of suicidal ideation among SGMY, no data exist on completed SGMY suicides in the United States or subsequent media coverage. This study examines variables related to completed SGMY suicides in the United States from written electronic media (N = 78) reports from 2004–12 using a mixed-method content analysis. Qualitative results indicate the presence of three major content domains: warning signs, denial of the problem, and conflicting reports. Quantitative results suggest a lack of contextual information but also increased media citation of prevention resources between 2010 and 2012. Clinical and public health implications of SGMY suicide media coverage are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority youth in mass media; Social acceptance; Suicidal behavior in youth; Suicide -- United States; Youth -- United States; Computer network resources; bullying; gender minority; LGBT; media; sexual minority; suicide; youth

RESTLESS URBAN MEANDERINGS: Mournful Flânerie in Troubled Times. - IV, Martin F. Manalansan (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author reflects on modern urban life through a queer perspective, discussing acts of violence, mourning, and acceptance. He discusses why LGBT individuals often seeking out cities as places they can belong. The author goes on to comment on acts of violence like the police killing of Eric Garner in New York City, extrajudicial killings in Manila, Philippines, and the massacre at the gay nightclub Pulse in Orlando, Florida.
Keywords: Social conditions of LGBTQ people; Violence; Orlando Nightclub Massacre, Orlando, Fla., 2016; Urban life -- Social aspects; Garner, Eric, 1970-2014

On Psychotherapy, LGBT Identity, and Cultural Visibility: In Conversation with Alison Bechdel. - Critchfield, Adam R.; Pula, Jack (Journal of Gay & Lesbian Mental Health, 2015)
Alison Bechdel is an acclaimed graphic novelist whose graphic memoirs have examined her closeted gay father's suicide, her own developing sexual and gender identity, and her experiences in psychoanalysis. The authors of this article interviewed Ms. Bechdel in order to explore her thoughts on the role of her early work in creating visibility for LGBT communities and the specific role of psychotherapy in her development and her artistic work. The article in turn examines Bechdel's work from the perspective of cultural representations of psychotherapy, development of gender identity and expression, and considers the implications of her work for the mental health practitioner caring for LGBT individuals. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ communities; Psychotherapy; Psychoanalysis; Women novelists; cultural studies, graphic novel, LGBT, mental health, psychotherapy, psychoanalysis, transgender; Bechdel, Alison, 1960-

Differential Reports of Suicidal Ideation and Attempts of Questioning Adults Compared to Heterosexual, Lesbian, Gay, and Bisexual Individuals. - Woodward, EvaN.; Pantalone, DavidW.; Bradford, Judith (Journal of Gay & Lesbian Mental Health, 2013)
Many sexual minority individuals attempt suicide each year, but little is known about the suicidality of individuals who are questioning their sexual orientation. This study assessed suicidal ideation and attempts of questioning individuals compared with lesbian/gay, bisexual, and heterosexual individuals. This cross-sectional study enrolled participants (N = 2,841) from a community health center. Questioning (OR = 4.286, 95% CI [2.119–8.671]), lesbian/gay (OR = 3.024, 95% CI [2.351–3.890]), and bisexual (OR = 4.389, 95% CI [2.942–6.575]) individuals had significantly greater odds of considering suicide compared to heterosexuals. However, questioning individuals had non-significant odds of attempting suicide compared to heterosexuals. We discuss possible explanations for these findings. [ABSTRACT FROM PUBLISHER]
Keywords: Sexual minorities; Suicidal ideation; Self-destructive behavior; Psychology of LGBTQ+ people; Heterosexuals; Psychology; LGB; questioning; sexual minority individuals; suicidal ideation; suicide attempts

THE PULSE NIGHTCLUB AND THE STATE OF OUR WORLD. - Ferguson, Roderick A. (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author comments on how the 2016 massacre at the gay nightclub Pulse in Orlando, Florida by Omar Mateen reflects the state of homophobia, racism, and xenophobia in the world. He criticizes attempts to connect Mateen to Islamic terror organizations that suggest homophobia is a foreign aggression to the U.S., citing the rise of white nationalist groups and violence against Muslims in Jews in the U.S. since the Pulse shootings.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; Racism; Homophobia; Social history -- 21st century; United States -- Social conditions -- 21st century; Mateen, Omar, 1986-2016

Interventions for LGBTQ Youth Suicide: A Review of Two Books. - Gandy, Megan E. (Journal of LGBT Youth, 2015)
Despite trends in society toward more inclusive and affirming environments for lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) persons, youth who identify as LGBTQ remain a vulnerable population. This paper reviews two recent books that address intervention in the lives of LGBTQ youth for the purpose of decreasing vulnerabilities to risk factors that contribute to unwanted mental health outcomes such as suicide, and increasing youth resiliency in the face of those vulnerabilities: Queer Youth Suicide, Culture, and Identity: Unliveable Lives? by Rob Cover (2012), and Safe Spaces: Making Schools and Communities Welcoming to LGBT Youth by Annemarie Vaccaro, Gerri August, and Megan S. Kennedy (2012). This review begins by providing a description of the content and style of each book, then moves into comparing and contrasting the books’ strengths and weaknesses and their respective approaches to addressing interventions with LGBTQ youth. The review concludes with implications for an audience of youth work practitioners, researchers, educators, and policymakers. [ABSTRACT FROM PUBLISHER]
Keywords: Suicide; LGBTQ+ people; Prevention of school violence; Adolescents; book review; intervention strategies; LGBT youth; mental health; suicide

High Prevalence of Multiple Syndemic Conditions Associated with Sexual Risk Behavior and HIV Infection Among a Large Sample of Spanish- and Portuguese-Speaking Men Who Have Sex with Men in Latin America. - Mimiaga, Matthew; Biello, Katie; Robertson, Angela; Oldenburg, Catherine; Rosenberger, Joshua; O'Cleirigh, Conall; Novak, David; Mayer, Kenneth; Safren, Steven (Archives of Sexual Behavior, 2015)
The HIV epidemic in Latin America is highly concentrated in men who have sex with men (MSM). In the United States, multiple co-occurring psychosocial conditions have been shown to act as intertwined epidemics to potentiate HIV transmission among MSM. To date, no study has examined the role of syndemics and condomless sex among MSM in Latin America. In 2012, an online survey was conducted among members of the largest social/sexual networking website for MSM in Latin America. Participants were asked about demographics, sexual behaviors, HIV/STI diagnoses, and psychosocial well-being, including depression, suicidal ideation, hazardous alcohol use, hard drug use during sex, history of childhood/adolescent sexual abuse, intimate partner violence, and sexual compulsivity. Multivariable logistic generalized estimation equations were used to assess the relationship of syndemic factors and (1) engagement in higher risk condomless anal sex and (2) self-report of prior HIV diagnosis. Among 24,274 survey respondents, 74.6 % of the sample had at least one syndemic factor. In an additive model, syndemics were associated with increased odds of higher risk condomless anal sex, ranging from adjusted odds ratio of 1.31 (95 % CI 1.20, 1.43) for one syndemic factor to 4.06 (95 % CI 3.25, 5.09) for 6/7 syndemic factors. Similarly, syndemics were associated with increased odds of HIV infection ( p < .0001). This study provides initial evidence that intertwined syndemics increase HIV risk behavior and HIV infection among MSM in Latin America. In the Latin American context, comprehensive HIV prevention interventions for MSM should be developed and tested that simultaneously address co-occurring psychosocial conditions and HIV risk. [ABSTRACT FROM AUTHOR]
Keywords: Unsafe sex; HIV infection risk factors; Men who have sex with men; Intimate partner violence; Syndemics; Latin Americans; Internet surveys; Generalized estimating equations; HIV; Internet; Latin America; Sexual behavior; Sexual orientation

PORTRAITS OF (UN)SETTLEMENT. - Lee, Ruthann (GLQ: A Journal of Lesbian & Gay Studies, 2015)
The article looks at "Quiet North," a series of paintings by artist Dominique Hui, and "Shooting Geronimo," a short film by artist Kent Monkman. Particular focus is given o the production of racialized masculinities in these artworks and to the ways in which Hui and Monkman use their art to challenge popular notions of home and nation in North America. Details on queer minority expression and on the relationship between diasporic and Indigenous minorities are presented. Multiculturalism is also discussed.
Keywords: LGBTQ+ artists; Minority LGBTQ people; Race in art; Masculinity in art; Home in art; Hui, Dominique; Monkman, Kent

Bullying and Suicide: The Mental Health Crisis of LGBTQ Youth and How You Can Help. - Ahuja, Amir; Webster, Cecil; Gibson, Nicole; Brewer, Athena; Toledo, Steven; Russell, Steven (Journal of Gay & Lesbian Mental Health, 2015)
Responding to increased awareness of the plight of lesbian, gay, bisexual, and transgender (LGBT) youth who may be isolated and subject to bullying, the Association of Gay and Lesbian Psychiatrists (AGLP) collaborated with the American Foundation for Suicide Prevention (AFSP), the Trevor Project and the Gay, Lesbian and Straight Education Network (GLSEN) to present a symposium on Bullying and Suicide at the American Psychiatric Association (APA) Annual Meeting in 2013. The objectives of the symposium were the following: to understand the link between anti-LGBTQ bullying and mental illness and to identify ways to help such patients. To identify the academic research being done on anti-LBGTQ bullying, and how this informs tactics to combat this problem. To identify areas of weakness in the approaches being used, ways to improve them, and areas of future research. To identify ways clinicians can be involved in furthering the awareness of bullying of all kinds, including research on prevention efforts. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Suicide; Adolescent psychology -- Research; Bullying research; Policy sciences; adolescents and young adults; bullying; LGBT; public policy; suicide

A Longitudinal Study of Predictors of Suicide Attempts Among Lesbian, Gay, Bisexual, and Transgender Youth. - Mustanski, Brian; Liu, Richard (Archives of Sexual Behavior, 2013)
This short-term prospective study examined general and lesbian, gay, bisexual, and transgender (LGBT)-specific risk and protective factors for suicide attempts in an ethnically diverse sample of LGBT youth ( N = 237, 47.7 % male). A structured psychiatric interview assessed clinical depression and conduct disorder symptoms, as well as past and prospective suicide attempts over a 1-year follow-up period (91 % retention). Participants completed questionnaires measuring general risk factors for suicide attempts, including hopelessness, impulsiveness, and perceived social support. They also completed measures of LGBT-specific suicide risk factors, including gender nonconformity, age of first same-sex attraction, and LGBT victimization. Correlation and multivariate regression analyses were conducted to examine the relations between predictors and suicide attempt, and to identify mediators. Of nine variables examined, seven were related to lifetime history of attempted suicide: hopelessness, depression symptoms, conduct disorder symptoms, impulsivity, victimization, age of first same-sex attraction, and low family support. Depressive symptoms and hopelessness mediated the relation between multiple risk and resilience factors and suicide attempts. Suicide attempt history was the strongest predictor of prospective suicide attempts. Participants who previously attempted suicide (31.6 % of the sample) had more than 10 times greater odds of making another attempt in the 1-year follow-up period than were those who had made no previous attempt. These results highlight the need for suicide prevention programs for LGBT youth and suggest the importance of addressing depression and hopelessness as proximal determinants and family support and victimization, which have more distal effects. [ABSTRACT FROM AUTHOR]
Keywords: Social life & customs of LGBTQ people; Suicide; Ethics; Risk factors in suicidal behavior; Teenage suicide; Suicidal behavior in young adults; Symptoms; Adolescents; Homosexuality; LGBT; Sexual orientation

A PLAYLIST FOR PULSE. - Vargas, Deborah R. (GLQ: A Journal of Lesbian & Gay Studies, 2018)
The author presents a playlist of songs she curated in memory of those killed during a Latin Night celebration at the gay nightclub Pulse in Orlando, Florida in June 2016 that features artists such as Albita, Gary Hobbs, and Juan Gabriel.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; Albita, 1962-; Hobbs, Gary

Family Rejection, Social Isolation, and Loneliness as Predictors of Negative Health Outcomes (Depression, Suicidal Ideation, and Sexual Risk Behavior) Among Thai Male-to-Female Transgender Adolescents. - Yadegarfard, Mohammadrasool; Meinhold-Bergmann, Mallika E.; Ho, Robert (Journal of LGBT Youth, 2014)
This study examined the influence of family rejection, social isolation, and loneliness on negative health outcomes among Thai male-to-female transgender adolescents. The sample consisted of 260 male respondents, of whom 129 (49.6%) were self-identified as transgender and 131 (50.4%) were self-identified as cisgender (nontransgender). Initial multivariate analysis of variance indicated that the transgender respondents, when compared to the cisgender respondents, reported significantly higher family rejection, lower social support, higher loneliness, higher depression, lower protective factors (PANSI-positive) and higher negative risk factors (PANSI-negative) related to suicidal behavior, and were less certain in avoiding sexual risk behaviors. Multiple regression analysis indicated that the exogenous variables of family rejection, social isolation, and loneliness were significant predictors of both transgender and cisgender adolescents’ reported levels of depression, suicidal thinking, and sexual risk behaviors. The implications of these findings are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Risk-taking behavior; Social isolation; Transsexuals; Family relations; Suicidal ideation; Analysis of variance; Mental depression; Psychological tests; Questionnaires; Scale analysis (Psychology); Multiple regression analysis; Thailand; Adolescents; depression; family rejection; loneliness; sexual risk behavior; social isolation; suicidal ideation; transgender

Domains of Distress Among People with Sexual Orientation Obsessions. - Williams, Monnica; Wetterneck, Chad; Tellawi, Ghazel; Duque, Gerardo (Archives of Sexual Behavior, 2015)
Although sexual obsessions in obsessive-compulsive disorder (OCD) are not uncommon, obsessions about sexual orientation have not been well studied. These obsessions focus on issues such as the fear of being or becoming gay, fear of being perceived by others as gay, and unwanted mental images involving homosexual acts. Sexual orientation obsessions in OCD are particularly distressing due to the ego-dystonic nature of the obsessions and, often, stigma surrounding a same-sex orientation. The purpose of this study was to better understand distress in people suffering from sexual orientation obsessions in OCD. Data were collected online ( n = 1,176) and subjects were 74.6 % male, 72.0 % heterosexual, and 26.4 % with an OCD diagnosis from a professional. The survey consisted of 70 novel questions that were assessed using a principal components analysis and the items separated into six components. These components were then correlated to distress among those with a prior OCD diagnosis and sexual orientation obsessions. Results indicated that sexual orientation obsessions in OCD were related to severe distress, including suicidal ideation. Implications of these findings and future directions for research are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Sex addiction; Compulsive behavior; Homophobia; Sexual orientation; Sexual desire disorders; Anxiety; Obsessive-compulsive disorder; Sexual obsessions; Suicide

The Mental Health of Multiethnic Lesbian and Bisexual Adolescent Females: The Role of Self-Efficacy, Stress and Behavioral Risks. - Craig, Shelley L.; Keane, Gina (Journal of Gay & Lesbian Mental Health, 2014)
Multiethnic lesbian and bisexual adolescent females (MLBAF) are vulnerable to health and mental health risks, such as depression, suicide, self-harm, family and school concerns, and stress resulting from a “triple jeopardy” of marginalization, yet these risks remain virtually unstudied. Based on minority stress theory, this pilot study found that for a sample of MLBAF (n = 116), the odds of self-reported poor mental health were more than five times higher for each unit increase in stress and almost seven times higher for sexual abuse. The presence of youth substance abuse academic problems and younger age made a significant contribution to poor self-reported mental health while high self-efficacy scores resulted in significantly fewer mental health concerns. Implications for practice are discussed. [ABSTRACT FROM PUBLISHER]
Keywords: Lesbian teenagers; LGBTQ+ teenagers; Bisexual teenagers; Bisexual youth; Psychology; Hispanic American teenagers; Psychiatric research; Self-efficacy; bisexual; Hispanic; lesbian; mental health; self-efficacy; sexual minority youth; stress

Comparing Trans-Spectrum and Same-sex-Attracted Youth in Australia: Increased Risks, Increased Activisms. - Jones, Tiffany; Hillier, Lynne (Journal of LGBT Youth, 2013)
Tran-spectrum youth include those who are gender questioning, transgender, intersex, genderqueer, and androgynous. Drawing on data from an Australian study of more than 3,000 same-sex-attracted and trans-spectrum youth aged 14 to 21, this article compares a group of 91 trans-spectrum youth from the study to “cisgender” same-sex-attracted peers (who feel their gender identity aligns more fully with their ascribed sex). Comparisons are made on topics including identity disclosure and support; experience of abuse; suicide and self-harm; and school experiences. The trans-spectrum respondents particularly reported experiencing homophobic abuse and suicide attempts in response to homophobia and cissexism significantly more often than their cisgender counterparts. However, an exciting finding of the study was that some of these youth were able to reframe social rejection of their identities using a variety of self-affirming strategies. They were also more likely to respond to discrimination through activism, and many held high hopes for the ways in which they might impact their worlds in the future. The article finally reflects on the special provisions needed for this group in areas such as youth services and education, and the need for individuals to be supportive of trans-spectrum youth who disclose their identities to them. [ABSTRACT FROM PUBLISHER]
Keywords: Gender identity; Homophobia; Sex differentiation disorders; Transsexuals; LGBTQ+ people; Transgender people; Social support; Suicide risk factors; Chi-squared test; Experience; Questionnaires; Self-injurious behavior; Students; Disclosure; Descriptive statistics; Australia; Abuse; activism; gender; gender identity; intersex; queer; resilience; suicide; transgender; youth

The Relationship between Sexual Minority Status and Suicidal Ideations among Urban Hispanic Adolescents. - Lardier Jr., David T.; Bermea, Autumn M.; Pinto, Stacy A.; Garcia-Reid, Pauline; Reid, Robert J. (Journal of LGBT Issues in Counseling, 2017)
Youth identifying as lesbian, gay, bisexual, transgender, and queer (LGBTQ), and more specifically Hispanic youth identifying as LGBTQ, experience suicidal ideation (SI) at disproportionate rates. Furthermore, adolescents identifying as LGBTQ are likely to experience high rates of bullying, depression, and limited social support, increasing SI. Counselors often have difficulty working with youth at the intersection of sexual and ethnic minority statuses. Using structural equation modeling techniques, the present study examined sexual minority status as a predictor of school bullying, depression, social support, and SI, among urban Hispanic youth (N = 538). The authors also tested social support as a buffering mechanism. [ABSTRACT FROM PUBLISHER]
Keywords: Suicide prevention; PSYCHOLOGY; Social support; Suicidal ideation; Psychology of LGBTQ+ people; Bullying & psychology; Hispanic Americans; Metropolitan areas; Structural equation modeling; Bullying; Hispanic urban adolescents; sexual minorities; social support; suicidal ideation

“A Hope to Lift Both My Spirits”: Preventing Bisexual Erasure in Aboriginal Schools. - Robinson, Margaret (Journal of Bisexuality, 2014)
Education is a treaty right for Aboriginal people in Canada and the United States, and Aboriginal schools aim to provide a comprehensive education rooted in indigenous knowledge and culture. In an Aboriginal context, antibullying programs may address microaggressions against lesbian, gay, bisexual, trans, queer, and two-spirited youth. Two-spirited identity offers a model of sexuality that may reduce youth suicide by providing a sense of cultural belonging and purpose for sexual and gender minority Aboriginal people. Yet even as it offers social support, the two-spirited identity model risks replicating the dichotomous constructions of sexuality that form the basis of bisexual erasure. This article discusses strategies for preventing such erasure within Aboriginal schools. [ABSTRACT FROM AUTHOR]
Keywords: Bisexual erasure; Bisexual youth; Bullying prevention; Suicide prevention; Social belonging; Two-spirit people; Native American LGBTQ people; Education of indigenous peoples; Aboriginal; bisexual; bullying; cultural continuity; First Nations; two-spirited

Conditions of Living: Queer Youth Suicide, Homonormative Tolerance, and Relative Misery. - Cover, Rob (Journal of LGBT Youth, 2013)
Despite the increasing social tolerance accorded nonheterosexual persons in many Western countries, queer youth suicide rates remain high. This opens the need to question not only how broad social conditions continue to make lives unlivable for many queer youth but whether queer community formations and representations that emerge within a tolerance framework provide supportive environments for fostering youth resilience. This article presents a theoretical approach to understanding the continuity of youth suicide by considering how queer community formations built on tolerance create new exclusions for some queer youth that can make a life unlivable in relation to peers. The article articulates the tolerance framework through a return to Dennis Altman's 40-year-oldHomosexual Oppression and Liberationand the more recent “homonormativity” critique of queer politics. It examines how tolerance and homonormativity are implicated in exclusions and suicidality through the “relative misery” suicide thesis and the concept of frustrated aspiration. [ABSTRACT FROM PUBLISHER]
Keywords: Homophobia; Attitude (Psychology); Communities; Culture; Group identity; Practical politics; Self-perception; Suicide; Social attitudes; Psychology of LGBTQ+ people; Attitudes toward sex; Conceptual structures; Mental depression; Social context; Prevention; Community; gay liberation; GLBT youth; homonormativity; suicide; tolerance

An Overview of Gay, Lesbian and Bisexual Issues in Botswana. - Selemogwe, Morekwe; White, Dale (Journal of Gay & Lesbian Mental Health, 2013)
In Botswana, homosexuality is criminalized, stigmatized, and considered by some to be “un-African.” Unsurprisingly in this context there has been scant research on lesbian, gay, and bisexual (LGB) issues. This paper reviews what research has been done in the areas of HIV risk, substance abuse, and mental health; explores the issues facing LGBs in Botswana; and offers recommendations for policy and future research. Notable findings reviewed include high rates of men who have sex with men also engaging in heterosexual relationships, and high rates of suicidal thoughts and substance use in the LGB community. Human rights practitioners and health professionals have called for repealing sodomy laws and creating programs specific for LGBs in order to effectively promote health in this population. [ABSTRACT FROM PUBLISHER]
Keywords: Homosexuality; HIV infection risk factors; Suicidal behavior; Substance abuse -- Research; Psychiatric research; Africa; bisexual; Botswana; gay; homosexual; lesbian; mental health; research

Deconstructing Homophobia Through Performance: A Review of Ugly Ducklings : A National Campaign to Reduce Bullying and Harassment of Lesbian, Gay, Bisexual, Transgender, and Questioning Youth. - Wilson, Anna (Journal of LGBT Youth, 2014)
This review critically examines Ugly Ducklings: A National Campaign to Reduce Bullying and Harassment of LGBTQ Youth through a DVD and educator's guidebook. The Ugly Ducklings Community Action Kit has two parts: (1) a documentary about the harassment of lesbian youth and (2) short dialogues with Ugly Ducklings cast members, parents, lesbian teens, and others. The guidebook is divided into three broad areas: Educators, Parents, and Youth, with additional information on teen suicide risk and prevention. [ABSTRACT FROM AUTHOR]
Keywords: Bullying prevention; Language & languages; Motion pictures; Human sexuality; LGBTQ+ people; Book review; bullying; curriculum; LGBTQ youth

Psychosocial Vulnerability and HIV-Related Sexual Risk Among Men who have Sex with Men and Women in the United States. - Dyer, Typhanye; Regan, Rotrease; Pacek, Lauren; Acheampong, Abenaa; Khan, Maria (Archives of Sexual Behavior, 2015)
In the U.S., HIV is concentrated among men who have sex with men (MSM), some of whom have had female partners (MSMW). MSMW are disproportionately impacted by psychosocial vulnerabilities, like depression and substance use that increase sexually transmitted infection (STI) and HIV risk. Research on psychosocial vulnerability and HIV-related sexual risk among MSMW is warranted to reduce infection transmission among MSM and to prevent bridging to female partners. We analyzed data from Wave IV (2007-2008) of the National Longitudinal Study of Adolescent Health to assess psychosocial vulnerability and HIV risk-taking among MSMW. Using lifetime and past year sexual activity, we classified men as ever having sex with: women only (MSW), men only (MSMO) or MSMW, with further refined categorization of MSMW with male only partners in the past 12 months, only female partners in the past 12 months, and both male and female partners in the past 12 months ( N = 6,945). We compared psychosocial vulnerability characteristics and HIV-related risk behaviors among the five categories of men. MSMW were more likely to report depression, suicidality, substance use, and incarceration than MSW and MSMO. Compared to MSW, MSMW with current female partners had greater odds of unprotected sex, exchange sex, and STI. MSMW with male partners in the past year had greater odds of multiple or concurrent partners in the past year. HIV risk and psychosocial vulnerability factors are elevated among MSMW, a priority population for HIV risk reduction. HIV risk reduction interventions should address this and heterogeneity of sexual partnerships among MSMW. [ABSTRACT FROM AUTHOR]
Keywords: HIV infection risk factors; Men who have sex with men; Men's sexual behavior; Unsafe sex; Psychosocial factors; Epidemiology; HIV; Sexual minorities; Sexual orientation; Sexually transmitted infections; Substance use

School Counseling Toward an LGBTQ-Inclusive School Climate: Implementing the SCEARE Model. - Asplund, Nancy R.; Ordway, Ann M. (Journal of LGBT Issues in Counseling, 2018)
The school environment is often perceived as hostile by sexual minority youth. Lesbian, gay, bisexual, transgender, queer (LGBTQ) students experience high rates of bullying and suicidal ideation yet are often underserved by school counselors. School counselors are uniquely situated to facilitate systemic change within a school. The proposed School Counselors: Educate, Affirm, Respond, and Empower (SCEARE, pronounced SKEER) model outlines components of an LGBTQ-inclusive school climate. It is designed to be a practical tool for helping school counselors conceptualize their interventions, and a theory of how systemic change might occur. It empowers school counselors to be catalysts of change toward an LGBTQ-inclusive school climate. [ABSTRACT FROM AUTHOR]
Keywords: Bullying; Counseling; Suicidal ideation; Psychology of LGBTQ+ people; Counselors; Psychology -- Mathematical models; School environment; Self-efficacy; Student attitudes; inclusive; LGBTQ; school climate; school counseling; systemic change

Using a Two-Step Method to Measure Transgender Identity in Latin America/the Caribbean, Portugal, and Spain. - Reisner, Sari; Biello, Katie; Rosenberger, Joshua; Austin, S.; Haneuse, Sebastien; Perez-Brumer, Amaya; Novak, David; Mimiaga, Matthew (Archives of Sexual Behavior, 2014)
Few comparative data are available internationally to examine health differences by transgender identity. A barrier to monitoring the health and well-being of transgender people is the lack of inclusion of measures to assess natal sex/gender identity status in surveys. Data were from a cross-sectional anonymous online survey of members (n > 36,000) of a sexual networking website targeting men who have sex with men in Spanish- and Portuguese-speaking countries/territories in Latin America/the Caribbean, Portugal, and Spain. Natal sex/gender identity status was assessed using a two-step method (Step 1: assigned birth sex, Step 2: current gender identity). Male-to-female (MTF) and female-to-male (FTM) participants were compared to non-transgender males in age-adjusted regression models on socioeconomic status (SES) (education, income, sex work), masculine gender conformity, psychological health and well-being (lifetime suicidality, past-week depressive distress, positive self-worth, general self-rated health, gender related stressors), and sexual health (HIV-infection, past-year STIs, past-3 month unprotected anal or vaginal sex). The two-step method identified 190 transgender participants (0.54 %; 158 MTF, 32 FTM). Of the 12 health-related variables, six showed significant differences between the three groups: SES, masculine gender conformity, lifetime suicidality, depressive distress, positive self-worth, and past-year genital herpes. A two-step approach is recommended for health surveillance efforts to assess natal sex/gender identity status. Cognitive testing to formally validate assigned birth sex and current gender identity survey items in Spanish and Portuguese is encouraged. [ABSTRACT FROM AUTHOR]
Keywords: Transgender identity; Gender identity; Transgender people's sexual behavior; HIV infections; Sexual health; Social status; Health; HIV; Surveillance; Transgender

Suicide Risk and Sexual Orientation: A Critical Review. - Plöderl, Martin; Wagenmakers, Eric-Jan; Tremblay, Pierre; Ramsay, Richard; Kralovec, Karl; Fartacek, Clemens; Fartacek, Reinhold (Archives of Sexual Behavior, 2013)
Many studies have reported higher rates of suicide attempts among sexual minority individuals compared with their heterosexual counterparts. For suicides, however, it has been argued that there is no sexual orientation risk difference, based on the results of psychological autopsy studies. The purpose of this article was to clarify the reasons for the seemingly discrepant findings for suicide attempts and suicides. First, we reviewed studies that investigated if the increased suicide attempt risk of sexual minorities resulted from biased self-reports or less rigorous assessments of suicide attempts. Second, we reanalyzed the only two available case-control autopsy studies and challenge their original 'no difference' conclusion by pointing out problems with the interpretation of significance tests and by applying Bayesian statistics and meta-analytical procedures. Third, we reviewed register based and clinical studies on the association of suicides and sexual orientation. We conclude that studies of both suicide attempts and suicides do, in fact, point to an increased suicide risk among sexual minorities, thus solving the discrepancy. We also discuss methodological challenges inherent in research on sexual minorities and potential ethical issues. The arguments in this article are necessary to judge the weight of the evidence and how the evidence might be translated into practice. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Sexual minorities; Homosexuality; Heterosexuals; Suicide risk factors; Psychological autopsy; Bayesian analysis; Bayesian statistics; Sexual minority; Suicide

Bisexuality in Education: Exploring the Experiences, Resourcing, and Representations of Bisexual Students, Bisexual Parents, and Educators in Educational Systems—A Discussion. - Elia, JohnP. (Journal of Bisexuality, 2014)
An introduction is presented in which the author discusses various reports within the issue including the invisibility of bisexuality in education policy in Australia by Tiffany Jones and Lynne Hillier, bisexual erasure regarding school safety and sexuality education in New Zealand by Mary-Anne McAllum, and anti-bullying and suicide reduction of Indigenous students in Aboriginal schools in Canada by Margaret Robinson.
Keywords: Bisexual students; Sex education; Bullying prevention; Native American LGBTQ people; Bisexuality & education; School safety; First Nations of Canada; Education policy; Australia

Stories We Tell After Orlando. - ROYSTER, FRANCESCA T. (Feminist Studies, 2018)
The author discusses the Pulse Nightclub shooting in Orlando, Florida. She mentions the picnic that she and her friends and daughters attended after hearing the news, the stories they told about past injuries, and the author trying to imagine the story of shooter Omar Mateen.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; Gay bars; Storytelling; Wounds & injuries; Picnics; Mateen, Omar, 1986-2016

Gender-Related Victimization, Perceived Social Support, and Predictors of Depression Among Transgender Australians. - Boza, Crystal; Nicholson Perry, Kathryn (International Journal of Transgenderism, 2014)
ABSTRACT. This study examined mental health outcomes, gender-related victimization, perceived social support, and predictors of depression among 243 transgender Australians (n = 83 assigned female at birth, n = 160 assigned male at birth). Overall, 69% reported at least 1 instance of victimization, 59% endorsed depressive symptoms, and 44% reported a previous suicide attempt. Social support emerged as the most significant predictor of depressive symptoms (p >.05), whereby persons endorsing higher levels of overall perceived social support tended to endorse lower levels of depressive symptoms. Second to social support, persons who endorsed having had some form of gender affirmative surgery were significantly more likely to present with lower symptoms of depression. Contrary to expectations, victimization did not reach significance as an independent risk factor of depression (p =.053). The pervasiveness of victimization, depression, and attempted suicide represents a major health concern and highlights the need to facilitate culturally sensitive health care provision. [ABSTRACT FROM AUTHOR]
Keywords: Mental health; Social support; Transgender people; Psychology; Discrimination & psychology; Suicide -- Psychological aspects; Violence -- Psychological aspects; Mental depression -- Psychological aspects; Questionnaires; Statistics; Judgment sampling; Cultural awareness; Data analysis; Multiple regression analysis; Data analysis software; Descriptive statistics; Australia; depression; discrimination; gender affirmative surgery; hormones; social support; Transgender; victimization

Suicide Ideation and Suicide Attempts Among White Southern Lesbians. - Irwin, JayA.; Austin, ErikaL. (Journal of Gay & Lesbian Mental Health, 2013)
Several studies find suicide behaviors to be more prevalent among lesbian, gay, and bisexual (LGB) populations than their heterosexual counterparts. Studies of non-LGB populations reveal 13% prevalence of lifetime ideation and 4% prevalence of lifetime attempts. This study analyzed data from the Lesbian Social Life (LSL) study, a primarily online, survey-based research project focusing on lesbians living in the southern United States, and found that more than 40% of participants had seriously considered suicide and more than 15% had attempted suicide. We estimated the likelihood of suicide ideation and attempts by utilizing known general risk factors and lesbian-specific indicators within hierarchical logistic regression. Predictors of suicide ideation and attempts included depressive symptoms, discrimination, social support, self-esteem, and stigma. Results highlight the magnitude of suicide behaviors in southern lesbians and important predictor variables. Analysis shows support for the minority stress theory, and policy and clinical recommendations are provided. [ABSTRACT FROM AUTHOR]
Keywords: Psychology of lesbians; Psychology of gay people; Bisexuals; Psychology; Risk factors in suicidal behavior; Suicide risk factors; Mental depression; United States; mental health; mental illness–suicide; mental illness–suicide; sexual identity–lesbian; sexual identity–lesbian

Risk and Resilience During Transgender Identity Development: The Effects of Awareness and Engagement with Other Transgender People on Affect. - Testa, RylanJ.; Jimenez, CrystalL.; Rankin, Susan(Sue) (Journal of Gay & Lesbian Mental Health, 2014)
Research examining risk and resilience among transgender individuals suggests that connection to a transgender community may be protective. Utilizing archival survey data of 3,087 adult transgender participants collected in 2005–06, this study further evaluated how awareness and engagement with other transgender people influences risk and resilience during early gender identity development. As hypothesized, among male-to-female and female-to-male respondents, both prior awareness and prior engagement with other transgender people were independently related to less fearfulness, less suicidality, and more comfort. These relationships were not significant among male-to-different-gender or female-to-different-gender participants. Implications of these findings are discussed. [ABSTRACT FROM PUBLISHER]
Keywords: Risk-taking behavior; Transgender identity; Transgender people; Psychology; Resilience (Personality trait); Awareness; Affect (Psychology); anxiety; community support; resilience; suicidal ideation; transgender

Unmet Mental Health and Substance Abuse Treatment Needs of Sexual Minority Elders. - Jessup, MarthaA.; Dibble, SuzanneL. (Journal of Homosexuality, 2012)
In a survey exploring the reliability and validity of a screening tool, we explored the substance abuse and mental health issues among 371 elders; 74 were sexual minorities. Analyses by age group indicated that elders 55–64 years had significantly more problems with substance abuse, posttraumatic stress disorder (PTSD), depression, anxiety, and suicidal thoughts compared to those 65 and older. Bisexuals reported significantly greater problems with depression, anxiety, and suicidality than either heterosexual or lesbian or gay elders. Mental health and substance abuse treatment utilization was low among all elders with problems. Implications for assessment, access to care, and group-specific services delivery are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Older sexual minorities; Older LGBTQ people; Mental health of bisexuals; Mental health services; Mental illness; Substance abuse; Substance abuse treatment; Comorbidity; Dual diagnosis; co-occurring disorders; LGB; mental health; substance abuse

Suicide and Suicide Risk in Lesbian, Gay, Bisexual, and Transgender Populations: Review and Recommendations. - Haas, AnnP.; Eliason, Mickey; Mays, VickieM.; Mathy, RobinM.; Cochran, SusanD.; D'Augelli, AnthonyR.; Silverman, MortonM.; Fisher, PrudenceW.; Hughes, Tonda; Rosario, Margaret; Russell, StephenT.; Malley, Effie; et al. (Journal of Homosexuality, 2011)
Despite strong indications of elevated risk of suicidal behavior in lesbian, gay, bisexual, and transgender people, limited attention has been given to research, interventions or suicide prevention programs targeting these populations. This article is a culmination of a three-year effort by an expert panel to address the need for better understanding of suicidal behavior and suicide risk in sexual minority populations, and stimulate the development of needed prevention strategies, interventions and policy changes. This article summarizes existing research findings, and makes recommendations for addressing knowledge gaps and applying current knowledge to relevant areas of suicide prevention practice. [ABSTRACT FROM AUTHOR]
Keywords: Psychology of LGBTQ+ people; Suicidal behavior; Suicide prevention; Sexual minorities; Human services; Suicide risk factors; Crisis intervention (Mental health services); Knowledge gap theory; LGBT; risk factors; suicide; suicide attempts; suicide prevention

Risk and Protective Factors for Suicidal Thoughts Among Sexual Minority Youth: Evidence from the Add Health Study. - Russell, StephenT.; Toomey, RussellB. (Journal of Gay & Lesbian Mental Health, 2013)
Sexual minority youth are at greater risk for suicidal thoughts compared to heterosexual youth: Directions for prevention and intervention are urgently needed. Few studies have examined a broad range of risk and protective factors that may explain this disparate risk. This study utilized theNational Longitudinal Study of Adolescent Healthto examine which protective and risk factors for suicidal thoughts behaved distinctly in sexual minority adolescents compared to their heterosexual counterparts. Although many risk factors did not differ for heterosexual and sexual minority adolescents, we found several that were statistically significant for predicting later suicidal thoughts for sexual minorities: personal and friends’ school connections, friendship activities, and maternal caring. [ABSTRACT FROM PUBLISHER]
Keywords: Suicidal behavior; Sexual minority youth; Heterosexuals; Friendship; Mental health; Psychology; Mental health of youth; Self-destructive behavior in adolescence; sexual minority; suicide ideation; youth

"This Is How You Hetero:" Sexual Minorities in Heteronormative Sex Education. - Hobaica, Steven; Kwon, Paul (American Journal of Sexuality Education, 2017)
The efficacy of sex education has been questioned, as students participate in high rates of unsafe sex after completion. Without exploring various sexual minority (SM) identities (e.g., gay, lesbian, and bisexual) and forms of sex, sex education may be especially unhelpful for SMs by perpetuating the heteronormative (i.e., assuming heterosexuality is normal) environment they typically experience. In the present qualitative study, semistructured interviews were conducted with 12 SMs regarding their experiences with sex education using a grounded theory approach. Participants described sex education as being heteronormative and exclusive of their identities, making them feel invisible, sexually unprepared, and shameful. Sex education also reportedly contributed to sexual hesitance, sexual violence, and risky sexual behaviors. Participants endorsed histories of depression, anxiety, and suicidality, often associated with their identity. To become more informed and sexually prepared, they sought information through conversations with others, online searching, college courses, and trial and error sexual experiences. Participants also advocated for inclusive sex education, which would incorporate all identities and associated safe sex practices. They concluded that inclusivity in curricula could lead to various improved outcomes for SMs, such as safe sex, a sense of community, identity confidence, healthy relationships, and resilience. [ABSTRACT FROM AUTHOR]
Keywords: Sex education; Sexual minorities; Heteronormativity; Sexual assault; Safe sex; bisexual; gay; Heteronormative; lesbian; LGB; queer; sex education; sexual minorities

Sociodemographic Factors Contribute to Mental Health Disparities and Access to Services Among Young Men Who Have Sex with Men in New York City. - Storholm, ErikDavid; Siconolfi, DanielE.; Halkitis, PerryN.; Moeller, RobertW.; Eddy, JessicaA.; Bare, MichaelG. (Journal of Gay & Lesbian Mental Health, 2013)
Young men who have sex with men (YMSM) may be at increased risk for mental health problems including depression, post-traumatic stress disorder (PTSD), and suicidality. The overriding goal of the current investigation was to examine mental health and mental health services in a diverse sample of YMSM. We analyzed cross-sectional data from a cohort study of 598 YMSM, including sociodemographics, mental health, and mental health care. We then tested for bivariate associations and used multivariable modeling to predict depression, PTSD, suicidality, and mental health care utilization. Lower socioeconomic status, unstable housing, and school nonenrollment predicted depression and PTSD scores, while unstable housing and school nonenrollment predicted recent suicide attempt(s). These recent suicide attempt(s) also predicted current utilization of counseling or treatment, any history of psychiatric hospitalization, and any history of psychiatric diagnosis. Black and Asian/Pacific Islander (API) men were less likely to have ever accessed mental health counseling or treatment. There were significant class-based differences with regard to mental health outcomes but not mental health services. Further, recent crises (i.e., suicide attempt, hospitalization) were strong predictors of accessing mental health services. Improving the mental health of YMSM requires addressing the underlying structural factors that influence mental health outcomes and service access. [ABSTRACT FROM AUTHOR]
Keywords: Mental health services; Mental health; Psychology; Sociodemographic factors; Health programs; Young men; depression; mental health; post-traumatic stress disorder; sociodemographics; suicide; YMSM

Supporting LGBT Lives? Complicating the suicide consensus in LGBT mental health research. - Bryan, Audrey; Mayock, Paula (Sexualities, 2017)
This article locates itself within an emergent, counter-discursive body of scholarship that is critical of universalizing depictions portraying queer-identified or LGBT youth as vulnerable and ‘at-risk’ of a range of negative mental health outcomes, including self-harm and suicidality. Drawing on key findings from a large-scale, mixed-methods study exploring the mental health and well-being of LGBT people, we seek to contribute to the development of a more expansive understanding of LGBT lives by demonstrating the diverse ways people engage with their sexuality and gender identity and illuminating the complex meanings that those LGBT people who have experienced psychological and suicidal distress ascribe to their feelings, thoughts and actions. [ABSTRACT FROM AUTHOR]
Keywords: Mental health of LGBTQ people; Suicidal behavior of LGBTQ teenagers; Heteronormativity; Suicide statistics; At-risk youth; Discourse analysis; Discourse; heteronormativity; LGBT youth; mixed-methods; suicidality

Learning from the Life Experiences of Male-to-Female Transsexuals. - Brown, Chris; Dashjian, LaurenT.; Acosta, TarynJ.; Mueller, ConradT.; Kizer, BobbyE.; Trangsrud, HeatherB. (Journal of GLBT Family Studies, 2013)
In this exploratory study, we sought to increase mental health professionals’ understanding and awareness of the life and transition experiences of male-to-female transsexuals. A sample of 9 predominately European male-to-female transsexuals, who were mostly middle-aged (M= 33.8,SD= 15.4) and residing in the Midwest region of the United States, were interviewed about their life experiences. Interview data were analyzed using consensual qualitative research (CQR) methods (Hill, Thompson, & Williams, 1997). The results indicated that on average participants realized at five-and-a-half years old that their biological sex was incongruent with their gender identity; they dated women and pursued marriage in order to comply with prescribed gender roles and battled depression and suicidal ideation. Results also revealed that following their decision to transition, participants reported increased quality of life and overall happiness, and varied changes in relationships with family members. Suggestions to include this group in future practice and research agendas are discussed. [ABSTRACT FROM PUBLISHER]
Keywords: Transsexuals; Sexual psychology; Gender identity; Family relations; Suicidal ideation; Mental health personnel; Qualitative research; family relationships; male-to-female; transgender; transition; transsexual

The Effects of Hormonal Gender Affirmation Treatment on Mental Health in Female-to-Male Transsexuals. - Colton Meier, StaceyL.; Fitzgerald, KaraM.; Pardo, SethT.; Babcock, Julia (Journal of Gay & Lesbian Mental Health, 2011)
Hormonal interventions are an often-sought option for transgender individuals seeking to medically transition to an authentic gender. Current literature stresses that the effects and associated risks of hormone regimens should be monitored and well understood by health care providers (Feldman & Bockting, 2003). However, the positive psychological effects following hormone replacement therapy as a gender affirming treatment have not been adequately researched. This study examined the relationship of hormone replacement therapy, specifically testosterone, with various mental health outcomes in an Internet sample of more than 400 self-identified female-to-male transsexuals. Results of the study indicate that female-to-male transsexuals who receive testosterone have lower levels of depression, anxiety, and stress, and higher levels of social support and health related quality of life. Testosterone use was not related to problems with drugs, alcohol, or suicidality. Overall findings provide clear evidence that HRT is associated with improved mental health outcomes in female-to-male transsexuals. [ABSTRACT FROM AUTHOR]
Keywords: Hormone therapy; Trans men; Psychotherapy; Mental health; Psychology; Physiological effects of testosterone; Affirmations; Treatment effectiveness; female-to-male transsexual; FTM; gender affirmation treatment; hormone replacement therapy; testosterone; transgender

Mediating Suicide: Print Journalism and the Categorization of Queer Youth Suicide Discourses. - Cover, Rob (Archives of Sexual Behavior, 2012)
This article undertakes textual analysis to examine some of the ways in which knowledge around sexuality-related youth suicide and its causes are produced and made available through news media discourses and news-making processes. Four categories of sexuality-related suicide discourses were identified in news stories and features over the past 20 years: statistical research that makes non-heterosexuality implicit as a cause of suicide; stories about deviancy, guilt, and shame; suicide survivor stories; and bullying/harassment of non-heterosexual persons by individuals in schools and other institutions as suicide cause. Through processes of news production and meaning-making, use of expert opinions of primary definers, experiential accounts, reliance on citations of quantitative data, private accounts given as entertainment, and the newsworthiness of suicide as drama, public knowledge on queer youth suicide is guided by contemporary journalism. In all cases, the underlying relationship between heteronormativity, mental health, depression, and despair were frequently excluded in news journalism on queer youth suicide. [ABSTRACT FROM AUTHOR]
Keywords: Suicide; Human sexuality; Sexual orientation; Deviant behavior; Human behavior; Bullying; Discourse; News; Queer youth

Identity, Relationship Satisfaction, and Disclosure. - Velkoff, Elizabeth A.; Forrest, Lauren N.; Dodd, Dorian R.; Smith, April R. (Psychology of Women Quarterly, 2016)
We tested the usefulness of combining the Interpersonal–Psychological Theory of Suicide and minority stress models in studying suicidality among sexual minority women. According to the Interpersonal–Psychological Theory of Suicide, perceptions of being a burden on others and feelings of failed belongingness predict suicidal ideation. In a sample of sexual minority women (n = 51), we tested first, if the interaction of perceived burdensomeness and failed belongingness predicted lifetime suicidal behavior; second, if identity affirmation was negatively related to perceived burdensomeness and if this relation was moderated by disclosure; and third, if relationship satisfaction was negatively related to failed belongingness and if this relation was moderated by acceptance concerns. The proposed interaction of perceived burdensomeness and failed belongingness predicted lifetime suicide attempts. Moreover, among sexual minority women with greater disclosure of their sexual minority identities, low identity affirmation was related to higher perceived burdensomeness. For sexual minority women with high acceptance concerns, relationship satisfaction did not relate to lower feelings of failed belongingness. These findings suggest that sexual minority related stressors moderate risk factors for suicidality—in particular, perceptions of burdensomeness and failed belongingness. We suggest clinicians and others encourage sexual minority individuals to engage in activities that promote effectiveness and interpersonal closeness. Online slides for instructors who want to use this article for teaching are available to PWQ subscribers on PWQ's website at http://pwq.sagepub.com/supplemental [ABSTRACT FROM AUTHOR]
Keywords: Lesbians; Psychology; Human sexuality; Women; LGBTQ+ people; Suicide risk factors; Confidence intervals; Mathematical models; Questionnaires; Regression analysis; Risk assessment; Statistical sampling; Theory; Statistical power analysis; identity; Interpersonal–Psychological Theory of Suicide; relationship satisfaction; sexual orientation; suicide

Fighting for survival: The experiences of lesbian, gay, bisexual, transgender, and questioning students in religious colleges and universities. - Craig, Shelley L.; Austin, Ashley; Rashidi, Mariam; Adams, Marc (Journal of Gay & Lesbian Social Services, 2017)
Little is known about the experiences of lesbian, gay, bisexual, transgender, and questioning (LGBTQ) students attending religious colleges and universities. This study used grounded theory to analyze the narratives (N= 271) of LGBTQ former and current students. The central theme described by LGBTQ students was a fight for survival with five subthemes: (a) institutionalized homo/transphobia (strict school policies, enforcement of heterosexuality and gender conformity through discipline, conversion therapy); (b) a culture of fear (fear of exposure, homophobic panic and code words, seeking cover); (c) marginalization and isolation; (d) struggle (suffering and suicide, reconciling faith and LGBTQ identity); and (e) coping and resilience (surviving through critical thinking and strategic activism). Implications for practice are provided. [ABSTRACT FROM PUBLISHER]
Keywords: LGBTQ+ people; Religious schools; Students; gay, lesbian, bisexual, and transgender students; hegemony; religious abuse; religious colleges and universities

Childhood Gender Nonconformity and Harassment as Predictors of Suicidality among Gay, Lesbian, Bisexual, and Heterosexual Austrians. - Plöderl, Martin; Fartacek, Reinhold (Archives of Sexual Behavior, 2009)
The role of childhood gender role nonconformity (CGNC) and childhood harassment (CH) in explaining suicidality (suicide ideation, aborted suicide attempts, and suicide attempts) was examined in a sample of 142 lesbian, gay, and bisexual (LGB) adults and 148 heterosexual adults in Austria. Current and previous suicidality, CGNC, and CH were significantly greater in LGB participants compared to heterosexual participants. After controlling for CGNC, the effect of sexual orientation on CH diminished. CGNC correlated significantly with current suicidality in the LGB but not in the heterosexual group, and only non-significant correlations were found for CGNC with previous suicidality. Controlling for CH and CGNC diminished the effect of sexual orientation on current suicidality. Bayesian multivariate analysis indicated that current suicidality, but not previous suicidality, depended directly on CGNC. CH and CGNC are likely implicated in the elevated levels of current suicidality among adult LGB participants. As for previous suicidality, the negative impact of CGNC on suicidality might be overshadowed by stress issues affecting sexual minorities around coming out. The association of CGNC with current suicidality suggests an enduring effect of CGNC on the mental health and suicide risk of LGB individuals. [ABSTRACT FROM AUTHOR]
Keywords: Harassment; Suicidal behavior; Gay people; Lesbians; Bisexuals; Heterosexuals; Sexual orientation; Mental health; Conformity; Austrians; Child abuse; Gender role nonconformity; Homosexuality; Suicide

Barriers to Optimal Care between Physicians and Lesbian, Gay, Bisexual, Transgender, and Questioning Adolescent Patients. - Kitts MD, RobertLi (Journal of Homosexuality, 2010)
The objective of this article was to identify barriers to optimal care between physicians and LGBTQ (lesbian, gay, bisexual, transgender, and questioning) adolescents. To this end, 464 anonymous, self-administered surveys were distributed in 2003 to residents and attending physicians in pediatrics, internal medicine, obstetrics-gynecology, psychiatry, emergency medicine, and family practice at Upstate Medical University. The survey included questions pertaining to practice, knowledge, and attitude pertaining to lesbian, gay, transgender, or questioning (LGBTQ) adolescents. One hundred eight four surveys were returned. The majority of physicians would not regularly discuss sexual orientation, sexual attraction, or gender identity while taking a sexual history from a sexually active adolescent. As well, the majority of physicians would not ask patients about sexual orientation if an adolescent presented with depression, suicidal thoughts, or had attempted suicide. If an adolescent stated that he or she was not sexually active, 41% of physicians reported that they would not ask additional sexual health-related questions. Only 57% agreed to an association between being a LGBTQ adolescent and suicide. The majority of physicians did not believe that they had all the skills they needed to address issues of sexual orientation with adolescents, and that sexual orientation should be addressed more often with these patients and in the course of training. This study concludes that barriers in providing optimal care for LGBTQ adolescents can be found with regard to practice, knowledge, and attitude regardless of medical field and other demographics collected. Opportunities exist to enhance care for LGBTQ adolescents. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Homophobia in medical care; Questioning youth; Medical care; Physician-patient relations; Health disparities; Discrimination in medical care; Surveys; attitude; bisexual; gay; knowledge; lesbian; physician; practice; sexual orientation; transgender adolescents

70 U.S. Veterans with Gender Identity Disturbances: A Descriptive Study. - McDuffie, Everett; Brown, GeorgeR. (International Journal of Transgenderism, 2010)
This study describes the largest population of veterans referred for a gender identity disorder (GID) evaluation. Most were self-referred, others were referred by their commanding officer. A search of the English language literature revealed no similar studies on veterans other than a pilot project by the second author. Methods: Retrospective descriptive data were obtained from chart reviews of 70 U.S. veterans who were evaluated by the second author for gender disturbances over a 20-year period (1987 to 2007). The modal veteran with gender identity disturbance was a natal male (91%) identifying as female, >40 years old, Caucasian, employed, with more than 12 years of education. Fifty-seven percent were parents with a history of sexual involvement with opposite sex individuals. Histories of autogynephilia were not elicited in vets interviewed since 1997. Classic “flight into hypermasculinity” was described by a majority of the natal male vets as a retrospective understanding of why they joined the military. Psychiatric comorbidities (43%) included post traumatic stress disorder (PTSD), depression, schizophrenia (N = 1), substance use disorders (17%), dissociative identity disorder (N = 1), and personality disorders (11%). Ninety-three percent met criteria for diagnosis of GID or GID not otherwise specified; suicidal ideation was reported by 61% with one or more suicide attempts by 11% of 56 responding; and 4% reported genital self-harm. Although 11% expressed active thoughts of surgical self-treatment, most expressed a desire for physician-performed sex reassignment surgery (SRS). Cross-dressing behaviors were common, and currently reported arousal with cross-dressing was reported by 13%, 63% of whom were not diagnosed with GID. Conclusion: Veterans often reported that they joined the military in an attempt to purge their transgender feelings, believing the military environment would “make men” of them. Most were discharged before completing a 20-year career. More than half received health care at veterans affairs medical centers, often due to medical or psychiatric disabilities incurred during service. Comorbid Axis I diagnoses were common, as were suicidal thoughts and behaviors. [ABSTRACT FROM AUTHOR]
Keywords: Gender dysphoria; Transgender people; Trans women; Veterans -- United States; United States; gender identity; military; Transsexual; veteran

When Christianity and Homosexuality Collide: Understanding the Potential Intrapersonal Conflict. - Subhi, Nasrudin; Geelan, David (Journal of Homosexuality, 2012)
Reconciling sexual orientation with religious and spiritual beliefs can be challenging for Christian homosexuals, since many Christian churches teach that homosexual behavior is sinful. A qualitative study of 10 male and 10 female Christian homosexuals was conducted via semistructured interviews. This article seeks to explore the potential conflict between Christianity and homosexuality faced by the respondents. Participants' life stories and experiences varied widely. A few respondents were unaffected by the potential conflict between Christianity and homosexuality, however, the majority were affected. Effects included depression, guilt, anxiety, suicidal ideation, and alienation. Implications of the findings for support personnel are included. [ABSTRACT FROM AUTHOR]
Keywords: Christianity; Homosexuality; Religion; Christian LGBTQ+ people; Sexual orientation; Psychology; Conflict (Psychology); Sociological research methods; Interviewing; conflict; homosexuality; interview

MARRIAGE, A 'COUPLE' OF QUESTIONS: SAME-SEX MARRIAGE, COUPLEDOM AND IDENTITY. - COVER, ROB (Gay & Lesbian Issues & Psychology Review, 2012)
Public and legislative debates, queer community activism, and partisan political policy on same-sex marriage rights have opened question as to the different ways in which marriage and relationships can be conceived. However, always marginalised in these discourses is the figure of 'coupledom, built on what can be considered the heteronormative 'marriage model and deployed to uphold all sides of same-sex marriage debates. 'Coupling, as the means by which relationships are defined, remains under-theorised. This article begins by showing how the notion of the 'couple can be de-naturalised by post-structuralist queer theory, before going on to consider the ways in which a coupledom/promiscuity binary functions in same-sex marriage debates in order to uphold the primacy and naturalness of the concept of the romantic couple as a kinship unit. It then demonstrates how 'coupledom operates as a performative mode of identification to which sexual subjects form a passionate attachment in order to stabilise sexuality and maintain sexual subjectivities. The article demonstrates some of the ways in which the matrix between sexual subjectivity and a coupledom/promiscuity binary excludes alternative sexual and romantic arrangements (celibacy, polygamy and other forms of attachment that are not primarily defined by coupledom on the 'marriage model). The article concludes with a brief coda examining how pro and con arguments for same-sex marriage have utilised concerns around queer youth suicide whilst unwittingly pushing for various normativities of coupledom. [ABSTRACT FROM AUTHOR]
Keywords: Same-sex marriage; Queer theory; Couples; Human sexuality; Promiscuity; Debate; coupledom/ promiscuity binary; heteronormativity; same-sex marriage; Heteronormativitaet und Homosexualitaeten (Book)

Mental Health Service Contacts Among Sexual Minority and Heterosexual Girls in Boston Public High Schools. - Kidd, JeremyD.; White, J.Lee; Johnson, ReneeM. (Journal of Gay & Lesbian Mental Health, 2012)
Although sexual minority (SM) adolescent girls are at high risk for suicidal behavior, little is known about their use of mental health services (MHS). Therefore, we examined survey data from a sample of Boston high school students to compare the prevalence of MHS use among SM and heterosexual girls.We used chi-square tests to assess the statistical significance of group differences. To test whether SM status moderated the association between MHS use and mental health need (i.e., whether the student reported self-harm, suicidal ideation, or a suicide attempt in the past year), we entered mental health need, SM status, and the interaction term of the two into a regression model that predicted past 12-month MHS use.SM girls (n = 89) were significantly more likely than heterosexual girls (n = 800) to report suicidal ideation, suicide attempts, and self-harm. SM girls were also more likely to have reported a past 12-month MHS contact (54% vs. 26%, p < 0.0001); this finding held for those with and without a high level of mental health need. The interaction term was not statistically significant, indicating that SM status does not moderate the effect of mental health need on MHS use. These results indicate that SM girls, particularly those experiencing suicidality, are likely to report a MHS contact. Future research is needed to elucidate when/how SM girls come to use MHS and what types of services they are receiving. [ABSTRACT FROM AUTHOR]
Keywords: girls; mental health services; school services; sexual minority; suicide attempts; youth

Self-Harming Thoughts and Behaviors in a Group of Children and Adolescents with Gender Dysphoria. - Skagerberg, Elin; Parkinson, Rachel; Carmichael, Polly (International Journal of Transgenderism, 2013)
This article presents the findings from an audit on self-harm in 125 children and adolescents referred to the Gender Identity Development Service in London. Data concerning self-harming thoughts and behaviors before attending the service were extracted from documents in the patient files and from clinician reports. The findings indicated that suicide attempts and self-harming were more common over the age of 12. Overall, thoughts of self-harm were more common in the natal males whereas actual self-harm was more common in the natal females. The number of suicide attempts did not differ significantly between the two genders. The implications of these findings are discussed. Limitations of the study are also discussed which include that the data was only collected over an 8-month period and that it was extracted from patient files and from clinician reports. [ABSTRACT FROM AUTHOR]
Keywords: Auditing; Chi-squared test; Cognition disorders; Self-injurious behavior; Data analysis software; Descriptive statistics; Great Britain; Gender dysphoria; gender noncomformity; self-harm

The Contribution of School to the Feeling of Acceptance and the Risk of Suicide Attempts among Austrian Gay and Bisexual Males. - Plöderl, Martin; Faistauer, Gregor; Fartacek, Reinhold (Journal of Homosexuality, 2010)
School-related factors contributing to the suicidality of lesbian, gay, and bisexual individuals are understudied, especially in German-speaking Europe. Among our Web-based sample of 468 Austrian gay or bisexual adults, 18% attempted suicide and about one half of them reported that hard times at school related to one's homosexuality partly or mainly caused the attempt. Such suicide attempts were associated with a lack of acceptance at school and harassment experiences. In contrast to suicide attempts, acceptance at school was significantly associated with protective factors such as teachers intervening against homophobia or presence of openly homosexual teachers or peers. These findings may be important for consideration in school-based suicide prevention programs. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Suicide; School bullying; Harassment in schools; Homophobia in schools; School environment; Prevention; Germany; Europe; adolescents; bisexual; gay; homosexuality; school; sexual orientation; suicidality; suicide; suicide attempt

Sexual Minority Youth Victimization and Social Support: The Intersection of Sexuality, Gender, Race, and Victimization. - Button, DeeannaM.; O'Connell, DanielJ.; Gealt, Roberta (Journal of Homosexuality, 2012)
In comparison to heterosexual youth, sexual minority youth are more likely to experience victimization. Multiple studies have connected anti-gay prejudice and anti-gay victimization to negative outcomes. Research shows that social support may protect sexual minorities from the harmful effects of anti-gay victimization. However, rates of victimization and the negative outcomes linked to sexual identity within the sexual minority community have been relatively unexplored. Using data from three years of statewide data from heterosexual and sexual minority adolescents in grades 9–12, this study examines victimization, substance use, suicidality, and access to social support by sexuality. Results indicate that sexual minority youth are at increased risk for victimization, substance use, suicidality, and social isolation compared to their heterosexual counterparts. Results also indicate that there is very little bivariate difference within the sexual minority community. Multivariate results indicate differences among sexual minorities' experiences with victimization and substance use. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority youth; Heterosexuals; Crime victims; Substance abuse; Suicidal behavior; Social support; Comparative studies; gay; lesbian; questioning; sexual minority youth; social support; victimization; violence against sexual minorities

How Depressed and Suicidal Sexual Minority Adolescents Understand the Causes of Their Distress. - Diamond, GaryM.; Shilo, Guy; Jurgensen, Erin; D'Augelli, Anthony; Samarova, Valeria; White, Khendi (Journal of Gay & Lesbian Mental Health, 2011)
This study examined how lesbian, gay, and bisexual (LGB) adolescents reporting clinically significant depressive and suicidal symptoms understand the causes of their psychological distress. The role of the quality of the adolescent-parent relationship as a risk or protective factor was explored. Ten qualitative interviews were analyzed using the Consensual Qualitative Research method. Results showed that adolescents viewed family rejection of sexual orientation, extra-familial LGB related victimization, and non-LGB related negative family life events as the most common causes of their psychological distress. Most of the adolescents also reported experiencing support from at least one family member, and half reported experiencing significant extra-familial (e.g., peers, school counselor) support. Almost all of the adolescents reported wishing that their relationships with their parents were closer and characterized by more acceptance, as well as a willingness to participate in family therapy to improve their relationships with their parents. Clinical implications are discussed. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ teenagers; Parental rejection; Crime victims; Distress (Psychology); Risk factors in suicidal behavior; Mental depression risk factors; adolescent; bisexual; depression; family therapy; gay; lesbian; parents; suicide

The Relation Between Sexual Orientation and Suicide Attempts in Austria. - Plöderl, Martin; Kralovec, Karl; Fartacek, Reinhold (Archives of Sexual Behavior, 2010)
Previous studies indicate that homosexual or bisexual individuals are at a higher risk of attempting suicide compared to heterosexuals. To overcome biases in these studies, more rigorous definitions of 'suicide attempts' and the assessment of multiple dimensions of sexual orientation are needed. In addition, studies from the German speaking region are sparse, especially those not recruiting participants from the gay or lesbian communities. We solicited self-reported suicide attempts among 1,382 Austrian adults recruited through structured snowball sampling from students' social networks. Suicide attempts were more frequently reported by those participants with homosexual or bisexual fantasies, partner preference, behavior, and self-identification, compared to their heterosexually classified counterparts. This was true for any dimension of sexual orientation and for suicide attempts with intent to die or suicide attempts that required medical treatment. Our Austrian study confirmed existing evidence that homosexual and bisexual individuals are at an increased risk for attempting suicide. This should be considered in suicide preventive efforts. [ABSTRACT FROM AUTHOR]
Keywords: Homosexuality; Bisexuals; Suicide; Sexual orientation; Austria; Suicide attempts

Sexual Orientation and Differences in Mental Health, Stress, and Academic Performance in a National Sample of U.S. College Students. - Oswalt, SaraB.; Wyatt, TammyJ. (Journal of Homosexuality, 2011)
This study examined the relationships of mental health issues and sexual orientation in a national sample of college students. Using the Fall 2009 American College Health Association-National College Health Assessment, responses from heterosexual, gay, lesbian, bisexual, and unsure students (N = 27,454) relating to mental health issues and impact of these issues on academics were examined. The findings indicate that gay, lesbian, bisexual, and unsure students consistently reported higher levels of mental health issues and a more frequent impact on academics because of these issues than heterosexual students. Bisexuals frequently reported higher levels than students identifying as gay, lesbian, and unsure. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Mental health; Psychological stress; Bisexual college students; Suicidal behavior; College students -- United States; Statistical sampling; Sexual minorities -- United States; United States; academics; college students; mental health; sexual orientation

"Queering Masculinity: Sexual Dissidence as Anti-bullying discourse in Kimberly Peirce's Boys Don't Cry". - Gieni, Justine (MP: A Feminist Journal Online, 2012)
The article presents criticism on the film "Boys Don't Cry," directed by Kimberly Peirce depicting the real-life story of Brandon Teena, a transgender man. The need to challenge the ways in which dominant culture is both complacent about and complicit in the securing of masculine dominance by violence is addressed. Further, the author also discusses the effects of homophobia on LGBT youth after more than ten years of release of the film and the shocking rise of suicides in the demographic.
Keywords: Homophobia; Violence against LGBTQ+ people; Peirce, Kimberly, 1967-; Teena, Brandon, 1972-1993

Homotolerance and Heterosexuality as Norwegian Values. - Røthing, Åse; Svendsen, StineHelena Bang (Journal of LGBT Youth, 2010)
In recent years, equality between homosexual and heterosexual relationships has increasingly been presented as a marker for Norwegian values. Norwegian schooling encourages tolerance toward homosexuals, and the state shows active interest in counteracting bullying against LGBT (lesbian, gay, bisexual, and transgender) youth by supporting research and prevention programs. Recent studies concerning LGBT youth in Norway do indicate, however, that young Norwegians in general find it difficult to imagine themselves living a nonheterosexual life. Suicide is still considered a “reasonable” reaction to having to face a future as a homosexual. How can this be understood? Our analyses of teaching and textbooks in Norwegian schools points to three approaches to understanding young peoples' reluctance to imagining themselves as nonheterosexual: the double message of homotolerance, the self-evidence of heterosexuality, and the absence of nonheterosexual futurescapes. [ABSTRACT FROM AUTHOR]
Keywords: Homosexuality; School bullying; Heterosexuality; Sexual orientation; Transgenderism; LGBTQ+ people's sexual behavior; Bisexuals' sexual behavior; Gay people's sexual behavior; Heterosexuals; Norwegians; Norway; Bullying; heterosexual; homosexual; LGBT; schooling; sexuality

The Present Case Does Involve Minors: An Overview of the Discriminatory Effects of Romeo and Juliet Provisions and Sentencing Practices on Lesbian, Gay, Bisexual, and Transgender Youth. - Silhan, Caitlyn (Law & Sexuality: A Review of Lesbian, Gay, Bisexual & Transgender Legal Issues, 2011)
The article offers information on the problems faced by the Lesbian, gay, bisexual, and transgender (LGBT) youth child welfare and juvenile justice systems in the U.S. It mentions that LGBT youth like LGBT adults faces homophobia and rejection in their families and communities. It states that the rates of homelessness, suicide and suicide attempts are more in LGBT students.
Keywords: LGBTQ+ youth; Child welfare; Homophobia; Homelessness; Juvenile justice administration; United States

It's Not Burnout, It's More : Queer College Activists of Color and Mental Health. - Vaccaro, Annemarie; Mena, JasmineA. (Journal of Gay & Lesbian Mental Health, 2011)
A phenomenological study of the experiences of self-identified queer activists of color revealed how they coped with the competing demands of academics, family, and activism. While participants exhibited innumerable strengths, they often contended with external and internal pressures, limited social support, poor boundaries, and lack of self-care. The absence of social support, in conjunction with poor self-care, a heightened sense of responsibility for others, and multiple minority identity explorations, left college student activists experiencing burnout, compassion fatigue, and in some cases suicidal ideation. [ABSTRACT FROM PUBLISHER]
Keywords: LGBTQ+ people of color; LGBTQ+ activists; Activism; Psychological burnout; Suicidal ideation; Psychology; Phenomenological sociology; College students; Student political activity; Mental health of college students; burnout; college students; compassion fatigue; race; sexual orientation

EMOTIONAL ATTACHMENTS AND SECULAR IMAGININGS. - Rastegar, Mitra (GLQ: A Journal of Lesbian & Gay Studies, 2013)
The article offers the author's insights on the emotional and secular influence of antigay persecution on LGBTQ activists. The author relates the hanging of teenagers Ayaz Marhoni and Mahmoud Asgari in Mashhad, Iran allegedly due to their being homosexuals, which has induced activists from Europe and North America to question the persecution. She says that executions that are interpreted as homophobic punishment resonates to LGBTQ people as an opposition between the religious and secular.
Keywords: Psychology of LGBTQ+ people; Homophobia; Hanging (Death); Executions & executioners; Implicit religion; Marhoni, Ayaz; Asgari, Mahmoud

Why Bisexual Health? - Ebin, Julie (Journal of Bisexuality, 2012)
Defining bisexual health and its components will help people better understand it, highlight its importance and give investigators and proponents a common language and starting point from which to discuss the purpose and foundation of work on the intersections of bisexuality and health. Bisexual health can be parsed into individual and community-level components, taking into account those who identify as bisexual and those who do not but who have sexual or romantic attractions and/or behaviors with more than one gender. These populations will benefit from efforts to describe and compare the health of these two groups in more detail, as well as compare it to the health of straight, gay and lesbian populations. This information will shed light on potential health disparities; will pinpoint when and how to tailor health education, outreach and messaging; will assist health providers in becoming culturally competent; will help individuals become empowered consumers and health advocates; and will illuminate successful strategies that bisexuals may use to protect their health and the health of their communities. [ABSTRACT FROM AUTHOR]
Keywords: Health of bisexuals; Health; Health of LGBTQ+ people; Sexual orientation; Sexual orientation identity; Public health; Psychology; Conferences & conventions; Health education; 2009 Bi Health Summit; bisexual; bisexual health; health; health education

CODA: THE COST OF GETTING BETTER. - Puar, Jasbir K. (GLQ: A Journal of Lesbian & Gay Studies, 2012)
The article presents the author's analysis on gay youth suicide in the U.S. The author attempts to go beyond a critique of the queer neoliberalism. He examined what is contained in the category of sexuality and what kinds of normative temporal assumptions are produced through the event of suicide. He addresses the issue of queer suicide from pathologization versus normativization of sexual identity.
Keywords: Gay youth; Suicide; Human sexuality; Queer theory; Neoliberalism

Sexual Orientation and Gender Identity/Expression Related Peer Victimization in Adolescence: A Systematic Review of Associated Psychosocial and Health Outcomes. - Collier, KateL.; van Beusekom, Gabriël; Bos, HennyM. W.; Sandfort, TheoG. M. (Journal of Sex Research, 2013)
This article reviews research on psychosocial and health outcomes associated with peer victimization related to adolescent sexual orientation and gender identity or expression. Using four electronic databases and supplementary methods, we identified 39 relevant studies. These studies were published between 1995 and 2012 and conducted in 12 different countries. The studies were diverse in terms of their approaches to sampling participants, assessing participants' sexual orientation, operationalizing peer victimization, and with regard to the psychosocial and health outcomes studied in relation to peer victimization. Despite the methodological diversity across studies, there is fairly strong evidence that peer victimization related to sexual orientation and gender identity or expression is associated with a diminished sense of school belonging and higher levels of depressive symptoms; findings regarding the relationship between peer victimization and suicidality have been more mixed. Peer victimization related to sexual orientation and gender identity or expression is also associated with disruptions in educational trajectories, traumatic stress, and alcohol and substance use. Recommendations for future research and interventions are discussed. [ABSTRACT FROM PUBLISHER]
Keywords: Teenagers' sexual behavior; Sexual orientation; Gender identity; Adolescence; Peers; Self-esteem in adolescence

Bisexual and Transgender Identities in a Nonclinical Sample of North Americans: Suicidal Intent, Behavioral Difficulties, and Mental Health Treatment. - Mathy, Robin M.; Lehmann, Barbara A.; Kerr, Deborah L. (Journal of Bisexuality, 2003)
We hypothesized that a higher proportion of bisexual females (n = 792) and transgender individuals (n = 73) than bisexual males (n = 1,457) would self-report suicidal intent, behavioral difficulties, and mental health treatment. Relative to bisexual males, bisexual females and transgender individuals had significantly higher prevalence rates of suicidal intent, mental health difficulties, and mental health services. Prevalence rates among transgender participants did not vary by sexual orientation. The findings suggest that sexism and heterosexism have an interactive effect that compounds the social weight of oppression and increases risks for overwhelming sexual minorities' adaptive functioning. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Suicidal behavior; Mental health; Sexual orientation; Sexism; Heterosexism; Behavior; Bisexual; Discrimination; Suicide; Transgender

Dr. John Alan Lee: In Memoriam. - Murray, Stephen O. (Journal of Homosexuality, 2015)
An obituary for former contributor and editorial member of the "Journal of Homosexuality," John Alan Lee, is presented.
Keywords: Periodical editors; Assisted suicide; Lee, John Alan

Growing the Research Base. - Barber, MaryE.; Schwartz, Alan (Journal of Gay & Lesbian Mental Health, 2013)
An introduction is presented in which the editor discusses various reports within the issue on topics including sexual orientation change efforts of LGBT people, suicidal thoughts of straight people compared to LGBT people and anxiety risk behaviors for HIV transmission in HIV positive gay and bisexual men.
Keywords: Psychology of LGBTQ+ people; Suicidal behavior; Sexual orientation

Correlates of Engaging in Survival Sex among Homeless Youth and Young Adults. - Walls, N. Eugene; Bell, Stephanie (Journal of Sex Research, 2011)
Using a sample of 1,625 homeless youth and young adults aged 10 to 25 from 28 different states in the United States, this study examines the correlates of having engaged in survival sex. Findings suggest that differences exist based on demographic variables (gender, age, race, and sexual orientation), lifetime drug use (inhalants, Valium™, crack cocaine, alcohol, Coricidin™, and morphine), recent drug use (alcohol, ecstasy, heroin, and methamphetamine), mental health variables (suicide attempts, familial history of substance use, and having been in substance abuse treatment), and health variables (sharing needles and having been tested for HIV). In addition to replicating previous findings, this study's findings suggest that African American youth; gay, lesbian, or bisexual youth; and youth who had been tested for HIV were significantly more likely to have engaged in survival sex than White, heterosexual youth, and youth who had not been tested for HIV, respectively. Implications for interventions with youth and suggestions for future research are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Prostitution; Homeless persons; HIV; Mental health; Substance abuse; Youths' sexual behavior; Homeless youth; Homeless persons -- United States; Intervention (Social services); African American youth; United States

Sexual Attraction Status and Adolescent Suicide Proneness: The Roles of Hopelessness, Depression, and Social Support. - Langhinrichsen-Rohling, Jennifer; Lamis, DorianA.; Malone, PatrickS. (Journal of Homosexuality, 2011)
This study explored the relationship between sexual attraction status (same-sex, both-sex, and opposite-sex) and suicidal behavior in a diverse sample of adolescents (N = 1,533 youth). Adolescents with attractions to both sexes reported greater suicide proneness, recent and lifetime suicidal ideation, and past suicide attempts than those with exclusively opposite-sex attractions; individuals reporting same-sex attractions generally demonstrated moderate elevations on these variables. As hypothesized, both hopelessness and depression mediated the relationship between sexual attraction status and suicide proneness. Social support moderated the mediating effect of depression but not hopelessness in the sexual attraction status-suicide proneness link. Targeting the distress that can be associated with experiencing same-sex or both-sex attractions may enhance suicide prevention efforts, particularly in U.S. youth with reduced social support. [ABSTRACT FROM AUTHOR]
Keywords: Sexual attraction; Suicidal behavior; Social support; Correlation (Statistics); Suicide risk factors; Teenage suicide; Hopelessness theory of depression; adolescents; depression; homosexuality; hopelessness; social support; suicidal behavior

Suicidal Ideation and Attempts in North American School-Based Surveys: Are Bisexual Youth at Increasing Risk? - Elizabeth M. Saewyc; Skay, Carol L.; Hynds, Patricia; Pettingell, Sandra; Bearinger, Linda H.; Resnick, Michael D.; Reis, Elizabeth (Journal of LGBT Health Research, 2007)
This study explored the prevalence, disparity, and cohort trends in suicidality among bisexual teens vs. heterosexual and gay/lesbian peers in 9 population-based high school surveys in Canada and the U.S. Multivariate logistic regressions were used to calculate age-adjusted odds ratios separately by gender; 95% confidence intervals tested cohort trends where surveys were repeated over multiple years. Results showed remarkable consistency: bisexual youth reported higher odds of recent suicidal ideation and attempts vs. heterosexual peers, with increasing; odds in most surveys over the past decade. Results compared to gay and lesbian peers were mixed, with varying gender differences in prevalence and disparity trends in the different regions. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal ideation; Self-destructive behavior; Suicidal behavior; Gay people; Lesbians; Surveys; bisexual gay lesbian adolescents; health disparities; population surveys; school-based surveys; Sexual orientation; suicide attempts

Contested Conclusions: Claims That Can (and Cannot) Be Made from the Current Research on Gay, Lesbian, and Bisexual Teen Suicide Attempts. - Saewyc, Elizabeth M. (Journal of LGBT Health Research, 2007)
As the press and communities interpret research reports, their conclusions may go far beyond a study's evidence, especially if groups are trying to support politically-motivated claims about controversial causes and solutions to health problems. Few research designs can "prove" cause and effect, especially in population health research. However, some designs are better than others at identifying influences on health. Several strategies can help non-researchers evaluate studies critically. Using these statistics, this paper explores claims that can (and cannot) be made about causes of suicide attempts among gay, lesbian, and bisexual adolescents, based on current research evidence available. [ABSTRACT FROM AUTHOR]
Keywords: Health of LGBTQ+ people; Gay teenagers; Suicide; Suicidal behavior; Public health research; Adolescents; bisexuality; causality; health disparities; homosexuality; population surveys; protective factors; risk factors; suicide; suicide attempts

Attempted Suicide Among Transgender Persons: The Influence of Gender-Based Discrimination and Victimization. - Clements-Nolle, Kristen; Marx, Rani; Katz, Mitchell (Journal of Homosexuality, 2006)
To determine the independent predictors of attempted suicide among transgender persons we interviewed 392 male-to-female (MTF) and 123 female-to-male (FTM) individuals. Participants were recruited through targeted sampling, respondent-driven sampling, and agency referrals in San Francisco. The prevalence of attempted suicide was 32% (95% CI = 28% to 36%). In multivariate logistic regression analysis younger age (<25 years), depression, a history of substance abuse treatment, a history of forced sex, gender-based discrimination, and gender-based victimization were independently associated with attempted suicide. Suicide prevention interventions for transgender persons are urgently needed, particularly for young people. Medical, mental health, and social service providers should address depression, substance abuse, and forced sex in an attempt to reduce suicidal behaviors among transgender persons. In addition, increasing societal acceptance of the transgender community and decreasing gender-based prejudice may help prevent suicide in this highly stigmatized population. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Suicidal behavior; Suicide prevention; Self-destructive behavior; Mental health; San Francisco (Calif.); California; discrimination; independent risk factors; stigmatization; suicide; transexual; Transgender; victimization

A Needs Assessment of Transgendered People of Color Living in Washington, DC. - Xavier, Jessica M.; Bobbin, Marilyn; Singer, Ben; Budd, Earline (International Journal of Transgenderism, 2005)
A needs assessment (N = 248) conducted in Washington, DC revealed that transgendered people of color are at high risk for HIV/AIDS, substance abuse, suicide and violence/crime victimization. Overall HIV prevalence was 25%, with 32% in natal males (MTFs, i.e., male-to-females). Four predictors for HIV positive status were identified through logistic regression--male sex at birth, a history of substance abuse, sexual assault, and unemployment. Substance abuse was found in nearly half the sample (48%) but only half of those (51%) had sought treatment for it. Thirty-eight percent reported experiencing suicidal ideation, with 63% of those attributing it to their gender issues. Of those with suicidal ideation, nearly half (49%, or 16% of the entire sample), went on to make attempt(s) to kill themselves. Forty three percent had been victims of violence or crime, including 13% who had been sexually assaulted. Knowledge of the Standards of Care of the Harry Benjamin International Gender Dysphoria Association was quite low (9%) and associated with white race, any higher education beyond high school, and access to sex reassignment surgery (SRS). Access to SRS, defined as obtaining vaginoplasties for natal males and chest surgeries for natal females, was just 4%. White race (versus all other races, p < .001) and female at birth (versus male, p < .01) were significantly associated with access to SRS. Use of hormones at some point during their lives was reported by 51% of participants. Thirty-five percent were currently taking hormones, with 72% acquiring their hormones from friends or on the street. Among natal males, 25% had injected silicone. Nineteen percent did not have their own living space, and employment, housing and job training were the most commonly-reported immediate needs of the sample. The results of this needs assessment provide evidence of an urgent need for increased medical and social services specific to transgendered people of color living in the District of Columbia. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people of color; Health of transgender people; LGBTQ+ people of color; Trans women; Crime victims; Health risk assessment; AIDS risk factors; Substance abuse -- Risk factors; Suicide risk factors; Washington (D.C.); African American; health and social services; Hispanic; HIV/AIDS

Are Transgender Persons at Higher Risk for HIV Than Other Sexual Minorities? A Comparison of HIV Prevalence and Risks. - Bockting, Walter; Huang, Chiung-Yu; Ding, Hua; Robinson, Beatrice; Rosser, J. R. Simon (International Journal of Transgenderism, 2005)
Recent studies have shown that transgender people are at high risk for HIV. Few studies, however, have directly compared the HIV risks and sexual health of transgender persons with that of other sexual minority populations. This study used baseline data of intervention studies targeting transgender persons, men who have sex with men, and women who have sex with women and men to compare their HIV risk behavior and sexual health. No significant differences were found between transgender persons and nontransgender men or women in consistent condom use or attitudes toward condom use. Transgender persons were less likely to have multiple partners and more likely to be monogamous than men who have sex with men. When combining data on condom use, monogamy, and multiple partners, transgender persons did not differ from either nontransgender group in their overall risk for HIV. Transgender persons were less likely than the men or the women to have been tested for HIV. With regard to HIV prevalence, 17% of the men compared to only one transgender person and none of the women reported being HIV-positive. Transgender persons were also less likely than men who have sex with men to use drugs; no differences were found in the use of alcohol. However, with regard to mental health, transgender persons were more likely than the men to have experienced depression and more likely than men or women to have considered or attempted suicide. Finally, transgender persons reported the lowest levels of support from family and peers. Thus, in our sample, transgender persons appear to be at lower risk for HIV but at higher risk for mental health concerns than men who have sex with men. Remarkably few differences were found between transgender persons and women who have sex with women and men-a finding which might reflect the impact of social stigma on sexual health and have implications for the design of future HIV/STI prevention efforts. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; HIV infection risk factors; Monogamous relationships; Condom use; Suicide; Social stigma; Sexual minorities; Competency assessment (Law); bisexual women; HIV risk; MSM; sexual health; transgender

Queer youth suicide and the psychopolitics of “It Gets Better”. - Grzanka, Patrick R; Mann, Emily S (Sexualities, 2014)
This article investigates a mass-mediated campaign against a perceived increase in suicides among gay (or presumed-to-be-gay) youth in the USA since September 2010. “It Gets Better” (IGB) became a rallying cry for “anti-bullying” activists, politicians, celebrities and ordinary people who created YouTube videos addressed to gay, lesbian, bisexual and transgender (LGBT) youth who might be considering suicide. A critical discourse analysis of a sample of IGB videos reveals a neoliberal frame that places the burden of a “better” life onto the emotional lives of LGBT youth, who are instructed to endure suffering in the interest of inevitable happiness. Drawing on Foucault and Orr's work on the construction and management of mental illness, we use the concept of “psychopower” to explore how these IGB videos render queer youth suicide both a psychological disorder and a sociological crisis for which the only viable solution is “homonormative” subjectivity. [ABSTRACT FROM PUBLISHER]
Keywords: Suicidal behavior of LGBTQ teenagers; It Gets Better project; Anti-bullying movements; Suicide prevention; LGBTQ+ activists; Neoliberalism; Homonormativity; mental health; neoliberalism; suicide; youth

Suicide Among Homosexual Youth. - Lebson, Micah (Journal of Homosexuality, 2002)
The contemporary literature on homosexual youth and suicide risk are reviewed in order to delineate the incidence, development, causes/risk factors, and effects of suicidality among homosexual youth. In comparison to heterosexual youth, homosexual youths are more likely to attempt and complete suicide. They confront more challenges in identity development and face more risk factors for suicidality. In some cases, homosexual youths might use suicidal ideation as a means of rediscovering a will to live. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Suicide; Gay youth; Homosexuality; Teenagers; Psychology

Male Street Prostitution in Dublin: A Psychological Analysis. - McCabe, Ian; Acree, Michael; O'Mahony, Finbar; McCabe, Jenny; Kenny, Jean; Twyford, Jennifer; Quigley, Karen; McGlanaghy, Edel (Journal of Homosexuality, 2011)
This study assessed the mental health characteristics of 12 male street prostitutes (MSPs) in Dublin, with particular regard to issues of homelessness, substance abuse, depression, suicidal ideation, and self-esteem. Participants completed five psychometric tests, which indicated that all of the participants had above average levels of depression and suicidal ideation and low levels of self-esteem. This study found that candidates likely to become MSPs are young males with a combination of factors, including a background of childhood sexual or physical abuse, leaving school early, running away from home, and a dependence on heroin. [ABSTRACT FROM AUTHOR]
Keywords: Male prostitution; Homelessness; Substance abuse; Suicidal ideation; Self-esteem; Mental depression; Psychometrics; Child abuse; Runaway children; Heroin abuse; Dublin (Ireland); Ireland; abuse; drugs; Dublin; gay; HIV; homeless; male mental health; male prostitution

Suicidality and Sexual Orientation: Differences Between Men and Women in a General Population-Based Sample From The Netherlands. - de Graaf, Ron; Sandfort, Theo G. M.; ten Have, Margreet (Archives of Sexual Behavior, 2006)
Homosexuality has been shown to be associated with suicidality and mental disorders. It is unclear whether homosexuality is related to suicidality, independently of mental disorders. This study assessed differences in lifetime symptoms of suicidality (death ideation, death wishes, suicide contemplation, and deliberate self-harm) between homosexual and heterosexual men and women, controlling for lifetime psychiatric morbidity. Interaction effects of age and the role of perceived discrimination were also examined. Data were collected on a representative sample of the Dutch population aged 18–64 years. Classification as heterosexual or homosexual was based upon reported sexual behavior in the preceding year. Of those sexually active, 2.8% of 2,878 men and 1.4% of 3,120 women had had same-sex partners. Homosexual men differed from their heterosexual counterparts on all four suicide symptoms ( OR ranging from 2.58 to 10.23, with higher ORs for more severe symptoms), and on the sum total of the four symptoms; homosexual women only differed from heterosexual women on suicide contemplation ( OR=2.12). Controlling for psychiatric morbidity decreased the ORs, but among men all associations were still significant; the significance for suicide contemplation among women disappeared. Younger homosexuals were not at lower risk for suicidality than older homosexuals in comparison with their heterosexual counterparts. Among homosexual men, perceived discrimination was associated with suicidality. This study suggests that even in a country with a comparatively tolerant climate regarding homosexuality, homosexual men were at much higher risk for suicidality than heterosexual men. This relationship could not only be attributed to their higher psychiatric morbidity. In women, there was no such clear relationship. [ABSTRACT FROM AUTHOR]
Keywords: Gender dysphoria; Homosexuality; Gay people; Gay & lesbian studies; Death instinct; epidemiology; general population study; general population study.; homosexuality; mental disorders; suicidality

Factors Associated with 'Feeling Suicidal': The Role of Sexual Identity. - Abelson, Jeanne; Lambevski, Sasho; Crawford, June; Bartos, Michael; Kippax, Susan (Journal of Homosexuality, 2006)
This paper examines factors associated with feeling suicidal in a large sample of urban men in Sydney and Melbourne, aged 18-50, including heterosexual, gay and bisexual men, HIV antibody positive and HIV antibody negative. As in previous research, sexuality (being homosexual or bisexual) was found to be a major predictor of suicidality. The research went some way towards explaining the close relationship between feeling suicidal and sexual orientation. Sexuality interacts with feeling bad in that, once men feel moderately bad/depressed, they are more likely to feel suicidal if they are homosexual or bisexual than if they are heterosexual. In addition, the research found that experience of verbal abuse and physical assault (harassment) increased feeling suicidal for both heterosexual and gay/bisexual men, not just for homosexual men as suggested by previous research, and that social isolation in the form of living alone is a further risk factor. Seeking counseling help and taking sexual risks were also independently associated with feeling suicidal. These actions may result from feeling suicidal rather than the reverse, and their association with feeling suicidal warrants further research. Many of the 46 independent variables examined in the research, including HIV antibody status and closeness to the HIV/AIDS epidemic, were related to feeling suicidal only through their association with being gay/bisexual. Celibacy and general risk taking were not related to feeling suicidal in this study. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Gay men; Bisexual men; HIV antibodies; Psychology; Diseases; Psychology of the sick; counseling; Feeling suicidal; harassment; HIV/AIDS; men's sexuality; sexual risk taking; social isolation; suicidality

Mental Health Issues: A Comparison of Lesbian, Bisexual and Heterosexual Women. - Koh, Audrey S.; Ross, Leslie K. (Journal of Homosexuality, 2006)
This study examines mental health issues among women of different sexual orientations. An anonymous survey was administered at 33 health care sites across the United States; the sample (N = 1304) included lesbians (n = 524), bisexual (n = 143) and heterosexual women (n = 637). Not only did sexual orientation influence the probability of experiencing emotional stress, but also whether a bisexual woman or lesbian had disclosed her sexual orientation (was "out") impacted the likelihood of having or having had mental health problems. Bisexual women and lesbians experienced more emotional stress as teenagers than did heterosexual women. Bisexual women were more than twice as likely to have had an eating disorder compared to lesbians. If a bisexual woman reported being out she was twice as likely to have had an eating disorder compared to a heterosexual woman. Lesbians who were not out and bisexual women who were out were 2-2.5 times more likely to experience suicidal ideation in the past 12 months. Lesbians and bisexual women who were not out were more likely to have had a suicide attempt compared to heterosexual women. Lesbians used psychotherapy for depression more commonly than did heterosexual or bisexual women. This is one of the few studies that compares lesbians, bisexual and heterosexual women. The implications of these findings are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Lesbians; Bisexual women; Heterosexual women; Mental health education; United States; bisexual women; eating disorders; lesbian; mental health; methodology; sexual orientation disclosure; suicidality

Eligibility and Readiness Criteria for Sex Reassignment Surgery: Recommendations for Revision of the WPATH Standards of Care. - De Cuypere, Griet; Vercruysse, Herman (International Journal of Transgenderism, 2009)
In a review of the literature on follow-up studies of sex reassignment surgery (SRS) with regard to regret, suicide, and prognosis, this article evaluates the eligibility and readiness criteria of the WPATH Standards of Care—Sixth Version. Because the literature shows a lack of high-quality follow-up studies on large numbers of operated transsexuals, it offers no evidence-based research above evidence Level B or Level C. Nevertheless, our review allows us to conclude that most of the eligibility criteria are evidence-based. Although psychiatric co-morbidity is consistently mentioned in the literature as a negative predictive factor, it is barely addressed in the eligibility and readiness criteria for SRS. Therefore this paper suggests some changes and a shift in emphasis in the eligibility and readiness criteria of the Standards of Care. [ABSTRACT FROM AUTHOR]
Keywords: Sex reassignment surgery; Standards of care (Transgenderism); Guidelines; Follow-up studies (Medicine); Evidence-based medicine; eligibility criteria; follow-up study; gender identity disorder; sex reassignment surgery; Transsexual; WPATH standards of care

Sexual Minority Youth Perspectives on the School Environment and Suicide Risk Interventions: A Qualitative Study. - Rutter, Philip A.; Leech, Nancy L. (Journal of Gay & Lesbian Issues In Education, 2006)
ABSTRACT. This qualitative study explored the experiences of five gay, lesbian, and bisexual adolescents' perspectives on their schools' acceptance of their sexual orientation, and perceptions of these schools' approach to suicide risk intervention. Focus groups were tape recorded, transcribed, and analyzed through constant comparative analysis. Themes that emerged from the data included participants feeling judged by school counselors and teachers, feeling unsafe at school, and concerned about school staff's response to suicide risk and interventions. Implications for school counselors, teachers and administrators are discussed. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ students; Social acceptance; School environment; Sexual orientation -- Social aspects; Risk factors in suicidal behavior; Student attitudes; Secondary education research

Initial Assessment and Screening with LGBTQ Clients: A Critical Perspective. - Moe, Jeffry L.; Finnerty, Peter; Sparkman, Narketta; Yates, Chad (Journal of LGBT Issues in Counseling, 2015)
Counseling with people that identify as lesbian, gay, bisexual, transgender, queer (LGBTQ), or who are otherwise nonheterosexual or cisgender identified, should be based on a critical approach to assessment. Although general competencies have been articulated, further guidance is needed to help counselors avoid hetero-normative and cisgender biases in their assessment practice. The authors provide recommendations, based on critical review of the literature, for how counselors can address biases in assessment and screening tools in work with LGBTQ clients. [ABSTRACT FROM PUBLISHER]
Keywords: Substance abuse; Prejudices; Gender identity; Social justice; Suicidal ideation; Intimate partner violence; Psychology of LGBTQ+ people; Attitudes toward sex; Psychology; Risk factors in suicidal behavior; Counselors; Critical theory; Medical needs assessment; Psychological tests; Questionnaires; Self-disclosure; Job performance; Client relations; Continuing education units; Prevention; United States; LGBTQ issues; prejudice; queer theory; social justice; treatment

Same-Sex Sexual Orientation, Childhood Sexual Abuse, and Suicidal Behavior in University Students in Turkey. - Eskin, Mehmet; Kaynak-Demir, Hadiye; Demir, Sinem (Archives of Sexual Behavior, 2005)
This questionnaire study investigated the prevalence of, and interrelationships among, self-reported same-sex sexual orientation, childhood sexual abuse, and suicidal behavior in 1262 university students in Turkey. Approximately 7% of the sample reported lifetime or current same-sex sexual attractions, 5% reported that they engaged in same-sex sexual behavior, and almost 2% self-identified as either homosexual or bisexual. Overall, almost 10% of the sample acknowledged some form of a same-sex sexual orientation. Twenty-eight percent of the participants reported at least one instance of sexual abuse during their childhood. Almost 42% of the students reported suicidal ideation during the past 12 months or lifetime, and 7% reported that they attempted to kill themselves during their lifetime or in the past 12 months. Five hypotheses about the interrelationships among same-sex sexual orientation, childhood sexual abuse, and suicidal behavior were developed and tested in the study. Self-reported childhood sexual abuse was associated with same-sex sexual behavior. Participants who engaged in same-sex sexual behavior and those who identified themselves as homosexual or bisexual perceived more distance between themselves and their fathers than those who did not. Being sexually abused by someone of one’s own sex was related to same-sex sexual orientation in male participants but not in female participants. Childhood sexual abuse was found to be an independent predictor of both suicidal ideation and attempts during the past 12 months. Only identifying oneself as homosexual or bisexual was associated with an increased risk for suicidal ideation during the past 12 months. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Same-sex relationships; Child sexual abuse; Bisexuals; Gay people; Suicidal behavior in college students; Turkey; childhood sexual abuse; same-sex sexual orientation; suicidal behavior

Health Risk-Factors for Gay American Indian and Alaska Native Adolescent Males. - Barney, David D. (Journal of Homosexuality, 2003)
Having multiple identities as a homosexual American Indian or Alaska Native adolescent male increases the likelihood for poorer health and diminished well-being. This study assessed the differences in self-perceived health status between gay adolescent males and their heterosexual counterparts. A national nonrepresentative sample of 5,602 Indian and Native adolescent males was surveyed about issues of sexual behavior, physical and sexual abuse, mental health status, substance use, attitudes about school, participation in violence, and access to health care. Results indicate that there were no real differences between gay and heterosexual male respondents for substance use or attitudes about school. Statistically significant differences were found, however, in areas of mental health, as well as physical and sexual abuse. Gay adolescents were twice as likely to have thought of or attempted suicide. Gay adolescents were twice as likely to have been physically abused and nearly six times more likely to have been sexually abused. Gay American Indian or Alaska Native adolescent males constitute a very vulnerable population and are clearly in need of targeted health and social services. Unfortunately, the benefits seen by adults of the "two-spirited" gay and lesbian American Indian movement have not been accessible to Indian and Native adolescents.
Keywords: Bisexuals; Native American gay men; Native American LGBTQ people; Native American lesbians; Teenagers' sexual behavior; Sex crimes; Gay teenagers; School violence; Mental health; Suicidal behavior; Pathological psychology; Alaska Native LGBTQ+ people; Native Americans; Gay Americans; Teenagers -- Substance use

Stigma management? The links between enacted stigma and teen pregnancy trends among gay, lesbian, and bisexual students in British Columbia. - Saewyc, Elizabeth M.; Poon, Colleen S.; Homma, Yuko; Skay, Carol L. (Canadian Journal of Human Sexuality, 2008)
Over the past decade, several large-scale school-based studies of adolescents in Canada and the U.S. have documented health disparities for lesbian, gay and bisexual teens compared to their heterosexual peers, such as higher rates of suicide attempts, homelessness, and substance use. Many of these disparities have been linked to "enacted stigma," or the higher rates of harassment, discrimination, and sexual or physical violence that sexual minority youth experience at home, at school, and in the community. An unexpected health disparity for lesbian, gay and bisexual youth is their significantly higher risk of teen pregnancy involvement (between two and seven times the rate of their heterosexual peers), especially in light of declining trends in teen pregnancy across North America since the early 1990s. What is behind this higher risk? Is it getting better or worse? Using the province-wide cluster-stratified British Columbia Adolescent Health Surveys from 1992, 1998, and 2003, this paper explores the trends in pregnancy involvement, related sexual behaviours, and exposure to forms of enacted stigma that may help explain this particular health disparity for gay, lesbian and bisexual youth in Canada. [ABSTRACT FROM AUTHOR]
Keywords: Social stigma; Sexual minorities; LGBTQ+ communities; Discrimination; Offenses against the person; Violence; Teenage pregnancy; Health surveys; British Columbia

Turn of the Century Conventional Wisdom. (Journal of Gay & Lesbian Issues In Education, 2004)
Presents an editorial that argues that being gay, lesbian, transgender or bisexual (GLBT) is not easier for youth than it was for prior generations. Discussion of articles found in the October 2004 issue of the journal; Study of southern gay Black adolescents in the United States; Reference to a study that found that Australian heterosexual college students are accepting of suicide among their gay peers; Discussion of the attitudes of parents of GLBT youth; Claim that policies for the prevention of discrimination based on sexual orientation have not affected education policies; Lack of correlation between countries that have policies protecting GLBT persons and school systems that promulgate supportive educational policies and practices on GLBT issues.
Keywords: LGBTQ+ students; Bisexual students; Gay students; Transgender students; Parents of LGBTQ people; Parents of gay people; Discrimination in education; Education policy

Suicide Among Gay and Lesbian Adolescents and Young Adults: A Review of the Literature. - Kulkin, Heidi S.; Chauvin, Elizabeth A. (Journal of Homosexuality, 2000)
Explores the issue of suicide among gay and lesbian adolescents and young adults by reviewing literature concerning homosexuals. Definition of suicide; Information to guide clinicians in working effectively with homosexuals; Theoretical perspectives on homosexual identity development; Durkheim's Suicide Theory; Risk factors pertaining to suicide of homosexuals.
Keywords: Gay people; Lesbians; Self-destructive behavior; Suicidal behavior; Suicide -- Social aspects

Sexual Minorities Seeking Services: A Retrospective Study of the Mental Health Concerns of Lesbian and Bisexual Women. - Rogers, Tracey L.; Emanuel, Kristen; Bradford, Judith (Journal of Lesbian Studies, 2003)
Presents a study that assessed the mental health needs of lesbian and bisexual women. Utilization of mental health services by lesbian and bisexual women; Frequency of symptoms among lesbians and bisexuals seeking mental health treatment; Substance abuse and suicidal ideation of lesbian and bisexual women.
Keywords: Gay & lesbian studies; Mental health; Lesbians; Bisexual women; Mental health services; Substance abuse; Psychiatric social work

Introduction to Special Issue on Suicide, Mental Health, and Youth Development. - Eliason, Mickey (Journal of Homosexuality, 2011)

Suicidal Behavior Among Gay Male Youth. - Halpert, Stephen C. (Journal of Gay & Lesbian Psychotherapy, 2002)
Discusses the factors affecting the suicidal behavior among gays and lesbians. Information on several studies supporting elevated suicide rates among gay male youth; Explanation for the disparity between the psychological autopsies and the self-reports of gay youth suicide attempts; Mental health concerns of gay youth.
Keywords: Suicidal behavior; Lesbians; Gay people; Gay & lesbian studies; LGBTQ+ youth; Gay young adults; Psychological autopsy

Sexuality and School Shootings: What Role Does Teasing Play in School Massacres? - Klein, Jessie (Journal of Homosexuality, 2006)
Conventional explanations-lax gun control laws, media violence, single and working parents--do not adequately explain the recent spate of school shootings, and neither does bullying by itself, an explanation recently gaining more traction. A certain type of bullying, however, is revealed as particularly culpable. Many of the recent shootings share a disturbing component: The perpetrators were repeatedly, even relentlessly, accused by "preps and jocks" of being gay. Gay harassment is proposed as a point of departure for understanding the causes of school shootings. When boys who believe on some level that they warrant privilege, are instead harassed, they may feel driven to avenge the "wrong," and re-assert a more dominant, powerful, and victorious masculinity. These circumstances call for a cultural transformation such that "boys will be boys" is no longer used as an alibi for violence. The author presents implications for school-based social work practice, teacher and administrator interventions, as well as other prevention strategies. [ABSTRACT FROM AUTHOR]
Keywords: Homosexuality; Peer pressure; Social groups; Harassment in schools; Masculinity; School shootings; Social workers; Intervention (Social services); masculinity; peer harassment; school social work

Childhood Sexual Experiences and Adult Health Sequelae Among Gay and Bisexual Men: Defining Childhood Sexual Abuse. - Arreola, Sonya; Neilands, Torsten; Pollack, Lance; Paul, Jay; Catania, Joseph (Journal of Sex Research, 2008)
Gay and bisexual men carry the burden of HIV infections in the United States and have high rates of childhood sexual abuse that predict HIV and other health outcomes. This study examined differential effects of forced, consensual, and no childhood sexual experiences (CSE) on health outcomes among a probability sample of adult men who have sex with men (MSM). The forced sex group had the highest levels of psychological distress, substance use, and HIV risk. There were no differences in rates of depression and suicidal ideation between the consensual- and no-sex groups. The consensual- and forced-sex groups had higher rates of substance use and transmission risk than the no-sex group. The forced-sex group, however, had significantly higher rates of frequent drug use and high-risk sex than the consensual group. Findings suggest that forced CSEs result in a higher-risk profile than consensual or no childhood sexual experiences, the kind of risk pattern differs between forced and consensual childhood sexual experiences, and the underlying mechanisms that maintain risk patterns may vary. It is important to clarify risk patterns and mechanisms that maintain them differentially for forced and consensual sex groups so that interventions may be tailored to the specific trajectories related to each experience. [ABSTRACT FROM AUTHOR]
Keywords: Gay men's sexual behavior; Bisexual men; HIV-positive gay men; Health of gay men; Children & sex; LGBTQ+ people's sexual behavior; Child sexual abuse -- United States; UNITED States; United States

INTRODUCTION. - Alley, Jason (GLQ: A Journal of Lesbian & Gay Studies, 2018)
An introduction is presented discussing the issue's focus on responses to the Jun 12, 2016 massacre of 49 people at the Pulse nightclub in Orlando, Florida.
Keywords: Orlando Nightclub Massacre, Orlando, Fla., 2016; LGBTQ+ communities

Differences Between Matched Heterosexual and Non-Heterosexual College Students on Defense Mechanisms and Psychopathological Symptoms. - Biernbaum, Mark A.; Ruscio, Michele (Journal of Homosexuality, 2004)
Differences between heterosexual and non-heterosexual college students on measures of defense mechanisms and psychopathological symptoms were examined. Fifty-six (28 heterosexual, 28 non-heterosexual) subjects were drawn from a larger study of college student adjustment. Non-heterosexual subjects were matched to a heterosexual peer on several demographic variables as well as on attachment security/insecurity. Differences between the two groups on the Defense Mechanism Inventory and the Brief Symptom Inventory were tested. Contrary to traditional psychoanalytic conceptions of homosexuality, no differences were found between the two groups on any subscale of the Defense Mechanism Inventory, thereby repudiating one important aspect of traditional psychoanalytic theories on the development of homosexuality. Non-heterosexual students reported significantly higher levels of anxiety, depression, somaticization, paranoid ideation, general symptoms severity, and suicidal ideation. These students appear to be at increased risk for psychopathology and suicidal ideation, despite similar defense profiles, when compared to matched heterosexual peers. Additional research is needed to determine the origins of this increased risk, and comprehensive and targeted preventions and intervention programs must be established to ameliorate such risks. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ college students; Homosexuality theory; Homosexuality; Psychology of college students; Defense mechanisms (Psychology); Symptoms; Risk factors in suicidal behavior; Health risk assessment; Attachment behavior; College students; defense mechanisms; psychoanalytic theory; psychopathology; suicide

Stigma management? The links between enacted stigma and teen pregnancy trends among gay, lesbian, and bisexual students in British Columbia. - Saewyc EM; Poon CS; Homma Y; Skay CL (Canadian Journal of Human Sexuality, 2008)
Over the past decade, several large-scale school-based studies of adolescents in Canada and the U.S. have documented health disparities for lesbian, gay and bisexual teens compared to their heterosexual peers, such as higher rates of suicide attempts, homelessness, and substance use. Many of these disparities have been linked to 'enacted stigma,' or the higher rates of harassment, discrimination, and sexual or physical violence that sexual minority youth experience at home, at school, and in the community. An unexpected health disparity for lesbian, gay and bisexual youth is their significantly higher risk of teen pregnancy involvement (between two and seven times the rate of their heterosexual peers), especially in light of declining trends in teen pregnancy across North America since the early 1990s. What is behind this higher risk? Is it getting better or worse? Using the province-wide cluster-stratified British Columbia Adolescent Health Surveys from 1992, 1998, and 2003, this paper explores the trends in pregnancy involvement, related sexual behaviours, and exposure to forms of enacted stigma that may help explain this particular health disparity for gay, lesbian and bisexual youth in Canada. [ABSTRACT FROM AUTHOR]

Psychiatric Impact of Gender-Related Abuse Across the Life Course of Male-to-Female Transgender Persons. - Nuttbrock, Larry; Hwahng, Sel; Bockting, Walter; Rosenblum, Andrew; Mason, Mona; Macri, Monica; Becker, Jeffrey (Journal of Sex Research, 2010)
The psychiatric impact of interpersonal abuse associated with an atypical presentation of gender was examined across the life course of 571 male-to-female (MTF) transgender persons from the New York City Metropolitan Area. Gender-related abuse (psychological and physical), suicidality, and Diagnostic and Statistical Manual of Mental Disorders (4th ed., text revision) major depression were retrospectively measured across five stages of the life course using the Life Chart Interview. Among younger respondents (current age of 19-39), the impact of both types of abuse on major depression was extremely strong during adolescence and then markedly declined during later stages of life. Among older respondents (current age of 40-59), the impact of both types of abuse on major depression was strong during adolescence and then marginally declined during later stages of life. The effects of both types of abuse on suicidality were weaker but more consistently observed across the life course among both the younger and older respondents. Gender-related abuse is a major mental health problem among MTF transgender persons, particularly during adolescence. As these individuals mature, however, the consequences of this abuse appear less severe, which may represent the development of moderately effective mechanisms for coping with this abuse. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people -- Abuse of; Transgender teenagers; American transgender people; Mental depression; Emotional trauma; Risk factors in suicidal behavior; New York (N.Y.); New York (State); United States

Clinical Characteristics, Psychiatric Comorbidities and Sociodemographic Profile of Transsexual Patients from an Outpatient Clinic in Brazil. - Lobato, Maria Inês; Koff, Walte José; Schestatsky, Sidnei Samuel; De Vasconcellos Chaves, Camila Pedrollo; Petry, Analídia; Crestana, Tiago; Amaral, Juliana Trindade; De Quadros Onófrio, Fernanda; Salvador, Jaqueline; Silveria, Esalba; Henriques, Alexandre Anne (International Journal of Transgenderism, 2007)
Objective: To provide a description of our transsexual population. Method: This descriptive observational study included 138 patients with a diagnosis of Transsexualism in Brazil, between March 1998 and September 2005. Demographic, clinical and psychiatry data were collected. Results: Age ranged from 16 to 54 years; 88.4% were male. The prevalence of sexually transmitted diseases was 19.5%, and 17.6% were HIV-positive. Hormone therapy was reported by 91.2%, and 47.4% referred drug and alcohol use; 14.2%, attempted suicide; and 12.5%, history of sexual abuse. Self-mutilation was reported by 5.2%s. Fifty-nine patients (42.7%) had at least one currently psychiatric comorbidity (axis I or II). Conclusions: Mental health professionals have a central role in coordinating the multidisciplinary care of transsexuals. [ABSTRACT FROM AUTHOR]
Keywords: Transsexuals; Hormone therapy; HIV infections; Clinical medicine; Diagnosis; Brazil; mental health; multidisciplinary care; psychiatric comorbidity; sexual and gender disorders; Transsexualism

The Health and Social Service Needs of Transgender People in Philadelphia. - Kenagy, Gretchen P. (International Journal of Transgenderism, 2005)
Two Philadelphia-based HIV service organizations and a local university collaborated on a study of health and social service needs of transgender people. Transgender people were the primary resource for the development of the needs assessment survey. In this article, the survey development process, including two discussion groups and two focus groups, are described. Findings on barriers to care, violence, perception of public safety and comfort, suicide and health and social service needs are presented. Total sample size was 81, with 49 male-to-female and 32 female-to-male transgender individuals. Most (68%) were African American. About half of the respondents had thought about attempting suicide. High levels of violence were reported, especially among male-to-females. Health and social service needs included job training/work, dental care, health care, legal services, transportation, education and housing. [ABSTRACT FROM AUTHOR]
Keywords: Health of transgender people; Social work with transgender people; Outreach programs; Social work with LGBTQ people; Trans women; Trans men; African American transgender people; Medical needs assessment; Needs assessment; Social services -- United States; health access; service needs; Transgender

The relationship between self-reported sexual orientation and behavior in a sample of middle-aged male injection drug users. - Washington, Thomas Alex; Galai, Noya; Cohn, Sylvia; Celentano, David D.; Vlahov, David; Strathdee, Steffanie A. (Archives of Sexual Behavior, 2006)
Data are sparse on injection drug using (IDU) men who have sex with men (MSM). Previous literature suggests perceived taboos can result in an underreporting of atypical sexual orientation (i.e., bisexuality, homosexuality). As a result, HIV prevention programs have been difficult to mount, particularly programs for IDU-MSM. The association between self-reported sexual orientation and sexual behavior at semi-annual study visits was longitudinally assessed in a population of 1300 male IDUs in Baltimore during the period 1993 to 1998. Overall, a small minority (5%) of the male IDUs inconsistently reported their sexual orientation over time. Logistic regression analyses were performed, which yielded five significant predictors. These men tended to be older, to have been incarcerated, to have attended shooting galleries during follow-up, and were more than twice as likely to be HIV-seropositive (OR, 2.66; 95% CI, 1.62-4.36) compared with those who consistently reported their sexual orientation. Furthermore, men reporting inconsistent sexual orientation tended to engage in higher risk behaviors, suggesting that these men should be especially targeted for interventions. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Substance abuse; Human sexuality; HIV infections; Intravenous drug abusers; Sex research; Logistic regression analysis; human immunodeficiency virus; injection drug users; sex behavior; sexual orientation; substance abuse

QUEER FAMILY ROMANCE. - Munro, Brenna M. (GLQ: A Journal of Lesbian & Gay Studies, 2009)
This essay examines the often overlooked role that the idea of gay rights played in producing the new imaginary of the postapartheid "rainbow nation" --and its neoliberal economic order. I suggest that the figure of the gay person became an embodiment of political change, symbolically mediating conflicts within multiracial modernity in South Africa's emergent public culture, and I analyze the work done by queer "minor characters" in novels by Nadine Gordimer and J. M. Coetzee. None to Accompany Me (1994), The House Gun (1998), and Disgrace (1999) all tell the story of white, middle-class Anglo-South Africans whose struggle to adjust to the new era includes dealing with the revelation that their children are not straight. These novels dramatize how the narrative of the nation as a raced, heterosexual family romance was in crisis after apartheid, and reconstitute their families in queer new configurations-- raising questions about the flexibility and persistence of the trope of reproductivity. These texts ask how whites are to "come out" as national subjects and indicate that sexuality alone cannot be the groups for reinventing race and nation without an attention to systemic economic injustice. [ABSTRACT FROM AUTHOR]
Keywords: Gay people in literature; Gay rights; Political change; Essays; South Africa -- Politics & government -- 1994-; South Africa

Sex, Drugs, Violence, and HIV Status Among Male-to-Female Transgender Persons in Houston, Texas. - Risser, Jan M. H.; Shelton, Andrea; McCurdy, Sheryl; Padgett, Paige; Atkinson, John; Useche, Bernardo; Thomas, Brenda; Williams, Mark (International Journal of Transgenderism, 2005)
To inform the Community Planning Group (Houston, Texas) in setting HIV-prevention priorities, risk behavior surveys were completed by 67 male-to-female (MtF) transgender persons. By self-identification, 58% were preoperative and 48% were self-described heterosexual women. We found this small sample of male-to-female transgender individuals to have high rates of HIV infection, and high prevalence of risky behaviors, intimate partner violence, and suicidal ideation. Twenty-seven percent were infected with HIV. Barriers were seldom used during oral sex and used less than half the time for anal sex with either primary or casual partners. Nearly one third of the sample reported use of methamphetamines, amyl nitrite or LSD and 40% reported crack or cocaine use. Intimate partner violence and forced sex were reported by 50% and 25%, respectively. Suicidal ideation was reported by 16% in the last 30 days; lifetime suicidal ideation was 60%. [ABSTRACT FROM AUTHOR]
Keywords: HIV-positive transgender people; Transgender people's sexual behavior; AIDS prevention; Trans women; Risk-taking behavior; Health of transgender people; LGBTQ+ people's sexual behavior; HIV infections; HIV-positive LGBTQ+ people; Human sexuality; drug use; HIV prevention; HIV risk; Transgender; violence

An Argument for Ethical Treatment of Sex and Gender-Diverse People by Professional Caregivers. - O'Keefe, Tracie (Transgender Tapestry, 2003)
Deals with issues related to the ethical treatment of sex and gender-diverse people by professional caregivers. Reminders to caregivers in providing care to sex and gender-diverse people; Insight on the occurrence of suicides; Analysis of the ongoing abuse by professionals.
Keywords: Medical ethics; Transsexuals; Caregivers

Health and Social Service Needs of Transgender People in Chicago. - Kenagy, Gretchen P.; Bostwick, Wendy B. (International Journal of Transgenderism, 2005)
A needs assessment of transgender people was conducted in Chicago in 2001 to assess their HIV risks, health and social service needs, and barriers to care. One-hundred and eleven transgender individuals, 78 male-to-females (MTFs) and 33 female-to-males (FTMs), participated in the study. Fourteen percent of respondents reported being HIV-positive; they were all male-to-female and the majority was of color. Risk factors for HIV included unprotected sex and willingness to have high-risk sex in the future. Respondents experienced high levels of violence. Two-thirds of respondents had thought of attempting suicide. Respondents reported a high need for health and social services, particularly MTFs and people of color. [ABSTRACT FROM AUTHOR]
Keywords: Health of transgender people; Social work with transgender people; Social work with LGBTQ people; Trans women; Trans men; Risk-taking behavior; Human sexuality; Medical needs assessment; Needs assessment; Social services -- United States; Chicago (Ill.); barriers; health; services; Transgender

Adolescent Same-Sex Attraction and Mental Health: The Role of Stress and Support. - Teasdale, Brent; Bradley-Engen, MindyS. (Journal of Homosexuality, 2010)
This study draws on the social stress model from the sociology of mental health to examine the impact of same-sex attraction on depressed mood and suicidal tendencies. Specifically, we hypothesize that across multiple contexts, adolescents with same-sex attractions are likely to experience more social stress and less social support than heterosexual adolescents. In turn, these experiences increase the likelihood of negative mental health outcomes. Using data from the National Longitudinal Study of Adolescent Health (n = 11,911), we find that adolescents with same-sex attraction are more likely than their heterosexual counterparts to report depressed mood and suicidal tendencies. Moreover, stress and social support were found to mediate a substantial part of the relationship between same-sex attraction and depressed mood. In addition, stress and social support mediated about one third of the relationship between same-sex attraction and suicidal tendencies. These findings give strong support for the social stress model. We conclude with a discussion of the role that alienation plays in same-sex-attracted adolescent mental health. [ABSTRACT FROM AUTHOR]
Keywords: Gay teenagers; Psychoanalysis & homosexuality; Social support; Social alienation; Depression in adolescence; Stress in adolescence; alienation; depressed mood; Same-sex attraction; social stress model; suicidal tendencies

Lesbian Studies and Activism in India. - Vanita, Ruth (Journal of Lesbian Studies, 2007)
This essay surveys public debates and writings about lesbianism and the history of activism around lesbian issues in twentieth-century India. Weddings between women and joint suicides by female couples over the last twenty-five years are among the under-researched, but increasingly reported, phenomena that suggest future directions that activism and the study of lesbianism in India may take. [ABSTRACT FROM AUTHOR]
Keywords: Gay & lesbian studies; Lesbianism; Lesbian marriage; Suicide; Feminism; India; Namjoshi, Suniti

A PUBLIC SILENCE: THE DISCURSIVE CONSTRUCTION OF HETERONORMATIVITY IN PUBLIC MENTAL HEALTH SERVICES AND THE IMPLICATIONS FOR CLIENTS. - SEMP, DAVID (Gay & Lesbian Issues & Psychology Review, 2008)
How well do public mental health services (PMHS) address the needs of queer clients? In the 30 years since homosexuality was depathologised by the APA, the field of lesbian and gay psychology has proliferated. One disturbing body of research suggests that men who have sex with men are at greater risk of suicide and other mental health problems. Many attribute these data to the effects of homonegative discourses and practices. Accordingly, mental health clinicians need to be able to identify when they are working with clients for whom these mental health issues are relevant. PMHS services often deal with people experiencing the most severe distress. However, within the literature on mental health issues for queer people, there is a relative dearth of information on PMHS. Within this limited research, there are many suggestions that such services should make themselves more affirmative of queer clients. Yet, how do clinicians know if their clients are queer and struggling with the effects of homonegativity? In this paper, I use interviews with queer staff of PMHS in Aotearoa/New Zealand to explore how a Foucauldian discourse analytic approach can help reveal the ways in which various discourses construct heteronormativity within PMHS and produce significant barriers to clinicians identifying queer clients. This has implications for clinical training and practice. [ABSTRACT FROM AUTHOR]
Keywords: Heteronormativity; Mental health services; Psychology of lesbians; PSYCHOLOGY; Homophobia; Discourse analysis; Gay men; New Zealand

The Attitudes of Australian Heterosexual University Students Toward the Suicide of Gay, Lesbian and Heterosexual Peers. - Molloy, Mari; McLaren, Suzanne (Journal of Gay & Lesbian Issues In Education, 2004)
This study sought to examine the attitudes of heterosexual university students to peer suicide when that peer was gay, lesbian, or heterosexual. University students (n = 206) completed several questionnaires, including The Suicide Attitude Vignette Experience. Results indicated that the suicide act was seen as more justified, acceptable, and necessary when the adolescent was gay or lesbian. Further, gay and lesbian youth suicide victims were shown significantly less empathy than heterosexual suicide victims. Participants' level of homophobia was found to be a significant predictor of attitudes toward gay and lesbian youth suicide. Results indicate that the peer group of gay and lesbian youth is unsupportive of their sexual orientation, and these attitudes may be an additional risk factor for gay and lesbian youth suicide. [ABSTRACT FROM AUTHOR]
Keywords: College student attitudes; Suicide; LGBTQ+ youth; Gay youth; Gay people; Suicide victims; Social psychology; Attitudes; Australia; Homophobia; Undergraduate students

Beyond Risk: Resilience in the Lives of Sexual Minority Youth. - Russell, Stephen T. (Journal of Gay & Lesbian Issues In Education, 2005)
Several decades of research tell us that sexual minority youth are among those most at risk for the negative outcomes of frequent concerns in the lives of young people: academic failure, emotional distress, compromised relationships, risk behavior, and suicidality. We know much less about the resilience, the characteristics, and factors that explain or predict the healthy adolescent and adult lives of most sexual minorities. How can we move "beyond risk" to understanding resilience? I outline a context for the focus on risk in studies of sexual minority youth and then discuss the conceptual distinctions between risk, risk factors, risk outcomes, protective factors, and resilience. I argue that an important area for further research will be to identify risk and protective factors that are unique to sexual minority youth. Recent research on school-based harassment and victimization is used as an example of research on LGBT issues in education that is grounded in the history of risk while offering the potential for significant advances in thinking about resilience. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minorities; Teenagers' sexual behavior; LGBTQ+ people; Harassment; Resilience (Personality trait); ADOLESCENCE; EDUCATION; MENTAL HEALTH; RESILIENCE; RISK; Schools; Special Needs and Programs; Victimization

Bullying and Homophobia in UK Schools: A Perspective on Factors , Affecting Resilience and Recovery. - Rivers, Ian; Cowie, Helen (Journal of Gay & Lesbian Issues In Education, 2006)
This article reports the results of a three-year study focusing on the experiences of a sample of lesbian, gay, and bisexual (LGB) people in the United Kingdom who were victimized by their peers at school. Data collected from 190 LGBs suggested that experiences of victimization at school were both long-term and systematic, and were perpetrated by groups rather than by individuals. Subsequently, data collected from a sub-sample of 119 participants indicated that over 50 percent had contemplated self-harm or suicide at the time they were being harassed, and that 40 percent had engaged in such behavior at least once. As adults, participants were found to exhibit symptoms associated with negative affect when contrasted with heterosexual and non-victimized LGB peers. Seventeen percent exhibited symptoms associated with PTSD. However, the results also demonstrated that the majority of participants did not differ significantly from comparison groups in terms of Self-esteem, and they had a positive attitude towards their sexual orientation. These findings are discussed with reference to the current literature about the development of resilience following exposure to violence and trauma. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; School bullying; Attitudes of LGBTQ+ people; Harassment; Post-traumatic stress disorder; Self-esteem; Bullying; Homophobia; Behavior; Great Britain; BULLYING; harassment; higher education; homophobia; mental health; post-traumatic stress; resilience; secondary education; sexual orientation; suicide; United Kingdom; victimization

Seven Poems. - Enszer, Julie R. (Harrington Lesbian Literary Quarterly, 2006)
The article presents several poems by Julie R. Enszer, "After Virginia Woolf's Suicide," First Line: Anonymous was a woman; Last Line: anymore or Anonymous or a Woman. "Epitaphs for my Transgender Sisters." First Line: She always believed in love; Last Line: blew her head off. "Monster." First Line: My sister tells me, "You must go see a Monster." Last Line: I understand. I understand. "Marital Anagnorisis." First Line: I boast to my friends, Last Line: beside me. She replies, in time, I do.
Keywords: Enszer, Julie R.; Monster (Poem); After Virginia Woolf's Suicide (Poem); Epitaphs for My Transgender Sisters (Poem)

Sieccan Newsletter. - Wells, Kristopher (Canadian Journal of Human Sexuality, 2009)
This article provides an overview of the critical risk factors that negatively impact the health, safety, personal wellness, and educational achievement of sexual minority youth. Contemporary and landmark studies of the key stressors faced by sexual minority are reviewed with an emphasis on Canadian data. Sexual minority youth often encounter multiple risk factors, have fewer protective factors (such as a sense of connectedness to school and family), and experience more bullying, harassment, alienation, suicide ideation, and substance abuse than do their heterosexual peers. Over a decade of research evidence clearly indicates that educational institutions have a legal, ethical, and professional responsibility to respond appropriately to the urgent health, safety, and educational needs of sexual minority youth (Grace & Wells, 2005, 2009; Wells, 2008). A failure to respond by important adults in the lives of such youth, places vulnerable youth at significant risk and denies them access to important protective factors in their lives. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority youth; Psychological abuse; Violence against LGBTQ+ people; Educational psychology; Psychological research; Suicide risk factors; Personality disorders; Safety; Canada

From "Male Bonding Rituals" to "Suicide Tuesday": A Qualitative Study of Issues Faced by Gay Male Ecstasy (MDMA) Users. - Klitzman, Robert (Journal of Homosexuality, 2006)
Use of MDMA and other club drugs has increased among gay men, hut questions remain concerning the use, context, and popularity of these drugs; and views of their side effects. We interviewed in-depth 12 gay MDMA users in New York. MDMA had specific appeals to gay men, who often described isolation and stigmatization. Users underwent a period of initiation and social networks often became comprised of greater numbers of other users. Club environments fostered drug use and vice versa. Awareness of potential adverse effects varied and was minimized. Appropriate educational and prevention programs are needed to address these issues, and must take into account the specific contexts of these gay men's lives. [ABSTRACT FROM AUTHOR]
Keywords: Gay men; Social groups; Substance abuse; Ecstasy (Drug); Drug abuse -- Social aspects; New York (State); United States; club drugs; crystal methamphetamine; drug abuse; ethnographic; Homosexuality; MDMA; prevention; risk behavior; side effects; substance use

Life on the Seesaw: A Qualitative Study of Suicide Resiliency Factors for Young Gay Men. - Fenaughty, John; Harré, Niki (Journal of Homosexuality, 2003)
While considerable research has highlighted the factors that increase gay youth suicide risk, there has been much less emphasis on protective factors. Using grounded theory methodology, we explored the suicide resiliency in eight young gay men in Aotearoa/New Zealand. Common themes emerged, including positive social norms and conditions, high levels of support, identification with role models and high self-esteem. These were integrated with "known" risk factors to form the Seesaw Model of Gay Male Suicide. This model demonstrates that the balance between risk and resiliency may be the key to gay suicide. Depending on the balance of these factors, youth might either be resilient, attempt suicide, or teeter somewhere in between. The current findings indicate that gay youth suicide prevention requires efforts to increase resiliency factors for this group. [ABSTRACT FROM AUTHOR]
Keywords: Suicide; Gay men; Homosexuality; Young men; Research; Methodology

Adjustment among Mothers Reporting Same-Gender Sexual Partners: A Study of a Representative Population Sample from Quebec Province (Canada). - Julien, Danielle; Jouvin, Emilie; Jodoin, Emilie; l’Archevêque, Alexandre; Chartrand, Elise (Archives of Sexual Behavior, 2008)
We examined the well-being of mothers and non-mothers reporting exclusive opposite-gender sexual partners (OG), same-gender sexual partners (SG), or both (BI) in a representative sample of 20,773 participants (11,034 women) 15-years-old or older from the population of Quebec province in Canada. Participants completed a self-administered questionnaire and SG and BI women ( n = 179) were matched to a sample of OG women ( n = 179) based on age, income, geographical area, and children (having at least one 18-year-old or younger biological or adopted child at home). We assessed social milieu variables, risk factors for health disorders, mental health, and quality of mothers’ relationship with children. The findings indicated a sexual orientation main effect: Mothers and non-mothers in the SG and BI group, as compared to their OG controls, were significantly less likely to live in a couple relationship, had significantly lower levels of social support, higher prevalence of early negative life events, substance abuse, suicide ideation, and higher levels of psychological distress. There were no Sexual Orientation X Parenthood status effects. The results further indicated that sexual orientation did not account for unique variance in women’s psychological distress beyond that afforded by their social milieu, health risk factors, and parenthood status. No significant differences were found for the quality of mothers’ relationship with children. SG-BI and OG mothers with low levels of social integration were significantly more likely to report problems with children than parents with high levels of social integration. We need to understand how marginal sexualities and their associated social stigma, as risk indicators for mothers, interact with other factors to impact family life, parenting skills, and children’s adjustment. [ABSTRACT FROM AUTHOR]
Keywords: Human sexuality; Sexual orientation; Social support; Mental health; Distress (Psychology); Québec (Province); Canada; Community studies; Mothers; Parenting; Population-based studies; Sexual minority

Dying to tell: Sexuality and suicide in Imperial Japan. - Robertson, Jennifer (Signs: Journal of Women in Culture & Society, 1999)
Discusses the social implications of suicide among lesbian couples in Japan. Historical account of overt lesbianism in Japan; Etymology of Japanese words used to pertain to lesbians; Different types of lesbian couples in Japanese society.
Keywords: Lesbian couples; Lesbianism; Suicidal behavior; Psychology; Mental health; Japanese people

Educating Gay Male Youth: Since When Is Pornography a Path Towards Self-Respect? - Kendall, Christopher N. (Journal of Homosexuality, 2004)
In 2000, in the case of Little Sisters Book and Art Emporium, the Canadian Supreme Court was asked to determine whether gay male pornography violated the sex equality protections guaranteed by the Canadian Charter of Rights and Freedoms. Throughout this case, gay male activists and academics emphasised the risk posed by antipornography legal strategies to the dissemination of materials intended to promote safer sexual behaviour. Other arguments were advanced that gay male pornography should not be restricted because it serves as a learning tool for young men and, in so doing, does much to reduce the alarming incidence of gay youth suicide. The author examines these assumptions within the context of the gay male pornography defended in Little Sisters. His conclusion is that the present gay male obsession with hyper-masculinity, best evidenced in the pornography now widely touted by some gay men as a source of gay male identity and freedom, undermines safer sexual practices and the self-respect needed to combat youth suicide. The author concludes that gay men must commit to a sexuality built on mutuality, respect and caring (i.e., an identity politic built around sex equality). [ABSTRACT FROM AUTHOR]
Keywords: Gay men; Legal status of gay people; Pornography; Gay youth; Suicide; Activists; Gay rights; Canada; Canada. Supreme Court

“ It Gets Better ” … but How? Exploring Resilience Development in the Accounts of LGBTQ Adults. - Asakura, Kenta; Craig, Shelley L. (Journal of Human Behavior in the Social Environment, 2014)
As reports of bullying and suicide increase, research on lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth must expand its focus from vulnerabilities to resilience development. The purpose of this inductive qualitative study was to explore resilience development in the accounts of LGBTQ adults by analyzing videos posted for theIt Gets Bettersocial media campaign (n= 21). Four major themes emerged: (1) leaving hostile social environments; (2) experiencing “coming out” in meaningful ways; (3) remembering the social environment; and (4) turning challenges into opportunities and strengths. These findings suggest that, despite the campaign's premise, life did not automatically get better for the LGBTQ participants. Rather, the findings offer a nuanced look at the pathways to resilience development. Implications for social work practice are discussed. [ABSTRACT FROM PUBLISHER]
Keywords: Social services; Social media; Suicidal ideation; Psychology of LGBTQ+ people; Adults; Bullying & psychology; Discrimination & psychology; Discourse analysis; Grounded theory; Resilience (Personality trait); Video recording; Qualitative research; Professional practice; Judgment sampling; Social context; Medical coding; bisexual; Gay; It Gets Better project; lesbian; qualitative research; queer; resilience; transgender; video analysis

Summer Holiday Camps for Gay and Lesbian Young Adults: An Evaluation of Their Impact on Social Support and Mental Well-Being. - Vincke, John; Van Heeringen, Kees (Journal of Homosexuality, 2004)
This study evaluates the effects of participating in a summer holiday camp for Flemish (Belgium) gay and lesbian young adults (N 197). Analysis showed to what extent participation affects the constitution and quality of friendships, the availability of confidant and appraisal support, and reported levels of hopelessness, self-esteem, and depression. The study is based on panel data with a six-months interval. At follow-up, respondents reported a higher proportion of gays and lesbians in their friendship network, more satisfaction with these friendships, higher levels of confidant and appraisal support, less hopelessness, higher self-esteem, and lower levels of depression. [ABSTRACT FROM AUTHOR]
Keywords: Social support; Gay & lesbian studies; Lesbian young adults; Young gay men; Quality of life; Identity (Psychology); Self-esteem; Prevention of mental depression; Psychological research; Camps; Belgium; depression; gay and lesbian youths; hopelessness; self-esteem; social support

“ It Gets Better ” … but How? Exploring Resilience Development in the Accounts of LGBTQ Adults. - Asakura, Kenta; Craig, Shelley L. (Journal of Human Behavior in the Social Environment, 2014)
As reports of bullying and suicide increase, research on lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth must expand its focus from vulnerabilities to resilience development. The purpose of this inductive qualitative study was to explore resilience development in the accounts of LGBTQ adults by analyzing videos posted for theIt Gets Bettersocial media campaign (n= 21). Four major themes emerged: (1) leaving hostile social environments; (2) experiencing “coming out” in meaningful ways; (3) remembering the social environment; and (4) turning challenges into opportunities and strengths. These findings suggest that, despite the campaign's premise, life did not automatically get better for the LGBTQ participants. Rather, the findings offer a nuanced look at the pathways to resilience development. Implications for social work practice are discussed. [ABSTRACT FROM AUTHOR]

From the Editor. - Chaney, Michael P. (Journal of LGBT Issues in Counseling, 2020)
An introduction is presented in which the editor discusses articles in the issue on the topics including how resiliency impacts psychosocial stressors, and suicide risk among transgender individuals; and study utilized interpretative phenomenological analysis to understand the treatment.
Keywords: Counseling; Psychology of LGBTQ+ people; Conformity; Phenomenology; Resilience (Personality trait); China; Great Britain

The Relationship Between Gender-Based Victimization and Suicide Attempts in Transgender People. - Goldblum, Peter; Testa, Rylan J.; Pflum, Samantha; Hendricks, Michael L.; Bradford, Judith; Bongar, Bruce (Professional Psychology: Research & Practice, 2012)
This article presents empirical research findings from a subsample of 290 transgender participants in the Virginia Transgender Health Initiative Survey (THIS) who reported whether or not they had experienced hostility or insensitivity related to their gender identity or expression during high school, termed in-school gender-based victimization (GBV). The purpose of this study was to assess the impact of in-school GBV on rates of suicide attempts among transgender people. Of the 290 respondents, 44.8% reported they had experienced in-school GBV, and 28.5% reported a history of suicide attempt. Among those who had attempted, 32.5% reported having made one attempt, 28.6% reported a history of two attempts, and 39.0% reported having made three or more attempts. Participants who reported experiencing GBV were approximately four times more likely to have attempted suicide than those who did not. Among the subgroups of 147 trans women and 81 trans men, GBV was associated both with history of suicide attempt, and with a higher number of suicide attempts over the life span. Implications for policy and clinical interventions are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Bullying; Suicidal behavior; Crime victims; Transgender people; Gender identity; bullying; gender nonconforming; gender-based victimization; suicide attempt; transgender

Associations Between Sexual Abuse and Negative Health Consequences Among High-Risk Men Who Have Sex with Men. - Rusow, Joshua A.; Fletcher, Jesse B.; Le, Hung; Reback, Cathy J. (Journal of Gay & Lesbian Social Services, 2014)
This study evaluated whether a history of sexual abuse could differentiate negative health consequences among men who have sex with men (MSM;N= 148) enrolled in a risk counseling program. More than half (51.4%) reported an experience of sexual abuse. A history of sexual abuse was associated with increased psychological distress, increased rates of alcohol (AOR = 2.91;p<.01) and/or drug abuse (AOR = 2;p<.01) treatment, increased risk of housing instability (AOR = 2.13;p<.05), and increased risk for suicidality (AOR = 4.3;p<.001). Findings demonstrate that screening for sexual abuse may be useful in determining the service needs of high-risk MSM. [ABSTRACT FROM PUBLISHER]
Keywords: Men who have sex with men; Sex crimes; Homelessness; Suicidal behavior; Mental health; Health; Psychology; Substance abuse treatment; homelessness; mental health; MSM; sexual abuse; substance abuse treatment; suicide

Suicidal Ideation and Self-Harm in Lesbian, Gay, Bisexual, and Transgender Youth - Liu, Richard T.; Mustanski, Brian (American Journal of Preventive Medicine, 2012)
Background: Suicide is the third-leading cause of death among adolescents and nonsuicidal self-harm occurs in 13%–45% of individuals within this age group, making these phenomena major public health concerns. Lesbian, gay, bisexual, and transgender (LGBT) youth particularly are at risk for engaging in these behaviors. Nevertheless, relatively little is known about the specific risk factors associated with suicidal ideation and self-harm behaviors in the population. Purpose: This study provides a longitudinal evaluation of the relative contributions of general and LGBT-specific risk factors as well as protective factors to the occurrence of suicidal ideation and self-harm in an ethnically diverse sample of LGBT youth. Methods: A community sample of 246 LGBT youth (aged 16–20 years) was followed prospectively over five time points at regular 6-month intervals. Participants completed a baseline structured interview assessing suicide attempt history and questionnaires measuring gender nonconformity, impulsivity, and sensation-seeking. At follow-up assessments, participants completed a structured interview assessing self-harm and questionnaires for suicidal ideation, hopelessness, social support, and LGBT victimization. Data were collected from 2007 to 2011, and HLM analyses were conducted in 2011. Results: A history of attempted suicide (p=0.05); impulsivity (p=0.01); and prospective LGBT victimization (p=0.03) and low social support (p=0.02) were associated with increased risk for suicidal ideation. Suicide attempt history (p<0.01); sensation-seeking (p=0.04); female gender (p<0.01); childhood gender nonconformity (p<0.01); and prospective hopelessness (p<0.01) and victimization (p<0.01) were associated with greater self-harm. Conclusions: General and LGBT-specific risk factors both uniquely contribute to likelihood of suicidal ideation and self-harm in LGBT youth, which may, in part, account for the higher risk of these phenomena observed in this population. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal ideation; LGBTQ+ youth; Social support; Public health; Despair; Conformity; Risk factors in suicidal behavior; Longitudinal method; Questionnaires

HIV/AIDS Knowledge Among Professional Counselors and Counseling Students in Ohio. - Rose, Jared S.; Sullivan, La Tasha; Hairston, Tiffany; Laux, John M.; Pawelczak, Mark (Journal of LGBT Issues in Counseling, 2015)
Mental health issues faced by individuals living with HIV and AIDS require a continuum of unique counseling services. The need for professional counselors to work with HIV-positive clients is paramount as trained counselors encompass holistic and developmental perspectives. This study was designed as an introductory look at current knowledge-level of HIV/AIDS among counseling professionals to better understand educational needs of counseling students and professional counselors. [ABSTRACT FROM PUBLISHER]
Keywords: HIV infections; Psychological adaptation; Counseling; Drugs; Social support; Suicidal ideation; Anti-HIV agents; Psychology; AIDS & psychology; PSYCHOLOGICAL aspects; Confidence intervals; Continuum of care; Counselors; Psychology of HIV-positive persons; Patient compliance; Probability theory; Professions; Questionnaires; Race; T-test (Statistics); Psychology of AIDS patients; Statistical reliability; Educational attainment; Professional licenses; Continuing education units; Information needs; Data analysis software; Descriptive statistics; Odds ratio; Ohio; counseling students; HIV/AIDS; professional counselors

Drivers of Disparity: Differences in Socially Based Risk Factors of Self-injurious and Suicidal Behaviors Among Sexual Minority College Students. - Blosnich, John; Bossarte, Robert (Journal of American College Health, 2012)
Lesbian, gay, and bisexual (ie, sexual minority) populations have increased prevalence of both self-injurious and suicidal behaviors, but reasons for these disparities are poorly understood. Objective: To test the association between socially based stressors (eg, victimization, discrimination) and self-injurious behavior, suicide ideation, and suicide attempt. Participants: A national sample of college-attending 18- to 24-year-olds. Methods: Random or census samples from postsecondary educational institutions that administered the National College Health Assessment during the Fall 2008 and Spring 2009 semesters. Results: Sexual minorities reported more socially based stressors than heterosexuals. Bisexuals exhibited greatest prevalence of self-injurious and suicidal behaviors. In adjusted models, intimate partner violence was most consistently associated with self-injurious behaviors. Conclusions: Sexual minorities’ elevated risks of self-injurious and suicidal behaviors may stem from higher exposure to socially based stressors. Within-group differences among sexual minorities offer insight to specific risk factors that may contribute to elevated self-injurious and suicidal behaviors in sexual minority populations. [ABSTRACT FROM PUBLISHER]
Keywords: Bisexuals; Discrimination; Heterosexuals; Mental illness; PSYCHOLOGY; LGBTQ+ people; Suicidal ideation; Violence -- Psychological aspects; Self-injurious behavior -- Risk factors; Chi-squared test; College students; Comparative studies; Confidence intervals; Correlation (Statistics); Epidemiology; Mathematical models; Minorities; Questionnaires; Statistical sampling; Statistics; Surveys; Data analysis; Multiple regression analysis; Secondary analysis; Social context; Disease prevalence; Descriptive statistics; bisexuality; homosexuality; mental health; self-injurious behavior

A Conceptual Framework for Clinical Work With Transgender and Gender Nonconforming Clients: An Adaptation of the Minority Stress Model. - Hendricks, Michael L.; Testa, Rylan J. (Professional Psychology: Research & Practice, 2012)
In the last few years, transgender and gender nonconforming people have become more visible in our society, which has sparked a marked increase in awareness, interest, and attention among psychologists. Questions have emerged about the extent to which psychologists are able to work competently with this population. This article presents a framework for understanding key clinical issues that psychologists who work with transgender and gender nonconforming individuals will likely encounter in their clinical work. This article does not address the knowledge and skills required to provide services related to gender transition, but rather to provide other psychological services that these clients may need, in light of the high levels of gender-related victimization and discrimination to which they are exposed. An adaptation of the Minority Stress Model (Meyer, 2003) is presented and translated to incorporate the unique experiences encountered by transgender and gender nonconforming individuals. In particular, we examine adverse experiences that are closely related to gender identity and expression, resulting expectations for future victimization or rejection, and internalized transphobia. The impact of Minority Stress Model factors on suicide attempts is presented as a detailed example. Mechanisms by which transgender and gender nonconforming persons develop resilience to the negative psychological effects of these adverse experiences are also discussed. Recommendations for clinicians are then made to assist psychologists in developing competence in working with this population. [ABSTRACT FROM AUTHOR]
Keywords: Transgender people; Suicidal behavior; Violence; Crime victims; Resilience (Personality trait); Psychologists; minority stress; resilience; suicide attempt; transgender; violence

'A MAN IN A CASSOCK IN WEARING A SKIRT' - Waller, James C. (GLQ: A Journal of Lesbian & Gay Studies, 1998)
Discusses the prevalence of exposed U.S. gay clergymen disappearing from their parish posts and of their lives being ruined by alcoholism or cut short by suicide. Nature of human personality and ideas of psychic conflict drawn from psychoanalysis and other psychiatric disciplines; Books and readings about the issue; Status quo of stereotyped conceptions of masculinity and femininity and of appropriate gender roles.
Keywords: Gay clergy; Religious life of gay people; Psychoanalysis; Gender role; Clergy; United States

Effects of Violence on Transgender People. - Testa, Rylan J.; Sciacca, Laura M.; Wang, Florence; Hendricks, Michael L.; Goldblum, Peter; Bradford, Judith; Bongar, Bruce (Professional Psychology: Research & Practice, 2012)
While recent research on transgender populations has demonstrated high rates of experiencing violence, there has been little research attention to the mental health implications of these experiences. This study utilized data collected from the Virginia Transgender Health Initiative Survey (THIS) of transgender people (individuals who described their gender identity as different from their sex assigned at birth) collected from 2005-2006. Current study analyses were limited to two subgroups: trans women (n = 179) and trans men (n = 92). We hypothesized that, as in the general population, exposure to physical and sexual violence would be related to suicidal ideation, suicide attempts, and substance abuse. Both trans women and trans men in this sample were at high risk for physical and sexual violence, as well as suicidal ideation and suicide attempt. Logistic regression analyses indicated that among both trans women and trans men, those who had endured physical and/or sexual violence were significantly more likely than those who had not had such experiences to report a history of suicide attempt and multiple suicide attempts. In addition, among trans men, history of physical and sexual violence were each related to alcohol abuse. Among trans women, history of sexual violence was related to alcohol abuse and illicit substance use. Patterns of violence against transgender people were identified and are discussed, including frequent gender-related motivation for violence, low prevalence of reporting violence to police, and variety of perpetrators of violence. Clinical implications and recommendations are provided. [ABSTRACT FROM AUTHOR]
Keywords: Violence; Suicidal behavior; Transgender people; Mental health; Suicidal ideation; Substance abuse; physical violence; sexual violence; substance abuse; suicide attempt; transgender

The Social Environment and Suicide Attempts in Lesbian, Gay, and Bisexual Youth. - Hatzenbuehler, MarkL. (Pediatrics, 2011)
OBJECTIVE: To determine whether the social environment surrounding lesbian, gay, and bisexual youth may contribute to their higher rates of suicide attempts, controlling for individual-level risk factors. METHODS: A total of 31 852 11th grade students (1413 [4.4%] lesbian, gay, and bisexual individuals) in Oregon completed the Oregon Healthy Teens survey in 2006-2008. We created a composite index of the social environment in 34 counties, including (1) the proportion of same-sex couples, (2) the proportion of registered Democrats, (3) the presence of gay-straight alliances in schools, and (4) school policies (nondiscrimination and antibullying) that specifically protected lesbian, gay, and bisexual students. RESULTS: Lesbian, gay, and bisexual youth were significantly more likely to attempt suicide in the previous 12 months, compared with heterosexuals (21.5% vs 4.2%). Among lesbian, gay, and bisexual youth, the risk of attempting suicide was 20% greater in unsupportive environments compared to supportive environments. A more supportive social environment was significantly associated with fewer suicide attempts, controlling for sociodemographic variables and multiple risk factors for suicide attempts, including depressive symptoms, binge drinking, peer victimization, and physical abuse by an adult (odds ratio: 0.97 [95% confidence interval: 0.96-0.99]). CONCLUSIONS: This study documents an association between an objective measure of the social environment and suicide attempts among lesbian, gay, and bisexual youth. The social environment appears to confer risk for suicide attempts over and above individual-level risk factors. These results have important implications for the development of policies and interventions to reduce sexual orientation-related disparities in suicide attempts. [ABSTRACT FROM AUTHOR]
Keywords: Social alienation; Substance abuse; Suicidal behavior; Social support; Psychology of LGBTQ+ people; Bullying & psychology; Prevention of mental depression; Risk factors in suicidal behavior; Confidence intervals; Epidemiology; Factor analysis; Research funding; School administration; Data analysis; Social context; Cross-sectional method; Oregon; disparities; sexual orientation; social determinants of health; Suicide attemps; suicide attempts

Men’s sexual orientation and suicide: Evidence for U.S. adolescent-specific risk - Russell, Stephen T.; Toomey, Russell B. (Social Science & Medicine, 2012)
Abstract: There is strong consensus in the research literature that adolescent and adult men who report same-sex sexual orientations, identities, and behaviors are at higher risk for suicide. Recent studies of general adolescent suicide risk have identified developmental trajectories that peak during the teenage years. Because the adolescent years are characterized by the development and heightened awareness of gender roles and sexual scripts closely tied to dominant cultural ideals of masculinity and heterosexuality, an adolescent-focused developmental trajectory for suicide risk might be particularly relevant for males with adolescent same-sex sexual orientations. We provide the first prospective examination of adolescent-specific risk for suicidality based on adolescent same-sex sexual orientation using data from the United States, the National Longitudinal Study of Adolescent Health. Tracing suicide ideation and attempts across four assessments from adolescence (Wave 1 average age 15.3 years) to young adulthood (Wave 4 average age 28.2), we documented that the risk for suicidal thoughts and attempts for adolescent same-sex attracted males is developmental in nature. Specifically, the risk for suicidal thoughts and attempts for males with same-sex attractions is largely limited to the adolescent years. These results offer new insights for suicide prevention and intervention for male adolescents and adults with same-sex sexual orientations. [Copyright &y& Elsevier]
Keywords: Homosexuality; Suicidal ideation; Suicide risk factors; Longitudinal method; Descriptive statistics; Adolescence; Adolescent development; Adolescents; Bisexual; Gay; Longitudinal; Sexual identity; Sexual orientation; Suicidality; Suicide; USA

Suicidality and Depression Disparities Between Sexual Minority and Heterosexual Youth: A Meta-Analytic Review - Marshal, Michael P.; Dietz, Laura J.; Friedman, Mark S.; Stall, Ron; Smith, Helen A.; McGinley, James; Thoma, Brian C.; Murray, Pamela J.; D'Augelli, Anthony R.; Brent, David A. (Journal of Adolescent Health, 2011)
Abstract: Purpose: To examine disparities between sexual minority youth (SMY) and heterosexual youth in rates of suicidality and depression symptoms. Methods: Separate meta-analyses were conducted to examine suicidality and depression disparities. Studies were included if the average age of the participants was <18 years, and if suicidality or depression symptoms were compared across SMY and heterosexual youth. Results: SMY reported significantly higher rates of suicidality (odds ratio [OR] = 2.92) and depression symptoms (standardized mean difference, d = .33) as compared with the heterosexual youth. Disparities increased with the increase in the severity of suicidality (ideation [OR = 1.96], intent/plans [OR = 2.20], suicide attempts [OR = 3.18], suicide attempts requiring medical attention [OR = 4.17]). Effects did not vary across gender, recruitment source, and sexual orientation definition. Conclusions: Disparities in suicidality and depression may be influenced by negative experiences including discrimination and victimization. Clinicians should assess sexual orientation, analyze psychosocial histories to identify associated risk factors, and promote prevention and intervention opportunities for SMY and their families. [Copyright &y& Elsevier]
Keywords: Bisexuality; Mental health services; Human sexuality; Psychology of LGBTQ+ people; Adolescence; Suicide risk factors; Analysis of variance; Computer software; Confidence intervals; Correlation (Statistics); Mental depression; Epidemiology; Information storage & retrieval systems; Psychology information storage & retrieval systems; Medical records -- Abstracting & indexing; MEDLINE; Meta-analysis; Regression analysis; Systematic reviews (Medical research); Data analysis; Effect sizes (Statistics); Bisexual; Depression; Disparities; Gay; Lesbian; LGBT youth; Sexual minority youth; Suicidality; Suicide

Managing uncertainty: A grounded theory of stigma in transgender health care encounters - Poteat, Tonia; German, Danielle; Kerrigan, Deanna (Social Science & Medicine, 2013)
Abstract: A growing body of literature supports stigma and discrimination as fundamental causes of health disparities. Stigma and discrimination experienced by transgender people have been associated with increased risk for depression, suicide, and HIV. Transgender stigma and discrimination experienced in health care influence transgender people''s health care access and utilization. Thus, understanding how stigma and discrimination manifest and function in health care encounters is critical to addressing health disparities for transgender people. A qualitative, grounded theory approach was taken to this study of stigma in health care interactions. Between January and July 2011, fifty-five transgender people and twelve medical providers participated in one-time in-depth interviews about stigma, discrimination, and health care interactions between providers and transgender patients. Due to the social and institutional stigma against transgender people, their care is excluded from medical training. Therefore, providers approach medical encounters with transgender patients with ambivalence and uncertainty. Transgender people anticipate that providers will not know how to meet their needs. This uncertainty and ambivalence in the medical encounter upsets the normal balance of power in provider–patient relationships. Interpersonal stigma functions to reinforce the power and authority of the medical provider during these interactions. Functional theories of stigma posit that we hold stigmatizing attitudes because they serve specific psychological functions. However, these theories ignore how hierarchies of power in social relationships serve to maintain and reinforce inequalities. The findings of this study suggest that interpersonal stigma also functions to reinforce medical power and authority in the face of provider uncertainty. Within functional theories of stigma, it is important to acknowledge the role of power and to understand how stigmatizing attitudes function to maintain systems of inequality that contribute to health disparities. [Copyright &y& Elsevier]
Keywords: Social stigma; Transgender people; Psychology; Grounded theory; Interviewing; Patient-professional relations; Qualitative research; Doctor–patient communication; Health care access; Health disparities; Stigma; Transgender; USA

Suicidal Ideation Among Sexual Minority Veterans: Results From the 2005-2010 Massachusetts Behavioral Risk Factor Surveillance Survey. - Blosnich, John R.; Bossarte, Robert M.; Silenzio, Vincent M. B. (American Journal of Public Health, 2012)
Suicide is a public health problem disproportionately associated with some demographic characteristics (e.g., sexual orientation, veteran status). Analyses of the Massachusetts Behavioral Risk Factor Surveillance Survey data revealed that more lesbian, gay, and bisexual (i.e., sexual minority) veterans reported suicidal ideation compared with heterosexual veterans. Decreased social and emotional support contributed to explaining the association between sexual minority status and suicidal ideation. More research is needed about suicide risk among sexual minority veterans; they might be a population for outreach and intervention by the Veterans Health Administration. [ABSTRACT FROM AUTHOR]
Keywords: Bisexuals; Gay people; Heterosexuals; Lesbians; Minorities; Human sexuality; Social isolation; Suicidal ideation; Comparative studies; Correlation (Statistics); Veterans; Public health surveillance; Questionnaires; Surveys; Secondary analysis; Massachusetts

HIV Risk, Substance Use, and Suicidal Behaviors Among Asian American Lesbian and Bisexual Women. - Lee, Jieha; Hahm, Hyeouk Chris (AIDS Education & Prevention, 2012)
The authors examined the association between lesbian/bisexual identity and three risky health behaviors (HIV risk, substance use, and suicidal behaviors) in a sample of Asian American women. This cross-sectional study was designed to investigate the prevalence of HIV risk behaviors and mental health functioning among unmarried Chinese, Korean, and Vietnamese women ages 18 to 35 who are children of immigrants ( N = 701), using computer-assisted survey interviews (CASI). Approximately one out of five Asian American women in the sample identified themselves as a lesbian and bisexual woman (18%). Overall, Asian American lesbian and bisexual women reported higher proportions of risky health behaviors than did their exclusively heterosexual counterparts. The odds of engaging in HIV risk behaviors, using substances, and experiencing suicidal ideation were two to three times higher for lesbian and bisexual women than for exclusively heterosexual women. These findings suggest that rigorous screening is necessary for identifying women in this lesbian/bisexual subgroup in order to provide them with better assessment and services. [ABSTRACT FROM AUTHOR]
Keywords: HIV infection risk factors; Acculturation; Bisexuality; Lesbians; Risk-taking behavior; Suicidal ideation; Sexual partners; Psychology; Substance abuse -- Risk factors; Automatic data collection systems; Epidemiology; Probability theory; Research funding; Statistical sampling; Asians; Data analysis; Cross-sectional method; Descriptive statistics

“Sensible” Suicide, Brutal Selfishness, and John Hughes’s Queer Bonds. - Goltz, Dustin Bradley (Cultural Studies/Critical Methodologies, 2013)
Queer bonds conceptualize inventive and resistant modes of belonging, sociability, and relation that push at, through, andoutside normative relational systems and their normative commitments. The essay juxtaposes contemporary gay suicidediscourse, specifically the "It Gets Better" campaign and 2009's Prayers for Bobby with the 1985 Molly Ringwald made-for-TV film Surviving: A Family in Crisis, examining how normative familial bonds in discourses of heterosexual suicide produce aresistant and relational discourse of brutal selfishness. Contrary to a rhetoric of selfishness, mediated representation of gayyouth suicide reproduces a discursive link between gay identity and suicide that constructs gay suicide as problematicallylogical, sensible, and intelligible. Conceptualizing a queered rhetoric of selfishness, resisting gay suicidal logics, the essaylooks to queer bonds forged in John Hughes's 'Brat Pack" films of otherness as maps of relational resistance and inventivearticulations of non-normative modes of queer selfishness and belonging. [ABSTRACT FROM AUTHOR]
Keywords: Queer theory; Suicide; Gay identity; Sociability; Hughes, John

Suicidal Ideation and Sexual Orientation in College Students: The Roles of Perceived Burdensomeness, Thwarted Belongingness, and Perceived Rejection Due to Sexual Orientation. - Hill, Ryan M.; Pettit, Jeremy W. (Suicide & Life-Threatening Behavior, 2012)
A theoretical model in which perceived burdensomeness and thwarted belongingness were hypothesized to account for the association between sexual orientation and suicidal ideation among college students was tested. Among 198 college students (mean age 21.28 years), gay, lesbian, and bisexual students ( n = 50) reported significantly higher levels of perceived burdensomeness and suicidal ideation than heterosexual students. The relationship between sexual orientation and suicidal ideation was partially accounted for by perceived burdensomeness, but not thwarted belongingness. This indirect effect was stronger at higher levels of perceived or anticipated rejection due to one's sexual orientation. Implications for intervention and prevention science are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal ideation; Social belonging; Sexual orientation; Heterosexuals; Suicidal behavior in college students

School Climate, Individual Support, or Both? Gay-Straight Alliances and the Mental Health of Sexual Minority Youth. - Walls, N. Eugene; Wisneski, Hope; Kane, Sarah (School Social Work Journal (Follmer Group), 2013)
Using a sample of 284 sexual minority youth and young adults, this paper examines the relationships between mental health variables, the absence or presence of a gay-straight alliance, and membership status in a gay-straight alliance. The results suggest that the presence of a gay-straight alliance in a school or college, rather than actual membership in the club, is correlated with decreased suicidality, while substance use and comfort with gender expression is correlated with membership specifically. Implications for social work practice and future research are suggested. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority students; Gay-straight alliances in schools; Mental health; Membership; School social work; United States; bisexual; gay; gay-straight alliance; gender conformity; lesbian; mental health; sexual minority youth; substance abuse; suicidality; transgender

Suicide Prevention for LGBT Students. - Johnson, R. Bradley; Oxendine, Symphony; Taub, Deborah J.; Robertson, Jason (New Directions for Student Services, 2013)
This chapter explores the intersection of mental health concerns and suicide of LGBT college students on campus, including bullying and cyberbullying. One campus's approach to providing support for these students is discussed. [ABSTRACT FROM AUTHOR]
Keywords: Suicide prevention; LGBTQ+ students; Suicidal behavior in college students; Mental health of college students; Suicide risk factors

Disproportionate exposure to early-life adversity and sexual orientation disparities in psychiatric morbidity - McLaughlin, Katie A.; Hatzenbuehler, Mark L.; Xuan, Ziming; Conron, Kerith J. (Child Abuse & Neglect, 2012)
Objectives: Lesbian, gay, and bisexual (LGB) populations exhibit elevated rates of psychiatric disorders compared to heterosexuals, and these disparities emerge early in the life course. We examined the role of exposure to early-life victimization and adversity—including physical and sexual abuse, homelessness, and intimate partner violence—in explaining sexual orientation disparities in mental health among adolescents and young adults. Methods: Data were drawn from the National Longitudinal Study of Adolescent Health, Wave 3 (2001–2002), a nationally representative survey of adolescents. Participants included gay/lesbian (n =227), bisexual (n =245), and heterosexual (n =13,490) youths, ages 18–27. We examined differences in the prevalence of exposure to child physical or sexual abuse, homelessness or expulsion from one's home by caregivers, and physical and sexual intimate partner violence according to sexual orientation. Next we examined the associations of these exposures with symptoms of psychopathology including suicidal ideation and attempts, depression, binge drinking, illicit drug use, tobacco use, alcohol abuse, and drug abuse. Finally, we determined whether exposure to victimization and adversity explained the association between sexual orientation and psychopathology. Results: Gay/lesbian and bisexual respondents had higher levels of psychopathology than heterosexuals across all outcomes. Gay/lesbian respondents had higher odds of exposure to child abuse and housing adversity, and bisexual respondents had higher odds of exposure to child abuse, housing adversity, and intimate partner violence, than heterosexuals. Greater exposure to these adversities explained between 10 and 20% of the relative excess of suicidality, depression, tobacco use, and symptoms of alcohol and drug abuse among LGB youths compared to heterosexuals. Exposure to victimization and adversity experiences in childhood and adolescence significantly mediated the association of both gay/lesbian and bisexual orientation with suicidality, depressive symptoms, tobacco use, and alcohol abuse. Conclusions: Exposure to victimization in early-life family and romantic relationships explains, in part, sexual orientation disparities in a wide range of mental health and substance use outcomes, highlighting novel targets for preventive interventions aimed at reducing these disparities. [Copyright &y& Elsevier]
Keywords: LGBTQ+ teenagers; Child sexual abuse; LGBTQ+ young adults; Suicidal ideation; Tobacco use; Alcoholism; Child abuse; Homeless children; Surveys; Child psychopathology; Childhood adversity; Disparities; LGB; Psychopathology; Sexual orientation; Victimization

Inequities in Educational and Psychological Outcomes Between LGBTQ and Straight Students in Middle and High School. - Robinson, Joseph P.; Espelage, Dorothy L. (Educational Researcher, 2011)
This study finds that, compared with straight-identified youth, youth who identify as lesbian, gay, bisexual, transgender, or questioning (LGBTQ) are at greater risk of suicidal thoughts, suicide attempts, victimization by peers, and elevated levels of unexcused absences from school. Results disaggregated by LGBTQ subgroups reveal heterogeneity within the broad LGBTQ group, with bisexual youth appearing to be particularly at risk. Also, although the risk gaps in school belongingness and unexcused absences are significant in high school, we find that these gaps are significantly greater in middle school, suggesting heightened early risk for LGBTQ-identified students. By raising awareness of educational inequities related to LGBTQ identification, this study lays the descriptive groundwork for interventions aimed at improving psychological and educational outcomes for these students. [ABSTRACT FROM PUBLISHER]
Keywords: LGBTQ+ youth; LGBTQ+ students; Social belonging; Health; Teenage suicide; Suicidal behavior in youth; At-risk students; Stress in adolescence; Heterogeneity; Educational equalization; Middle school students; High school students; at-risk students; gay/lesbian studies; multilevel mod- eling; stress/coping

Offsetting Risks: High School Gay-Straight Alliances and Lesbian, Gay, Bisexual, and Transgender (LGBT) Youth. - Heck, Nicholas C.; Flentje, Annesa; Cochran, Bryan N. (School Psychology Quarterly, 2011)
Lesbian, gay, bisexual, and transgender (LGBT) youth are at risk for engaging in negative health behaviors and for experiencing at-school victimization. Specific benefits of attending a high school with a gay-straight alliance (GSA), including lower levels of suicidality, have been published; however, it is unclear whether GSAs are related to lower levels of problematic substance use, depressive symptoms, and psychological distress. Using a sample of 145 LGBT youth recruited from college and university organizations for LGBT students, we examined whether attending a high school with a GSA was related to more positive school experiences and mental health outcomes for LGBT youth. The results indicate that youth who attended a high school with a GSA report significantly more favorable outcomes related to school experiences, alcohol use, and psychological distress. The implications of the findings are discussed as they relate to school psychologists. Important limitations of this study are reviewed. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority youth; Gay-straight alliances in schools; LGBTQ+ youth; Alcoholism; High schools; alcohol; gay-straight alliance; high school; LGBT; sexual minority youth

Mental Health Disorders, Psychological Distress, and Suicidality in a Diverse Sample of Lesbian, Gay, Bisexual, and Transgender Youths. - Mustanski, Brian S.; Garofalo, Robert; Emerson, Erin M. (American Journal of Public Health, 2010)
Objectives. We examined associations of race/ethnicity, gender, and sexual orientation with mental disorders among lesbian, gay, bisexual, and transgender (LGBT) youths. Methods. We assessed mental disorders by administering a structured diagnostic interview to a community sample of 246 LGBT youths aged 16 to 20 years. Participants also completed the Brief Symptom Inventory 18 (BSI 18). Results. One third of participants met criteria for any mental disorder, 17% for conduct disorder, 15% for major depression, and 9% for posttraumatic stress disorder. Anorexia and bulimia were rare. Lifetime suicide attempts were frequent (31%) but less so in the prior 12 months (7%). Few racial/ethnic and gender differences were statistically significant. Bisexually identified youths had lower prevalences of every diagnosis. The BSI 18 had high negative predictive power (90%) and low positive predictive power (25%) for major depression. Conclusions. LGBT youths had higher prevalences of mental disorder diagnoses than youths in national samples, but were similar to representative samples of urban, racial/ethnic minority youths. Suicide behaviors were similar to those among representative youth samples in the same geographic area. Questionnaires measuring psychological distress may overestimate depression prevalence among this population. [ABSTRACT FROM AUTHOR]
Keywords: Psychology of LGBTQ+ people; LGBTQ+ youth; LGBTQ+ young adults; Suicidal behavior; Psychology; Psychiatric research; Distress (Psychology)

Creating Safe Environments for Students With Disabilities Who Identify as Lesbian, Gay, Bisexual, or Transgender. - Morgan, Joseph J.; Mancl, Dustin B.; Kaffar, Bradley J.; Ferreira, Danielle (Intervention in School & Clinic, 2011)
Adolescence is an important time in human development. Teenagers spend much time questioning their core belief structures and developing the foundations of their identity. For students who identify as lesbian, gay, bisexual, or transgender (LGBT), this path of development is difficult in American schools because of strongly held homophobic beliefs. Barriers in sexuality identity development could cause problems for students with disabilities, including low self-esteem, psychological problems, and suicidal ideations. This article addresses action steps that educators can take to support this student population. [ABSTRACT FROM PUBLISHER]
Keywords: LGBTQ+ teenagers; Sexual orientation identity; Sex education; Cultural pluralism; Education; Teenagers with disabilities; Classroom environment; Classroom management research; United States; classroom environment; classroom management; cultural and linguistic diversity; sexuality education

Suicidal ideation among patients with gender identity disorder - Terada, Seishi; Matsumoto, Yosuke; Sato, Toshiki; Okabe, Nobuyuki; Kishimoto, Yuki; Uchitomi, Yosuke (Psychiatry Research, 2011)
Abstract: In this study, we tried to clarify the prevalence of suicidal ideation and self-mutilation including suicide attempts among patients with gender identity disorder (GID) and the relationship of those behaviors to demographic characteristics. A total of 500 consecutive Japanese GID patients without any other psychiatric comorbidity were evaluated at the outpatient GID Clinic of Okayama University Hospital. The lifetime rate of suicidal ideation was 72.0% of the total sample. There were no significant differences in the prevalence of suicidal ideation among groups divided by sex, age, age at onset or education. The lifetime prevalence of self-mutilation including suicide attempts was 31.8% of the total sample. Low level of education was significantly related to self-mutilation among both male-to-female and female-to-male GID patients. Younger age at onset was a significant factor affecting self-mutilation only among MTF GID patients. A lack of strategies to cope with severe distress among persons with lower education might induce a high frequency of self-mutilation including suicidal attempt. GID patients with a low level education might be at high risk of self-mutilation and should be watched with special attention to self-mutilation. [Copyright &y& Elsevier]
Keywords: Suicidal ideation; Gender dysphoria; Demographic characteristics; Psychiatry; Self-mutilation; Suicidal behavior; Gender; Gender identity disorder

Religious Abuse: Implications for Counseling Lesbian, Gay, Bisexual, and Transgender Individuals. - Super, John T.; Jacobson, Lamerial (Journal of LGBT Issues in Counseling, 2011)
Religion is often the place a lesbian, gay, bisexual, or transgender (LGBT) individual may turn to understand and navigate their sexual orientation identity development. However, religious abuse may occur when a religious group or leader, whether intentionally or unintentionally, uses coercion, threats, rejection, condemnation, or manipulation to force the individual into submission of the religious views about sexuality. The abuse may result in great harm to the victim by causing low self-esteem, guilt, shame, spirituality loss, substance abuse, or thoughts of suicide. Counselors need to be aware of religious abuse to help clients navigate any spiritual divide between religious beliefs and sexuality. Therefore, the purpose of this article is to (a) describe the differences between religion and spirituality,(b) define religious abuse, (c) describe the effects of religious abuse on LGBT individuals and society, and (d) delineate the counseling implications of religious abuse in working with LGBT individuals. [ABSTRACT FROM PUBLISHER]
Keywords: Homophobia; Attitude (Psychology); Gay men; Gender identity; Group identity; Religion; Spirituality; Psychology of LGBTQ+ people; Attitudes toward sex; Psychology; Goal (Psychology); Conceptual structures; Counseling -- Methodology

Correlates of Depressed Mood among Young Stimulant-Using Homeless Gay and Bisexual Men. - Nyamathi, Adeline; Branson, Catherine; Idemundia, Faith; Reback, Cathy; Shoptaw, Steven; Marfisee, Mary; Keenan, Colleen; Khalilifard, Farinaz; Liu, Yihang; Yadav, Kartik (Issues in Mental Health Nursing, 2012)
Homeless gay and bisexual (G/B) men are at risk for suicide attempts and have high risk of depressed mood, defined as elevated level of depressive symptoms. This study describes baseline socio-demographic, cognitive, psychosocial, and health- and drug-related correlates of depressed mood in 267 stimulant-using homeless G/B young men who entered a study designed to reduce drug use. G/B men without social support were 11 times more likely to experience depressed mood than their counterparts who had support; those who reported severe body pain were almost six times more likely to report depressed mood than those without pain. Other factors that increased risk of depressed mood included being homeless in the last four months, injecting drugs, reporting poor or fair health status, and high levels of internalized homophobia. This study is one of the first studies to draw a link between pain experienced and depressed mood in homeless young G/B men. Understanding the correlates of depressed mood among homeless G/B young men can help service providers design more targeted treatment plans and provide more appropriate referrals to ancillary care services. [ABSTRACT FROM AUTHOR]
Keywords: Bisexuality; Clinical trials; Gay men; Homeless persons; Substance abuse; Mental depression; Statistical sampling; Data analysis software; Descriptive statistics; California

Gay Children and Suicidality: The Importance of Professional Nurturance. - McAndrew, Sue; Warne, Tony (Issues in Mental Health Nursing, 2012)
Suicidality among young people is a global concern, with international studies demonstrating an increased prevalence among young gay men. Being gay is not inevitably linked to mental illness, but growing up gay in a heterosexist society can compromise mental well being. This qualitative study, using free association narrative interviewing, offers an in-depth understanding of gay men's experience. One shared experience that emerged was 'knowing and not knowing,' the story of gay children growing up in a heterosexist society. This story provides valuable insights for mental health nurses becoming more attuned to the importance of providing professional nurturing of gay children. [ABSTRACT FROM AUTHOR]
Keywords: Child welfare; Homosexuality; Social support; Well-being; Suicide risk factors; Interviewing; Psychoanalytic interpretation; Research; Sound recordings; Qualitative research; Narratives; Disease prevalence

Improving the lives of students, gay and straight alike: Gay-straight alliances and the role of school psychologists. - MURPHY, HEATHER ELISE (Psychology in the Schools, 2012)
Lesbian, gay, bisexual, and transgender (LGBT) students face many risk factors every day when they enter their school's door. These students often fear for their safety at school, are victimized, have academic difficulties, suffer from issues with their identity development, and are at risk for suicide. School-based Gay-Straight Alliances (GSAs) have been shown to reduce the risk for LGBT students in these areas. School psychologists are in a unique position to be instrumental in alleviating many of the problems LGBT students face every day by being a GSA advisor. This article reviews the literature on LGBT student risk in terms of the benefits of a GSA and guides school psychologists on how to start and advise a GSA in their schools. [ABSTRACT FROM AUTHOR]
Keywords: Gay-straight alliances in schools; LGBTQ+ students; LGBTQ+ student organizations & activities; Faculty advisors; Prevention of school violence; School psychology; School psychologists; Literature reviews

Shooting ourselves in the foot: discrimination in the LGBT community. - Staunton, Shaun (HIV Australia, 2008)
The article focuses on the impression of the public on LGBT people in Australia. According to the author, the most common type of prejudice that LGBT people were experiencing are public ridicule, exclusion, and verbal abuse. Moreover, it mentions that discrimination usually occur in spaces that they were supposed to be able to go to for refuge, support and belonging.
Keywords: LGBTQ+ people; Discrimination; Genderism; Prejudices; Australia

Lesbian, Gay, Bisexual, and Transgender Health Issues, Disparities, and Information Resources. - McKay, Becky (Medical Reference Services Quarterly, 2011)
Lesbian, gay, bisexual, and transgender (LGBT) persons, while widely diverse in many ways, share health disparities related to the stigma and discrimination they experience, including disproportionate rates of psychiatric disorders, substance abuse, and suicide. Lesbians, gay men, bisexuals, and the transgender communities have additional health concerns and disparities unique to each population. This paper highlights the national recognition of these health issues and disparities and presents web-based information resources about them and their mitigation. [ABSTRACT FROM AUTHOR]
Keywords: Alcoholism; Bisexuals; Discrimination; Gay people; Health services accessibility; Human rights; Internet; Mental health; Substance abuse; Transgender people; Information resources; Cultural competence; Centers for Disease Control & Prevention (U.S.)

Sexual Orientation and Its Relation to Mental Disorders and Suicide Attempts: Findings From a Nationally Representative Sample. - Bolton, Shay-Lee; Sareen, Jitender (Canadian Journal of Psychiatry, 2011)
Objective: To compare the rates of all Axis I and II mental disorders and suicide attempts in sexual orientation minorities with rates in heterosexuals using a nationally representative sample. Method: Data used were from the National Epidemiologic Survey on Alcohol and Related Conditions Wave 2 (n = 34 653, response rate = 70.2%). Cross-tabulations and multivariate logistic regression analyses were performed to determine differences in rates of mental disorders and suicide attempts by sexual orientation. All analyses were stratified by sex. Results: Compared with their heterosexual counterparts, lesbians and bisexual women demonstrated a 3-fold increased likelihood of substance use disorders, and gay and bisexual men showed twice the rate of anxiety disorders and schizophrenia and (or) psychotic illness, even after accounting for mental disorder comorbidity. Suicide attempts were independently associated with bisexuality, with odds 3 times higher than in heterosexuals. Conclusion: Findings from our study emphasize the fact that sexual orientation minorities are vulnerable to poor mental health outcomes, including suicide attempts. Clinicians need to be aware of these specific negative mental health consequences when assessing sexual orientation minorities. (English) [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Mental illness; Suicidal behavior; Heterosexuals; Lesbians; PSYCHOLOGY; Substance abuse; Psychology; Multivariate analysis; Regression analysis; Gay men; attempts; gay; lesbian; mental disorders; National Epidemiologic Survey on Alcohol and Related Conditions; sexual minorities; suicide

Increased Risk of Suicide Attempts Among Black and Latino Lesbians, Gay Men, and Bisexuals. - O'Donnell, Shannon; Meyer, Ilan H.; Schwartz, Sharon (American Journal of Public Health, 2011)
Members of racial/ethnic minority groups have a lower lifetime prevalence than have Whites of mental disorders, a risk factor for suicide attempts; paradoxically, however, lesbian, gay, and bisexual (LGB) ethnic minority youths may be at increased risk for suicide attempts relative to White LGB youths. We found that the increased risk of suicide attempts among racial/ethnic minority LGB respondents in our sample relative to White respondents was not explained by excess youth onset of depression and substance abuse or by a higher susceptibility to suicide in the racial/ethnic minority LGB group. [ABSTRACT FROM AUTHOR]
Keywords: Substance abuse; Suicidal behavior; LGBTQ+ people; Metropolitan areas; Hypothesis; Age distribution; Black people; Comparative studies; Confidence intervals; Mental depression; Epidemiology; Hispanic Americans; Mathematical models; Research funding; Statistical sampling; Statistics; White people; Data analysis; Disease prevalence; New York (State)

The Co-Occurrence of Mental Illness and High HIV Risk in a Sample of African American MSM: Findings and Implications. - Loue, Sana; Daugherty-Brownrigg, Brittany; Heaphy, Emily; Mendez, Nancy; Sajatovic, Martha (Journal of HIV/AIDS & Social Services, 2012)
African American men who have sex with men often experience rejection and discrimination. Mental illness may contribute to high HIV risk behavior. We assessed the relationship between mental illness and HIV risk among African American men who have sex with men. We assessed 125 African American men who have sex with men aged 18 years or older in Ohio for mental illness, substance use, HIV knowledge, and risk. Bivariate analyses were conducted. Any mental illness was associated with substance abuse (p = .001), child abuse (p = .032), suicide attempts (p = .028), and trading sex for money or drugs (p = .002). Bipolar disorder was associated with trading sex for money or drugs (p = .008). Mood disorders appear undertreated among African American men who have sex with men. More adequate mental health and substance abuse treatment are needed both in the prison system and the community setting to reduce HIV risk and transmission. [ABSTRACT FROM PUBLISHER]
Keywords: HIV infection risk factors; Adult child abuse victims; Men's health; Mental illness; Prostitution; Risk-taking behavior; Substance abuse; Suicidal ideation; Sexual partners; Black people; Correlation (Statistics); Interviewing; Research funding; Risk assessment; Statistics; Comorbidity; Cross-sectional method; Health literacy; Ohio

Expert Testimony of the Battered Person Syndrome, Defendant Gender, and Sexual Orientation in a Case of Duress: Evaluating Legal Decisions. - Russell, Brenda; Ragatz, Laurie; Kraus, Shane (Journal of Family Violence, 2012)
The current study examined the utility of expert testimony of the battered person syndrome (BPS) in a case of duress and the extent to which defendant gender, defendant sexual orientation, and participant gender influence mock jury decisions in a case of duress. Participants ( N = 413) read a scenario based on U.S. v. Dixon () and answered questions assessing verdict, guilt, sentence length, duress legal elements, and attributes typically ascribed to victims of abuse. Results showed heterosexual female defendants were assigned the lowest sentences and met more of the legal elements of duress (i.e., were coerced, more likely to be believed, and purchased a gun to prevent harm) and attributes (i.e., experienced severe abuse, learned helplessness) compared to other defendants. When mock jurors received expert testimony, they provided lower rates of guilt and sentencing for defendants. Results also showed the inclusion of BPS expert testimony increased ratings for many of the legal elements of duress and attributes typically associated with intimate partner violence. In addition, results suggested that while heterosexual female defendants are more likely to be believed in a case of duress, expert testimony of BPS is helpful to all defendants. Limitations and future directions for research and practice are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Crime; Gay men; Heterosexuals; Internet; Lesbians; Psychology; Human sexuality; Intimate partner violence -- Law & legislation; Control (Psychology); Analysis of variance; Chi-squared test; Correlation (Statistics); Courts; Decision making; Firearms; Guilt (Psychology); Helplessness (Psychology); Jury; Multivariate analysis; Punishment; Self-defense; Sex distribution; Surveys; Victims; Witnesses; Theory; Legal status of abused women; Psychosocial factors; Abused men -- Legal status, laws, etc.; Battered person syndrome; Duress; Expert testimony; Gender; Guilt; Sexual orientation; Verdict

Broom Closet or Fish Bowl? An Ethnographic Exploration of a University Queer Center and Oneself. - Teman, Eric D.; Lahman, Maria K. E. (Qualitative Inquiry, 2012)
The authors detail an educational ethnography of a university queer cultural center’s role on campus and in the surrounding community. The data include participant observation, in-depth interviews, and artifacts. The authors review lesbian, gay, bisexual, transgender, ally, and questioning (LGBTAQ) issues in higher education, heterosexual attitudes, and queer theory. The findings of barriers to the Center’s mission plus the suicide of a Center student prompted the authors to explore research poetry as a means to express the inexpressible. Furthermore, they illustrate tensions between contemporary queer and gay theories through the telling of a straight tale (traditional research report) and a gay tale (experiential research report), interrupted with queer tales (poetic interludes) and queer asides. At the heart of the tale is the transformation of the first author, a gay male, to a researcher and scholar of gay issues. This tale is therefore at all times queer, gay, and straight. [ABSTRACT FROM PUBLISHER]
Keywords: Ethnology; LGBTQ+ people; Queer theory; Higher education; Cultural centers; cultural center; ethics; ethnography; GLBT; higher education; LGBT; poetry; queer; suicide; tale; university; violence

Understanding suicide among sexual minority youth in America: An ecological systems analysis - Hong, Jun Sung; Espelage, Dorothy L.; Kral, Michael J. (Journal of Adolescence, 2011)
Abstract: This article examines major risk factors for suicide among sexual minority youth using Bronfenbrenner’s ecological systems theory. Although suicidal behavior among sexual minority youth is a major public concern in the United States, understanding of this phenomenon has been limited since the majority of empirical research studies have addressed individual level characteristics without much consideration to the larger environmental contexts. This review integrates past and current empirical findings on suicidal behaviors of sexual minority youth within the context of micro-, meso-, exo-, macro-, and chrono-systems levels. Finally, it draws implications for assessment, prevention, and intervention strategies. [Copyright &y& Elsevier]
Keywords: Sexual minority youth; Social psychology; Risk factors in suicidal behavior; Ecological systems theory; Empirical research; Social context; Youth psychology; United States; Sexual minority; Sexuality; Suicide; Youth

Long-Term Follow-Up of Transsexual Persons Undergoing Sex Reassignment Surgery: Cohort Study in Sweden. - Dhejne, Cecilia; Lichtenstein, Paul; Boman, Marcus; Johansson, Anna L. V.; Långström, Niklas; Landén, Mikael (PLoS ONE, 2011)
Context: The treatment for transsexualism is sex reassignment, including hormonal treatment and surgery aimed at making the person's body as congruent with the opposite sex as possible. There is a dearth of long term, follow-up studies after sex reassignment. Objective: To estimate mortality, morbidity, and criminal rate after surgical sex reassignment of transsexual persons. Design: A population-based matched cohort study. Setting: Sweden, 1973-2003. Participants: All 324 sex-reassigned persons (191 male-to-females, 133 female-to-males) in Sweden, 1973-2003. Random population controls (10:1) were matched by birth year and birth sex or reassigned (final) sex, respectively. Main Outcome Measures: Hazard ratios (HR) with 95% confidence intervals (CI) for mortality and psychiatric morbidity were obtained with Cox regression models, which were adjusted for immigrant status and psychiatric morbidity prior to sex reassignment (adjusted HR [aHR]). Results: The overall mortality for sex-reassigned persons was higher during follow-up (aHR 2.8; 95% CI 1.8-4.3) than for controls of the same birth sex, particularly death from suicide (aHR 19.1; 95% CI 5.8-62.9). Sex-reassigned persons also had an increased risk for suicide attempts (aHR 4.9; 95% CI 2.9-8.5) and psychiatric inpatient care (aHR 2.8; 95% CI 2.0-3.9). Comparisons with controls matched on reassigned sex yielded similar results. Female-to-males, but not male-to-females, had a higher risk for criminal convictions than their respective birth sex controls. Conclusions: Persons with transsexualism, after sex reassignment, have considerably higher risks for mortality, suicidal behaviour, and psychiatric morbidity than the general population. Our findings suggest that sex reassignment, although alleviating gender dysphoria, may not suffice as treatment for transsexualism, and should inspire improved psychiatric and somatic care after sex reassignment for this patient group. [ABSTRACT FROM AUTHOR]
Keywords: Sex reassignment surgery; Gender; Gender dysphoria; Transsexualism; Mortality; Confidence intervals; Hospital care; Sweden

Sexual Attraction and Trajectories of Mental Health and Substance Use During the Transition from Adolescence to Adulthood. - Needham, Belinda (Journal of Youth & Adolescence, 2012)
Previous research suggests that sexual minority youth have poorer health-related outcomes than their heterosexual peers. The purpose of this study is to determine whether sexual orientation disparities in mental health and substance use increase, decrease, or remain the same during the transition from adolescence to adulthood. Data are from Waves 1-4 of the National Longitudinal Study of Adolescent Health ( n = 8,322; 55% female). Respondents were in grades 7-12 at Wave 1 and aged 24-32 at Wave 4. Latent growth curve modeling is used to compare the mental health and substance use trajectories of youth who consistently report heterosexual attraction versus those who consistently report lesbian, gay, or bisexual (LGB) attraction, those who report a transition to LGB attraction, and those who report a transition to heterosexual attraction. Among women and men, sexual orientation disparities in depressive symptoms and suicidal thoughts persist, but do not increase, during the transition from adolescence to adulthood. The same pattern is observed for disparities in smoking, heavy drinking, and marijuana use among women. Among men, disparities in substance use are only observed between those who report consistent heterosexual attraction and those who transition to heterosexual attraction. Disparities between these groups persist over time for heavy drinking and marijuana use but decrease over time for smoking. While this study finds evidence of numerous disparities in mental health and substance use outcomes during adolescence and young adulthood, particularly among young women, there is no indication that these disparities get larger over time. [ABSTRACT FROM AUTHOR]
Keywords: Alcoholism; Bisexuality; Heterosexuality; Homosexuality; Human sexuality; Substance abuse; Adolescence; Competency assessment (Law); Chi-squared test; Interviewing; Probability theory; Psychological tests; Research funding; Smoking; Sound recordings; Descriptive statistics; Mental health; Sexual orientation; Substance use; Transition to adulthood

Racial and Sexual Identity-Related Maltreatment Among Minority YMSM: Prevalence, Perceptions, and the Association with Emotional Distress. - Hightow-Weidman, Lisa B.; Phillips, Gregory; Jones, Karen C.; Outlaw, Angulique Y.; Fields, Sheldon D.; Smith, for The YMSM of Color SPNS Initiative Study Group, Justin C. (AIDS Patient Care & STDs, 2011)
Bullying is a form of violence characterized as an aggressive behavior that is unprovoked and intended to cause harm. Prior studies have found that lesbian, gay, bisexual, and transgender (LGBT) youth experience high levels of bullying related to their sexuality and this harassment can lead to engagement in risk behaviors, depression, and suicide. Ethnic/racial minority young men who have sex with men (YMSM) may experience dual levels of stigma and maltreatment due to both their sexuality and their race. The aim of the current study was to assess the prevalence and perceptions of racial and sexual identity-based abuse among a sample of minority YMSM, and whether this maltreatment plays a role in the emotional distress of these youth. We found that overall 36% and 85% of participants experienced racial and sexuality-related bullying, respectively. There was a significant association between experiencing a high level of sexuality-related bullying and depressive symptomatology ( p=0.03), having attempted suicide ( p=0.03), and reporting parental abuse ( p=0.05). We found no association between racial bullying and suicide attempts. In a multivariable logistic regression model, experiencing any racial bullying and high sexuality-related bullying were significant predictors of having a CES-D score ≥16; adjusted odds ratio (OR) 1.83 and 2.29, respectively. These findings contribute to the existing literature regarding the negative experiences and daily stressors facing LGBT youth with regard to both their minority status and LGBT identities. Future interventions for racial/ethnic minority YMSM should provide assistance to achieve a positive view of self that encompasses both their racial and sexual identities. [ABSTRACT FROM AUTHOR]
Keywords: Attitude (Psychology); Bullying; PSYCHOLOGY; HIV-positive persons; Racism; Social stigma; Psychological stress; Suicidal behavior; Social support; Patients; Analysis of variance; Chi-squared test; Child abuse; Confidence intervals; Mental depression; Epidemiology; Gay men; Interviewing; Longitudinal method; Race; Research funding; Statistics; Logistic regression analysis; Data analysis; Multiple regression analysis

Differences in Motivations of Cutting Behavior Among Sexual Minority Youth. - Nickels, Sarah; Walls, N.; Laser, Julie; Wisneski, Hope (Child & Adolescent Social Work Journal, 2012)
This aim of this study is to examine predictors of specific motivations for engaging in cutting behavior among a community sample of sexual minority youth. The study involved secondary analysis of data collected by a community-based organization serving lesbian, gay, bisexual, and transgender (LGBT) youth and their allies. Descriptive and logistic regression analyses were conducted using a final sample of 131 sexual minority youth ages 13-24. Analyses indicate that cutting occurs at high rates among sexual minority youth and that certain demographic characteristics, psychosocial variables, and mental health issues significantly predict endorsement of particular motivations for cutting among youth in this sample. Implications for social work assessment and intervention with sexual minority youth are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Motivation (Psychology); Self-mutilation; LGBTQ+ people; Logistic regression analysis; Descriptive statistics; Colorado; Bisexual; Cutting; Gay; Lesbian; Non-suicidal self-injury; Sexual minority; Transgender; Youth

High levels of psychological distress in MSM are independent of HIV status. - Gibbie, Tania M.; Mijch, Anne; Hay, Margaret (Journal of Health Psychology, 2012)
This study assessed psychological distress (PD) in men who have sex with men (MSM) accessing primary health clinics in Australia. Relationships between PD, HIV status and substance use were explored. A cross-sectional convenience sample of 250 MSM completed the Personality Assessment Screener (PAS). One-third (n = 83) scored in the PAS clinically significant range, suggesting significant mental health symptoms. Negative Affect (27 per cent clinically significant), Suicidal Thinking (29 per cent clinically significant) and Amphetamine use significantly positively correlated with PD. There were no significant differences between HIV diagnostic groups on PD. A third of MSM displayed PD. Psychological screening may provide valuable information for improving the psychological well-being of MSM, regardless of their HIV status. [ABSTRACT FROM PUBLISHER]
Keywords: PSYCHOLOGY; HIV infections; Psychological stress; Correlation (Statistics); Demography; Gay men; Classification of mental disorders; Personality assessment; Primary health care; Questionnaires; Statistical sampling; Socioeconomic factors; Cross-sectional method; Descriptive statistics; Victoria; HIV/AIDS; men who have sex with men; psychological distress

Youth on the Virtual Edge: Researching Marginalized Sexualities and Genders Online. - McDermott, Elizabeth; Roen, Katrina (Qualitative Health Research, 2012)
Research shows clear links between lesbian, gay, bisexual, and transgender (LGBT) youth and deliberate self-harm (DSH), but there is a lack of research investigating the social context of young LGBT people’s lives and helping to explain the higher DSH risk. In this article, we report on a small-scale methodological study intended to test the feasibility of online qualitative interviews for investigating young people, sexual and gender identity, and emotional distress. There are many methodological dilemmas arising from researching such sensitive issues with marginalized groups. The study reported here was designed to examine (a) sampling diversity in terms of sexuality, gender identities, and class; and (b) the type of data produced. We found that a virtual methodology was effective in recruiting young LGBT participants who might otherwise not take part in research. Online interviewing successfully produced in-depth, “immediate” data that potentially gave access to insights that might not emerge through face-to face interviews. [ABSTRACT FROM PUBLISHER]
Keywords: Attitude (Psychology); Group identity; Internet; Self-mutilation; LGBTQ+ people; Self-injurious behavior -- Risk factors; Interviewing; Research funding; Statistical sampling; Surveys; Qualitative research; Pilot projects; Cultural awareness; adolescents / youth, at-risk; bisexuals; gays and lesbians; gender; interviews, electronic; minorities; research, access to participants; research, online; research, qualitative; self-harm; sensitive topics; sexuality / sexual health; social identity; suicide; transsexuals; vulnerable populations; young adults

The Case for the World Health Organization's Commission on the Social Determinants of Health to Address Sexual Orientation. - Logie, Carmen (American Journal of Public Health, 2012)
The World Health Organization's (WHO's) social determinants of health discussion underscores the need for health equity and social justice. Yet sexual orientation was not addressed within the WHO Commission on the Social Determinants of Health final report Closing the Gap in a Generation. This omission of sexual orientation as a social determinant of health stands in stark contrast with a body of evidence that demonstrates that sexual minorities are disproportionately affected by health problems associated with stigma and discrimination, such as mental health disorders. I propose strategies to integrate sexual orientation into the WHO's social determinants of health dialogue. Recognizing sexual orientation as a social determinant of health is an important first step toward health equity for sexual minorities. [ABSTRACT FROM AUTHOR]
Keywords: Discrimination; Minorities; Social stigma; LGBTQ+ people; Mental illness risk factors; Suicide risk factors; Conceptual structures; Health disparities; World Health Organization

Health Care Utilization and Health Indicators Among a National Sample of U.S. Veterans in Same-Sex Partnerships. - Blosnich, John; Bossarte, Robert; Silver, Eric; Silenzio, Vincent (Military Medicine, 2013)
Objectives: To examine health indicators of same-sex partnered veterans as compared with their opposite-sex partnered veteran and nonveteran peers. Methods: Same-sex partner status was derived by self-reported same-sex partnerships in data from the 2004 Behavioral Risk Factor Surveillance System. Outcome variables included health risk disparities associated with sexual minority status (e.g., frequent mental distress) and veteran status (e.g., firearm ownership). Stratified multiple logistic regression models were used to examine the association of same-sex partnered veteran status with health indicators. Results: Same-sex partnered veterans had higher odds of being over-weight and keeping firearms in the house compared with same-sex partnered nonveterans. Same-sex partnered veterans were less likely than opposite-sex partnered veterans to be overweight, and they were more than twice as likely to be current smokers when compared with opposite-sex partnered nonveterans. Conclusions: Findings suggest both that some health disparities patterns identified by same-sex partnership status among the general population also exist among veteran populations, and that some unique distinctions may exist, particularly related to BMI and firearm ownership. Collection of information about sexual minority status within Department of Veterans Affairs data sources is needed to more accurately assess the health of this minority population. [ABSTRACT FROM AUTHOR]
Keywords: Gay couples; Obesity; Health status indicators; Veterans; Cigarette smokers

A study of changes in bone metabolism in cases of gender identity disorder. - Miyajima, Tsuyoshi; Kim, Yoon; Oda, Hiromi (Journal of Bone & Mineral Metabolism, 2012)
The aim of this study was to determine the effect of increasing estrogen and decreasing androgen in males and increasing androgen and decreasing estrogen in females on bone metabolism in patients with gender identity disorder (GID). We measured and examined bone mineral density (BMD) and bone metabolism markers retrospectively in GID patients who were treated in our hospital. In addition, we studied the effects of treatment on those who had osteoporosis. Patients who underwent a change from male to female (MtF) showed inhibition of bone resorption and increased L2-4 BMD whereas those who underwent a change from female to male (FtM) had increased bone resorption and decreased L2-4 BMD. Six months after administration of risedronate to FtM patients with osteoporosis, L2-4 BMD increased and bone resorption markers decreased. These results indicate that estrogen is an important element with regard to bone metabolism in males. [ABSTRACT FROM AUTHOR]
Keywords: Gender dysphoria; Sexual dysfunction; Sex hormones; Transgender people; Bone metabolism; Bone metabolism marker; Bone mineral density; Gender identity disorder; Sex hormone; Transgender

Young, Gay, and Suicidal: Dynamic Nominalism and the Process of Defining a Social Problem with Statistics. - Waidzunas, Tom (Science, Technology & Human Values, 2012)
Since 1989, widely circulating statistics on gay teen suicide in the United States have acted as catalysts for institutional reforms, scientific research, and the creation of an identity category “gay youth.” While one figure has been replicated scientifically, these numbers originated not from a scientific research study but as risk estimates developed by a social worker and published in a government document. Many people within the public took up these original numbers, attributing their author the status of scientific researcher. In effect, the numbers became “black boxed,” often traveling without citation. Drawing on Ian Hacking’s “dynamic nominalist” perspective, this article utilizes interviews with the author of these statistics and other key claimants, along with textual analysis, to trace the origins, uptake, and effects of these figures. While making vital policy contributions, the numbers have led to some ironic consequences including the fostering of gay youth identification with suicide as a potential correlate of their identity and the potential antigay redeployment of decontextualized numbers. They have also led to a reaction in the form of “resilience” narratives. [ABSTRACT FROM PUBLISHER]
Keywords: Social problems; Suicidal behavior of LGBTQ teenagers; Gay youth; Nominalism; Social workers; Content analysis; United States; epistemology; gay youth; historical ontology; looping effects; statistics

Falling through the cracks: the gap between evidence and policy in responding to depression in gay, lesbian and other homosexually active people in Australia. - Carman, Marina; Corboz, Julienne; Dowsett, Gary W. (Australian & New Zealand Journal of Public Health, 2012)
Objective: To examine the evidence for a national policy response to depression among gay, lesbian and other homosexually active people in Australia. Methods: A literature review using database searches on depression among non-heterosexual people then a web-based search of national policy investigating how mental health needs in this population are addressed in Australia. Results: The literature review found that non-heterosexual people experience depression at higher rates, but the literature on interventions was sparse. The policy analysis found no mention of depression or the broader mental health needs of non-heterosexual people in key national mental health policy documents. These documents outline a policy approach for population groups with a higher prevalence of mental health problems, and stigma and discrimination are relevant associated factors, but only the National Suicide Strategy considers non-heterosexual people an 'at-risk group'. Conclusions: The results suggest that the evidence on higher rates of depression in non-heterosexual people is strong, but that this is not recognised in current national policy. Implications: Defining non-heterosexual people as an 'at-risk' group is appropriate, as is prioritising access to mental health services that are socially and culturally appropriate. Addressing homophobia as an associated factor would require a strategic policy approach across a range of sectors. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Prevention of mental depression; Therapeutics; Medical policy; Mental depression; Systematic reviews (Medical research); Australia; bisexuality; evidence‐based practice; homosexuality; mental health; policy

Erratum to: A Comparative Analysis of a Community and General Sample of Lesbian, Gay, and Bisexual Individuals. - Kuyper, Lisette; Fernee, Henk; Keuzenkamp, Saskia (Archives of Sexual Behavior, 2016)
A correction to the article "A Comparative Analysis of a Community and General Sample of Lesbian, Gay and Bisexual Individuals" that was published in the previous issue is presented.
Keywords: Mental health of LGBTQ people; Suicidal ideation; Distress (Psychology)

Social Support, Exposure to Violence and Transphobia, and Correlates of Depression Among Male-to-Female Transgender Women With a History of Sex Work. - Nemoto, Tooru; Bödeker, Birte; Iwamoto, Mariko (American Journal of Public Health, 2011)
Objectives. We determined racial/ethnic differences in social support and exposure to violence and transphobia, and explored correlates of depression among male-to-female transgender women with a history of sex work (THSW). Methods. A total of 573 THSW who worked or resided in San Francisco or Oakland, California, were recruited through street outreach and referrals and completed individual interviews using a structured questionnaire. Results. More than half of Latina and White participants were depressed on the basis of Center For Epidemiologic Studies Depression Scale scores. About three quarters of White participants reported ever having suicidal ideation, of whom 64% reported suicide attempts. Half of the participants reported being physically assaulted, and 38% reported being raped or sexually assaulted before age 18 years. White and African American participants reported transphobia experiences more frequently than did others. Social support, transphobia, suicidal ideation, and levels of income and education were significantly and independently correlated with depression. Conclusions. For THSW, psychological vulnerability must be addressed in counseling, support groups, and health promotion programs specifically tailored to race/ethnicity. [ABSTRACT FROM AUTHOR]
Keywords: Violence -- History; Attitude (Psychology); Ethnic groups; Income; Prostitution; Rape; Human sexuality; Suicidal behavior; Transgender people; Social support; Suicidal ideation; Analysis of variance; Assault & battery; Birthplaces; Black people; Chi-squared test; Correlation (Statistics); Mental depression; Hispanic Americans; Interviewing; Race; Research funding; White people; Multiple regression analysis; Educational attainment; California

STATE CHILD EMOTIONAL ABUSE LAWS: THEIR FAILURE TO PROTECT CHILDREN WITH GENDER IDENTITY DISORDER. - Ford, Andrew (Family Court Review, 2011)
Emotional abuse of children with Gender Identity Disorder by parents is very difficult to identify and prevent. State investigators of abuse and neglect often have a hard time determining if the reasons for mental illness and psychological harm in children are due to the actions of their parents, or if they stem from other sources. Once identified, it becomes even harder to prove in court for purposes of ordering services or removing the child from the home if the abuse is severe enough. With children who are gender non‐conforming, this task becomes exponentially more difficult due to the low prevalence rate, discrimination, stereotypes, and a parent's right to bring up their child as they choose. These youth face discrimination and violence in school, work, their communities, and also within their own families. Emotional abuse statutes are too vague to protect youth who are gender non‐conforming. The vague and unclear laws lead to inconsistency in the application of the law and lack of protection of the children because judges and investigators are not aware of how parent's actions harms youth with gender identity disorder. Therefore, states should adopt the model statute within this Note which defines specific actions by parents which would not qualify as abuse when involving gender conforming youth but qualifies as abuse for children with gender identity disorder. Many states already have statutes which define physical abuse, sexual abuse and abandonment by specific actions by parents towards their children. This proposal will enable both the state and the judges to properly identify victims with gender identity disorder of emotional abuse and provide for their protection. [ABSTRACT FROM AUTHOR]
Keywords: Gender dysphoria in children; Suicide; Psychological child abuse; Legal status of children -- United States; Child abuse -- United States; Prevention; United States; abuse; child abuse; emotional abuse; gender; gender identity disorder; neglect; youth

Sexual Minority-Related Victimization as a Mediator of Mental Health Disparities in Sexual Minority Youth: A Longitudinal Analysis. - Burton, Chad; Marshal, Michael; Chisolm, Deena; Sucato, Gina; Friedman, Mark (Journal of Youth & Adolescence, 2013)
Sexual minority youth (youth who are attracted to the same sex or endorse a gay/lesbian/bisexual identity) report significantly higher rates of depression and suicidality than heterosexual youth. The minority stress hypothesis contends that the stigma and discrimination experienced by sexual minority youth create a hostile social environment that can lead to chronic stress and mental health problems. The present study used longitudinal mediation models to directly test sexual minority-specific victimization as a potential explanatory mechanism of the mental health disparities of sexual minority youth. One hundred ninety-seven adolescents (14-19 years old; 70 % female; 29 % sexual minority) completed measures of sexual minority-specific victimization, depressive symptoms, and suicidality at two time points 6 months apart. Compared to heterosexual youth, sexual minority youth reported higher levels of sexual minority-specific victimization, depressive symptoms, and suicidality. Sexual minority-specific victimization significantly mediated the effect of sexual minority status on depressive symptoms and suicidality. The results support the minority stress hypothesis that targeted harassment and victimization are partly responsible for the higher levels of depressive symptoms and suicidality found in sexual minority youth. This research lends support to public policy initiatives that reduce bullying and hate crimes because reducing victimization can have a significant impact on the health and well-being of sexual minority youth. [ABSTRACT FROM AUTHOR]
Keywords: Bullying; Psychology of LGBTQ+ people; Adolescence; Competency assessment (Law); Confidence intervals; Longitudinal method; Probability theory; Psychological tests; Questionnaires; Research funding; Scales (Weighing instruments); Self-evaluation; Descriptive statistics; Ohio; Pennsylvania; Depression; Minority stress; Sexual minority youth; Suicidality; Victimization

Suicidal Ideation and Attempt Among Adolescents Reporting "Unsure" Sexual Identity or Heterosexual Identity Plus Same-Sex Attraction or Behavior: Forgotten Groups? - Yue Zhao; Montoro, Richard; Igartua, Karine; Thombs, Brett D. (Journal of the American Academy of Child & Adolescent Psychiatry, 2010)
The article presents a study which compared risk of suicide ideation and attempts among adolescents with unsure identity; heterosexual identity with same sex attraction; and gay, lesbian, or bisexual (GLB) identity in Montreal, Quebec. Results showed that those with GLB and unsure identities are at greater risk of committing suicide than heterosexual youth without the same attraction to the opposite sex. Participants of the study were teenage students from public and private high schools.
Keywords: Suicidal ideation; Gender identity; Bisexual identity; Gender dysphoria in adolescence; Risk factors in suicidal behavior; Teenage suicide; Montréal (Québec); Québec (Province); Adolescence; Sexual identity; Suicidality

Parental Acceptance and Illegal Drug Use among Gay, Lesbian, and Bisexual Adolescents: Results from a National Survey. - Padilla, Yolanda C.; Crisp, Catherine; Rew, Donna Lynn (Social Work, 2010)
Although gay, lesbian, and bisexual (GLB) adolescents face many of the same developmental challenges as do heterosexual adolescents, they must also deal with the stress of being part of a stigmatized group. The purpose of this study was to examine the extent to which family support and involvement with the queer community may buffer the effects of life stress on substance use among GLB youths. Drawing on a large national online survey, the authors examined drug use in 1,906 GLB youths 12 to 17 years of age. Overall, 20 percent of the youths reported using illegal substances in the past 30 days. Results from multivariate analyses revealed that stress, as measured by suicidal ideation, significantly increased the risk of drug use. A positive reaction from the mother to the youth's coming out served as a significant protective factor, whereas involvement in a queer youth group had no effect. The authors found evidence that, for GLB adolescents, parental acceptance of sexual identity is an important aspect of a strong family relationship and, thus, has important ramifications for their healthy development. Implications of the findings for social work practice are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Parents of LGBTQ people; Drug addiction; LGBTQ+ communities; Families; Social stigma; Coming out (Sexual orientation); adolescent; family support; gay; illegal drug use; lesbian

Age of MSM Sexual Debut and Risk Factors: Results from a Multisite Study of Racial/Ethnic Minority YMSM Living with HIV. - Outlaw, Angulique Y.; Phillips, Gregory; Hightow-Weidman, Lisa B.; Fields, Sheldon D.; Hidalgo, Julia; Halpern-Felsher, Bonnie; Green-Jones, and The Young MSM of Color SPNS Initiative Study Group, Monique (AIDS Patient Care & STDs, 2011)
The average reported age of sexual debut for youth in the United States is 14.4 years, with approximately 7% reporting their sexual debut prior to age 13. While the research literature on sexual debut for youth addresses gender and ethnic differences (with males and African-American youth experiencing earlier sexual debut), there is limited data regarding factors associated with sexual debut for young men who have sex with men (YMSM). Early sexual debut poses potential health risks, such as contracting HIV with an increased risk of unprotected intercourse. Given current high HIV infection rates for racial/ethnic minority YMSM, learning more about their sexual debuts and associated risk factors of this population is of great importance. This study investigated risk behaviors and emotional distress, and their association with MSM sexual debut for a multisite cohort of racial/ethnic minority YMSM living with HIV. We hypothesized that a MSM sexual debut younger than age 16 would be associated with engagement in more high-risk sexual behaviors (unprotected sex and exchange sex), substance use, and emotional distress than a MSM sexual debut at age 16 or older. Results indicated that participants having a MSM sexual debut before the age of 16 reported more exchange sex; drug use (specifically marijuana); emotional/psychological problems related to substance use; and a history of suicide attempts, compared to participants with later MSM sexual debuts. Comprehensive interventions that are racially/ethnically sensitive, inquire about initial sexual experiences, and focus on sexual health and healthy relationships are needed to improve health outcomes for this population. [ABSTRACT FROM AUTHOR]
Keywords: HIV infection risk factors; Bisexuals; Child sexual abuse; Gay men; HIV-positive persons; Minorities; Risk-taking behavior; Human sexuality; Unsafe sex; Age distribution; Analysis of variance; Black people; Chi-squared test; Hispanic Americans; Interviewing; Longitudinal method; Race; Research funding; Statistical sampling; United States

Suicide Attempts among Norwegian Gay, Lesbian and Bisexual Youths. - Hegna, Kristinn; Wichstrøm, Lars (Acta Sociologica (Sage Publications, Ltd.), 2007)
The aim of the study was to identify the specific factors that affect the risk of attempted suicide in Norwegian gay, lesbian and bisexual (GLB) youths beyond the effect of general risk factors presumed to be of importance irrespective of sexual orientation, The national non-probability sample included 407 GLB youths aged between 16 and 25 years of age, among whom 26 per cent of both genders reported a previous suicide attempt. General risk factors for attempted suicide among GLB youths were: lack of parental contact, internalizing problems (depression/anxiety), low self-esteem, regular smoking and victimization, The following risk factors specific for GLB youths increased the risk of attempted suicide even when controlling for general risk factors: currently being in a steady heterosexual relationship, early heterosexual debut (<16), young age of coming out (<15), infrequent contact with heterosexual friends and openness to all heterosexual friends. For practitioners engaged in social work among young people in general or GLB youths in particular, these results show that while coming out is a vital aspect of sexual identity formation that enhances psychological well-being and should be celebrated, in another sense it is a serious stressor with potentially negative consequences unless a strong social support network is there to be relied upon. [ABSTRACT FROM AUTHOR]
Keywords: NORWAY; adolescence; identity; risk factors; sexual orientation; suicidal behaviour; young adults

Group Differences in Risk Across Three Domains Using an Expanded Measure of Sexual Orientation. - Loosier, Penny S.; Dittus, Patricia J. (Journal of Primary Prevention, 2010)
The purpose of this study was to highlight associations between sexual orientation and risk outcomes in late adolescence and early adulthood using an expanded measure of sexual orientation. Recent data indicate higher levels of risk behavior in a newly identified population, mostly heterosexuals, as compared to heterosexuals. Comparisons among groups using an expanded measure of sexual orientation such as this, however, often do not include all possible groups or may restrict comparisons between groups. Data were derived from the National Longitudinal Study of Adolescent Health (Add Health); participants identified as heterosexual, mostly heterosexual, bisexual, mostly gay, or gay. Main risk outcomes were parental mistreatment, home displacement, thoughts of suicide, depressive symptoms, frequency of drinking, and delinquency. A priori planned comparisons examined differences between: (a) heterosexual vs. mostly heterosexual, (b) gay vs. mostly gay, (c) mostly heterosexual vs. bisexual, (d) mostly gay vs. bisexual, (e) mostly heterosexual vs. mostly gay, (f) heterosexual vs. gay, (g) heterosexual vs. bisexual, and (h) gay vs. bisexual. Mostly heterosexual youth were at significantly greater risk than heterosexual youth on all outcomes but did not differ from bisexual or mostly gay youth. Heterosexuals were at lower risk as compared to mostly heterosexuals and bisexuals. This study provides further evidence of differential risk associations for sexual minorities. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Sexual minority youth; Adolescence; Heterosexuals; Bisexuals; Gay people; Alcoholism risk factors; Suicide risk factors; Depression in adolescence; Mental illness risk factors; Bisexual; Externalizing behaviors; Heterosexual; Homosexual; Internalizing behaviors; Sexual minority

Substance Use and Mental Health Disparities among Sexual Minority Girls: Results from the Pittsburgh Girls Study - Marshal, Michael P.; Sucato, Gina; Stepp, Stephanie D.; Hipwell, Alison; Smith, Helen A.; Friedman, Mark S.; Chung, Tammy; Markovic, Nina (Journal of Pediatric & Adolescent Gynecology, 2012)
Abstract: Purpose: To examine substance use and mental health disparities between sexual minority girls and heterosexual girls. Methods: Data from the Pittsburgh Girls Study were analyzed. All girls were 17 years old. Girls were included if they were not missing self-reported sexual orientation and mental health data (N = 527). Thirty-one girls (6%) endorsed same-sex romantic orientation/identity or current same-sex attraction. Bivariate analyses were conducted to test group differences in the prevalence of substance use and suicidal behavior, and group differences in depression, anxiety, borderline personality disorder (BPD), oppositional defiant disorder (ODD), and conduct disorder (CD) symptoms. Results: Compared with heterosexual girls, sexual minority girls reported higher past-year rates of cigarette, alcohol, and heavy alcohol use, higher rates of suicidal ideation and self-harm, and higher average depression, anxiety, BPD, ODD, and CD symptoms. Conclusions: Sexual minority girls are an underrepresented group in the health disparities literature, and compared with heterosexual girls, they are at higher risk for mental health problems, most likely because of minority stress experiences such as discrimination and victimization. The disparities found in this report highlight the importance of discussing sexual orientation as part of a comprehensive preventive care visit. [Copyright &y& Elsevier]
Keywords: Mental health; Substance abuse; Sexual minority women; Heterosexual women; Health disparities; Pittsburgh (Pa.); Pennsylvania; Adolescent mental health disparities; Adolescent substance use; LGBT health; Sexual minority girls

Suicidality among Gay, Lesbian and Bisexual Youth: The Role of Protective Factors. - Eisenberg, Marla E.; Resnick, Michael D. (Journal of Adolescent Health, 2006)
Abstract: Purpose: Many reports have indicated that gay, lesbian and bisexual (GLB) youth are particularly vulnerable to poor outcomes, including suicide. Certain protective factors are likely to reduce this risk. The present study examines four protective factors (family connectedness, teacher caring, other adult caring, and school safety) and their association with suicidal ideation and attempts among adolescents with same-gender experience. Methods: Data come from the 2004 Minnesota Student Survey of 9th and 12th grade students; 21,927 sexually active youth were grouped according to the gender of their sex partner(s) into GLB and non-GLB groups. Four protective factors and suicidal ideation and attempts were compared across groups. Logistic regression was used to examine the influence of protective factors on suicide, and predicted probabilities of suicidal ideation and attempts were estimated using general linear modeling. Results: There were 2,255 respondents who reported same-gender experience. Over half of GLB students had thought about suicide and 37.4% reported a suicide attempt. GLB youth reported significantly lower levels of each protective factor than their non-GLB peers. Family connectedness, adult caring, and school safety were significantly protective against suicidal ideation and attempts. Risk associated with a GLB sexual orientation is largely mediated through protective factors. Conclusions: Sexual orientation alone accounts for only a small portion of variability in suicidal ideation and attempts. If protective factors were enhanced among GLB youth, suicide in this population is expected to be considerably lower. Protective factors examined here are amenable to change and should be targeted in interventions. [Copyright 2006 Elsevier]

Lesbian, gay, bisexual and transgender young people's experiences of distress: resilience, ambivalence and self-destructive behaviour. - Scourfield, Jonathan; Roen, Katrina; McDermott, Liz (Health & Social Care in the Community, 2008)
The research presented in this paper set out to explore the cultural context of youth suicide and more specifically any connections between sexual identity and self-destructive behaviour, in the light of international evidence about the disproportionate risk of suicidal thoughts and suicide attempts in lesbian, gay, bisexual and transgender (LGBT) young people. The empirical basis for the paper is qualitative research that was carried out in the North West of England and South Wales. Focus groups and interviews were conducted with a total of 69 young people, with a purposive sample to reflect diversity of sexual identity, social class and regional and rural-urban location. The paper presents a thematic analysis of the data specifically relating to the experiences of LGBT young people. A range of strategies that LGBT young people employ in the face of distress are described. These are categorised as resilience, ambivalence and self-destructive behaviour (including self-harm and suicide). The potential implications for health and social care of these strategies include the need for ecological approaches and for sexual cultural competence in practitioners, as well as prioritisation of LGBT risk within suicide prevention policies. [ABSTRACT FROM AUTHOR]
Keywords: Suicide prevention; LGBTQ+ youth; Self-destructive behavior; Suicidal behavior; Social conflict; Quality of life; Resilience (Personality trait); Ambivalence; Self-control; Europe; qualitative research; sexuality; suicide and self‐destructive behaviour; suicide and self-destructive behaviour; young people

Suicidal acts and ideation in homosexual and bisexual young people: a study of prevalence and risk factors. - van Heeringen, C.; Vincke, J. (Social Psychiatry & Psychiatric Epidemiology, 2000)
Background: Suicide attempts are the most robust clinical predictor of suicide, which is now the second cause of death among young people in many countries. Previous research has shown an increased risk of attempted suicide associated with a homosexual orientation. However, the mechanisms underlying this increased risk are not yet clear. This study therefore aimed to determine the risk of attempted suicide and the effect of potential risk factors on the occurrence of suicidal ideation and behaviour among homosexual youngsters.Methods: The association between suicidal ideation and behaviour and potential risk factors was assessed by means of a questionnaire in a general population sample of homosexual or bisexual young people and a control sample consisting of school pupils.Results: A twofold increased risk of suicidal ideation was found associated with a homosexual or bisexual orientation. A significantly increased risk of attempted suicide associated with homosexuality or bisexuality was found in females. Independent of sexual orientation, depression was identified as a significant risk factor for suicidal ideation, while suicidal behaviour was associated with low self-esteem, higher levels of hopelessness and suicidal behaviour in someone close. Among homosexual or bisexual young people, less satisfying homosexual friendships were an additional risk factor for suicidal behaviour.Conclusions: The identified increased risk of suicidal ideation among homosexual or bisexual young people is associated with depression and may lead to suicidal behaviour, independent of sexual orientation, especially in the presence of a role model of suicidal behaviour, and among those with unsatisfying friendships. [ABSTRACT FROM AUTHOR]
Keywords: Gay people; Homosexuality; Bisexuals; Suicidal behavior; Suicide risk factors

Transgender Youth and Life-Threatening Behaviors. - Grossman, Arnold H.; D'Augelli, Anthony R. (Suicide & Life-Threatening Behavior, 2007)
Sexual minority status is a key risk factor for suicide among lesbian, gay, and bisexual youth; however, it has not been studied among transgender youth. Fifty-five transgender youth reported on their life-threatening behaviors. Nearly half of the sample reported having seriously thought about taking their lives and one quarter reported suicide attempts. Factors significantly related to having made a suicide attempt included suicidal ideation related to transgender identity; experiences of past parental verbal and physical abuse; and lower body esteem, especially weight satisfaction and thoughts of how others evaluate the youths' bodies. Sexual minority status is a key risk factor for life-threatening behaviors among transgender youth. [ABSTRACT FROM AUTHOR]
Keywords: Psychological aspects; TRANSGENDER youth; SUICIDE -- Risk factors; SUICIDAL behavior; RESEARCH; TRANSGENDER people -- Identity; PSYCHIATRY -- Research; GENDER identity

Mental Health of Lesbian, Gay, Bisexual, and Heterosexual Siblings: Effects of Gender, Sexual Orientation, and Family. - Balsam, Kimberly F.; Beauchaine, Theodore P.; Mickey, Ruth M.; Rothblum, Esther D. (Journal of Abnormal Psychology, 2005)
Self-identified lesbian, gay male, and bisexual (LGB) individuals were recruited via convenience sampling, and they in turn recruited their siblings (79% heterosexual, 19% LGB). The resulting sample of 533 heterosexual, 558 lesbian or gay male, and 163 bisexual participants was compared on mental health variables and their use of mental health services. Multilevel modeling analyses revealed that sexual orientation predicted suicidal ideation, suicide attempts, self-injurious behavior, use of psychotherapy, and use of psychiatric medications over and above the effects of family adjustment. Sexual orientation was unrelated to current psychological distress, psychiatric hospitalizations, and self-esteem. This is the lst study to model family effects on the mental health of LGB participants and their siblings. [ABSTRACT FROM AUTHOR]
Keywords: bisexual; gay; lesbian; mental health; sexual orientation

Sexual Orientation and Mortality Among US Men Aged 17 to 59 Years: Results From the National Health and Nutrition Examination Survey III. - Cochran, Susan D.; Mays, Vickie M. (American Journal of Public Health, 2011)
Objectives. We investigated associations between minority sexual orientation and mortality among US men. Methods. We used data from a retrospective cohort of 5574 men aged 17 to 59 years, first interviewed in the National Health and Nutrition Examination Survey III (NHANES III; 1988-1994) and then followed for mortality status up to 18 years later. We classified men into 3 groups: those reporting (1) any same-sex sexual partners (men who have sex with men [MSM]; n=85), (2) only female sexual partners (n=5292), and (3) no sexual partners (n=197). Groups were then compared for all-cause mortality, HIV-related mortality, suicide-related mortality, and non-HIV-related mortality. Results. Compared with heterosexual men, MSM evidenced greater all-cause mortality. Approximately 13% of MSM died from HIV-related causes compared with 0.1% of men reporting only female partners. However, mortality risk from non-HIV-related causes, including suicide, was not elevated among MSM. Conclusions. In the United States, the HIV epidemic continues to be the major contributing factor for premature death rates among MSM. Cohorts such as the NHANES III offer a unique opportunity to track the effects of the HIV epidemic on this population. [ABSTRACT FROM AUTHOR]
Keywords: Gay people; Heterosexuals; HIV infections; Men; Minorities; Mortality; Human sexuality; Sexual abstinence; Highly active antiretroviral therapy; Analysis of variance; Comparative studies; Confidence intervals; Correlation (Statistics); Causes of death; Longitudinal method; Research funding; Surveys; Time; Secondary analysis; Proportional hazards models; United States

Coming out to talk about suicide: Gay men and suicidality. - McAndrew, Sue; Warne, Tony (International Journal of Mental Health Nursing, 2010)
International studies report increased rates of mental health problems and subsequent suicidality among homosexual populations. While international health-care policy is concerned with reducing suicide among young people, important research findings relating to gay people and suicidality remain unacknowledged in the Suicide Prevention Strategy for England. This qualitative study, utilizing single case studies, was used to gain an in-depth understanding of the life experiences contributing to the suicidality of four gay men. The methodology was psychoanalytically informed, using free association narrative interviewing. The initial data analysis involved interpretation of each of the case studies and a subsequent analysis exploring the shared experiences found in each of the individual narratives. Thematically, these are described as ‘knowing and not knowing’, ‘the centrality of the father–son relationship’, ‘the loneliness of outsiderness’, ‘leading a double life’, and ‘crime and punishment’. The significance of the life experiences these themes illustrate reveal why some gay men might not only experience long-term mental health problems, but also engage in suicidality. Individually and collectively, the analyses provide important insights for mental health nurses becoming more attuned to provide sensitive mental health care to those who have a gay sexual orientation. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Gay people; Mental health; Suicide prevention; Psychiatric nurses; England; bricolage; free association narrative interviewing; gay men; suicidality

Victimization and Suicidality Among Dutch Lesbian, Gay, and Bisexual Youths. - Van Bergen, Diana D.; W. Bos, Henny M.; Lisdonk, Jantine van; Keuzenkamp, Saskia; M. Sandfort, Theo G. (American Journal of Public Health, 2013)
We examined Netherlands Institute for Social Research data, collected between May and August 2009, on 274 Dutch lesbian, gay, and bisexual youths. The data showed that victimization at school was associated with suicidal ideation and actual suicide attempts. Homophobic rejection by parents was also associated with actual suicide attempts. Suicidality in this population could be reduced by supporting coping strategies of lesbian, gay, and bisexual youths who are confronted with stigmatization by peers and parents, and by schools actively promoting acceptance of same-sex sexuality. [ABSTRACT FROM AUTHOR]
Keywords: Psychological adaptation; Bullying; Suicidal behavior; LGBTQ+ people; Suicidal ideation; Parent attitudes; Suicide risk factors; Surveys; Confidence intervals; Epidemiology; Research funding; School administration; Victims; Logistic regression analysis; Data analysis; Secondary analysis; Descriptive statistics; Netherlands

Suicide Protective and Risk Factors for Sexual Minority Youth: Applying the Cumulative Factor Model. - Rutter, Philip A. (Journal of LGBT Issues in Counseling, 2008)
This report explores suicide protective and risk factors for lesbian, gay and bisexual (LGB) youth and offers a Cumulative Factor Model constructed from these factors. Numerous studies to date have concluded that a youth's sexual minority identity is a key risk factor for suicide. Few studies however have explored the internal and external protective factors that may cumulate to increase or reduce suicidal ideation and risk among this LGB population. Counseling implications for both assessment and intervention strategies are discussed in light of this cumulative factor approach to understand and potentially stem LGB youth suicide. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority youth; Social perception; Gender identity; Social work with sexual minority youth; LGBTQ+ people; Sexual minorities; Sexual orientation; Suicide risk factors; Social consciousness; bisexual; gay; lesbian; Sexual minority; suicide protective factors; suicide risk factors; youth

Role of Islam in the management of Psychiatric disorders. - Sabry, Walaa M.; Vohra, Adarsh (Indian Journal of Psychiatry, 2013)
With the significant growth of the Muslim population all over the world, there exists a corresponding increase in the need for mental health services that suit this group of patients. Research demonstrates the effectiveness of the integration of spirituality and religiosity into psychotherapy and how religious beliefs could affect the management plans. This article discusses the impact of various beliefs in the Islamic faith on the bio-psychosocial model for the management of different psychiatric disorders including focusing on the modification of psychotherapeutic techniques as cognitive restructuring. It also shows other types of therapies such as music therapy, meditation therapy, and aromatherapy. The main emphasis remains to ensure that Muslim psychiatric patients get ethical, acceptable, and effective treatment. [ABSTRACT FROM AUTHOR]
Keywords: Mental health services; Suicide prevention; Grief; Homosexuality; Islam; Mental illness; Psychotherapy; Spirituality; Family roles; Therapeutics; Mental depression; Mental illness treatment; Obsessive-compulsive disorder; Anxiety disorders treatment; Aromatherapy; Cognitive therapy; Meditation; Music therapy; Bio-psychosocial; compliance; mental health; Muslims; religious psychotherapy; spirituality

Family Acceptance in Adolescence and the Health of LGBT Young Adults. - Ryan, Caitlin; Russell, Stephen T.; Huebner, David; Diaz, Rafael; Sanchez, Jorge (Journal of Child & Adolescent Psychiatric Nursing, 2010)
ISSUE: The role of family acceptance as a protective factor for lesbian, gay, bisexual, and transgender (LGBT) adolescents and young adults has not been established. METHODS: A quantitative measure with items derived from prior qualitative work retrospectively assessed family accepting behaviors in response to LGBT adolescents' sexual orientation and gender expression and their relationship to mental health, substance abuse, and sexual risk in young adults ( N= 245). FINDINGS: Family acceptance predicts greater self-esteem, social support, and general health status; it also protects against depression, substance abuse, and suicidal ideation and behaviors. CONCLUSIONS: Family acceptance of LGBT adolescents is associated with positive young adult mental and physical health. Interventions that promote parental and caregiver acceptance of LGBT adolescents are needed to reduce health disparities. [ABSTRACT FROM AUTHOR]
Keywords: Adolescent psychology; Attitude (Psychology); Families; Gender identity; Mental health; Human sexuality; Psychology of LGBTQ+ people; Analysis of variance; Chi-squared test; Confidence intervals; Epidemiology; Health status indicators; Hispanic Americans; Nurses; Probability theory; Research funding; Sound recordings; White people; Logistic regression analysis; Data analysis; Occupational roles; Quantitative research; Socioeconomic factors; Retrospective studies; Early medical intervention; California

A Systematic Review of Parental Influences on the Health and Well-Being of Lesbian, Gay, and Bisexual Youth: Time for a New Public Health Research and Practice Agenda. - Bouris, Alida; Guilamo-Ramos, Vincent; Pickard, Angela; Shiu, Chengshi; Loosier, Penny; Dittus, Patricia; Gloppen, Kari; Michael Waldmiller, J. (Journal of Primary Prevention, 2010)
Relatively little is known about how parents influence the health and well-being of lesbian, gay, and bisexual (LGB) adolescents and young adults. This gap has led to a paucity of parent-based interventions for LGB young people. A systematic literature review on parental influences on the health of LGB youth was conducted to better understand how to develop a focused program of applied public health research. Five specific areas of health among LGB young people aged 10-24 years old were examined: (a) sexual behavior; (b) substance use; (c) violence and victimization; (d) mental health; and (e) suicide. A total of 31 quantitative articles were reviewed, the majority of which were cross-sectional and relied on convenience samples. Results indicated a trend to focus on negative, and not positive, parental influences. Other gaps included a dearth of research on sexual behavior, substance use, and violence/victimization; limited research on ethnic minority youth and on parental influences identified as important in the broader prevention science literature; and no studies reporting parent perspectives. The review highlights the need for future research on how parents can be supported to promote the health of LGB youth. Recommendations for strengthening the research base are provided. [ABSTRACT FROM AUTHOR]
Keywords: Parental influences; Homosexuality; Sex customs; Crime victims; Mental health; Adolescent psychology; Bisexuals; Gay people; Lesbians; Suicide risk factors; Substance abuse -- Risk factors; Adolescents; Bisexual; Gay; Health risk behavior; Lesbian; Same-sex attraction; Sexual behavior; Substance use; Suicide; Victimization; Violence; Young adults

Sexual Revictimization and Mental Health: A Comparison of Lesbians, Gay Men, and Heterosexual Women. - Balsam, Kimberly F.; Lehavot, Keren; Beadnell, Blair (Journal of Interpersonal Violence, 2011)
Childhood sexual abuse (CSA) has several deleterious effects on health and well-being, including increased risk for rape in adulthood. Such revictimization experiences are linked to negative mental health outcomes. The vast majority of literature on prevalence and impact of sexual revictimization has focused on heterosexual women. In an effort to extend this research to lesbians and gay men, who are known to face higher rates of both CSA and adult rape, we conducted a study (N = 871) comparing adult lesbians, gay men, and heterosexual women on prevalence and mental health correlates of sexual revictimization. Results indicated that CSA is associated with elevated rates of adult rape for all three groups. In addition, revictimization showed comparable associations with mental health variables for all three groups. Participants with both CSA and adult rape had higher levels of psychological distress, suicidality, alcohol use, and self-harm behaviors relative to those with only one type of victimization and those with no victimization, and those with any victimization were more likely to report recent use of drugs compared to those with no victimization. [ABSTRACT FROM AUTHOR]
Keywords: Alcoholism; Child sexual abuse; Gay men; Heterosexuals; Lesbians; Mental health; Rape; Sex crimes; Psychological stress; Suicidal ideation; Computer software; Distress (Psychology); Psychological tests; Self-injurious behavior; Statistics; Surveys; Data analysis; Effect sizes (Statistics); Inter-observer reliability; Cross-sectional method; gay; lesbian; revictimization; sexual abuse

Sexual Orientation, Parental Support, and Health During the Transition to Young Adulthood. - Needham, Belinda L.; Austin, Erika L. (Journal of Youth & Adolescence, 2010)
Some recent studies suggest that sexual minorities may have worse health-related outcomes during adolescence because they report lower levels of family connectedness, a key protective resource. Using data from wave 3 of the National Longitudinal Study of Adolescent Health ( n = 11,153; 50.6% female; mean age = 21.8 years), this study extends prior research on adolescents to young adults. We examine whether lesbian, gay, and bisexual (LGB) young adults report lower levels of parental support than their heterosexual peers and whether differences in parental support help explain why LGB young adults tend to have worse health-related outcomes. We find that lesbian and bisexual women report lower levels of parental support than heterosexual women and that gay men report lower levels of parental support than bisexual and heterosexual men. Compared to heterosexual women, lesbian and bisexual women have higher odds of suicidal thoughts and recent drug use; bisexual women also have higher odds of elevated depressive symptomatology and heavy drinking. Gay men have higher odds of suicidal thoughts than heterosexual men. With the exception of heavy drinking, parental support either partially or fully mediates each of the observed associations. Even though the transition from adolescence to young adulthood is characterized by increased independence from parents, parental support remains an important correlate of health-related outcomes during this stage of life. Sexual minorities report lower levels of parental support during young adulthood, which helps explain why they have worse health-related outcomes. Interventions designed to strengthen relationships between LGB young adults and their parents could lead to a reduction in health disparities related to sexual orientation. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Mental health; Sexual minorities; LGBTQ+ young adults; LGBTQ+ teenagers; Social support; Adolescent psychology; Psychology; Psychology of adults; Health behavior; Parental support

Gender role, sexual orientation and suicide risk - Fitzpatrick, Kathleen Kara; Euton, Stephanie J.; Jones, Jamie N.; Schmidt, Norman B. (Journal of Affective Disorders, 2005)
Abstract: Background: There has been interest in the relationship between homosexuality, gender role and suicide risk. Though homosexuals are more likely to identify as cross-gender, research has not simultaneously examined sexual orientation and gender role in assessing suicide risk. In the current study, the unique and interactive effects of sexual orientation and gender role were assessed in regard to suicidal ideation, related psychopathology and measures of coping. Methods: 77 participants were recruited from an undergraduate psychology subject pool (n =47) or from gay, lesbian and transgender student organizations (n =30) and assessed on measures of gender role, homosexuality, and psychopathology. Results: Consistent with expectations, cross-gender role (i.e., personality traits associated with the opposite sex) is a unique predictor of suicidal symptoms. Moreover, gender role accounted for more of the overall variance in suicidal symptoms, positive problem orientation, peer acceptance and support, than sexual orientation. After accounting for gender role, sexual orientation contributed little to the variance in suicidal symptoms, associated pathology and problem-solving deficits. There was no support for gender role by sexual orientation interaction effects. Limitations: The cross-sectional nature of the data limits statements regarding causality. Conclusions: Cross-gendered individuals, regardless of sexual orientation, appear to have higher risk for suicidal symptoms. Researchers and clinicians should assess gender role in evaluations of youth samples. [Copyright &y& Elsevier]
Keywords: Homosexuality; Gender role; Suicidal behavior; Personality; Mood; Sexual orientation; Suicide

Don't ask, don't tell? Does disclosure of gay identity affect partner performance? - Everly, Benjamin A.; Shih, Margaret J.; Ho, Geoffrey C. (Journal of Experimental Social Psychology, 2012)
Abstract: Supporters of policies that force gay and lesbian individuals to conceal their sexual orientation in the workplace argue that working with openly gay individuals undermines performance. We examine this claim in two studies and find the opposite effect. Specifically, participants working with openly gay partners performed better on a cognitive task (i.e., a math test) and a sensory-motor task (i.e., a Wii shooting game) than individuals left to wonder about the sexual orientation of their partners. These results suggest that policies, such as “Don''t Ask, Don''t Tell,” that introduce uncertainty into social interactions harm rather than protect performance. [Copyright &y& Elsevier]
Keywords: Gay identity; Lesbians; Sexual orientation; Social interaction; Disclosure; Affect (Psychology); Cognitive ability; Performance; Identity; Stigma

A Report from a Single Institute's 14-Year Experience in Treatment of Male-to-Female Transsexuals. - Imbimbo, Ciro; Verze, Paolo; Palmieri, Alessandro; Longo, Nicola; Fusco, Ferdinando; Arcaniolo, Davide; Mirone, Vincenzo (Journal of Sexual Medicine, 2009)
Introduction. Gender identity disorder or transsexualism is a complex clinical condition, and prevailing social context strongly impacts the form of its manifestations. Sex reassignment surgery (SRS) is the crucial step of a long and complex therapeutic process starting with preliminary psychiatric evaluation and culminating in definitive gender identity conversion. Aim. The aim of our study is to arrive at a clinical and psychosocial profile of male-to-female transsexuals in Italy through analysis of their personal and clinical experience and evaluation of their postsurgical satisfaction levels SRS. Methods. From January 1992 to September 2006, 163 male patients who had undergone gender-transforming surgery at our institution were requested to complete a patient satisfaction questionnaire. Main Outcome Measures. The questionnaire consisted of 38 questions covering nine main topics: general data, employment status, family status, personal relationships, social and cultural aspects, presurgical preparation, surgical procedure, and postsurgical sex life and overall satisfaction. Results. Average age was 31 years old. Seventy-two percent had a high educational level, and 63% were steadily employed. Half of the patients had contemplated suicide at some time in their lives before surgery and 4% had actually attempted suicide. Family and colleague emotional support levels were satisfactory. All patients had been adequately informed of surgical procedure beforehand. Eighty-nine percent engaged in postsurgical sexual activities. Seventy-five percent had a more satisfactory sex life after SRS, with main complications being pain during intercourse and lack of lubrication. Seventy-eight percent were satisfied with their neovagina's esthetic appearance, whereas only 56% were satisfied with depth. Almost all of the patients were satisfied with their new sexual status and expressed no regrets. Conclusions. Our patients' high level of satisfaction was due to a combination of a well-conducted preoperative preparation program, competent surgical skills, and consistent postoperative follow-up. Imbimbo C, Verze P, Palmieri A, Longo N, Fusco F, Arcaniolo D, and Mirone V. A Report from a single institute's fourteen year experience in treatment of male-to-female transsexuals. J Sex Med 2009;6:2736–2745. [ABSTRACT FROM AUTHOR]
Keywords: Trans women; Transsexuals; Gender dysphoria; Transsexualism; Sex reassignment surgery; Vaginoplasty; Italy; Gender Identity Disorders; Male to Female Transsexualism; Patient's satisfaction questionnaire; Sex Reassignment Surgery; Transsexual

Suicidality and Self-Harm Among Sexual Minorities in Japan. - DiStefano, Anthony S. (Qualitative Health Research, 2008)
In this study, I used ethnographic methods to examine suicidality and nonsuicidal self-harm among gay, lesbian, bisexual, and transgender persons in Japan. Participants (N = 84) indicated that suicidality and self-harm are serious problems among sexual minorities and tend to be driven by (a) a homophobic/transphobic environment and the negative consequences of sexual minorities either disclosing their true selves or remaining hidden and silent within such an environment; (b) various antecedents to poor mental health; and (c) factors not directly related to being a sexual minority, particularly unemployment and debt in the context of a protracted national economic decline in Japan prior to the study period of 2003-2004. Participants also perceived a potentially higher risk for suicidality and self-harm among sexual minority adolescents and persons in their early 20s; those who work in the entertainment, bar, or sex industries; and survivors of violence perpetrated by intimate partners or family members. [ABSTRACT FROM AUTHOR]
Keywords: Homosexuality; First person narrative; Asia; bisexuals; ethnography; gays and lesbians; general; Japan; Japanese; minorities; qualitative methods; sexuality; transsexuals; violence; vulnerable populations

School support groups, other school factors, and the safety of sexual minority adolescents. - Goodenow, Carol; Szalacha, Laura; Westheimer, Kim (Psychology in the Schools, 2006)
Sexual minority adolescents—those self-identifying as lesbian, gay, or bisexual (LGB) or with same-sex desires or sexual experiences—report higher rates of victimization and suicidality than their heterosexual peers, yet little empirical research has examined school factors associated with these risks. This study used data from the Massachusetts Youth Risk Behavior Survey (Massachusetts Department of Education, 2000), matched with school-level data from state records and school principals, to compare the safety of 202 sexual minority adolescents in 52 schools with and without support groups for LGB students, to investigate the relationship between perceived staff support and safety, and to explore other school factors associated with victimization and suicidality among these youth. As hypothesized, sexual minority adolescents in schools with LGB support groups reported lower rates of victimization and suicide attempts than those in other schools. Victimization and perceived staff support predicted suicidality. Several additional school factors were associated with the safety of sexual minority students. © 2006 Wiley Periodicals, Inc. Psychol Schs 43: 573–589, 2006. [ABSTRACT FROM AUTHOR]
Keywords: SEXUAL minorities; SCHOOL environment; SAME-sex relationships; SUICIDAL behavior; YOUTH; HETEROSEXUALITY; RISK-taking (Psychology); EMPIRICISM; SCHOOL management & organization

Ignoring the evidence dictating the practice: sexual orientation, suicidality and the dichotomy of the mental health nurse. - McAndrew, S.; Warne, T. (Journal of Psychiatric & Mental Health Nursing (Wiley-Blackwell), 2004)
McANDREW S. & WARNE T. (2004) Journal of Psychiatric and Mental Health Nursing 11, 428–434 Ignoring the evidence dictating the practice: sexual orientation, suicidality and the dichotomy of the mental health nurse International epidemiological studies demonstrate that gay and bisexual males are four times more likely to report a serious suicide attempt than their heterosexual counterparts. Data on completed suicides, usually derived from mortality statistics misrepresent the rate of suicides among homosexual populations. However, an increasing number of studies comparing representative samples of gay, lesbian and bisexual youths with heterosexual controls demonstrate increased rates of mental health problems and subsequent suicide among the homosexual population. Homosexual orientation must therefore be considered a risk factor for mental distress and as such should be a focus for any contemporary public health agenda. One of the difficulties of addressing the problem through a public health agenda is the juxtaposition proffered by our political and social environment. The Diagnostic and Statistical Manual of Mental Disorder ceased to define homosexuality as pathological in 1973 replacing it with a new ‘illness’ of ‘gender identity disorder’. Until recently in England, Section 28 of the Local Government Act (1988), forbidding the promotion of homosexuality, further reinforced negativity towards this group of people. This compounded the negative mental health consequences for those developing a gay sexual orientation in a climate of heterosexism. Current health care policy in England concerns itself with the rising number of suicides among young people but fails to acknowledge the importance of the research findings relating to gay people by integrating them into the development of mental health policy. This paper reviews the literature relating to homosexual people and suicidality, and addresses the seriousness of a policy rhetoric which results from ignoring the evidence while dictating mental health nursing practice. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Suicide; Mental health; Nursing; Psychiatry; Psychiatric nursing; gay; lesbian; mental health

Lesbians and Alcohol Abuse: Identifying Factors for Future Research. - Ricks, JaniceL. (Journal of Social Service Research, 2012)
This article explores the reasons why lesbians become substance abusers more frequently than individuals in the heterosexual population. A variety of reasons for this phenomenon are explored using 18 studies to assist in helping to identify reasons for the higher rate of substance abuse among the lesbian population. Factors identified as crucial for further research include: self-esteem, social identity and the influence of bars on substance abuse, the prevalence of suicide, disclosure identification, coming out, religious influence, sexual abuse, and gender self-presentation (butch-appearing masculine/femme-appearing effeminate). [ABSTRACT FROM PUBLISHER]
Keywords: Lesbians; Group identity; Substance abuse; Substance abuse -- Research; Factor analysis; Self-esteem in women; Bars (Drinking establishments); Alcohol abuse; butch; femme; gay; gender presentation; homosexuality; lesbian; substance abuse; suicide

Where Risks and Protective Factors Operate Differently: Homeless Sexual Minority Youth and Suicide Attempts. - Walls, N.; Potter, Cathryn; Leeuwen, James (Child & Adolescent Social Work Journal, 2009)
Using a sample of 628 homeless youth and young adults from eight US cities, this study examines whether the relationship between having been in custody of social services and suicide attempts, and the relationship between engaging in survival sex and suicide attempts differ based on sexual orientation. Findings suggest that being in custody of social services is associated with a significant increase in likelihood of suicide attempts for heterosexual youth, it does not, however, significantly change the already increased risk of suicide attempts for sexual minority youth. Engaging in survival sex appears to be associated with increased risks of suicide attempts for both heterosexual and sexual minority youth, but the increase in likelihood is much stronger for heterosexual youth than for sexual minority youth. Implications for practice and future research are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority youth; Psychology; Youths' sexual behavior; Homeless youth; Teenage suicide; Suicidal behavior in young adults; Psychiatric social work; Street youth; Bisexual; Child welfare; Gay; Lesbian; Sexual minority; Social services custody; Suicide; Survival sex

Suicidality and associated risk factors among lesbian, gay, and bisexual compared to heterosexual Austrian adults. - Plöderl, Martin; Fartacek, Reinhold; Plöderl, Martin (Suicide & Life-Threatening Behavior, 2005)
This is the first study in German-speaking countries to compare the suicidality of lesbian, gay, and bisexual adults (n = 358) with matched heterosexual adults (n = 267). The former had significantly elevated incidences of current suicide ideation (28% vs. 13%) and lifetime suicide attempts defined in three ways (14% vs. 1% to 10% vs. 2%), including higher incidences for most suicidality-related risk factors. Increased psychosocial stress and vulnerability is indicated, especially with respect to a lack of family support. Controlling for risk factors in multivariate analysis diminished the association of sexual orientation with current suicide ideation. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ communities; Homosexuality; Heterosexuals; Suicidal behavior; Sexual orientation; Suicide; Heterosexuality; Suicide risk factors; Homicide

A Population-Based Study of Sexual Orientation Identity and Gender Differences in Adult Health. - Conron, Kerith J.; Mimiaga, Matthew J.; Landers, Stewart J. (American Journal of Public Health, 2010)
Objectives. We provide estimates of several leading US adult health indicators by sexual orientation identity and gender to fill gaps in the current literature. Methods. We aggregated data from the 2001-2008 Massachusetts Behavioral Risk Factor Surveillance surveys (N=67359) to examine patterns in self-reported health by sexual orientation identity and gender, using multivariable logistic regression. Results. Compared with heterosexuals, sexual minorities (i.e., gays/lesbians, 2% of sample; bisexuals, 1%) were more likely to report activity limitation, tension or worry, smoking, drug use, asthma, lifetime sexual victimization, and HIV testing, but did not differ on 3-year Papanicolaou tests, lifetime mammography, diabetes, or heart disease. Compared with heterosexuals, bisexuals reported more barriers to health care, current sadness, past-year suicidal ideation, and cardiovascular disease risk. Gay men were less likely to be overweight or obese and to obtain prostate-specific antigen tests, and lesbians were more likely to be obese and to report multiple risks for cardiovascular disease. Binge drinking and lifetime physical intimate partner victimization were more common among bisexual women. Conclusions. Sexual orientation disparities in chronic disease risk, victimization, health care access, mental health, and smoking merit increased attention. More research on heterogeneity in health and health determinants among sexual minorities is needed. [ABSTRACT FROM AUTHOR]
Keywords: Health of LGBTQ+ people; Gender differences (Psychology); Sexual orientation; Health of adults; Sexual minorities -- United States; Health status indicators; Health disparities; United States

Psychological Distress Following Suicidality Among Gay, Lesbian, and Bisexual Youths: Role of Social Relationships. - Rosario, Margaret; Schrimshaw, Eric W.; Hunter, Joyce (Journal of Youth & Adolescence, 2005)
Longitudinal relations between past suicidality and subsequent changes in psychological distress at follow-up were examined among gay, lesbian, and bisexual (GLB) youths, as were psychosocial factors (e.g., self-esteem, social support, negative social relationships) that might mediate or moderate this relation. Past suicide attempters were found to have higher levels of depressive symptoms, anxious symptoms, and conduct problems at a later time than youths who neither attempted nor ideated. Psychosocial factors failed to mediate this relation. The interaction among past suicidality, social support, and negative relationships was associated with subsequent changes in all 3 psychological distress indicators 6 months later. Specifically, high levels of support (either from family or friends) or negative relationships were found to predict increased psychological distress among those with a history of suicide attempts, but not among youths without a history of suicidality. The findings suggest that GLB youths who attempt suicide continue to have elevated levels of psychological distress long after their attempt and they highlight the importance of social relationships in the youths’ psychological distress at follow-up. [ABSTRACT FROM AUTHOR]
Keywords: Social interaction; Homosexuality; Social networks; Suicidal behavior; Distress (Psychology); Violent deaths; Mental depression; adolescents; bisexual; conduct problems; gay; lesbian; longitudinal research; negative social relationships; psychological distress; self-esteem; social support; suicidal ideation; suicide attempts

Sexual Orientation and Suicide Attempt: A Longitudinal Study of the General Norwegian Adolescent Population. - Wichstrøm, Lars; Hegna, Kristinn (Journal of Abnormal Psychology, 2003)
Past and future suicide attempt rates among gay, lesbian, and bisexual (GLB) young people were compared with those of heterosexual young people. A sample of Norwegian students (N = 2.924; grades 7-12) was followed in 3 data collection waves. Risk factors included previous suicide attempt, depressed mood, eating problems, conduct problems, early sexual debut, number of sexual partners, pubertal timing, self-concept, alcohol and drug use, atypical gender roles, loneliness, peer relations, social support, parental attachment, parental monitoring, and suicidal behavior among family and friends. When homosexual attraction, homosexual identity, and same-sex sexual behavior were entered to predict suicide attempt, only same-sex sexual behavior was significantly predictive. The increased odds could not be attributed to GLB students' greater exposure to risk factors for suicide attempt. [ABSTRACT FROM AUTHOR]
Keywords: NORWAY

Sexual minority youth, social connection and resilience: From personal struggle to collective identity - DiFulvio, Gloria T. (Social Science & Medicine, 2011)
Abstract: Sexual minority youth are at increased risk for negative health outcomes including substance abuse, depression, anxiety, and suicide. Researchers suggest that sexual orientation victimization is a predictor of such outcomes. Social connectedness—or the importance of belonging where youth perceive they are cared for and empowered within a given context—has been associated with positive youth outcomes. This qualitative study utilized life story methodology. Life stories are considered to be important expressions of one’s identity and are shaped by personal, social, and cultural contexts. Twenty-two interviews were conducted with 15 young people ranging in age from 14 to 22 years. Two focus groups with youth were also conducted. Youth were recruited from rural and urban communities in Massachusetts. This study contributes to the literature on resilience by including the voices of sexual minority youth and explores the meaning of social connection in their lives. Youth discuss the ways in which individual connection and group affiliation served to affirm one’s identity, and provided a forum for moving personal struggle to collective action. The findings suggest the need to reconceptualize consequences of disconnection (such as depression or suicide) from individual pathology and attend to these consequences as a response to discrimination and stigma. Implications for these findings and areas for future research are discussed. [Copyright &y& Elsevier]
Keywords: Attitude (Psychology); Discrimination; Group identity; PSYCHOLOGY; Human sexuality; Psychology of LGBTQ+ people; Experience; Focus groups; Interviewing; Minorities; Resilience (Personality trait); Social skills; Marginalized groups; Resilience; Sexual minority; Social connection; USA; Youth

Gay, Lesbian, and Bisexual College Students The Relationship Between Sexual Orientation and Depression, Loneliness, and Suicide. - Westefeld, John S.; Maples, Michael R.; Buford, Brian; Taylor, Steve (Journal of College Student Psychotherapy, 2001)
This study compared 70 gay male/lesbian/bisexual (lesbigay) college students with a control group of 154 college students on measures of loneliness, depression, and suicidal risk. Results indicated significant differences in several important areas. Issues concerning a variety of attitudes/feelings of the gay male/lesbian/bisexual group are discussed as are implications for college mental health and student development professionals. [ABSTRACT FROM PUBLISHER]
Keywords: Gay college students; Lesbian college students; Bisexual college students; Sexual orientation; Social isolation; Loneliness; Suicidal behavior; Mental depression; College student development programs; bisexual; depression; Gay; lesbian; loneliness; sexual orientation; suicide

Attitudes and Beliefs About Suicidal Behavior When Coming Out Is the Precipitant of the Suicidal Behavior. - Cato, Jennifer Ellen; Canetto, Silvia Sara (Sex Roles, 2003)
Young persons who identify as lesbian, gay, or bisexual (LGB) have higher rates of nonfatal suicidal behavior than their heterosexual peters. It has been suggested that suicidal behavior may be a painful but unavoidable rite of passage for LGB youths at the coming out stage. Could this mean that suicidal behavior is considered understandable and even permissible behavior for LGB youths at this stage? In this study we explored reactions to a suicidal decision when coming out was the precipitant of the suicidal act. Specifically, we compared attitudes toward a suicidal decision after coming out and being rejected by one's parents with attitudes toward a suicidal decision after experiencing other stressors (i.e., a physical illness, a relationship loss, or an academic failure). Contrary to expectation, the decision to engage in suicidal behavior following coming out was not viewed in relatively accepting terms. Rather, it was perceived as unsound and weak. As in previous studies, physical illness was singled out as a relatively understandable motivation for suicidal behavior. In addition, we found that androgynous persons viewed the suicidal decision as more unsound than other gender-identity types, independent of precipitant. Given similar evidence from other studies, future research might explore the role of androgyny in the protection against suicidal behavior. [ABSTRACT FROM AUTHOR]
Keywords: Suicide; Lesbians; Bisexual communities; Androgyny (Psychology); Gender identity

Mental Health Implications of Same-Sex Marriage: Influences of Sexual Orientation and Relationship Status in Canada and the United States. - Mathy, Robin M.; Kerr, Shelly K.; Lehmann, Barbara A. (Journal of Psychology & Human Sexuality, 2003)
Marriage is a mental health protective factor and homosexuality is sometimes a risk factor. The combined effect of these factors on mental health was examined in this study. We conducted a secondary analysis of an international, cross-sectional survey completed in 2000 (N = 7,616). We examined risks of suicide ideations and attempts, behavioral problems, and treatment histories for male and female participants from Canada and the United States. We found significant relations between sexual orientation and suicidality in all four gender-country groups. We found significant associations between relationship status and suicidality for men but not women in both countries. Behavioral problems and treatment histories were equivocal. We discuss the mental health implications of these findings for same-sex marriage. [ABSTRACT FROM AUTHOR]
Keywords: Marriage; Homosexuality; Mental health; Suicidal behavior; Sexual orientation; Same-sex marriage; attempted suicide; bisexual; homosexual; service utilization

Psychiatric comorbidity among patients with gender identity disorder. - Hoshiai, Masahiko; Matsumoto, Yosuke; Sato, Toshiki; Ohnishi, Masaru; Okabe, Nobuyuki; Kishimoto, Yuki; Terada, Seishi; Kuroda, Shigetoshi (Psychiatry & Clinical Neurosciences, 2010)
ims: Psychiatric comorbidity and mental instability seem to be important unfavorable prognostic factors for long-term psychosocial adjustment in gender identity disorder (GID). However, psychiatric comorbidity in patients with GID has rarely been assessed. In this study, we investigated the psychiatric comorbidity and life events of patients with GID in Japan. Methods: A total of 603 consecutive patients were evaluated independently by at least two senior psychiatrists at the GID clinic using clinical information and results of examinations. Results: Using DSM-IV criteria, 579 patients (96.0%) were diagnosed with GID. Among the GID patients, 349 (60.3%) were the female-to-male (FTM) type, and 230 (39.7%) were the male-to-female (MTF) type. Current psychiatric comorbidity was 19.1% (44/230) among MTF patients and 12.0% (42/349) among FTM patients. The lifetime positive history of suicidal ideation and self mutilation was 76.1% and 31.7% among MTF patients, and 71.9% and 32.7% among FTM patients. Among current psychiatric diagnoses, adjustment disorder (6.7%, 38/579) and anxiety disorder (3.6%, 21/579) were relatively frequent. Mood disorder was the third most frequent (1.4%, 8/579). Conclusions: Comparison with previous reports on the psychiatric comorbidity among GID patients revealed that the majority of GID patients had no psychiatric comorbidity. GID is a diagnostic entity in its own right, not necessarily associated with severe comorbid psychological findings. [ABSTRACT FROM AUTHOR]
Keywords: Gender dysphoria; Trans men; Trans women; Comorbidity; Psychiatrists; Japan; female‐to‐male type; gender; gender identity disorder; male‐to‐female type; psychiatric comorbidity

Predicting the suicide attempts of lesbian, gay, and bisexual youth. - D'Augelli, Anthony R.; Grossman, Arnold H.; Salter, Nicholas P.; Vasey, Joseph J.; Starks, Michael T.; Sinclair, Katerina O. (Suicide & Life-Threatening Behavior, 2005)
In this study predictors of serious suicide attempts among lesbian, gay, and bisexual (LGB) youth were examined. Three groups were compared: youth who reported no attempts, youth who reported attempts unrelated to their sexual orientation, and youth whose attempts were considered related to their sexual orientation. About one third of respondents reported at least one suicide attempt; however, only half of the attempts were judged serious based on potential lethality. About half of all attempts were related to youths' sexual orientation. Factors that differentiated youth reporting suicide attempts and those not reporting attempts were greater childhood parental psychological abuse and more childhood gender-atypical behavior. Gay-related suicide attempts were associated with identifiability as LGB, especially by parents. Early openness about sexual orientation, being considered gender atypical in childhood by parents, and parental efforts to discourage gender atypical behavior were associated with gay-related suicide attempts, especially for males. Assessment of past parental psychological abuse, parental reactions to childhood gender atypical behavior, youths' openness about sexual orientation with family members, and lifetime gay-related verbal abuse can assist in the prediction of suicide attempts in this population. [ABSTRACT FROM AUTHOR]
Keywords: Suicide; LGBTQ+ communities; Sexual orientation; Homosexuality; Suicidal behavior; Psychological abuse; Youth; Transgender youth; Homicide

Emotional Distress Among LGBT Youth: The Influence of Perceived Discrimination Based on Sexual Orientation. - Almeida, Joanna; Johnson, Renee M.; Corliss, Heather L.; Molnar, Beth E.; Azrael, Deborah (Journal of Youth & Adolescence, 2009)
The authors evaluated emotional distress among 9th–12th grade students, and examined whether the association between being lesbian, gay, bisexual, and/or transgendered (i.e., “LGBT”) and emotional distress was mediated by perceptions of having been treated badly or discriminated against because others thought they were gay or lesbian. Data come from a school-based survey in Boston, Massachusetts ( n = 1,032); 10% were LGBT, 58% were female, and ages ranged from 13 to 19 years. About 45% were Black, 31% were Hispanic, and 14% were White. LGBT youth scored significantly higher on the scale of depressive symptomatology. They were also more likely than heterosexual, non-transgendered youth to report suicidal ideation (30% vs. 6%, p < 0.0001) and self-harm (21% vs. 6%, p < 0.0001). Mediation analyses showed that perceived discrimination accounted for increased depressive symptomatology among LGBT males and females, and accounted for an elevated risk of self-harm and suicidal ideation among LGBT males. Perceived discrimination is a likely contributor to emotional distress among LGBT youth. [ABSTRACT FROM AUTHOR]
Keywords: Homophobia; LGBTQ+ youth; Sexual orientation; Suicidal ideation; Psychology; Student surveys; Self-destructive behavior in adolescence; Adolescent psychopathology; Boston (Mass.); Massachusetts; Depression; Emotional distress; LGBT; Self-harm; Suicide

Comparing Health and Mental Health Needs, Service Use, and Barriers to Services among Sexual Minority Youths and Their Peers. - Williams, Kelly A.; Chapman, Mimi V. (Health & Social Work, 2011)
Using a representative national sample (N = 20,745), this article explores health and mental health needs, service use, and barriers to services among sexual minority youths (SMYs) and heterosexual peers. SMYs were defined by ever having a same-sex romantic attraction or having a recent same-sex romantic relationship or sexual partner. SMYs accounted for 7.5 percent of the sample. Data were analyzed to ascertain prevalence of risks and explore group differences. Compared with peers, SMY self-reports indicated higher prevalence rates on all indicators of health and mental health need. SMYs reported more sexual activity, more sexually transmitted disease diagnoses, a higher perceived risk for HIV/AIDS, and more forgone medical care than peers. Also compared with peers, SMYs reported higher levels of anxiety, depression, suicidality, and physical and sexual victimization and higher rates of unmet mental health need. SMYs also reported greater concerns about confidentiality and were less likely to use school-based services. The majority of SMYs reported same-sex attraction only. Social work and other helping professionals should incorporate same-sex attraction questions into assessment protocols to target services for this population. School- and office-based providers must consider whether their services are welcoming and offer sufficient assurances of confidentiality to facilitate access by SMYs. [ABSTRACT FROM AUTHOR]
Keywords: Gay people; Health services accessibility; Medical care; Medical ethics; Mental health services; Minorities; Privacy; Human sexuality; Sexually transmitted diseases; Adolescence; Chi-squared test; Help-seeking behavior; Interviewing; Medical needs assessment; Self-evaluation; Social case work; Surveys; Affinity groups; Secondary analysis; Disease prevalence; Data analysis software; Health; LGB youths; mental health need; service use; sexual minority

Connecting the invisible dots: Reaching lesbian, gay, and bisexual adolescents and young adults at risk for suicide through online social networks - Silenzio, Vincent M.B.; Duberstein, Paul R.; Tang, Wan; Lu, Naiji; Tu, Xin; Homan, Christopher M. (Social Science & Medicine, 2009)
Abstract: Young lesbian, gay, and bisexual (young LGB) individuals report higher rates of suicide ideation and attempts from their late teens through early twenties. Their high rate of Internet use suggests that online social networks offer a novel opportunity to reach them. This study explores online social networks as a venue for prevention research targeting young LGB. An automated data collection program was used to map the social connections between LGB self-identified individuals between 16 and 24 years old participating in an online social network. We then completed a descriptive analysis of the structural characteristics known to affect diffusion within such networks. Finally, we conducted Monte Carlo simulations of peer-driven diffusion of a hypothetical preventive intervention within the observed network under varying starting conditions. We mapped a network of 100,014 young LGB. The mean age was 20.4 years. The mean nodal degree was 137.5, representing an exponential degree distribution ranging from 1 through 4309. Monte Carlo simulations revealed that a peer-driven preventive intervention ultimately reached final sample sizes of up to 18,409 individuals. The network''s structure is consistent with other social networks in terms of the underlying degree distribution. Such networks are typically formed dynamically through a process of preferential attachment. This implies that some individuals could be more important to target to facilitate the diffusion of interventions. However, in terms of determining the success of an intervention targeting this population, our simulation results suggest that varying the number of peers that can be recruited is more important than increasing the number of randomly-selected starting individuals. This has implications for intervention design. Given the potential to access this previously isolated population, this novel approach represents a promising new frontier in suicide prevention and other research areas. [Copyright &y& Elsevier]
Keywords: LGBTQ+ young adults; LGBTQ+ teenagers; Suicide prevention; Suicide risk factors; Online social networks; Suicidal behavior in young adults; Monte Carlo method; Simulation methods & models; Adolescent suicide; Adult suicide; Algorithms; Bisexual; Gay; Human sexuality; Internet; Lesbian; Network analysis

Suicidal Ideation and Attempts among Sexual Minority Youths Receiving Social Services. - Walls, N. Eugene; Freedenthal, Stacey; Wisneski, Hope (Social Work, 2008)
The increased risk of suicidal ideation and attempts among sexual minority youths have been documented in studies using both convenience samples and representative community samples. However, as most youths do not access social services, these studies do not necessarily represent the sexual minority youths that community-based social workers may encounter in their day-to-day practice. As such, the present study on risk and protective factors related to suicidality surveyed 182 sexual minority youths (14 to 21 years of age) who sought assistance at a community-based social services agency in Denver. Similar to existing literature, the findings suggest that risk factors related to suicidality include hopelessness, methamphetamine use, homelessness, and in-school victimization. However, unlike studies of the general youth population, this study found that African American and male sexual minority youths were not at a lower risk of suicidality than sexual minority youths who were, respectively, white or female. In addition, our findings suggest that the presence of gay-straight alliances in schools may function as a protective resource for sexual minority youths. Implications for social work practice are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Services for; SUICIDAL ideation; SEXUAL minority youth; SUICIDAL behavior; PREVENTION; MINORITY youth; YOUTH; SUICIDAL behavior; SOCIAL service; DENVER (Colo.); COLORADO; gay; gay--straight alliance; lesbian; suicide; youths

Sexual Orientation and Gender Identity: An Administrative Approach to Diversity. - Quinn, Tara L. (Child Welfare, 2002)
Research indicates that gay, lesbian, bisexual, transgender, and questioning (GLBTQ) teens in the care of a northeastern child welfare department do not receive adequate services due to the workers' homophobic attitudes. These teens are at high risk for alcohol and drug abuse, homelessness, prostitution, and suicide. A training module was developed for administrators. Pretest and posttest instruments measured their education and support of GLBTQ issues before and after the training. [ABSTRACT FROM AUTHOR]

Suicidality Patterns and Sexual Orientation-Related Factors Among Lesbian, Gay, and Bisexual Youths. - D'Augelli, Anthony R.; Hershberger, Scott L.; Pilkington, Neil W. (Suicide & Life-Threatening Behavior, 2001)
; Investigates the suicidal behaviors of lesbians, gays and bisexual youths. Relationship between sexual orientation and suicidality; Influence of sexual orientation on suicidal thoughts and feelings; Correlation between parental reactions to disclosures and suicidal attempts.

Lesbian, Gay, and Bisexual Suicidal Behavior: Testing a Constructivist Model. - McBee-Strayer, Sandra M.; Rogers, James R. (Suicide & Life-Threatening Behavior, 2002)
; Investigates the suicidal behavior of lesbian, gay and bisexuals in Ohio. Indication of serious consideration of suicide; Identification of specific suicide plan and past suicide attempt; Determination of suicide risk factors.
Keywords: OHIO; UNITED States

The Impact of Community Size on Lesbian and Bisexual Women's Psychosexual Development: Child Maltreatment, Suicide Attempts, and Self-Disclosure. - Mathy, Robin M.; Carol, Helen M.; Schillace, Marc (Journal of Psychology & Human Sexuality, 2003)
We tested competing hypotheses about the impact of rural-urban gradients on sexual minorities with a public Internet chat room sample (n = 82) and a community-owned coffee house sample (n = 92). We found associations between rural-urban gradient and reports of paternal maltreatment as a child as well as self-disclosure of sexual orientation to a family member. In the coffee house sample, rural-urban gradient mediated the mean age at which participants self-disclosed their sexual orientation to another person, close friend, family member, and parent, though it was associated in the Internet sample only with disclosure of sexual orientation to a family member. Rural-urban gradient was not associated with suicidal intent or victimization. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ communities; Online chat; Coffeehouses; Sexual orientation; Child abuse; Self-disclosure; child abuse; lesbian; psychosexual development; Religiosity; suicide

Suicide and gay/lesbian/bisexual youth: implications for clinicians. - Morrison, Linda L.; L'Heureux, Jeff (Journal of Adolescence, 2001)
; Examines the research indicating the incidence rates and specific risks for suicides in the gay, lesbian and bisexual youth population. Presentation of the ecological model of suicide risk assessment; Factors affecting high suicidal rates; Macrosystem risk factors.

Mental Health Pathways From Interpersonal Violence to Health-Related Outcomes in HIV-Positive Sexual Minority Men. - Pantalone, David W.; Hessler, Danielle M.; Simoni, Jane M. (Journal of Consulting & Clinical Psychology, 2010)
Objective: We examined mental health pathways between interpersonal violence (IPV) and healthrelated outcomes in HIV-positive sexual minority men engaged with medical care. Method: HI V-positive gay and bisexual men (N = 178) were recruited for this cross-sectional study from 2 public HIV primary care clinics that treated outpatients in an urban setting. Participants (M age = 44.1 years, 36% non-White) filled out a computer-assisted survey and had health-related data extracted from their electronic medical records. We used structural equation modeling to test associations among the latent factors of adult abuse and partner violence (each comprising indicators of physical, sexual, and psychological abuse) and the measured variables: viral load, health-related quality of life (HRQOL), HIV medication adherence, and emergency room (ER) visits. Mediation was tested for the latent construct mental health problems, comprising depression, anxiety, symptomatology of posttraumatic stress disorder, and suicidal ideation. Results: The final model demonstrated acceptable fit, x2(l23) = 157.05, p = .02, CFI = .95, TLI = .94, RMSEA = .04, SRMR = .06, accounting for significant portions of the variance in viral load (13%), HRQOL (41%), adherence (7%), and ER visits (9%), as well as the latent variable mental health problems (24%). Only I direct link emerged: a positive association between adult abuse and ER visits. Conclusions: Findings indicate a significant role of IPV and mental health problems in the health of people living with HIV/AIDS. HIV care providers should assess for IPV history and mental health problems in all patients and refer for evidence-based psychosocial treatments that include a focus on health behaviors. [ABSTRACT FROM AUTHOR]
Keywords: Intimate partner violence; HIV-positive persons; Mental health; Health outcome assessment; Structural equation modeling; HIV/AIDS; interpersonal violence; men who have sex with men; mental health

Political Suicide: GLBT Politics, Human Rights (to Life), and the Politicization of Queer Youth Suicide. - Cover, Rob (Journal of Intergroup Relations, 2004)
Focuses on the effect of current social and political arrangements on gays, lesbians, bisexual and transgender youth in their longevity as a group. Discrimination over alternative sexual practices and broad opposition to overt homophobia and heteroxism; Relevance of significant suicides to lesbian and gay communities; Consideration of the right of youth to life in public debate as a goal of human rights activity.
Keywords: Gay people; Civil rights; Suicide; Human sexuality; Discrimination; Homophobia; Right to life (International law)

Public Health Consequences of the Defense of Marriage Act for Lesbians and Bisexual Women: Suicidality, Behavioral Difficulties, and Psychiatric Treatment. - Mathy, Robin M.; Lehmann, Barbara A. (Feminism & Psychology, 2004)
Examines the associations between women's relationship status and sexual orientation in relation to suicidality, self-perceived excessive use or difficulties controlling the use of alcohol, drugs, and sex, and self-reported psychotherapy and psychiatric medications. Adverse health consequences that the U.S. Defense of Marriage Act and the ban on same-sex marriage may have for lesbians and bisexual women.
Keywords: Women; Suicidal behavior; Interpersonal relations; Alcohol drinking; Drug abuse; Human sexuality; Marriage; United States

Sexualities Equality in Schools: Why Every Lesbian, Gay, Bisexual or Transgender (LGBT) Child Matters. - Biddulph, Max (Pastoral Care in Education, 2006)
In an increasingly complex global society, schools frequently have to re-examine their understanding of the social and cultural dimensions that constitute ‘community’. One such dimension is the sexual orientation of individuals who make up this group. Historically, this has been a difficult task, given the tension that exists between sexuality and education and the heteronormative practices within schools. Consequently, individuals who identify as Lesbian, Gay, Bisexual or Transgender (LGBT), are thought to be LGBT or who are connected with the LGBT community, have frequently found themselves in a marginalized and vulnerable position. In the case of young people, the consequences of this include lowered self-esteem, absenteeism, underachievement and, in some cases, suicide. Given the mantra that Every Child Matters, schools now have a strategic opportunity to formulate new responses in supporting this group. A key question in this article relates to the ways in which the dimensions of strategy can be integrated into ‘joined-up’, effective action. [ABSTRACT FROM AUTHOR]
Keywords: Conduct of life; Respect for persons; Homophobia; Gender role; Sexual psychology; School children; ethos; homophobia; schools; sexuality; support

Transgender Identity and Suicidality in a Nonclinical Sample: Sexual Orientation, Psychiatric History, and Compulsive Behaviors. - Mathy, Robin M. (Journal of Psychology & Human Sexuality, 2002)
Examines the relation between sexual orientation and suicidality among transgender individuals in the U.S. Discussion on heterosexism and sexism; Comparison between gay and lesbian; Information on transgender suicidality by psychiatric and compulsive behavior; Limitations, advantages and implications of the study.
Keywords: Sexual orientation; Suicidal behavior; Transgender people; Heterosexism; Sexism; Gay & lesbian studies; Compulsive behavior; United States

Young Adult Suicide and Sexual Orientation: What Should Counselors Know? - Rutter, Philip A. (Journal of LGBT Issues in Counseling, 2006)
The current project focused on the suicidal ideation and risk potential of young adults (N = 312) and explored scores on self-report measures of suicidal ideation inclusive of various sexual orientations. Results suggest that the Lesbian, Gay, and Bisexual (LGB) youth surveyed (N = 73) differ in their display of suicide risk with significantly higher Beck Hopelessness Scale (BHS) and Suicide Probability Scale (SPS) scores. Social support served as a mitigating factor relating significantly to lower levels of hopelessness and suicidal ideation, especially among those LGB participants. The SPS held a significant relationship to suicide attempt in the past year, while the BHS held a significant relationship to suicide attempt in the past six months. Implications for counselors serving young adults are addressed, including specific suggestions to enhance counselor education and supervision related to suicide assessment and LGB counselor competency. [ABSTRACT FROM AUTHOR]
Keywords: Young adults; Sexual orientation; Social networks; Offenses against the person; Suicide; Adults; assessment; counseling; LGB; sexual orientation; suicide risk

Social Work Practice With Gay, Lesbian, Bisexual, and Transgender Adolescents. - Morrow, Deana F. (Families in Society: Journal of Contemporary Social Services, 2004)
The author addresses social work practice with gay, lesbian, bisexual, and transgender (GLBT) youth. Identity development, including disclosure and the emergence of sexuality are discussed, along with family and school issues. Particular emphasis is given to a number of risk factors that GLBT youth encounter: emotional distress, isolation, internalized homophobia/transphobia, depression, substance abuse, suicide, violence/victimization, family conflict, school performance, and sexually transmitted diseases and pregnancy. Guidelines for social work practice with GLBT youth are presented. [ABSTRACT FROM AUTHOR]
Keywords: Social services; Social work with LGBTQ people; Teenagers; Homophobia; Sexually transmitted diseases

Information needs of gay, lesbian, bisexual, and transgendered health care professionals: results of an Internet survey. - Fikar, Charles R.; Keith, Latrina (Journal of the Medical Library Association, 2004)
Objectives: To obtain basic facts and considered opinions from health care professionals and students (nonlibrarian and librarian) about the information needs of gay, lesbian, bisexual and transgendered (GLBT) health care professionals and their interactions with medical librarians. Methods: The survey instrument was a Web-based questionnaire. A nonrandom sample of health care professionals and students (librarian and nonlibrarian) was obtained by posting messages to several large Internet electronic discussion groups (GLBT and general) and to randomly selected members of the Gay and Lesbian Medical Association. A total of 152 forms were analyzed with about 50% of the participants being GLBT persons. Results: GLBT people have specific health information needs and concerns. More than 75% of medical librarians and students believed that GLBT persons have special information needs, with similar response rates by nonlibrarian health professionals and students. The delivery of services needs to be done with privacy and respect for the feelings of the patron. Major areas of need include the topics of health care proxy, cancer, adolescent depression and suicide, adoption, sexual health and practices, HIV infection, surrogate parenting, mental health issues, transgender health issues, intimate partner violence, and intimate partner loss. Conclusions: Most GLBT health care professionals desire GLBT-friendly health information services. Making GLBT-oriented health information resources available on a library Web page and making an effort to show acceptance of cultural diversity through signs or displays would be helpful. Education directed toward instilling an awareness of GLBT persons may also be advisable. Most survey participants make some use of medical reference services and many find medical librarians to be very helpful and resourceful. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Medical informatics; Medical librarians; Medical personnel; Students

Perceptions of lesbian, gay and bisexual people of primary healthcare services. - Neville, Stephen; Henrickson, Mark (Journal of Advanced Nursing, 2006)
Aim. This paper reports a study exploring people's perceptions of disclosure about lesbian, gay and bisexual identity to their primary healthcare providers. Background. Disclosure of sexual identity to healthcare professionals is integral to attending to the health needs of lesbian, gay and bisexual populations, as non-disclosure has been shown to have a negative impact on the health of these people. For example, an increased incidence of suicide, depression and other mental health problems have been reported. Method. From April to July 2004, a national survey of lesbian, gay and bisexual persons was carried out in New Zealand. Participants were recruited through mainstream and lesbian, gay and bisexual media and venues, and 2269 people completed the questionnaire, either electronically or via hard copy. The 133-item instrument included a range of closed-response questions in a variety of domains of interest. Results. In this paper, we report results from the health and well-being domain. More women than men identified that the practitioner's attitude toward their non-heterosexual identity was important when choosing a primary healthcare provider. Statistically significantly more women than men reported that their healthcare provider usually or always presumed that they were heterosexual and in addition more women had disclosed their sexual identity to their healthcare provider. Conclusion. Nurses need to reconsider their approach to all users of healthcare services by not assuming everyone is heterosexual, integrating questions about sexual identity into health interviews and ensuring that all other aspects of the assessment process are appropriate and safe for lesbian, gay and bisexual people. [ABSTRACT FROM AUTHOR]
Keywords: LESBIANS; BISEXUALS; MEDICAL care; GENDER identity; SUICIDE; NEW Zealand; attitudes; bisexual; gay; homosexual; lesbian; nursing; primary health care; survey

Family Rejection as a Predictor of Negative Health Outcomes in White and Latino Lesbian, Gay, and Bisexual Young Adults. - Ryan, Caitlin; Huebner, David; Diaz, Rafael M.; Sanches, Jorge (Pediatrics, 2009)
OBJECTIVE. We examined specific family rejecting reactions to sexual orientation and gender expression during adolescence as predictors of current health problems in a sample of lesbian, gay, and bisexual young adults. METHODS. On the basis of previously collected in-depth interviews, we developed quantitative scales to assess retrospectively in young adults the frequency of parental and caregiver reactions to a lesbian, gay, or bisexual sexual orientation during adolescence. Our survey instrument also included measures of 9 negative health indicators, including mental health, substance abuse, and sexual risk. The survey was administered to a sample of 224 white and Latino self-identified lesbian, gay, and bisexual young adults, aged 21 to 25, recruited through diverse venues and organizations. Participants completed self-report questionnaires by using either computer-assisted or pencil-and-paper surveys. RESULTS. Higher rates of family rejection were significantly associated with poorer health outcomes. On the basis of odds ratios, lesbian, gay, and bisexual young adults who reported higher levels of family rejection during adolescence were 8.4 times more likely to report having attempted suicide, 5.9 times more likely to report high levels of depression, 3.4 times more likely to use illegal drugs, and 3.4 times more likely to report having engaged in unprotected sexual intercourse compared with peers from families that reported no or low levels of family rejection. Latino men reported the highest number of negative family reactions to their sexual orientation in adolescence. CONCLUSIONS. This study establishes a clear link between specific parental and caregiver rejecting behaviors and negative health problems in young lesbian, gay, and bisexual adults. Providers who serve this population should assess and help educate families about the impact of rejecting behaviors. Counseling families, providing anticipatory guidance, and referring families for counseling and support can help make a critical difference in helping decrease risk and increasing well-being for lesbian, gay, and bisexual youth. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Lesbians; Gay people; Bisexuals; Rejection (Psychology) -- Social aspects; Adolescence -- Social aspects; gay youth; homosexuality; LGB adolescents; risk factors; sexual orientation

Suicide protective and risk factors for sexual minority youth: applying the Cumulative Factor Model. - Rutter PA (Journal of LGBT Issues in Counseling, 2008)
This report explores suicide protective and risk factors for lesbian, gay and bisexual (LGB) youth and offers a Cumulative Factor Model constructed from these factors. Numerous studies to date have concluded that a youth's sexual minority identity is a key risk factor for suicide. Few studies however have explored the internal and external protective factors that may cumulate to increase or reduce suicidal ideation and risk among this LGB population. Counseling implications for both assessment and intervention strategies are discussed in light of this cumulative factor approach to understand and potentially stem LGB youth suicide. [ABSTRACT FROM AUTHOR]

Psychosocial Concerns of Sexual Minority Youth: Complexity and Caution in Group Differences. - V. Paul Poteat; Brian W. Koenig; Aragon, Steven R.; Espelage, Dorothy L. (Journal of Consulting & Clinical Psychology, 2009)
This investigation tested a large adolescent sample (n = 14,439) for significant group differences on psychosocial concerns on the basis of intersecting identities of sexual orientation (lesbian, gay, bisexual, questioning/less certain, heterosexual), race (Whites, racial minorities), and gender (boys, girls). A significant 2-way interaction between sexual orientation and gender was identified on victimization. Boys reported higher victimization than did girls among heterosexual and questioning/less certain students. Furthermore, significant 3-way interactions between sexual orientation, race, and gender were identified for substance use and depressed/suicidal thoughts. Questioning/less certain youth generally reported the highest levels of victimization, substance abuse, and suicidal thoughts. However, results suggest that, on the basis of small effect sizes for most comparisons, significant differences should be interpreted with caution. Results indicate the need to consider the diversity of subgroups within the sexual minority youth community and that intervention efforts might be more effective if tailored to the unique needs of specific subgroups. [ABSTRACT FROM AUTHOR]
Keywords: Sexual minority youth; Sexual orientation; Gender; Suicide; Crime victims; Teenagers -- Substance use; Biocomplexity; adolescents; racial minorities; sexual orientation; substance use; victimization

The Impact of Religiosity on Lesbian and Bisexual Women's Psychosexual Development: Child Maltreatment, Suicide Attempts, and Self-Disclosure. - Mathy, Robin M.; Schillace, Mark (Journal of Psychology & Human Sexuality, 2003)
We examined the relation between religiosity (importance of religion) and child maltreatment, psychosexual development, self-disclosure of homosexuality and reactions to same with two samples of sexual minority women (Internet n = 84, Coffee House n = 92) obtained with block sampling designs. Extremely important religiosity currently was associated with precocious psychosexual development and self-disclosure in the Internet sample only. Very important religiosity currently was associated with psychosexual development and self-disclosure of minority sexual orientation at significantly older ages. We discuss these results in the context of arguments that religiosity may be a risk factor for sexual minorities. Although not a risk factor in our samples, religiosity appeared to have lost the protective influence observed in studies of the general population. [ABSTRACT FROM AUTHOR]
Keywords: Psychosexual development; Sexual orientation; Homosexuality; Religiousness; Child abuse; Self-disclosure; child abuse; Lesbian; psychosexual development; Religiosity; suicide attempt

Sexuality in patients with spinal cord injuries due to attempted suicide. - Lombardi, G.; Mondaini, N.; Iazzetta, P.; Macchiarella, A.; Popolo, G. D. (Spinal Cord, 2008)
Objective:To evaluate the specific characteristics of sexuality in spinal cord injury (SCI) patients resulting from attempted suicide pre- and post-SCI.Methods:From March 1998 to March 2005, n=27 were compared with a SCI group with similar characteristics. In March 2006, all patients completed a final sexual check-up. Using our database we reviewed their sexuality path.Results:Suicide group (SG):Examination of personal/clinical history revealed in three how sexuality represented a possible co-factor for suicidal tendencies: one female reported a history of sexual abuse, two were homosexual (one gay and one lesbian). Five reported sexual dysfunctions. Nine females consistently showed via the Female Sexual Function Index (FSFI) at least one sexual disorder in all follow-ups; six females were in a stable relationship pre-SCI, seven during the final check-up; eight males in the SG presented erectile dysfunction using the International Index of Erectile Function (IIEF5); and eight were in a stable relationship pre-SCI and seven during the final visit.Control group (CG):Pre-SCI only one male presented erectile dysfunction. Seven females consistently showed sexual disorders. 11 females and 11 males were in stable relationships pre-SCI, respectively, 10 and 11 at the final check-up. In women the overall sexual satisfaction is statistically significant, correlated to the duration of the relationship P<0.05. Nine patients showed erectile dysfunction in the final follow-up.Conclusions:The SG showed a higher percentage of sexual dysfunction pre-SCI compared with CG, and they presented constant difficulty in establishing a stable relationship causing both an obstacle in the initial sexual rehabilitation and in achieving a satisfactory overall sexual life.Spinal Cord (2008) 46, 53–57; doi:10.1038/sj.sc.3102062; published online 10 April 2007 [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Sexual psychology; Spinal cord; Spinal cord injuries; Central nervous system; attempted suicide; mental disorders; sexual dysfunctions; sexuality; spinal cord injury

Suicide & Homosexual Teens. - Smith, Mike U.; Drake, Mary Ann (American Biology Teacher, 2001)
; Assesses the role of biology teachers in preventing suicidal attempts among homosexual teenagers in the United States. Life of homosexual teenagers; Issues regarding change and morality; Ways to address sexual orientation in the biology classroom.
Keywords: UNITED States

Links Between Past Abuse, Suicide Ideation, and Sexual Orientation Among San Diego College Students. - Garcia, Jacob; Adams, Joyce; Friedman, Lawrence; East, Patricia (Journal of American College Health, 2002)
Abstract. The authors explored relationships among childhood abuse, suicidal ideation, and sexual orientation of 18- to 30-year-old students enrolled in 2 San Diego area colleges, using responses from anonymous questionnaires. Sixty percent of the 138 eligible respondents were women, and 22% were self-identified gay/bisexual individuals. Women were more likely than men to report at least 1 form of emotional abuse (odds ratio [OR] = 2.3; p = .02) and unwanted sexual touching (OR = 4.3; p = .0004). Lesbian/bisexual women were significantly more likely to report past suicidal ideation than were heterosexual women (OR = 3.7, p = .03). Gay/bisexual men were more likely to report unwanted sexual touching than were heterosexual men (OR = 5.1, p = .04), but the men did not report significantly higher rates of past suicide ideation or suicide attempts. Sexual orientation and a past history of child sexual, physical, and emotional abuse could be compounding risk factors for suicidal ideation among college students. [ABSTRACT FROM AUTHOR]

Risk Factors for Attempted Suicide in Gay and Bisexual Youth. - Remafedi, Gary; Farrow, James A.; Deisher, Robert W. (Pediatrics, 1991)
Abstract. Studies of human sexuality have noted high rates of suicidality among homosexual youth, but the problem has not been systematically examined. This work was undertaken to identify risk factors for suicide attempts among bisexual and homosexual male youth. Subjects were 137 gay and bisexual males, 14 through 21 years of age, from the upper Midwest and Pacific Northwest. Forty-one subjects (41/137) reported a suicide attempt; and almost half of them described multiple attempts. Twenty-one percent of all attempts resulted in medical or psychiatric admissions. Compared with non-attempters, attempters had more feminine gender roles and adopted a bisexual or homosexual identity at younger ages. Attempters were more likely than peers to report sexual abuse, drug abuse, and arrests for misconduct. The findings parallel previous studies' results and also introduce novel suicide risk factors related to gender nonconformity and sexual milestones. [ABSTRACT FROM AUTHOR]

Young adult suicide and sexual orientation: what should counselors know? - Rutter PA (Journal of LGBT Issues in Counseling, 2006)
The current project focused on the suicidal ideation and risk potential of young adults (N = 312) and explored scores on self-report measures of suicidal ideation inclusive of various sexual orientations. Results suggest that the Lesbian, Gay, and Bisexual (LGB) youth surveyed (N = 73) differ in their display of suicide risk with significantly higher Beck Hopelessness Scale (BHS) and Suicide Probability Scale (SPS) scores. Social support served as a mitigating factor relating significantly to lower levels of hopelessness and suicidal ideation, especially among those LGB participants. The SPS held a significant relationship to suicide attempt in the past year, while the BHS held a significant relationship to suicide attempt in the past six months. Implications for counselors serving young adults are addressed, including specific suggestions to enhance counselor education and supervision related to suicide assessment and LGB counselor competency. [ABSTRACT FROM AUTHOR]

Being Lesbian, Gay, Bisexual, and 60 or Older in North America. - Grossman, Arnold H.; D'Augelli, Anthony R.; O'Connell, Timothy S. (Journal of Gay & Lesbian Social Services, 2001)
This study examined mental and physical health, perceived social support, and experiences with HIV/AIDS of 416 lesbian, gay, and bisexual adults aged 60 to 91. Most participants reported fairly high levels of self-esteem; however, many experienced loneliness. Most also reported low levels of internalized homophobia, but men reported significantly higher levels than women did. Ten percent of respondents sometimes or often considered suicide, with men reporting significantly more suicidal thoughts related to their sexual orientation. Men also had significantly higher drinking scores than women, and more men could be classified as problem drinkers. Only 11% of the respondents said that their health status interfered with the things they wanted to do. Although 93% of the participants knew people diagnosed with HIV/AIDS, 90% said that they were unlikely to be HIV-infected. Participants averaged six people in their support networks, most of whom were close friends. Most support network members knew about the participants' sexual orientation, and the respondents were more satisfied with support from those who knew. Those living with domestic partners were less lonely and rated their physical and mental health more positively than those living alone. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; AIDS patients; Mental health; Social networks; Self-esteem; Sexual orientation; Experience; North America; homosexuality; internalized homophobia; loneliness.; mental health; physical health; Social support; support networks

Sexual Minority Youth and Suicide Risk. - Russell, Stephen T. (American Behavioral Scientist, 2003)
Numerous studies spanning the past quarter century have used varied designs and methods in multiple settings and have consistently demonstrated that sexual minority youth are among those most likely to report suicidality (suicidal thoughts, plans, and attempts). This article reviews the methodological challenges that have defined and limited research in this area, including issues of sampling, the measurement of sexual minority status, and the measurement of suicide risk. Attention is then given to risk and protective factors for suicide among sexual minority youth. Normative risk and protective factors, those common to all youth, and risk and protective factors unique to sexual minority youth are reviewed. In closing, attention is given to the state of suicide prevention and intervention efforts that target sexual minority youth, along with recommendations for further research. [ABSTRACT FROM AUTHOR]
Keywords: Suicide; Psychology; Minority youth; Suicidal behavior in youth

Homophobic Teasing, Psychological Outcomes, and Sexual Orientation Among High School Students: What Influence Do Parents and Schools Have? - Espelage, Dorothy L.; Aragon, Steven R.; Birkett, Michelle; Koenig, Brian W. (School Psychology Review, 2008)
Homophobic teasing is often long-term, systematic, and perpetrated by groups of students (Rivers, 2001); it places targets at risk for greater suicidal ideation, depression, and isolation (Elliot & Kilpatrick, 1994). This study fills a gap in the literature by examining buffering influences of positive parental relations and positive school climate on mental health outcomes for high school students who are questioning their sexual orientation. Participants were 13,921 high school students from a Midwestern U.S. public school district. Students completed a survey consisting of a wide range of questions related to their school experiences (bullying, homophobia, school climate), parental support, mood, and drug--alcohol use. Students were categorized into three groups: (a) youth who identified as heterosexual, (b) youth who questioned their sexual orientation, and (c) youth who identified as lesbian, gay, or bisexual (LGB). As hypothesized, sexual minority youth were more likely to report high levels of depression-- suicide feelings and alcohol--marijuana use; students who were questioning their sexual orientation reported more teasing, greater drug use, and more feelings of depression and suicide than either heterosexual or LGB students. Sexually questioning students who experienced homophobic teasing were also more likely than LGB students to use drugs--alcohol and rate their school climate as negative. Finally, positive school climate and parental support protected LGB and questioning students against depression and drug use. [ABSTRACT FROM AUTHOR]
Keywords: School bullying; Abuse of LGBTQ+ people; Homophobia in language; Gay people; Students -- Abuse of; Invective; School environment -- Social aspects; Mental depression; Teasing; Educational sociology; Bullying research

The Health and Health Care of Lesbian, Gay, and Bisexual Adolescents. - Coker, Tumaini R.; Austin, S. Bryn; Schuster, Mark A. (Annual Review of Public Health, 2010)
Adolescents face a variety of challenges in their transition to adulthood; lesbian, gay, and bisexual adolescents face these typical challenges as well as additional challenges that are related to the social stigma of their sexual orientation. For some lesbian, gay, and bisexual adolescents, this stigma may induce psychosocial stress, leading to increased health risk behaviors and poorer health outcomes. In this article, we review data on the health and health care ofLGB adolescents. We examine health mdicators and health risks for LGB youth, including substance use, eating disorders, suicidality, risky sexual behaviors, violence exposure and victimization, and homelessness. We also examine health care provision and utilization for LGB youth. Lastly, we discuss ways in which researchers and clinicians can improve LGB adolescent health and health care. [ABSTRACT FROM AUTHOR]
Keywords: Teenagers' sexual behavior; Health of LGBTQ+ people; Social stigma; Sexual orientation; Health behavior in adolescence; United States; health risk behaviors; sexual minority; sexual orientation; youth

Aspects of mental health among older lesbian, gay, and bisexual adults. - D'Augelli, A. R.; Grossman, A. H.; Hershberger, S. L.; O'Connell, T. S. (Aging & Mental Health, 2001)
This study examined aspects of mental health among 416 lesbian, gay, and bisexual adults aged 60 to 91 years old, attending social and recreational programs. Mental health indicators were perceived mental health status; self-esteem; internalized homophobia; loneliness; alcohol and drug abuse; and suicidality. Better mental health was correlated with higher self-esteem, less loneliness, and lower internalized homophobia. Compared to women, men reported significantly more internalized homophobia, alcohol abuse, and suicidality related to their sexual orientation. Less lifetime suicidal ideation was associated with lower internalized homophobia, less loneliness, and more people knowing about participants' sexual orientation. [ABSTRACT FROM AUTHOR]
Keywords: MENTAL health; LESBIANS; GAY men; BISEXUALS

Attempted suicide, psychological health and exposure to harassment among Japanese homosexual, bisexual or other men questioning their sexual orientation recruited via the internet. - Hidaka, Y.; Operario, D. (Journal of Epidemiology & Community Health, 2006)
Objective: To investigate the rates of attempted suicide and its association with psychological distress, experiences of bullying and verbal harassment, and demographic characteristics among Japanese homosexual, bisexual or other men questioning their sexual orientation. Design: A cross-sectional design using Japanese participants recruited through the internet. Results: Of the 1025 respondents, 154 (15%) of the men reported a history of attempted suicide, 716 (70%) showed high levels of anxiety and 133 (13%) showed high levels of depression. 851 (83%) experienced school bullying and 615 (60%) were verbally harassed because of being perceived by others as homosexual. Independent correlates of attempted suicide were psychological distress, history of being verbally harassed, history of sex with a woman, history of meeting a male through the internet, disclosing sexual orientation to six or more friends and not having a university degree. Conclusions: Mental health services and prevention programmes are needed to deal with the psychological consequences of social stigma for Japanese men who are homosexual, bisexual or questioning their sexual orientation. [ABSTRACT FROM AUTHOR]
Keywords: SEXUAL orientation; GENDER identity; IDENTITY (Psychology); MENTAL health services; MEDICAL care; JAPAN

A needs assessment of transgendered people of color living in Washington, DC. - Xavier JM; Bobbin M; Singer B; Budd E (International Journal of Transgenderism, 2005)
A needs assessment (N = 248) conducted in Washington, DC revealed that transgendered people of color are at high risk for HIV/AIDS, substance abuse, suicide and violence/ crime victimization. Overall HIV prevalence was 25%, with 32% in natal males (MTFs, i.e., male-to-females). Four predictors for HIV positive status were identified through logistic regressionmale sex at birth, a history of substance abuse, sexual assault, and unemployment. Substance abuse was found in nearly half the sample (48%) but only half of those (51%) had sought treatment for it. Thirty-eight percent reported experiencing suicidal ideation, with 63% of those attributing it to their gender issues. Of those with suicidal ideation, nearly half (49%, or 16% of the entire sample), went on to make attempt(s) to kill themselves. Forty three percent had been victims of violence or crime, including 13% who had been sexually assaulted. Knowledge of the Standards of Care of the Harry Benjamin International Gender Dysphoria Association was quite low (9%) and associated with white race, any higher education beyond high school, and access to sex reassignment surgery (SRS). Access to SRS, defined as obtaining vaginoplasties for natal males and chest surgeries for natal females, was just 4%. White race (versus all other races, p < .001) and female at birth (versus male, p < .01) were significantly associated with access to SRS. Use of hormones at some point during their lives was reported by 51% of participants. Thirty-five percent were currently taking hormones, with 72% acquiring their hormones from friends or on the street. Among natal males, 25% had injected silicone. Nineteen percent did not have their own living space, and employment, housing and job training were the most commonly-reported immediate needs of the sample. The results of this needs assessment provide evidence of an urgent need for increased medical and social services specific to transgendered people of color living in the District of Columbia. [ABSTRACT FROM AUTHOR]

Suicide Attempts Among Sexual-Minority Youths: Population and Measurement Issues. - Savin-Williams, Ritch C. (Journal of Consulting & Clinical Psychology, 2001)
; Examines suicide attempts among sexual-minority youths, or gays. Population and measurement issues; Comparison of rates of suicide attempts with heterosexual youths; Assessment of suicide attempts through an in-depth methodology.
Keywords: SUICIDAL behavior; GAYS; MENTAL health

Out Yonder: Sexual-Minority Adolescents in Rural Communities in British Columbia. - Poon, Colleen S.; Saewyc, Elizabeth M. (American Journal of Public Health, 2009)
Objectives. We compared sexual-minority adolescents living in rural communities with their peers in urban areas in British Columbia, exploring differences in emotional health, victimization experiences, sexual behaviors, and substance use. Methods. We analyzed a population-based sample of self-identified lesbian) gay, or bisexual respondents from the British Columbia Adolescent Health Survey of 2003 (weighted n = 6905). We tested rural-urban differences separately by gender with the χ² test and logistic regressions. Results. We found many similarities and several differences. Rural sexual-minority adolescent boys were more likely than were their urban peers to report suicidal behaviors and pregnancy involvement. Rural sexual-minority adolescents, especially girls, were more likely to report various types of substance use. Rural status was associated with a lower risk of dating violence and higher risk of early sexual debut for sexual-minority girls and a higher risk of dating violence and lower risk of early sexual debut for sexual-minority boys. Conclusions. Location should be a demographic consideration in monitoring the health of sexual-minority adolescents. Lesbian, gay, and bisexual adolescents in rural communities may need additional support and services as they navigate adolescence. (Am J Public Health. 2009;99:118-124. doi:10.2105/AJPH.2007.122945) [ABSTRACT FROM AUTHOR]
Keywords: Teenagers' sexual behavior; Sexual intercourse; Sexual orientation; Suicidal behavior; Safe sex; Substance abuse; Bisexual men; Heterosexuality; Heterosexuals; British Columbia

Queer Subjects of Suicide: Cultural Studies, Sexuality and Youth Suicide Concepts in New Zealand. - Cover, Rob (New Zealand Sociology, 2005)
This article examines how research on sexuality and youth suicide might be re-thought from a queer cultural studies perspective in a New Zealand context across three areas: cultural studies, sexuality, and youth suicide. The author, at first, suggests that sexuality might be deemed to play a significant role in suicide risk factors broadly as a result of a continuing cultural anxiety over sex, sexuality and gender. He then discusses the queer theory in order to expand on what it is meant by sexuality. The theory attempts to append sexuality-related risk factors to suicide studies that often leave intact an essentialist and minoritarian approach to sexuality that wrongly presumes the fixity and self-evidence of a hetero/homo binary, despite increasing evidence that sexual identity is blurred, confused, complex and is particularly so among younger persons. It is argued that the most significant feature of sexuality-related youth suicide in the New Zealand context is the way in which isolation is dealt with as a factor in non-heterosexual self-identification. By showing how youth sexuality is either marginalised or mis-read by policy-makers and researchers, some early indicators of directions suicide researches are illustrated here.
Keywords: Psychological stress; Suicidal behavior; Gender identity; Youth; Suicide risk factors; Violent deaths; Psychoanalysis & culture; New Zealand

Adolescent Sexual Orientation and Suicide Risk: Evidence From a Natural Study. - Russell, Stephen T.; Joyner, Kara (American Journal of Public Health, 2001)
Conclusions. The findings provide strong evidence that sexual minority youths are more likely than their peers to think about and attempt suicide. (Am J Public Health. 2001;91:1276-1281) [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Adolescent psychology; Alcoholism; Risk factors in suicidal behavior; Teenage suicide; Health behavior in adolescence; Mental depression

Domestic Violence Screening: Prevalence and Outcomes in a Canadian HIV Population. - Siemieniuk, Reed A. C.; Krentz, Hartmut B.; Gish, Jessica A.; Gill, M. John (AIDS Patient Care & STDs, 2010)
There is a strong association between domestic violence victimization and HIV infection. This may lead to poor health outcomes including mental health disorders and reduced access to care. A standardized domestic violence screening interview was incorporated into ongoing care in the large and diverse population living with HIV in Southern Alberta, Canada. Results from May through December 2009 are reported, including the prevalence and outcomes of abuse. Thirty-four percent of 853 patients screened reported abuse. Of these, 16% reported abuse in their current relationship, 58% in a previous relationship, and 57% reported a history of childhood abuse. High-risk groups for abuse included females (43%), gay/bisexual males (35%), and Aboriginals (61%). We found an association between a history of domestic violence and delayed access to care ( p < 0.05), missed appointments ( p < 0.001), and an increased use of clinic resources such as social work ( p < 0.0001) and psychiatry ( p < 0.001). Mental health conditions prior to HIV diagnosis, including depression ( p < 0.0001), suicidal ideation ( p < 0.0001), and anxiety disorder ( p < 0.0001) were associated with abuse at any time, while a history of adjustment disorder was associated with childhood abuse ( p < 0.05). A simple domestic violence screening tool was helpful for identifying patients experiencing abuse in our diverse HIV-infected population. This high prevalence of domestic violence among our HIV patients was associated with poor outcomes and an increased use of medical resources. HIV caregivers should be aware of domestic violence in order to optimize care and refer patients to appropriate support professionals as needed. [ABSTRACT FROM AUTHOR]
Keywords: Domestic violence; Health services accessibility; HIV-positive persons; Mental health; T cells; Lifestyles; Prevention of family violence; Analysis of variance; Blood cell count; Chi-squared test; Confidence intervals; Epidemiology; Eskimos; Indigenous peoples of the Americas; Interviewing; Research methodology; Population geography; Statistical sampling; Self-evaluation; Sex distribution; Statistics; T-test (Statistics); White people; Data analysis; Classification; Alberta

Attempted Suicide, LGBT Identity, and Heightened Scrutiny. - Halady, StevenWilliam (American Journal of Bioethics, 2013)
The article focuses on high numbers of suicide attempts which are seen among LGBT youth and adults and on the article "Withdrawal of Nonfutile Life Support After Attempted Suicide" by Samuel M. Brown, C. Gregory Elliott and Robert Paine. In the article the author offers his opinions on the challenges of attempted suicide among the LGBT community and on several points which are raised in Brown et al.'s article.
Keywords: Social stigma; Suicidal behavior; LGBTQ+ people; Family roles

Violence against women and suicide risk: The neglected impact of same-sex sexual behaviour. - Lhomond, Brigitte; Saurel-Cubizolles, Marie-Josèphe (Social Science & Medicine, 2006)
Abstract: We used data from the National Survey on Violence against Women in France carried out in 2000 on a representative sample of 6970 women to compare the social characteristics of women who had sex with women (WSW) and women who had sex only with men (WSM). The WSW were more likely to be of a high socio-economic level and living in large cities. They were more frequently unmarried, without children, and had a more diverse sexual life, generally beginning younger, with more partners, mainly men. They were also more likely to use tobacco, alcohol and drugs. WSW reported more physical violence in the recent past and more suicide attempts than WSM, despite a lack of difference in psychological distress and stress. These results, in a field little studied in France, are consistent with international findings attesting to the difficulties faced by women in situations involving autonomy and marginality. [Copyright 2006 Elsevier]
Keywords: WOMEN -- Sexual behavior; LESBIANISM; SINGLE women; CHILDLESSNESS; TOBACCO use; DRUG abuse; DRINKING of alcoholic beverages; SUICIDAL behavior

Alcohol and drug use and related consequences among gay, lesbian and bisexual college students: Role of experiencing violence, feeling safe on campus, and perceived stress - Reed, Elizabeth; Prado, Guillermo; Matsumoto, Atsushi; Amaro, Hortensia (Addictive Behaviors, 2010)
Abstract: Objective: To examine differences between gay, lesbian, and bisexual (GLB) and non-GLB university students in alcohol and other drug use (AOD) and related consequences as well as the relevance of violence, perceived safety, and stress to any such differences in AOD use and related concerns. Methods: A random representative sample of university students (n =988) were recruited via email for an online survey. Linear regression models assessed associations between identifying as GLB and AOD use and related consequences. Results: Regression models (adjusted for gender) indicated that, in comparison to heterosexual students, GLB students were more likely to report recent illicit drug use (AOR=2.0; 95% CI: 1.1–3.9), more frequent negative AOD consequences (β =5.5, SE=1.4, p <0.0001), and having seriously thought about/attempted suicide due to AOD use in the past year (AOR=6.6; 95% CI: 3.0–14.3). Study findings also suggested that violence, safety, and stress variables partially contribute to AOD use and related concerns among GLB students. Conclusions: Findings highlight the need for future efforts to investigate and address mechanisms, including aspects of campus life, which contribute to AOD related risks among GLB students. [Copyright &y& Elsevier]
Keywords: Alcohol drinking; Drug abuse; Psychology of gay people; Internalized homophobia; Psychology of lesbians; Bisexuals; Violence; Psychology; College students; Internet surveys; Alcohol use; Campus environment; Drug use; GLBT; Stress; Substance use; Victimization

A General Review of Recent Reports on Homosexuality and Lesbianism. - Hughes, John R. (Sexuality & Disability, 2006)
This review deals with the most recent reports on male homosexuality (H) and lesbianism (L). The reviewer checked the most recent 1000 articles in the Internet’s Medline to report the major new findings in H and L. First discussed is the presumed etiology or cause, including the “maternal immunization hypothesis” and the evidence for both genetic and environmental factors. Next the prevalence in various countries is reported. The related diseases include HIV+, syphilis and other venereal diseases. Factors like drug involvement, unprotected anal sex, casual partners are included, as is suicidal ideation, violence, child molestation and changes in sexual orientation over time. The goal of this review is to make available to all readers the most recent reports on H and L so that pre-existing problems and any new disorders that have arisen can be better understood and that attempts at their solution can be pursued. [ABSTRACT FROM AUTHOR]
Keywords: HOMOSEXUALITY; LESBIANISM; BISEXUALS; UNSAFE sex; SEXUAL orientation; SEXUALLY transmitted diseases; HIV-positive persons; Bisexual; Casual sex; HIV+; Homosexuality; Lesbianism; Unprotected sex; Venereal disease

Risk Factors of Gay, Lesbian, and Bisexual Adolescents: Review of Empirical Literature and Practice Implications. - Thompson, Sanna J.; Johnston, Lon (Journal of Human Behavior in the Social Environment, 2003)
Many researchers of gay, lesbian, and bisexual adolescents describe them as an "invisible" minority. These youth are also one of the most "at risk" youth populations, as they often experience a range of problems related to society's stigmatization of same-sex orientation. Although sexual orientation is not necessarily related to heightened difficulties, lack of social support, infrequent positive interactions, and chronic stress may lead to increased problem behaviors for these youth. To further understand the risk and protective factors experienced by sexual minority adolescents, this article explores a number of these factors and reviews the current empirical research on specific topics, including: family, peer and school, substance use, suicide, and HIV/AIDS issues. Finally, practice implications are discussed to guide clinicians in working more effectively with this youth population. [ABSTRACT FROM AUTHOR]
Keywords: Adolescent psychology; Gay people; Lesbians; Bisexuals; AIDS; Disease risk factors

Suicide attempts among people living with HIV in France. - Préau, M.; Bouhnik, A.-D.; Peretti-Watel, P.; Obadia, Y.; Spire, B.; the ANRS-EN12-VESPA Group (AIDS Care, 2008)
This study examined the prevalence and characteristics of attempted suicide among a representative sample of French Human Immunodeficiency virus (HIV) infected individuals. In 2003, a face-to-face survey was conducted among people living with HIV/AIDS (PLWHA) selected in a random, stratified sample of French hospital departments. Among solicited individuals, 2,932 agreed to participate and were asked if they had ever AS. Among the respondents, 23% had AS. Female gender, younger age, native French citizenship, reporting household financial difficulties, having been HIV-contaminated through homosexual contact or through injection drug use and suffering from lipodystrophy-related symptoms were all independently associated with AS. HIV-discrimination and the lack of social support from family remained independently associated with AS. Our findings indicate a high level of AS among PLWHA and emphasize the multiple roles of factors associated with living with HIV, together with sociodemographic factors. The results enable the possibility for vulnerable groups to be targeted for specific future interventions in order to prevent attempted suicide. [ABSTRACT FROM AUTHOR]
Keywords: HIV infections; Suicidal behavior; Discrimination; Psychology of HIV-positive persons; PSYCHOLOGICAL aspects; HIV-associated lipodystrophy syndrome; France; discrimination; Keywords: suicide attempt; lipodystrophy; side-effects; suicide attempt

Drinking Patterns, Problems, and Motivations Among Collegiate Bisexual Women. - Bostwick, Wendy B.; McCabe, Sean Esteban; Horn, Stacey; Hughes, Tonda; Johnson, Timothy; Valles, Jesus Ramirez (Journal of American College Health, 2007)
Objective and Participants: The authors compared the drinking behaviors, motivations, and problems of collegiate bisexual women with those of heterosexual women (N = 2,788; n = 86 bisexual women). Methods: Data came from the 2003 Student Life Survey, a random population-based survey at a large midwestern university. The authors explored the hypothesis that bisexual women would be more likely than heterosexual women to report drinking motivations related to stress and coping as a result of sexual identity stigma. Results: They found that bisexual women drank significantly less than did heterosexual women. There were few differences between the 2 groups in drinking motivations and problems. Bisexual women reported a comparable number of problems related to their drinking but were significantly more likely to report contemplating suicide after drinking than were heterosexual women. Conclusions: More research is needed to understand the finding that despite lower levels of alcohol consumption, bisexual women reported a comparable number of drinking problems. College health educators and health care providers need to be aware of findings related to heightened suicidal risk among bisexual women. [ABSTRACT FROM AUTHOR]
Keywords: Substance use; Psychological aspects; BISEXUAL women; BISEXUAL college students; WOMEN college students; DRINKING behavior; DRINKING of alcoholic beverages; UNIVERSITIES & colleges; ALCOHOL; SUICIDAL ideation; bisexual women; college health; drinking motivations; drinking problems

Mental Health Problems among Lesbian, Gay, and Bisexual Youths Ages 14 to 21. - D'Augelli, Anthony R (Clinical Child Psychology & Psychiatry, 2002)
The mental health problems of lesbian, gay, and bisexual (1gb) youths were studied using a sample of 542 youths from community settings. Information about the development of sexual orientation, problems related to sexual orientation, parents' reactions, and victimization based on sexual orientation was related to mental health symptoms and suicidality. Lesbian, gay, and bisexual youths were found to demonstrate more symptoms than a comparison group of adolescents. Over onethird of the sample reported a past suicide attempt. More symptoms were related to parents not knowing about youths' sexual orientation or with both parents having negative reactions to youths' sexual orientation. More than three-quarters had been verbally abused because of their sexual orientation, and 15 percent reported physical attacks. More than one-third said they had lost friends because of their sexual orientation. Youths who had experienced more victimization and who had lost friends reported more mental health symptoms. Mental health professionals are urged to attend to the distinct problems of these youths, especially dealing with conflicts with families and peers. [ABSTRACT FROM AUTHOR]
Keywords: Lesbians; Gay people; Bisexuals; Mental health

Lesbian, Gay, Bisexual, Sexual-Orientation Questioning Adolescents Seeking Mental Health Services: Risk Factors, Worries and Desire to Talk About Them. - Ciro, Dianne; Surko, Michael; Bhandarkar, Kalpana; Helfgott, Nora; Peake, Ken; Epstein, Irwin (Social Work in Mental Health, 2005)
Lesbian, gay, bisexual, and sexual-orientation questioning (LGBQ) adolescents have many of the same health needs as straight adolescents. In addition, they must learn to manage a stigmatized identity that may create confusion, anxiety, and emotional turbulence for them. Beyond stigma, LGBQ youth are often found to be at higher risk for substance abuse, violence, depression, suicide, and sexual health problems. Based on responses given by urban adolescents seeking mental health services to a clinical self-assessment questionnaire (Adquest), this article examines the relationship between sexual identity and risk factors related to safety, health, sex, substance use, family and friends, worries, and their desire to talk about these in counseling. Findings indicate that LGBQ youth are at higher risk than straights, and express greater desire to talk about substance use, health, their personal lives, and their friends. Mental health practitioners working with these young persons must properly assess and address their risks by creating a sense of community and safe environment for open discussion. [ABSTRACT FROM PUBLISHER]
Keywords: Sexual orientation; Lesbians; Gay people; Bisexuals; Substance abuse; Teenagers' health; adolescent; bisexual; gay; help-seeking; lesbian; mental health; questioning; risk; sexual identity; sexual orientation

Are transgender persons at higher risk for HIV than other sexual minorities? A comparison of HIV prevalence and risks. - Bockting W; Huang C; Ding H; Robinson B; Rosser BRS (International Journal of Transgenderism, 2005)
Recent studies have shown that transgender people are at high risk for HIV. Few studies, however, have directly compared the HIV risks and sexual health of transgender persons with that of other sexual minority populations. This study used baseline data of intervention studies targeting transgender persons, men who have sex with men, and women who have sex with women and men to compare their HIV risk behavior and sexual health. No significant differences were found between transgender persons and nontransgender men or women in consistent condom use or attitudes toward condom use. Transgender persons were less likely to have multiple partners and more likely to be monogamous than men who have sex with men; no differences were found between transgender persons and the women in this respect. When combining data on condom use, monogamy, and multiple partners, transgender persons did not differ from either nontransgender group in their overall risk for HIV. Transgender persons were less likely than the men or the women to have been tested for HIV. With regard to HIV prevalence, 17% of the men compared to only one transgender person and none of the women reported being HIV-positive. Transgender persons were also less likely than men who have sex with men to use drugs; no differences were found in the use of alcohol. However, with regard to mental health, transgender persons were more likely than the men to have experienced depression and more likely than men or women to have considered or attempted suicide. Finally, transgender persons reported the lowest levels of support from family and peers. Thus, in our sample, transgender persons appear to be at lower risk for HIV but at higher risk for mental health concerns than men who have sex with men. Remarkably few differences were found between transgender persons and women who have sex with women and men-a finding which might reflect the impact of social stigma on sexual health and have implications for the design of future HIV/STI prevention efforts. [ABSTRACT FROM AUTHOR]

Suicide Attempts Among Gay and Bisexual Men: Lifetime Prevalence and Antecedents. - Paul, Jay P.; Catania, Joseph; Pollack, Lance; Moskowitz, Judith; Canchola, Jesse; Mills, Thomas; Binson, Diane; Stall, Ron (American Journal of Public Health, 2002)
Objectives. We examined lifetime prevalence of suicide attempts and psychosocial correlates in a large population-based sample of men who have sex with men (MSM). Methods. A telephone probability sample of US urban MSM (n=2881) were interviewed between November 1996 and February 1998. Results. Twenty-one percent had made a suicide plan; 12% had attempted suicide (almost half of those 12% were multiple attempters). Most who attempted suicide made their first attempt before age 25. Although prevalence of parasuicide (i.e., attempted suicide) has remained constant across birth cohorts, mean age at initial attempts has declined. Conclusions. MSM are at elevated risk for suicide attempts, with such risk clustered earlier in life. Some risk factors were specific to being gay or bisexual in a hostile environment. (Am J Public Health. 2002;92:1338-1345) [ABSTRACT FROM AUTHOR]
Keywords: SUICIDAL behavior; PARASUICIDE; GAYS; BISEXUAL men; PSYCHOSOCIAL factors

Primary Care for Lesbians and Bisexual Women. - Mravcak, Sally A. (American Family Physician, 2006)
For the most part, lesbians and bisexual women face the same health issues as heterosexual women, but they often have difficulty accessing appropriate care. Physicians can improve care for lesbians and bisexual women by acknowledging the potential barriers to care (e.g., hesitancy of physicians to inquire about sexual orientation and of patients to disclose their sexual behavior) and working to create a therapeutic physician-patient relationship. Taking an inclusive and nonjudgmental history and being aware of the range of health-related behaviors and medico-legal issues pertinent to these patients enables physicians to perform relevant screening tests and make appropriate referrals. Some recommendations, such as those for screening for cervical cancer and intimate partner violence, should not be altered for lesbians and bisexual women. Considerations unique to lesbians and bisexual women concern fertility and medico-legal issues to protect familial relationships during life changes and illness. The risks of suicidal ideation, self-harm, and depression may be higher in lesbians and bisexual women, especially those who are not open about their sexual orientation, are not in satisfying relationships, or lack social support. Because of increased rates of nulliparity, the risks of conditions such as breast and ovarian cancers also may be higher. The comparative rates of alcohol and drug use are controversial. Smoking and obesity rates are higher in lesbians and bisexual women, but there is no evidence of an increased risk of cardiovascular disease. [ABSTRACT FROM AUTHOR]
Keywords: PRIMARY care (Medicine); LESBIANS; MEDICAL care; BISEXUAL women; MEDICAL care; MEDICAL care; AMBULATORY medical care

An Exploratory Study of Correlates, Onset, and Offset of Non-Suicidal Self-Injury. - Deliberto, TaraL.; Nock, MatthewK. (Archives of Suicide Research, 2008)
The study of non-suicidal self-injury (NSSI) has focused largely on identifying diagnostic correlates and the functions of this behavior; however, little is known about the broader range of factors related to NSSI. We examined a wide array of factors hypothesized to correlate with non-suicidal self-injury (NSSI) and provided a qualitative analysis of adolescents' self-reported motivations for starting and stopping this behavior. Participants were 64 adolescents with a history of NSSI and 30 comparison adolescents without such a history matched on age, sex, and ethnicity recruited from the community and assessed during one laboratory visit. The presence of NSSI was associated with a family history of suicidal ideation, violence, and drug and alcohol abuse, but not with more general forms of psychopathology. NSSI also was associated with the presence of in utero complications, the occurrence of non-injurious repetitive behaviors during childhood, and endorsement of a homosexual or bisexual orientation. Self-injurers reported getting the idea to self-injure from peers (38%) more often than any other source, and most (78%) reported at least one reason for wanting to stop self-injury. Less than half were currently receiving treatment. This exploratory study provides new information about the correlates of NSSI that has implications for research and clinical work in this area. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal ideation; Self-destructive behavior; Suicidal behavior; Pathological psychology; Homosexuality; Behaviorism (Psychology); Behavior modification; correlates; onset; self-harm; self-injury; self-mutilation; treatment

Ten years of lesbian health survey research in the UK West Midlands. - Meads, Caherine; Buckley, Emily; Sanderson, Paul (BMC Public Health, 2007)
Background: Very little is known about the physical health needs of lesbian and bisexual women in the UK; most research has looked at mental or sexual health only. This article reports the results of four surveys carried out in the West Midlands between 1995 and 2005. Methods: The first two surveys were conducted in 1995-6 by a volunteer group, with participants from a lesbian health conference (n = 69) and in a convenience sample from a wide range of relevant groups and venues (n = 354). The second two surveys were commissioned by the West Midlands South Strategic Health Authority in partnership with the Gay Men's Health Network and were conducted in 2002 (n = 449) and 2005 (n = 166) and again used convenience sampling methods including the internet. Results: The mean age of respondents varied between 29-33 years and 5-7% were from a nonwhite ethnic background. The smoking rates varied from 42% o 55%, being twice the West Midlands regional average of 21% for women aged 16 or more. Similarly, problems with alcohol were reported in 25-37% of respondents, higher than the West Midlands regional average of 7% for women aged 16+. The prevalence of any mental health problem varied between 31-35% and any suicide attempt between 20-31%. Only 29-45% had revealed their sexual orientation to their GP and of these, approximately 50% had experienced a positive reaction. Conclusion: The results suggest health needs that current UK health services may not be meeting. There is a need to identify and target specific health measures for lesbians and bisexual women in order to ensure improved physical and mental health in the longer term. [ABSTRACT FROM AUTHOR]

The Effects of Sexual Orientation, Gender Identity, and Gender Role on the Mental Health of Women in Taiwan's T-Po Lesbian Community. - Mei-Fun Kuang; Mathy, Robin M.; Carol, Helen M.; Nojima, Kazuhiko (Journal of Psychology & Human Sexuality, 2003)
We obtained via the Internet a convenience sample of Taiwanese heterosexual (n = 287) and sexual minority females (n = 260). A significantly greater percentage of sexual minorities (lesbian and bisexual females) than heterosexuals reported they had used tobacco or alcohol. Relative to heterosexuals, sexual minorities were significantly more likely to report a serious suicide attempt. Overall, gender identity (masculine, feminine, and androgynous) and gender role (butch, femme, and pure or undifferentiated) were poor discriminators of lesbian mental health. Differences between sexual minorities and heterosexuals were more robust than were the variations in gender identities and gender roles among lesbian and bisexual women. We discuss the implications of these findings for further clinical research. [ABSTRACT FROM AUTHOR]
Keywords: Mental health; Gender identity; Minorities; Lesbians; Lesbian community; Taiwan; Gender; lesbian; mental health; suicide attempt

Violence and Sexual Minority Youth. - Lock, James (Journal of School Violence, 2002)
Among the most maligned and harassed students in high schools are those who are perceived not to fit the norms for sexual behavior. These include gay and lesbian students, bisexual students, transgendered students, effeminate heterosexual males, and masculine-acting heterosexual females. Together these students are the targets of a wide range of negative behaviors from subtle exclusion to physical assault. In addition, many develop negative attitudes towards themselves which put them at increased risk for self-harm and suicide. The origin of these attitudes and behaviors is societal homophobia that fuels social aggression against this stigmatized group. Although challenging, educators can assist in undermining the effects of homophobia on sexual minorities through teaching tolerance, sponsoring support groups that address these issues, and providing educational opportunities about sexual minority youth. [ABSTRACT FROM PUBLISHER]
Keywords: School violence; LGBTQ+ students; Homophobia; High schools; Student attitudes; Aggression (Psychology) in youth; Gay; high school; lesbian; violence

Sexual Orientation and Self-Harm in Men and Women. - Skegg, Keren; Nada-Raja, Shyamala; Dickson, Nigel; Paul, Charlotte; Williams, Sheila (American Journal of Psychiatry, 2003)
Objective: Recent studies of homosexual people have found higher rates of nonfatal suicidal behavior than among heterosexuals. The purpose of this study was to determine associations between selfharm and sexual orientation for men and women separately, defining sexual orientation by sexual attraction rather than by behavior. Method: In a birth cohort of 1,019 New Zealand young adults eligible to be interviewed at age 26 years, 946 participated in assessments of both sexual attraction and self-harm. Results: Both women and men who had experienced same-sex attraction had higher risks of self-harm. The odds ratios for suicidal ideation in the past year were 3.1 for men and 2.9 for women. Odds ratios for ever having deliberately selfharmed were 5.5 for men and 1.9 for women. Men with same-sex attraction were also significantly more likely to report having attempted suicide. In both sexes, a greater degree of same-sex attraction predicted increasing likelihood of self-harm, with over one-third of men and women with persistent major same-sex attraction reporting this. Men with even a minor degree of same-sex attraction had high rates of self-harm and resulting physical injury. One-quarter of deliberate self-harm among men and one-sixth among women was potentially attributable to same-sex attraction. Conclusions: This study provides evidence of a link between increasing degrees of same-sex attraction and self-harm in both men and women, with the possibility of some difference between the sexes that needs to be explored further. [ABSTRACT FROM AUTHOR]

Avoiding shame: young LGBT people, homophobia and self-destructive behaviours. - McDermott, Elizabeth; Roen, Katrina; Scourfield, Jonathan (Culture, Health & Sexuality, 2008)
This paper reports on findings from qualitative research conducted in the UK that sought to explore the connections between sexual identities and self-destructive behaviours in young people. International evidence demonstrates that there are elevated rates of suicide and alcohol abuse amongst lesbian, gay, bisexual and transgender (LGBT) youth. Rarely included in this body of research are investigations into young LGBT people's views and experiences of self-destructive behaviours. Data from interviews and focus groups with young LGBT participants suggest a strong link between homophobia and self-destructive behaviours. Utilising a discourse analytic approach, we argue that homophobia works to punish at a deep individual level and requires young LGBT people to manage being positioned, because of their sexual desire or gendered ways of being, as abnormal, dirty and disgusting. At the centre of the complex and multiple ways in which young LGBT people negotiate homophobia are 'modalities of shame-avoidance' such as: the routinization and minimizing of homophobia; maintaining individual 'adult' responsibility; and constructing 'proud' identities. The paper argues that these strategies of shame-avoidance suggest young LGBT people manage homophobia individually, without expectation of support and, as such, may make them vulnerable to self-destructive behaviours. (English) [ABSTRACT FROM AUTHOR]
Keywords: Shame; LGBTQ+ people; Homophobia; Gender identity; Self-destructive behavior; Qualitative research; homophobia; sexuality; shame; suicide; youth

Gynecologic Care of the Female-to-Male Transgender Man - Dutton, Lauren; Koenig, Karel; Fennie, Kristopher (Journal of Midwifery & Women's Health, 2008)
Transgender men are a vulnerable population whose health care needs have been difficult to identify because of limited research and an inability to identify the population. Limited evidence suggests that transgender men are at increased risk of having polycystic ovarian syndrome, contracting HIV, experiencing violence, and committing suicide. This qualitative study, conducted through face-to-face interviews of a convenient sample, was a three-part interview containing a demographic and health questionnaire, the Norbeck Social Support Questionnaire, as well as the Health Care Relationship Trust Scale. Audio recordings and written notes were reviewed and common themes were identified via content analysis. Six self-identified transgender men between the ages of 19 and 45 years were enrolled in the study. Participants were at varying degrees of social and medical transition. Four major themes were identified: 1) receiving gynecologic care was perceived to be important; 2) breasts caused the most gender identity conflict; 3) transgender men struggle with revealing their gender identity to health care providers; and 4) the male/female boxes on health intake forms, as well as pronoun usage by medical staff, were barriers to receiving health care. This gynecologic health care needs assessment of transgender men begins to characterize the barriers transgender men face when seeking health care. [Copyright &y& Elsevier]
Keywords: Health of transgender people; Gender dysphoria; Medical needs assessment; Polycystic ovary syndrome; Sound recordings; cultural competency; gynecology; Pap smear; primary care; transgender; transsexual

Sexual minority youth perspectives on the school environment and suicide risk interventions: a qualitative study. - Rutter PA; Leech NL (Journal of Gay & Lesbian Issues In Education, 2006)
This qualitative study explored the experiences of five gay, lesbian, and bisexual adolescents' perspectives on their schools' acceptance of their sexual orientation, and perceptions of these schools' approach to suicide risk intervention. Focus groups were tape recorded, transcribed, and analyzed through constant comparative analysis. Themes that emerged from the data included participants feeling judged by school counselors and teachers, feeling unsafe at school, and concerned about school staff's response to suicide risk and interventions. Implications for school counselors, teachers and administrators are discussed. [ABSTRACT FROM AUTHOR]

Well-Being Among Same-Sex- and Opposite-Sex-Attracted Youth at School. - Rivers, Ian; Noret, Nathalie (School Psychology Review, 2008)
In this study, 53 students who reported being solely or primarily attracted to members of the same sex were matched with 53 peers who reported being attracted solely to members of the opposite sex on various demographic factors as well as exposure to bullying at school. Data relating to tobacco and alcohol use, drug use, health risk behaviors, concerns and sources of social support, interpersonal sensitivity, depression, anxiety, hostility, suicide ideation, loneliness, and concentration were analyzed. Results indicated that same-sex-attracted students reported drinking alcohol alone more than opposite-sex-attracted peers; however, they were no more likely to engage in health-risk behaviors, or use Class 1 and 2 drugs. They were more likely to report being worded about being lesbian or gay, and were more likely to seek support from a member of school staff than opposite-sex-attracted peers. In terms of psychological well-being, same-sex-attracted students scored significantly higher on a hostility subscale when compared to opposite-sex-attracted peers and were more likely to report feeling lonely. These results suggest that the management of reactive aggression or hostility toward others may be a key determinant of healthy gay, lesbian, and bisexual development. [ABSTRACT FROM AUTHOR]
Keywords: Sex research; Homosexuality; Sexual intercourse; School bullying; Teenagers; Psychological stress; Lesbianism; Drug abuse; Alcohol research; School children; Social network research; Bullying research

Mental Health and Substance Use Disorders Among Latino and Asian American Lesbian, Gay, and Bisexual Adults. - Cochran, Susan D.; Mays, Vickie M.; Ortega, Alexander N.; Alegria, Margarita; Takeuchi, David (Journal of Consulting & Clinical Psychology, 2007)
Growing evidence suggests that lesbian, gay, and bisexual adults may be at elevated risk for mental health and substance use disorders, possibly due to anti-gay stigma. Little of this work has examined putative excess morbidity among ethnic/racial minorities resulting from the experience of multiple sources of discrimination. The authors report findings from the National Latino and Asian American Survey (NLAAS), a national household probability psychiatric survey of 4,488 Latino and Asian American adults. Approximately 4.8% of persons interviewed identified as lesbian, gay, bisexual, and/or reported recent same-gender sexual experiences. Although few sexual orientation-related differences were observed, among men, gay/bisexual men were more likely than heterosexual men to report a recent suicide attempt. Among women, lesbian/bisexual women were more likely than heterosexual women to evidence positive 1-year and lifetime histories of depressive disorders. These findings suggest a small elevation in psychiatric morbidity risk among Latino and Asian American individuals with a minority sexual orientation. However, the level of morbidity among sexual orientation minorities in the NLAAS appears similar to or lower than that observed in population-based studies of lesbian, gay, and bisexual adults. [ABSTRACT FROM AUTHOR]
Keywords: Mental illness; LGBTQ+ people; Public health; Hispanic Americans; Asian Americans; Reporting of diseases; Racial minorities; Health surveys; Psychiatric treatment; Asian American; bisexual; gay; Latino; psychiatric epidemiology

The transsexual: what about the future? - Michel, A.; Ansseau, M.; Legros, J.J.; Pitchot, W.; Mormont, C. (European Psychiatry, 2002)
Since the 1950s, sexual surgical reassignments have been frequently carried out. As this surgical therapeutic procedure is controversial, it seems important to explore the actual consequences of such an intervention and objectively evaluate its relevance. In this context, we have carried out a review of the literature. After looking at the methodological limitations of follow-up studies, the psychological, sexual, social, and professional futures of the individuals subject to a transsexual operation are presented. Finally, prognostic aspects are considered. In the literature, follow-up studies tend to show that surgical transformations have positive consequences for the subjects. In the majority of cases, transsexuals are very satisfied with their intervention and any difficulties experienced are often temporary and disappear within a year after the surgical transformation. Studies show that there is less than 1% of regrets, and a little more than 1% of suicides among operated subjects. The empirical research does not confirm the opinion that suicide is strongly associated with surgical transformation. [Copyright &y& Elsevier]
Keywords: Transsexuals; Sex reassignment surgery; Follow-up; Literature review; Transsexualism

Contested conclusions: claims that can (and cannot) be made from the current research on gay, lesbian, and bisexual teen suicide attempts. - Saewyc EM (Journal of LGBT Health Research, 2007)
As the press and communities interpret research reports, their conclusions may go far beyond a study's evidence, especially if groups are trying to support politically-motivated claims about controversial causes and solutions to health problems. Few research designs can "prove" cause and effect, especially in population health research. However, some designs are better than others at identifying influences on health. Several strategies can help non-researchers evaluate studies critically. Using these statistics, this paper explores claims that can (and cannot) be made about causes of suicide attempts among gay, lesbian, and bisexual adolescents, based on current research evidence available. [ABSTRACT FROM AUTHOR]

GAY ADOLESCENTS AND SUICIDE: UNDERSTANDING THE ASSOCIATION. - Li Kitts, Robert (Adolescence, 2005)
Suicide among gay* adolescents is a major public health concern, but it is still under-emphasized within mainstream healthcare. This article brings together information garnered from past studies, articles, and experiences to create a more in-depth understanding of why gay adolescents are at a higher risk for suicide. By creating a better understanding, this article attempts to push forward the significance of this issue and encourages physicians to take a more active role in suicide prevention. The article initially explores why issues involving homosexuality are seldom discussed and provides evidence for an increased risk in suicide among gay adolescents. By addressing major psychosocial issues faced by gay adolescents, it spends the majority of time facilitating an understanding of the increased risk. *In this article "gay" refers to homosexual males and females, and bisexuals unless otherwise indicated. [ABSTRACT FROM AUTHOR]
Keywords: GAY teenagers; TEENAGERS -- Suicidal behavior; HOMOSEXUALITY; SUICIDAL behavior -- Risk factors; MEDICAL care

Mental Health Needs of Sexual Minorities in Jamaica. - White, YohannR. G.; Barnaby, Loraine; Swaby, Antoneal; Sandfort, Theo (International Journal of Sexual Health, 2010)
This study examined the prevalence of Axis I disorders and associated risk factors in a sample of sexual minority men and women in Jamaica, a country that is widely known for its high societal rejection of homosexuality. Poor relationships with family, negative or abusive experiences related to one's sexual orientation, and greater openness about one's sexual orientation were independent risk factors for Axis I disorders. Prevention of mental disorders in sexual minorities in Jamaica should focus on rebuilding family support and promoting social acceptance of sexual minorities. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; PSYCHOLOGY; Homophobia; Mental illness risk factors; Minorities; Jamaica; Depression; LGBT; mental health; minority; stress; suicide

Disclosure of Sexual Orientation, Victimization, and Mental Health Among Lesbian, Gay, and Bisexual Older Adults. - D'Augelli, Anthony R.; Grossman, Arnold H. (Journal of Interpersonal Violence, 2001)
This study examined the lifetime victimization based on sexual orientation of 416 lesbian, gay, or bisexual (LGB) older adults aged 60 or older. Participants reported the ages at which they were aware of their sexual orientation, self-identified as LGB, and first disclosed their sexual orientation to anyone. Frequencies of nine kinds of verbal and physical victimization were obtained. Nearly three quarters reported some kind of sexual orientation victimization. Men reported more overall victimization than women. The more open participants were about their sexual orientation and the less time they spent before disclosing their sexual orientation, the more victimization they reported. Physical victimization was associated with earlier achievement of sexual orientation milestones and more time being open about one's sexual orientation. Participants who had been physically attacked reported lower self-esteem, more loneliness, and poorer mental health than others. More suicide attempts were reported among those older adults who were physically attacked. [ABSTRACT FROM AUTHOR]
Keywords: Sexual Assault Assessment; Victim Profile and Diagnosis

The relationship between suicide risk and sexual orientation: Results of a population-based study. - Remafedi, Gary; French, Simone; Story, Mary; Resnick, Michael D.; Blum, Robert (American Journal of Public Health, 1998)
Objectives. This study examined the relationship between sexual orientation and suicide risk in a population-based sample of adolescents. Methods. Participants were selected from a cross-sectional, statewide survey of junior and senior public high school students. All males (n = 212) and females (n = 182) who described themselves as bisexual/homosexual were compared with 336 gender-matched heterosexual respondents on three outcome measures: suicidal ideation, intent, and self-reported attempts. Logistic regression analyses were used to examine the association between sexual orientation and outcome measures with adjustment for demographic characteristics. Results. Suicide attempts were reported by 28.1% of bisexual/ homosexual males, 20.5% of bisexual/ homosexual females, 14.5% of heterosexual females, and 4.2% of heterosexual males. For males, but not females, bisexual/homosexual orientation was associated with suicidal intent (odds ratio [OR] = 3.61; 95% confidence interval [CI] = 1.40, 9.36) and attempts (OR = 7.10; 95% CI = 3.05, 16.53). Conclusions. There is evidence of a strong association between suicide risk and bisexuality or homosexuality in males. [ABSTRACT FROM AUTHOR]
Keywords: SEXUAL orientation; TEENAGERS -- Suicidal behavior; HEALTH surveys; SELF-destructive behavior; ADOLESCENT psychology

Characteristics of HIV patients who attempt suicide. - Roy, A (Acta Psychiatrica Scandinavica, 2003)
Objective: To examine the risk factors for suicidal behaviour in human immunodeficiency virus (HIV) positive patients. Method: HIV substance dependent positive patients who had attempted suicide were compared with HIV substance dependent positive patients who had never attempted suicide for suicide risk factors. Results: Among the 149 HIV positive patients examined almost half had attempted suicide. Significantly more HIV positive patients who had attempted suicide were female. Attempters were significantly younger than non-attempters. Significantly more of the attempters had a family history of suicidal behaviour. Attempters also reported significantly more childhood trauma, scored significantly higher for neuroticism, had experienced significantly more comorbidity with depression, and more of them had received antidepressant medication. Conclusion: These data suggest that both distal and proximal risk factors are involved in suicidal behaviour in HIV positive substance dependent patients. [ABSTRACT FROM AUTHOR]
Keywords: ATTEMPT; factors; human immunodeficiency virus; risk; suicide

Gay and Lesbian Youth: Contributing Factors to Serious Attempts or Considerations of Suicide. - Hammelman, Tracie L. (Journal of Gay & Lesbian Psychotherapy, 1993)
This is a study of gay and lesbian youths' tendencies for suicide and the extent to which these tendencies are influenced by sexual orientation, violence, age, substance abuse, physical or emotional abuse, family rejection, or gender. Based on a sample of 48 respondents, nearly one-half seriously considered suicide while one- third actually attempted suicide. Close to three-quarters of this population cited sexual orientation as some or most of the reason for their suicide consideration or attempt with the majority revealing that they had done so at age 17 or before. Fifty percent or more of those who (1) had a substance abuse problem, (2) were physically or emotionally abused, or (3) experienced family rejection, reported that sexual orientation was the main reason for these problems. These results are clinically significant for therapists who work with this population. The mere existence of suicide considerations or attempts because of sexual orientation calls for a proactive stance which includes conducting a thorough psycho-social assessment, performing crisis intervention and assisting youth to increase their coping mechanisms. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Lesbians -- Attitudes; Sexual orientation; Substance abuse; Psychological adaptation; Drug use testing; Homosexuality and Homosexuals; SEXUAL ATTITUDES, BEHAVIOR, AND PROBLEMS

Suicidality in a venue-based sample of young men who have sex with men. - Remafedi, Gary (Journal of Adolescent Health, 2002)
<ST>Purpose</ST>To examine the incidence, prevalence, and characteristics of suicide attempts in a unique, venue-based sample of young men who have sex with men (YMSM). <ST>Methods</ST>Eligible participants were 15–25-year-old men who were living in a major metropolitan area (Minneapolis/St. Paul, Minnesota) and had sex with men within 12 months of the interview. A total of 255 subjects were randomly sampled from popular venues for a structured, 20-min interview (1999) that included four items regarding suicide intentions and attempts. Data were analyzed using bivariate and multivariate tests of statistical significance. <ST>Results</ST>Eighty-six percent of eligible individuals completed the survey. One-third of all respondents reported at least one suicide attempt, and 4.7% attempted suicide in the past year. Although suicide attempts were more prevalent among African-Americans and urban residents; only school enrollment was significantly associated with attempts in the multivariate analysis (odds ratio = .55, 95% confidence interval = .31, .97). <ST>Conclusions</ST>This study corroborates the findings of prior studies of high rates of suicide attempts among YMSM. In addition, it demonstrates that attempts are more prevalent among out-of-school youths. [Copyright 2002 Elsevier]
Keywords: Adolescence; Homosexuality; Sexuality; Suicide

School social work with gay, lesbian and bisexual students: the case of Fairfax County. - Batelaan, Sanderijn (Intercultural Education, 2000)
Teenagers who are coming to terms with their sexual orientation are a high-risk population in terms of substance abuse and suicide. They are often in need of counseling, especially when the school climate is hostile towards lesbian, gay and bisexual (LGB) students. School officials in Fairfax County, Virginia, are reluctant to address the issue of sexual orientation, and school social workers must abide by the policies of the school. Community resources for LGB teenagers are scarce in this affluent county. It is the author's opinion that school social workers have an obligation to be advocates for oppressed populations, including GLB youth, and should take a leading role in promoting a climate of safety, acceptance and freedom from harassment. [ABSTRACT FROM AUTHOR]
Keywords: Social work with LGBTQ youth; Social services; School social work; Virginia; Fairfax County (Va.); United States

Trying to Hide: A Cross-National Study of Growing Up for Non-Identified Gay and Bisexual Male Youth. - Carragher, Daniel J; Rivers, Ian (Clinical Child Psychology & Psychiatry, 2002)
Research shows that 'out' lesbian, gay and bisexual youth often experience longterm and repeated abuse when they are growing up. Currently, very little is known about the experiences of those youth who do not disclose their sexual orientation at school, but also face discrimination because of their perceived sexual orientation. A cross-cultural comparison of two groups of gay and bisexual men from the US and UK who were non-identified at school was conducted by the authors. Quantitative and qualitative data were analysed focusing upon recollections of sexual orientation developmental milestones, the nature of the victimization experienced in adolescence, alternative behaviours adopted for self-preservation and suicidal ideation. In addition, current functioning in adulthood was also assessed, and measures relating to personal homonegativity and sexual behaviour were compared. The results suggested that there were variations in the nature and correlates of the victimization experienced by US and UK gay and bisexual males during adolescence, including the alternative behaviours adopted for selfpreservation. As adults, UK males were more likely to report feelings of internalized homonegativity, however, US males were proportionally more likely to engage in transient sexual encounters. The implications of these findings are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Gay teenagers; Lesbian teenagers; Abuse of LGBTQ+ people; Bisexuals; Teenagers -- Abuse of; Abuse of teenage girls

Effects of at-school victimization and sexual orientation on lesbian, gay, or bisexual youths’ health risk behavior. - Bontempo, Daniel E.; D’Augelli, Anthony R. (Journal of Adolescent Health, 2002)
Purpose: To examine the link between victimization at school and health risk behaviors using representative data comparing lesbian, gay, and bisexual (LGB) youths and heterosexual youths.Methods: Data from the 1995 Youth Risk Behavior Survey taken in Massachusetts and Vermont were examined. This sample included 9188 9th through 12th grade students; 315 of these students were identified as LGB. Analyses of variance were used to examine health risk behaviors by sexual orientation by gender by victimization level.Results: The combined effect of LGB status and high levels of at-school victimization was associated with the highest levels of health risk behaviors. LGB youths reporting high levels of at-school victimization reported higher levels of substance use, suicidality, and sexual risk behaviors than heterosexual peers reporting high levels of at-school victimization. Also, LGB youths reporting low levels of at-school victimization reported levels of substance use, suicidality, and sexual-risk behaviors that were similar to heterosexual peers who reported low at-school victimization.Conclusions: The findings provide evidence that differences in health risks among LGB youth are mediated by victimization at school. Such victimization of LGB youth is associated with health risk behaviors. [Copyright 2002 Elsevier]
Keywords: Adolescents; Gay; Gender differences; Health risk factors; Lesbian; Sexual orientation; Victimization; Youth

Lifetime Risk Factors for HIV/Sexually Transmitted Infections Among Male-to-Female Transgender Persons. - Nuttbrock, Larry; Hwahng, Sel; Bockting, Walter; Rosenblum, Andrew; Mason, Mona; Macri, Monica; Becker, Jeffrey (JAIDS: Journal of Acquired Immune Deficiency Syndromes, 2009)
The article presents a study on the HIV disease and other sexually transmitted infections lifetime risk factors among male-to-female (MTF) transgender persons. It notes that using the life chart interview, it was drawn that such diseases were low among white Americans and very high among Hispanics and African Americans, wherein expression of transgenderism was the most common predictor of infections. It suggests that infection prevention programs must focus on Hispanics and African Americans.
Keywords: HIV infection risk factors; Trans women; Transgenderism; Diseases; Sexually transmitted disease risk factors; Americans; Hispanic Americans; Diseases in African Americans; Prevention of communicable diseases; Disease risk factors; life chart interview; major depression; male-to-female transgender persons; suicidality

A Portrait of Risk Behavior among Gay, Lesbian, and Bisexual Youth in a GLB Youth Group in Suburban/Rural Wisconsin. - Van Voorhis, Carmen R. Wilson; Vogt, Kimberly A. (Sociological Imagination, 2003)
Gay, lesbian, and bisexual (GLB) youth attending a GLB youth group completed the Youth Risk Behavior Survey (YRBS), the Center for Epidemiological Studies Depression Scale (CESD), and the Social Provisions Scale (SPS). Z-tests were used to compare proportions of GLB youth engaging in risky behaviors to Wisconsin and National youth engaging in the behaviors. Compared to other youth, GLB youth are more depressed and suicidal, drink at earlier ages, and report higher rates of occasional smoking, marijuana, cocaine experimentation and cocaine use, and sexual activity. Alternatively, GLB youth report lower rates of current drinking, binge drinking, and substance use before sexual activity than other youth. Interestingly, GLB youth report the same numbers of opposite sex partners as other youth. Finally, GLB youth report high levels of depression as measured by the CESD. [ABSTRACT FROM AUTHOR]
Keywords: Gay people; Lesbians; Bisexuals; Drug abuse; Substance abuse; Mental depression

Mental health in sexual minorities: Recent indicators, trends, and their relationships to place in North America and Europe - Lewis, Nathaniel M. (Health & Place, 2009)
Abstract: This meta-analysis featuring 12 national adult studies and 16 state/regional youth studies of sexuality and mental health finds that sexual minorities—as a likely consequence of place-contingent minority stress—experience mental health outcomes such as depression, anxiety, and suicide ideation much more frequently than their heterosexual counterparts. By interrogating the geographic variations in the findings, such as high rates of poor mental health outcomes in the United Kingdom, large gay-heterosexual disparities in the Netherlands, and lower and improving rates of both outcomes and risk factors in Vermont and British Columbia, this study asserts that policy regimes, health programming, and the ways in which sexual minorities are constructed in places all contribute to their mental health. [Copyright &y& Elsevier]
Keywords: Mental health; Sexual minorities; Psychological stress; Health of gay people; Meta-analysis; Health outcome assessment; Health programs; Great Britain; North America; Europe; Gay; Place determinants; Queer; Sexuality

Gay, lesbian, and bisexual student suicide. - McFarland, William P. (Professional School Counseling, 1998)
; Offers an explanation for the statistical profile of suicidal gay, lesbian and bisexual youth. Background; Suicide rates in all youth; Suicide among sexual minority youth; Risk factors; Developmental guidance program response.

Theoretical perspectives on suicide in gay men with AIDS. - McNaught, Angela; Spicer, John (Social Science & Medicine, 2000)
; Explores three concepts from theoretical literature on suicide among gay men with AIDS. Search for meaning in the midst of suffering; Notion of unendurable psychological pain and hopelessness; Demonstration on how concepts can incorporate experiences of gay men with AIDS.
Keywords: AIDS (Disease) -- Patients; GAY men; PSYCHOLOGY; SUICIDAL behavior

Is Sexual Orientation Related to Mental Health Problems and Suicidality in Young People? - Fergusson, David M.; Horwood, L. John; Beautrais, Annette L. (Archives of General Psychiatry, 1999)
Background: This study examines the extent to which gay, lesbian, and bisexual young people are at increased risk of psychiatric disorder and suicidal behaviors using data gathered on a New Zealand birth cohort studied to age 21 years. Methods: Data were gathered during the course of the Christchurch Health and Development Study, a 21-year longitudinal study of a birth cohort of 1265 children born in Christchurch, New Zealand. At 21 years of age, 1007 sample members were questioned about their sexual orientation and relationships with same-sex partners since the age of 16 years. Twenty-eight subjects (2.8%) were classified as being of gay, lesbian, or bisexual sexual orientation. Over the period from age 14 to 21 years, data were gathered on a range of psychiatric disorders that included major depression, generalized anxiety disorder, conduct disorder, and substance use disorders. Data were also gathered on suicidal ideation and suicide attempts. Results: Gay, lesbian, and bisexual young people were at increased risks of major depression (odds ratio [OR], 4.0; 95% confidence interval [CI], 1.8-9.3), generalized anxiety disorder (OR, 2.8; 95% CI, 1.2-6.5), conduct disorder (OR, 3.8; 95% CI, 1.7-8.7), nicotine dependence (OR, 5.0; 95% CI, 2.3-10.9), other substance abuse and/or dependence (OR, 1.9; 95% CI, 0.9-4.2), multiple disorders (OR, 5.9; 95% CI, 2.4-14.8), suicidal ideation (OR, 5.4; 95% CI, 2.4-12.2), and suicide attempts (OR, 6.2; 95% CI, 2.7-14.3). Conclusions: Findings support recent evidence suggesting that gay, lesbian, and bisexual young people are at increased risk of mental health problems, with these associations being particularly evident for measures of suicidal behavior and multiple disorder. [ABSTRACT FROM AUTHOR]

HOPE AND RESILIENCE IN SUICIDE IDEATION AND BEHAVIOR OF GAY AND BISEXUAL MEN FOLLOWING NOTIFICATION OF HIV INFECTION. - Siegel, Karolynn; Meyer, Ilan H. (AIDS Education & Prevention, 1999)
This article examines the narratives of gay men who contemplated or attempted suicide soon after they had learned of their HIV infection. Upon being notified that they tested positive for HIV people experience terror and confusion that may evoke thoughts of suicide or suicidal behaviors. Like others who test positive for HIV, gay men typically foresee a protracted struggle to cope with the disease and its psychosocial sequel. Intense fears about future suffering, disfigurement and dependency may arise and momentarily overwhelm the person, leading to suicidal thought or actions. Clearly, issues surrounding suicidal ideation and behavior are complex; the reasons for suicide were multifaceted and the coping tasks diverse. In reviewing the respondents' narratives on suicidality, researchers were impressed that through contemplating suicide many have found opportunities for growth and resilience. Following the existential perspective, researchers suggest that opportunity for growth is one important function of suicidality among people who learn that they have a life-threatening disease.
Keywords: Suicidal behavior; Self-destructive behavior; Gay men; Diagnosis of HIV infections; Suicide; Human behavior; Diseases

Homosexuality and Risk for Psychiatric Disorders. - Alexander, Christopher J. (Journal of Gay & Lesbian Social Services, 2002)
Social science researchers have traditionally found it difficult to obtain representative samples of gay men and lesbians. Still, this has not prevented some from making broad conclusions about the lives and mental status of homosexuals as a group. In recent months, two separate national studies have examined sexual attitudes and behaviors of adults and adolescents. Collectively, the sample size of males and females surveyed in these studies is in the thousands. Because the subjects in both studies were randomly selected, the findings were based on persons with a wide spectrum of sexual attitudes and behaviors. In many respects, these studies confirm some of the data from smaller studies. That is, homosexual orientation can be a risk factor for psychiatric disturbance for some men and women. In addition, adolescents struggling with issues related to sexual orientation, are two times more likely than their peers to consider or attempt suicide. [ABSTRACT FROM AUTHOR]
Keywords: Gay people; Lesbians; Sexual orientation; Psychiatry; Disease risk factors; Health surveys; anxiety; depression; Mental illness; substance abuse; suicide

Identification Without Intervention: Transforming the Anti-LGBTQ School Climate. - Adelman, Madelaine; Woods, Kathryn (Journal of Poverty, 2006)
How do students who recognize the negative effects of name-calling and harassment based on sexual orientation explain their lack of intervention? In this paper we document the anti-LGBTQ school climate as reported by gay and straight high school students involved in an intensive diversity awareness program. Then, drawing on qualitative survey data obtained from the same group of students, we ask why young people, more often than not, do not intervene when they face such circumstances in school. Students point to four areas of concern: institutional norms too risky to challenge; pragmatic rationales based on the ubiquitous nature of such remarks; personal worries about loss of social status; and finally, adult reinforcement of unacceptable student remarks. [ABSTRACT FROM AUTHOR]
Keywords: SCHOOL environment; STUDENTS; SEXUAL orientation; HIGH school students; GAY students; SOCIAL status; SCHOOLS; EDUCATION, Secondary; ANXIETY; anti-gay; bisexual; bullying; diversity awareness; gay; intervention; lesbian; School; school climate; sexual orientation; social change; transgender

LGB and Questioning Students in Schools: The Moderating Effects of Homophobic Bullying and School Climate on Negative Outcomes. - Birkett, Michelle; Espelage, Dorothy L.; Koenig, Brian (Journal of Youth & Adolescence, 2009)
Lesbian, gay, and bisexual students (LGB) and those questioning their sexual orientation are often at great risk for negative outcomes like depression, suicidality, drug use, and school difficulties (Elliot and Kilpatrick, How to Stop Bullying, A KIDSCAPE Guide to Training, ; Mufoz-Plaza et al., High Sch J 85:52–63, ; Treadway and Yoakam, J School Health 62(7):352–357, ). This study examined how school contextual factors such as homophobic victimization and school climate influence negative outcomes in LGB and questioning middle school students. Participants were 7,376 7th and 8th grade students from a large Midwestern county (50.7% Female, 72.7% White, 7.7% Biracial, 6.9% Black, 5.2% Asian, 3.7% Hispanic, and 2.2% reported “other”). LGB and sexually questioning youth were more likely to report high levels of bullying, homophobic victimization, and various negative outcomes than heterosexual youth. Students who were questioning their sexual orientation reported the most bullying, the most homophobic victimization, the most drug use, the most feelings of depression and suicidality, and more truancy than either heterosexual or LGB students. A positive school climate and a lack of homophobic victimization moderated the differences among sexual orientation status and outcomes. Results indicate that schools have the ability to lessen negative outcomes for LGB and sexually questioning students through creating positive climates and reducing homophobic teasing. [ABSTRACT FROM AUTHOR]
Keywords: Violence against LGBTQ+ people; School bullying; Homosexuality; Homophobia; Psychology; Gender identity -- Social aspects; School environment; Bullying; Middle school students; Moderators; School climate; Victimization

Women's Sexual Orientation and Health: Results from a Canadian Population-Based Survey. - STEELE, LEAH S.; ROSS, LORI E.; DOBINSON, CHERYL; VELDHUIZEN, SCOTT; TINMOUTH, JILL M. (Women & Health, 2009)
The current study sought to determine whether health status and health risk behaviors of Canadian women varied based on sexual identity. This was a cross-sectional analysis of data from the Canadian Community Health Survey: cycle 2.1, a national population-based survey designed to gather health data on a representative sample of over 135,000 Canadians including 354 lesbian respondents, 424 bisexual women respondents, and 60,937 heterosexual women respondents. Sexual orientation was associated with disparities in health status and health risk behaviors for lesbian and bisexual women in Canada. Bisexual women were more likely than lesbians or heterosexual women to report poor or fair mental and physical health, mood or anxiety disorders, lifetime STD diagnosis, and, most markedly, life-time suicidality. Lesbians and bisexual women were also more likely to report daily smoking and risky drinking than heterosexual women. In sum, sexual orientation was associated with health status in Canada. Bisexual women, in particular, reported poorer health outcomes than lesbian or heterosexual women, indicating this group may be an appropriate target for specific health promotion interventions. [ABSTRACT FROM AUTHOR]
Keywords: Gender identity; Heterosexuality; Mental health; Health status indicators; Health surveys; bisexual women; health status; health tatus; lesbian; mental health; risk behaviors; sexual orientation; women's health

Lifetime Prevalence of Suicide Symptoms and Affective Disorders Among Men Reporting Same-Sex Sexual Partners: Results From NHANES III. - Cochran, Susan D.; Mays, Vickie M. (American Journal of Public Health, 2000)
Objectives. This study examined lifetime prevalence of suicide symptoms and affective disorders among men reporting a history of same-sex sexual partners. Methods. In the third National Health and Nutrition Examination Survey, men aged 17 to 39 years were assessed for lifetime hi story of affective disorders and sexual behavior patterns. The study classified this subset of men into 3 groups: those reporting same-sex sexual partners, those reporting only female sexual partners, and those reporting no sexual partners. Groups were compared for histories of suicide symptoms and affective disorders. Results. A total of 2.2% (95% confidence interval [CI] = 1.3%, 3.1%) of men reported same-sex sexual partners. These men evidenced greater lifetime prevalence rates of suicide symptoms than men reporting only female partners. However. homosexually/bisexually experienced men were no more likely than exclusively heterosexual men to meet criteria for lifetime diagnosis of other affective disorders. Conclusions. These data provide further evidence of an increased risk for suicide symptoms among homosexually experienced men. Results also hint at a small, increased risk of recurrent depression among gay men, with symptom onset occurring, on average, during early adolescence. (Am J Public Health. 2000:90:573-578) [ABSTRACT FROM AUTHOR]
Keywords: SUICIDE; AFFECTIVE disorders; SAME-sex relationships; GAY male relationships; MEN -- Sexual behavior; GAY men

Family and Community Influences on the Social and Sexual Lives of Latino Gay Men. - Guarnero, Peter A. (Journal of Transcultural Nursing, 2007)
The purpose of this study was to explore the effect of family and community on the social and sexual lives of a group of Latino gay men living in a metropolitan area. A secondary analysis of four focus groups with 28 Latino gay men was conducted. Families had a difficult time acknowledging and supporting participants' homosexuality. Participants experienced racism, discrimination, and physical and verbal abuse as a result of their ethnicity and homosexuality. These negative effects contributed to their marginalization and made them vulnerable to depression and suicide. Health care professionals should be aware of the effect of family and culture on the social and sexual lives of Latino gay men so that they can intervene and direct the client to the services needed to manage depression, suicidal ideation, and high-risk sexual behavior. [ABSTRACT FROM AUTHOR]
Keywords: community; family; gay men; Latino

Suicidal behavior and gay-related stress among gay and bisexual male adolescents. - Rotheram-Borus, Mary J.; Hunter, Joyce (Journal of Adolescent Research, 1994)
; Presents a study on adolescents suicidal behavior and gay related stress among gay and bisexual male adolescent. Methodology; Prevalence of suicide; Suicidal attempters and nonattempters; Discussion.
Keywords: Homosexuality and Homosexuals; SEXUAL ATTITUDES, BEHAVIOR, AND PROBLEMS

Prevalence of Suicide Attempts and Suicidal Ideation Among Lesbian and Gay Youth. - Saulnier, Christine Flynn (Journal of Gay & Lesbian Social Services, 1998)
Researchers argue that a disproportionate number of lesbian and gay adolescents attempt suicide. The problem demands careful attention from social work. Most, perhaps all, social workers serve lesbian and gay clients. Some are aware of it. Yet all too often social workers assume that the sexual orientation of the adolescents with whom they work does not vary. When that assumption is made, social workers may be missing a key opportunity to understand and intervene with and on behalf of gay and lesbian teens. This paper begins by defining several pertinent terms. Next, it examines findings concerning prevalence and risk factors for suicidality in lesbian and gay youth, and provides information on recognizing lesbian and gay adolescents. The paper ends with an overview of areas in which social workers need to intervene. [ABSTRACT FROM PUBLISHER]

Modernism, Memory and Desire: Queer Cultural Production in Alison Bechdel's Fun Home. - Tolmie, Jane (Topia (York University), 2009)
Using what Barbara Christian has called the technique of "rememorying"-the deliberate reconstruction of memory to void fixed categories-Alison Bechdel's Fun Home: A Family Tragicomic expands the perimeters of graphic memoir and creates a sense of queer canonicity-in the process. Fun Home's structure is recursive rather than linear, returning again and again to' the same sites of emotional pain: the author's coming out, her father's suicide, the pressures of compulsory heterosexuality, the always-impossible search for lost time. Like other graphic memoirs, such as Art Spiegelman's Maus:A Survivor's Thle and Marjane Satrapi's Persepolis, Fun Home tackles subjects rooted in trauma and memory. Fun Home offers a lesbian feminist counterpoint to texts such as Maus, adding queer autobiography to the purview of the growing canon of women's alternative comic art. Moving freely from Marcel Proust to Roald Dahi, mixing memory and desire, Bechdel interrogates some comfortable perceptions of the autobiographical materials that constitute high culture. (English) [ABSTRACT FROM AUTHOR]
Keywords: Memory; Desire; Culture; Memoirs; Modernism (Aesthetics); Bechdel, Alison, 1960-; Fun Home: A Family Tragicomic (Book : Bechdel)

Predictors of suicide attempts among gay, lesbian, and... - Hershberger, Scott L.; Pilkington, Neil W. (Journal of Adolescent Research, 1997)
; Identifies predictors of past suicide attempts in a number of lesbian, gay, and bisexual youth from ages 15 through 21 years who attended social and recreational groups in urban community settings. Suicide attempt patterns; Variables distinguishing suicide attempters from nonattempters; Multivariate associations with suicide attempt status; Variables distinguishing single-occasion from multiple-occasion attempters.
Keywords: Adolescent Problems and Treatment

Impact of Victimization on Risk of Suicide Among Lesbian, Gay, and Bisexual High School Students in San Francisco - Shields, John P.; Whitaker, Kelly; Glassman, Jill; Franks, Heather M.; Howard, Kelli (Journal of Adolescent Health, 2012)
Abstract: Purpose: This study investigated the association between sexual orientation, victimization, and suicide risk-related outcomes among youth attending public high schools in San Francisco. Methods: Data from the 2009 Youth Risk Behavior Survey were analyzed using bivariate and logistic regression methods for complex samples to examine the relationship between sexual orientation, victimization, and three suicide risk-related outcomes (sadness/depression, suicide planning, and attempting suicide) while controlling for demographics and substance use. Results: Lesbian, gay, or bisexual (LGB) youth reported significantly higher rates of substance use, victimization, and suicide risk-related outcomes than heterosexual youth. However, in the controlled regression models, victimization was a significant predictor of sadness/depression and suicide attempts, regardless of sexual orientation. There was a significant interaction effect between sexual orientation and victimization on suicide planning, with heterosexual youth more affected than LGB youth. Conclusions: Results underscore the deleterious effect of victimization on suicide risk-related outcomes, regardless of sexual orientation. As LGB youth continue to report higher rates of victimization, effective violence prevention approaches must focus on reducing violence among youth, specifically LGB youth. Additional research should focus on identification of other factors that may help further explain elevated suicide risk among LGB youth. [Copyright &y& Elsevier]
Keywords: LGBTQ+ people; Adolescence; Suicide risk factors; Mental depression; Psychology of high school students; Regression analysis; Surveys; Victim psychology; Descriptive statistics; California; Lesbian, gay, and bisexual youth; Logistic regression; Suicide risk; Victimization; Youth Risk Behavior Survey (YRBS)

A Model of Predictors and Outcomes of Outness Among Lesbian and Bisexual Women. - Morris, Jessica F.; Waldo, Craig R.; Rothblum, Esther D. (American Journal of Orthopsychiatry, 2001)
; Examines a model of predictors and outcomes of outness among lesbian and bisexual women in the United States. Association of greater outness with self-identification toward the lesbian end; Relation to psychological distress; Prediction of increased suicidality by psychological distress.
Keywords: UNITED States

Sexual Orientation and Suicidality: A Co-twin Control Study in Adult Men. - Herrell, Richard; Goldberg, Jack; True, William R.; Ramakrishnan, Visvanathan; Lyons, Michael; Eisen, Seth; Tsuang, Ming T. (Archives of General Psychiatry, 1999)
Background: Several recent studies have found a higher lifetime prevalence of suicide attempts in homosexual males compared with heterosexual control subjects or population rates. These studies used either convenience samples, most without controls, or population-based samples in which confounding factors such as depression and substance abuse were not measured. Methods: This study used twins from the population-based Vietnam Era Twin Registry, Hines, Ill. An analytic sample of 103 middle-aged male-male twin pairs from the registry was identified in which one member of the pair reported male sex partners after age 18 years while the other did not. Four lifetime symptoms of suicidality as measured by the Diagnostic Interview Schedule were analyzed: thoughts about death, wanting to die, thoughts about committing suicide, and attempted suicide. A composite measure of reporting at least one suicidality symptom was also assessed. Results: Same-gender sexual orientation is significantly associated with each of the suicidality measures. Unadjusted matched-pair odds ratios follow: 2.4 (95% confidence interval [CI], 1.2-4.6) for thoughts about death; 4.4 (95% CI, 1.7-11.6) for wanted to die; 4.1 (95% CI, 2.1-8.2) for suicidal ideation; 6.5 (95% CI, 1.5-28.8) for attempted suicide; and 5.1 (95% CI, 2.4-10.9) for any of the suicidal symptoms. After adjustment for substance abuse and depressive symptoms (other than suicidality), all of the suicidality measures remain significantly associated with same-gender sexual orientation except for wanting to die (odds ratio, 2.5 [95% CI, 0.7-8.8]). Conclusions: The substantially increased lifetime risk of suicidal behaviors in homosexual men is unlikely to be due solely to substance abuse or other psychiatric comorbidity. While the underlying causes of the suicidal behaviors remain unclear, future research needs to address the inadequacies in the measurement of both sexual orientation and suicidality in population-based samples. [ABSTRACT FROM AUTHOR]

Suicidal ideation and attempts in North American school-based surveys: are bisexual youth at increasing risk? - Saewyc EM; Skay CL; Hynds P; Pettingell S; Bearinger LH; Resnick MD; Reis E (Journal of LGBT Health Research, 2007)

Risk Factors for Suicide among Gay, Lesbian, and Bisexual Youths. - Proctor, Curtis D.; Groze, Victor K. (Social Work, 1994)
; The article presents a study which explores risk factors for suicide among gay, lesbian and bisexual youths. Most research on gay, lesbian, and bisexual suicide has historically operated under the climate of psychopathology or psychiatric settings instead of investigating it as a response to the difficulties of a hostile environment. As a result, it has been difficult to substantiate without bias whether gay men and lesbians are at greater risk for suicidal ideation or attempts. Although studies of adult gay men and lesbians provide evidence that gay men and lesbians are at greater risk for suicide, such studies are inconclusive about what leads to the increased risk. For example, researchers have commented on the spurious assumption that homosexuality as pathology leads to suicide. Several studies have identified factors associated with gay, lesbian, and bisexual youth suicide, including low self-esteem, social isolation, depression, negative family interactions, and negative social attitudes.
Keywords: adolescents; bisexuals; gay men; lesbians; suicide

Experiences of Harassment, Discrimination, and Physical Violence Among Young Gay and Bisexual Men. - Huebner, David M.; Rebchook, Gregory M.; Kegeles, Susan M. (American Journal of Public Health, 2004)
Objectives. We examined the 6-month cumulative incidence of anti-gay harassment, discrimination, and violence among young gay/bisexual men and documented their associations with mental health. Methods. Gay/bisexual men from 3 cities in the southwestern United States completed self-administered questionnaires. Results. Thirty-seven percent of men reported experiencing anti-gay verbal harassment in the previous 6 months; 11.2% reported discrimination, and 4.8% reported physical violence. Men were more likely to report these experiences if they were younger, were more open in disclosing their sexual orientation to others, and were HIV positive. Reports of mistreatment were associated with lower self-esteem and increased suicidal ideation. Conclusions. Absent policies preventing anti-gay mistreatment, empowerment and community-building programs are needed for young gay/bisexual men to both create safe social settings and help them cope with the psychological effects of these events. (Am J Public Health. 2004;94:1200-1203). [ABSTRACT FROM AUTHOR]
Keywords: Offenses against the person; Gay men; Mental health; Discrimination; United States

Depression, hopelessness, suicidality, and related factors in sexual minority and heterosexual... - Safren, Steven A.; Heimberg, Richard G. (Journal of Consulting & Clinical Psychology, 1999)
; Investigates factors related to depression, hopelessness and suicidality in gay, lesbian and bisexual adolescents compared with similar heterosexual adolescents. Greater depression, hopelessness and suicidality in sexual minority adolescents; Major role of environmental factors associated with sexual orientation in predicting distress in adolescents.
Keywords: DEPRESSION in adolescence; DESPAIR; SUICIDAL behavior; GAY teenagers; PSYCHOLOGY; BISEXUAL youth; PSYCHOLOGY

Rates and predictors of mental illness in gay men, lesbians and bisexual men and women: Results from a survey based in England and Wales. - Warner, James; McKeown, Eamonn; Griffin, Mark; Johnson, Katherine; Ramsay, Angus; Cort, Clive; King, Michael (British Journal of Psychiatry, 2004)
Background: There is a dearth of research into the mental health of gay men, lesbians and bisexual men and women in the UK.Aims: To assess rates and possible predictors of mental illness in these groups.Method: A comprehensive assessment was made of the psychological and social well-being of a sample of gay men, lesbians and bisexual men and women, identified using 'snowball' sampling.Results: Of the 1285 gay, lesbian and bisexual respondents who took part, 556 (43%) had mental disorder as defined by the revised Clinical Interview Schedule (CIS - R). Out of the whole sample, 361 (31%) had attempted suicide. This was associated with markers of discrimination such as recent physical attack (OR=1.7, 95% CI 1.3-2.3) and school bullying (OR=1.4, 95% CI 1.1-2.0), but not with higher scores on the CIS-R.Conclusions: Gay, lesbian and bisexual men and women have high levels of mental disorder, possibly linked with discrimination. [ABSTRACT FROM AUTHOR]
Keywords: Mental health; Gay men; Lesbians; Bisexual men; Women's health; Mental illness; Medical care; Discrimination; Great Britain

Walker, Uncle Will, and I: A Homophobe and Two Queens. - Percy III, WilliamArmstrong; Flax-Clarke, Aidan; Gannett, Lewis (Southern Communication Journal, 2009)
The noted novelist Walker Percy (1916-1990) endured the suicides of his grandfather, father, and mother during his childhood. His cousin William Alexander Percy (1885-1942) adopted Walker and his two brothers following those tragedies. “Uncle Will” took great interest in the education of his adoptive sons. Walker in particular benefited from this; later in life, Walker and his good boyhood friend, Shelby Foote, who himself was to gain fame as a Civil War historian, speculated that Will Percy's influence played a major role in the incubation of their literary careers. There is an irony in this. Will Percy, a World War I combat hero, published poet of stature, world traveler, member of the Uranian movement, and author of the classic Southern memoir Lanterns on the Levee (1941), led a piquantly gay life. To present-day sensibilities, Will Percy's poetry and his memoir emanate a palpable queerness. Yet, Walker Percy denied his benefactor's homosexuality and indeed, with his brothers, took exhaustive steps to try to conceal that reality. Walker also became a celebrated moralist who expressed a decided aversion to homosexuality. This aspect of the family history exemplifies deletion of queer history in the particular historical context of hereditary Southern gentry with a literary bent in the mid- to late twentieth century. [ABSTRACT FROM AUTHOR]
Keywords: LGBTQ+ people; Families; Suicide victims; Upper class; Percy, Walker, 1916-1990

Lives in a chiaroscuro. Should we suspend the puberty of children with gender identity disorder? - Giordano, S. (Journal of Medical Ethics, 2008)
Transgender children who are not treated for their condition are at high risk of violence and suicide. As a matter of survival, many are willing to take whatever help is available, even if this is offered by illegal sources, and this often traps them into the juvenile criminal system and exposes them to various threats. Endocrinology offers a revolutionary instrument to help children/adolescents with gender identity disorder: suspension of puberty. Suspension of puberty raises many ethical issues, and experts dissent as to when treatment should be commenced and how children should be followed up. This paper argues that suspension of puberty is not only not unethical: if it is likely to improve the child's quality of life and even save his or her life, then it is indeed unethical to defer treatment. [ABSTRACT FROM AUTHOR]
Keywords: Gender identity; Puberty; Transgender people; Medical ethics; Ethics; Endocrinology; Social medicine

Risk Comparison Among Youth Who Report Sex With Same-Sex Versus Both-Sex Partners. - Moon, Martha W.; Fornili, Katherine; O'Briant, Amanda L. (Youth & Society, 2007)
This article examines risk behavior among youth attending support groups for sexual minority youth in Richmond, Virginia, using a structured survey, with particular attention to partner selection and its relationship to risk. Within this generally high-risk group, youth reporting sex partners of both sexes had significantly higher risk profiles, including histories of drug use, suicide attempts, sexual victimization, and having run away from or been removed from the home, than those reporting only same-sex partners. [ABSTRACT FROM AUTHOR]
Keywords: GLBT young adults; GLBT youth; YOUNG adults; YOUTH -- Sexual behavior; SEXUAL ethics for youth; VIRGINIA; adolescents; sexual minority youth; substance use; suicide

Young adults' reactions to gay and lesbian peers who became suicidal following "coming out" to their parents. - Cato, Jennifer E.; Canetto, Silvia Sara (Suicide & Life-Threatening Behavior, 2003)
Rates of nonfatal suicidal behavior among gay and lesbian youth surpass those recorded among their heterosexual peers. A frequently cited precipitant of gay and lesbian nonfatal suicidal behavior is the turmoil associated with coming out to one's family. This study investigated young adults' attitudes toward peers who engaged in suicidal behavior after coming out and being rejected by their parents, and compared them with attitudes toward persons who had become suicidal in response to other stressors (a physical illness, a relationship loss, or an academic failure). Our goal was to explore whether young persons hold beliefs that may encourage lesbian and gay suicidal behavior. We found that gays and lesbians who engaged in suicidal behavior following coming out were not viewed in particularly forgiving or empathic ways, as was the case for persons who became suicidal following an incurable illness. All suicidal persons were perceived as relatively feminine. At the same time, suicidal males were rated as more masculine if they engaged in suicidal behavior because of an academic failure or a physical illness, while suicidal females were viewed as more masculine only if their suicidal behavior followed an academic failure. Finally, we found that both respondent sex and respondent gender-identity influenced evaluations of suicidal persons. Building on these findings, future research should explore attitudes toward the permissibility of a suicidal decision by lesbian and gay persons. [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Heterosexuals

Ignored to death. - Emslie, Mic (Youth Studies Australia, 1996)
; Focuses on representations of young gay men, lesbians and bisexuals in Australian youth suicide policy and programs. Significance of mental health for an understanding of youth suicide; Anecdotal evidence on the experience of young gay people; Suicide rate; Connection between sexuality and suicide.
Keywords: AUSTRALIA

Sexual orientation and mental health in a birth cohort of young adults. - DAVID M. FERGUSSON; L. JOHN HORWOOD; ELIZABETH M. RIDDER; ANNETTE L. BEAUTRAIS (Psychological Medicine, 2005)
Background. This paper sought to examine the relationship between sexual orientation and mental health in a New Zealand birth cohort studied to age 25 years.Method. The analysis is based on a sample of 967 participants (469 males; 498 females) in the Christchurch Health and Development Study. As part of this study information was gathered on: (a) measures of sexual orientation, same-sex behaviour and sexual attraction obtained at ages 21 and 25 years; (b) measures of mental disorders and suicidal behaviours over the interval 21–25 years; (c) measures of childhood and family background.Results. Latent class analysis was used to combine indicators of sexual orientation, same sex behaviour and attraction to form an empirically based classification of sexual orientation. The best-fitting model classified the sample into three groups: exclusively heterosexual orientation (87·6%); predominantly heterosexual but with same-sex inclinations or experience (9·6%); predominantly homosexual (2·8%). Proportionately more women than men were classified as predominantly heterosexual (14·2% v. 4·8% respectively) or predominantly homosexual (3·9% v. 1·5% respectively). Cohort members with a predominantly homosexual orientation had rates of mental disorder and suicidal behaviours that were between 1·5 and 12 times higher than for those with an exclusively heterosexual orientation. These associations persisted after adjustment for confounding. The associations between sexual orientation and mental health were more marked for males than females.Conclusions. The findings suggest a continuum of sexual preferences amongst young adults. Variations in sexual orientation were clearly associated with mental health. These associations tended to be stronger for males. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Mental health; Sexual attraction; Mental illness; Psychiatric research

Sex, drugs, violence, and HIV status among male-to-female transgender persons in Houston, Texas. - Risser JMH; Shelton A; McCurdy S; Atkinson J; Padgett P; Useche B; Thomas B; Williams M (International Journal of Transgenderism, 2005)
To inform the Community Planning Group (Houston, Texas) in setting HIV-prevention priorities, risk behavior surveys were completed by 67 male-to-female (MtF) transgender persons. By self-identification, 58% were preoperative and 48% were self-described heterosexual women. We found this small sample of male-to-female transgender individuals to have high rates of HIV infection, and high prevalence of risky behaviors, intimate partner violence, and suicidal ideation. Twenty-seven percent were infected with HIV. Barriers were seldom used during oral sex and used less than half the time for anal sex with either primary or casual partners. Nearly one third of the sample reported use of methamphetamines, amyl nitrite or LSD and 40% reported crack or cocaine use. Intimate partner violence and forced sex were reported by 50% and 25%, respectively. Suicidal ideation was reported by 16% in the last 30 days; lifetime suicidal ideation was 60%. [ABSTRACT FROM AUTHOR]

Risk assessment of adolescents with same-sex relationships. - Udry, J. Richard; Chantala, Kim (Journal of Adolescent Health, 2002)
Purpose: To compare the risk status on health and behavior for those with same-sex partners and those without.Methods: Add Health data provide a sample of 20,745 adolescents in grades 7 through 12 interviewed at home. The risk statuses of respondents with no partners, same-sex-only partners, and partners of both sexes were compared to respondents with opposite-sex partners only. Respondents were evaluated on selected personal and social attributes (verbal IQ, family structure, masculinity, popularity), and risk status (substance use, depression, suicidal thoughts, anal sex, general delinquency, being physically attacked, perceived risk of being killed or getting AIDS). Data were analyzed by logistic and linear regression using STATA to adjust for clustering and sampling weights.Results: Compared to boys with opposite-sex-only partners, boys with same-sex-only partners were at high risk for emotional problems, but not delinquency or substance use. Boys with partners of both sexes were at high risk for delinquency and substance use, but not for emotional problems. Neither group of boys with same-sex partners is at high risk of being attacked compared to those with opposite-sex partners only. Girls with only same-sex partners are never a high-risk group, while girls with partners of both sexes are the high-risk category in every case.Conclusions: Adolescents with same-sex-only partners do not resemble those with partners of both sexes in risk status. Combining the two categories obscures the unique risk profile of those with both-sex partners, and obscures the low risk on most variables but the high emotional risk of boys with only same-sex partners. [Copyright 2002 Elsevier]
Keywords: Add Health; Homosexual; Risk behavior; Same-sex partners

Lesbians' Drinking Patterns: Beyond the Data. - Hughes, Tonda L. (Substance Use & Misuse, 2003)
Early studies report very high rates of ''alcohol abuse'' and alcoholism among lesbians. However, serious methodological problems, including non-representative samples that were often recruited in lesbian or gay lesbian bars, limit the validity of findings from these studies. In this article, I briefly review the literature on lesbians' use of alcohol and present findings from a recent study conducted in Chicago (USA). This study recruited a race- and age-diverse sample of lesbians and a demographically matched group of heterosexual women. Rates of ''heavy'' alcohol use and alcohol-use-related problems among lesbians were much lower in this study than in early studies. However, lesbians were more likely than their heterosexual counterparts to be in recovery and to have been in treatment for alcohol-use-related problems. Further, high rates of childhood sexual abuse, depression, and suicidal ideation reported by lesbians suggest that at least some groups may be at heightened risk for ''heavy'' drinking and drinking-related problems. Nevertheless, results of this and other studies suggest that reports of heavy drinking and drinking-related problems among lesbians may have been inflated in earlier studies, or that heavy drinking and drinking-related problems may have declined among lesbians. [ABSTRACT FROM AUTHOR]
Keywords: Gay & lesbian studies; Lesbians; Drug abuse; LGBTQ+ people -- Alcohol use; Substance abuse; Statistics; Chicago (Ill.); Illinois; United States; Alcohol use; Homosexuality; Lesbian; Mental health risks; Mental health risks.; Sexual orientation; Substance use

Reagan's Rainbow Rodeos: Queer Challenges to the Cowboy Dreams of Eighties America. - Le Coney, Christopher; Trodd, Zoe (Canadian Review of American Studies, 2009)
During the 1980s, both Hollywood and the Reagan administration attempted to resurrect frontier masculinity by rewriting the Vietnam War and rehabilitating its defeated hero: the straight-shooting cowboy. But a quarter-century before Ang Lee's Brokeback Mountain (2005) collided in the space of myth-making with America's latest cowboy president, individuals opened a counter-hegemonic space that challenged social marginalization in the public sphere. Picking up where subversive westerns from the late 1960s had left off, the little-known artist Delmas Howe and the founders of the International Gay Rodeo Association (IGRA) resisted the imposition of a rigidly heterosexual cowboy mythology and met the Reagan-era cowboy revival on a queer frontier. Examining John Schlesinger's Midnight Cowboy (1969), Andy Warhol's Lonesome Cowboys (1969), Howe's series of paintings entitled Rodeo Pantheon (1977–91), and the founding and rise of the IGRA (accompanied by interviews with IGRA participants), this article uncovers a rainbow rodeo that has challenged America's cowboy dreams. [ABSTRACT FROM AUTHOR]
Keywords: Gay rodeos; Masculinity; Mythology; Counterculture; Cultural movements; HISTORY; Cowboys; Cowboys in art; Popular culture; UNITED States; United States; cowboy masculinity; frontière gaie; gay rodeo; John Wayne; masculinité du cowboy; queer frontier; rodéo gai; Ronald Reagan

Prediction of Depressive Distress in a Community Sample of Women: The Role of Sexual Orientation. - Matthews, Alicia K.; Hughes, Tonda L.; Johnson, Timothy; Razzano, Lisa A.; Cassidy, Roberta (American Journal of Public Health, 2002)
Objectives. This study compared factors known or hypothesized to influence depressive symptomatology in a community sample of lesbians and heterosexual women. Methods. Data were collected in a multisite survey of lesbians' physical and mental health. Results. Findings confirmed earlier reports suggesting that traumatic life events such as physical and sexual abuse, and individual traits and coping styles are risk factors for depressive distress. However, findings of higher rates of suicidal behavior and of several risk factors for depressive distress among lesbians suggest that risk for depression may differ among lesbians and heterosexual women. Conclusions. Sexual orientation may represent an important but poorly understood risk factor for depressive distress as well as suicidal ideation and behavior. (Am J Public Health. 2002;92:1131-1139) [ABSTRACT FROM AUTHOR]
Keywords: SEXUAL orientation; DEPRESSION in women; LESBIANS -- Psychology; WOMEN -- Suicidal behavior; UNITED States

Social Exclusion, Absenteeism And Sexual Minority Youth. - Rivers, Ian (Support for Learning, 2000)
In this article, on a topic not previously explored in this journal, Ian Rivers compares two groups of lesbian, gay and bisexual adults (mean age, 28 years) who reported having been subjected to anti-lesbian/gay abuse at school. The first group recalled a history of absenteeism at school while the second group, although experiencing similar levels of harassment, reported attending school on a regular basis. The findings suggest an association between the experience of harassment and a history of absenteeism and an ideation of self-harm and suicide while at school. Rivers proposes that anti-harassment initiatives be set up to ensure a safe environment in which sexual minority youth can learn. [ABSTRACT FROM AUTHOR]
Keywords: Social isolation; Gay students; School attendance; Social conditions of students

Sexually Transmitted Disease (STD) Diagnoses and Mental Health Disparities Among Women Who Have Sex With Women Screened at an Urban Community Health Center, Boston, MA, 2007. - Reisner, Sari L.; Mimiaga, Matthew J.; Case, Patricia; Grasso, Chris; O'Brien, Casey T.; Harigopal, Padmini; Skeer, Margie; Mayer, Kenneth H. (Sexually Transmitted Diseases, 2010)
The article discusses a study which correlates sexually transmitted disease (STD) diagnoses and possible mental health disparities of women who have sex with women (WSW). It notes that WSW diagnosed with STDs are at high chances of having bipolar disorders than WSW without STDs. It also mentions that WSW with histories of STD were at increased odds of suicidal attempts in the past. It states that WSW with STDs are traced of high possibilities for having psychosocial problems.
Keywords: Sexually transmitted diseases; Human sexuality; Psychology; Women's mental health; Bipolar disorder; Risk factors in suicidal behavior; Psychosocial factors

The attitudes of Australian heterosexual university students toward the suicide of gay, lesbian and heterosexual peers. - Molloy M; McLaren S (Journal of Gay & Lesbian Issues In Education, 2004)
This study sought to examine the attitudes of heterosexual university students to peer suicide when that peer was gay, lesbian, or heterosexual. University students (n = 206) completed several questionnaires, including The Suicide Attitude Vignette Experience. Results indicated that the suicide act was seen as more justified, acceptable, and necessary when the adolescent was gay or lesbian. Further, gay and lesbian youth suicide victims were shown significantly less empathy than heterosexual suicide victims. Participants' level of homophobia was found to be a significant predictor of attitudes toward gay and lesbian youth suicide. Results indicate that the peer group of gay and lesbian youth is unsupportive of their sexual orientation, and these attitudes may be an additional risk factor for gay and lesbian youth suicide. [ABSTRACT FROM AUTHOR]

Bullying and homophobia in UK schools: a perspective on factors affecting resilience and recovery. - Rivers I; Cowie H (Journal of Gay & Lesbian Issues In Education, 2006)
This article reports the results of a three-year study focusing on the experiences of a sample of lesbian, gay, and bisexual (LGB) people in the United Kingdom who were victimized by their peers at school. Data collected from 190 LGBs suggested that experiences of victimization at school were both long-term and systematic, and were perpetrated by groups rather than by individuals. Subsequently, data collected from a sub-sample of 119 participants indicated that over 50 percent had contemplated self-harm or suicide at the time they were being harassed, and that 40 percent had engaged in such behavior at least once. As adults, participants were found to exhibit symptoms associated with negative affect when contrasted with heterosexual and non-victimized LGB peers. Seventeen percent exhibited symptoms associated with PTSD. However, the results also demonstrated that the majority of participants did not differ significantly from comparison groups in terms of self-esteem, and they had a positive attitude towards their sexual orientation. These findings are discussed with reference to the current literature about the development of resilience following exposure to violence and trauma. [ABSTRACT FROM AUTHOR]

Evaluation of a sexual health approach to reducing HIV/STD risk in the transgender community. - Bockting, W. O.; Robinson, B. E.; Forberg, J.; Scheltema, K. (AIDS Care, 2005)
Despite reports of high prevalence of human immunodeficiency virus (HIV) and other sexually transmitted diseases (STDs) among the transgender community, very little prevention education has targeted this population. To fill this gap, we developed and evaluated a transgender-specific intervention, All Gender Health, which incorporates prevention strategies into comprehensive sexuality education. Transgender participants (N=181) attended the two-day seminar in community-based venues. The curriculum was delivered via lectures, panel discussions, videos, music, exercises and small group discussions. Attitudes toward condom use, safer sex self-efficacy and sexual risk behaviour were evaluated before participation in the intervention (pre-test), immediately after participation (post-test) and at three-month follow-up. Compared to pre-test values, significant improvements were seen in attitudes toward condom use and in safer sex self-efficacy at post-test, and in attitudes toward condom use, increased monogamy and decreased sexual risk behaviour at three-month follow-up. Pre-test data identified unprotected anal, vaginal and oral sex as the most commonly reported risk behaviours. Many respondents also indicated problems with social discrimination, depression, suicidal ideation and sexual functioning. Future interventions should address these risk co-factors. Alternative interventions need to be developed to target those who, as a result of social marginalization, are less likely to be reached with an intensive seminar-based intervention. [ABSTRACT FROM AUTHOR]
Keywords: SEXUALLY transmitted diseases; COMMUNICABLE diseases; HIV (Viruses); SEX instruction; GLBT communities; TRANSGENDER communities

Telling Truths: Wounded Truths and the Activity of Truth Telling. - Harwood, Valerie (Discourse: Studies in the Cultural Politics of Education, 2004)
It appears that being young and queer seems to be all about woundedness: it means experiencing suffering, including the risk of suicide, increased drug use, homelessness and violence. Yet how are these wounded truths told, and further, why is it that people in education seem to tell them "unproblematically"? This paper considers these questions by analysing wounded truth telling in the recent debate over the Western Australia Lesbian and Gay Law Reform Bill. Using Foucault's (2001) discussion of Greek parrhesia (truth telling), the Western Australian debate is analysed in terms of its problematisation of wounded truth telling. Questions are raised regarding the implications of unproblematised educational practices that engage in the telling of wounded truths. [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Legal status of gay people; Sexual psychology; Legislation; Truthfulness & falsehood; Australia

GENERATING STORIES OF RESILIENCE: HELPING GAY AND LESBIAN YOUTH AND THEIR FAMILIES. - Sanders, Gary L.; Kroll, Ian T. (Journal of Marital & Family Therapy, 2000)
Lesbian, gay, and bisexual youth have often been forgotten in the provision of care to families. Not only are 10%-12% of all youth lesbian, gay, or bisexual they all have families of origin and many also have "families of choice" that are dramatically increasing the numbers of persons who are directly affected. These youth can suffer disqualification ranging from internalized poor esteem and suicidality to physical danger, often at the hands of those very persons who are expected to care for them--families, educators, and health care providers. This article examines both how homophobia and heterosexism are both manifest and recovered from using case examples and offering therapeutic suggestions to clinicians. [ABSTRACT FROM AUTHOR]
Keywords: HOMOPHOBIA; HETEROSEXISM; SEXISM; BISEXUAL youth; GAY youth; LESBIAN youth; FAMILY psychotherapy

A Tribute to Matthew Shepard. - Boulden, Walt (Journal of Gay & Lesbian Social Services, 2001)
The article focuses on the death of Matthew Shepard, author's friend. Shepard went to a local bar for a drink following a meeting of the University of Wyoming's Lesbian, Gay, Bisexual, Transgendered Association. He had not been able to get any of his friends to go with him, so he had gone alone. While there, he met two men in their 20s who posed as gays and lured him outside. They kidnapped him at gun point, drove him to a remote area outside Laramie, tortured and pistol-whipped him while he begged for his life, tied him to a buck-rail fence, and left him hanging in the cold winds of this high plateau, located over 7,000 feet above sea level. Matt was being transported by ambulance to a hospital in Ft. Collins and was in very serious condition -- he had been beaten close to death. At 12:35 a.m., Monday October 12, 1998 he died, and things became even more surreal. With the shock and exhaustion wearing thin, the memories of Matthew still have to fight their way past the horrible image of his broken and battered body lying in the hospital bed of that intensive care unit.
Keywords: Death; Kidnapping victims; Ambulances; Hospital beds; Intensive care units; Shepard, Matthew, 1976-1998

A LEGAL REMEDY FOR HOMOPHOBIA: FINDING A CURE IN THE INTERNATIONAL RIGHT TO HEALTH. - Boucai, Michael D. (Georgetown Journal of Gender & the Law, 2005)
; This article discusses various issues related to a legal remedy for homophobia. The article author uses homophobia's hazardousness to health as the starting point of an argument that states have an obligation under the international right to health to combat homophobia. He sets out the powerful evidence that the stigma, prejudice, and violence directed toward lesbians and gay men constitute drastic dangers to their physical and mental well-being. Because discussion of this problem is virtually absent from legal scholarship, the author describes here at some length, with an emphasis on several particular conditions prevalent in homosexual populations, namely AIDS/HIV, substance abuse, inadequate health care, mental disorders, and suicide. He further outlines the legal content of the international right to health, showing that it can and legally must be interpreted expansively. Application of this interpretation to the public health problem of homophobia illustrates that governments must end a range of state-sponsored discrimination against gay men and lesbians, must afford them substantial legal protection against discrimination by non-state actors, and must combat homophobia through education and other positive efforts.
Keywords: HOMOPHOBIA; GAYS; PUBLIC health; HUMAN rights; LESBIANS; HOMOSEXUALITY

Factors Influencing Suicide Intent in Gay and Bisexual Suicide Ideators: Differing Models for Men With and Without Human Immunodeficiency Virus. - Schneider, Stephen G.; Taylor, Shelley E.; Hammen, Constance; Kemeny, Margaret E.; Dudley, Jan (Journal of Personality & Social Psychology, 1991)
Of 778 gay and bisexual men (none with acquired immunodeficiency syndrome [AIDS]), 27% (n = 212) reported suicidal ideation over the previous 6 months. Covariance structure models were used to explore predictors of suicide intent among (n = 112) suicide ideators with (n = 100) and without (n = 112) human immunodeficiency virus (HIV). Current AIDS-related stressors (deaths and illnesses and perceived AIDS risk) and past levels of adaptive functioning (social isolation and depression) were significantly more powerful predictors of suicide intent among HIV-positive than among HIV-negative ideators. Biological AIDS risk predicted neither suicide intent, current distress, nor perceived AIDS risk. Pathways to suicide intent appear to be psychologically, rather than biologically, mediated. Among HIV-positive ideators, AIDS-related death and illness events predicted suicide intent but not current distress symptoms. Some suicidal ideation in response to AIDS-related events may be an effort to cope rather than a manifestation of psychological distress. [ABSTRACT FROM AUTHOR]
Keywords: BISEXUAL men; AIDS (Disease) -- Prevention; SUICIDAL behavior; GAYS; STRESS (Psychology); HEALTH risk assessment

Transgender Health: Findings from Two Needs Assessment Studies in Philadelphia. - Kenagy, Gretchen P. (Health & Social Work, 2005)
HIV/AIDS, suicide, violence, and barriers to health care access among transgender people were explored using two needs assessment surveys conducted in Philadelphia in 1997. A total of 182 people responded to a face-to-face interview or self-administered mail survey: 113 male-to-female individuals and 69 female-to-male individuals. About three-fifths of respondents had engaged in unprotected sexual activity during the past 12 months. The risk for HIV infection from unprotected sex was significantly higher among respondents of color than among white respondents. About one-third (30.1 percent) of respondents had attempted suicide. More than half of respondents had been forced to have sex, 56.3 percent had experienced violence in their homes, and 51.3 percent had been physically abused. Twenty-six percent of respondents had been denied medical care because they were transgender. These findings suggest that prevention services that specifically address HIV/AIDS, suicide, and violence among transgender people are urgently needed. [ABSTRACT FROM AUTHOR]
Keywords: Health services accessibility; HIV infections; AIDS; Suicide; Transgender people; Violence; health barriers; HIV/AIDS; suicide; transgender; violence

The health and social service needs of transgender people in Philadelphia. - Kenagy GP (International Journal of Transgenderism, 2005)
Two Philadelphia-based HIV service organizations and a local university collaborated on a study of health and social service needs of transgender people. Transgender people were the primary resource for the development of the needs assessment survey. In this article, the survey development process, including two discussion groups and two focus groups, are described. Findings on barriers to care, violence, perception of public safety and comfort, suicide and health and social service needs are presented. Total sample size was 81, with 49 male-to-female and 32 female-to-male transgender individuals. Most (68%) were African American. About half of the respondents had thought about attempting suicide. High levels of violence were reported, especially among male-to-females. Health and social service needs included job training/work, dental care, health care, legal services, transportation, education and housing. [ABSTRACT FROM AUTHOR]

Black Ground, Gay Figure: Working through Another Country, Black Power, and Gay Liberation. - Bell, Matt (American Literature, 2007)
; An essay is presented for how the novel "Another Country," by James Baldwin, helped to shape the gay liberation movement and black history, according to the author. The author relates the homosexual encounter of the characters Vivaldo and Eric. The character Rufus's suicide by falling and the idea of being "pushed" into being a homosexual or "pushed" off a bridge are considered. The characters' transference in the novel are explored.
Keywords: ESSAYS; CHARACTERS & characteristics in literature; GAY liberation movement; TRANSFERENCE (Psychology); BALDWIN, James; ANOTHER Country (Book)

FOREWORD: CAN GLUCKSBERG SURVIVE LAWRENCE? ANOTHER LOOK AT THE END OF LIFE AND PERSONAL AUTONOMY. - Kamisar, Yale (Michigan Law Review, 2008)
In Washington v. Glucksberg, the Court declined to find a right to physician-assisted suicide ("PAS") in the Constitution. Not a single Justice dissented. One would expect such a ruling to be quite secure. But Lawrence v. Texas, holding that a state cannot make consensual homosexual conduct a crime, is not easy to reconcile with Glucksberg. Lawrence certainly takes a much more expansive view of substantive due process than did Glucksberg. It is conceivable that the five Justices who made up the Lawrence majority--all of whom still sit on the Court--might overrule Glucksberg. For various reasons, however, this seems improbable. Unlike the situation with respect to the pre-Lawrence era, Glucksberg does not stigmatize any political(v vulnerable group. When there is no democratic defect in the political process, there is much to be said for courts deferring to reasonable legislative judgments. Moreover, unlike the developments preceding Lawrence, there has been no emerging awareness of a right or liberty to enlist the assistance of a physician in committing suicide. No state supreme court has found a right to PAS in its own state constitution. Nor, in the decade since Glucksberg, has any state legislature legalized PAS. And attempts have been made to do so in some twenty states. In addition, various considerations might cause a court to balk at constitutionalizing PAS for the terminally ill. Such a right is not easily cabined. If personal autonomy extends to the time and manner of one's death, why doesn't it also apply whenever a competent person believes that death is better than continued life? Once the right to PAS is grounded on self-determination or personal autonomy in controlling one's own life and death, it no longer seems plausible to limit it to the terminally ill. Why should people who have to endure pain, suffering, or indignity for a much longer time than the terminally ill (often defined as those with six months or less to live) be denied this right? The argument made by many proponents of PAS that the right to forgo medical treatment and the right to PAS are merely subcategories of the same broad right is not convincing. Most of the two million people who die every year in this country do so in hospitals and long-term care institutions and do so after a decision to forgo life-sustaining treatment has been made. If medical treatment could not be rejected, vast numbers of patients would be at the mercy of every technological advance. (For example, Nancy Cruzan could have been kept alive in her persistent vegetative state for thirty, years.) Allowing a patient to die at some point is a practical condition upon the successful operation of medicine. The same can hardly be said of PAS. [ABSTRACT FROM AUTHOR]
Keywords: Terminally ill; Assisted suicide laws; Washington v. Glucksberg (Supreme Court case); Constitutional law; Judgments (Law); Medical laws & legislation

Health and social service needs of transgender people in Chicago. - Kenagy GP; Bostwick WB (International Journal of Transgenderism, 2005)
A needs assessment of transgender people was conducted in Chicago in 2001 to assess their HIV risks, health and social service needs, and barriers to care. One-hundred and eleven transgender individuals, 78 male-to-females (MTFs) and 33 female-to-males (FTMs), participated in the study. Fourteen percent of respondents reported being HIV-positive; they were all maletofemale and the majority was of color. Risk factors for HIV included unprotected sex and willingness to have high-risk sex in the future. Respondents experienced high levels of violence. Two-thirds of respondents had thought of attempting suicide. Respondents reported a high need for health and social services, particularly MTFs and people of color. [ABSTRACT FROM AUTHOR]

Sexual orientation and mental health: results from a community survey of young and middle-aged adults. - Jorm, Anthony F.; Korten, Ailsa E.; Rodgers, Bryan; Jacomb, Patricia A.; Christensen, Helen (British Journal of Psychiatry, 2002)
Background: Community surveys have reported a higher rate of mental health problems in combined groups of homosexual and bisexual participants, but have not separated these two groups.Aims: To assess separately the mental health of homosexual and bisexual groups compared with heterosexuals.Method: A community survey of 4824 adults was carried out in Canberra, Australia. Measures covered anxiety, depression, suicidality, alcohol misuse, positive and negative affect and a range of risk factors for poorer mental health.Results: The bisexual group was highest on measures of anxiety, depression and negative affect, with the homosexual group falling between the other two groups. Both the bisexual and homosexual groups were high on suicidality. Bisexuals also had more current adverse life events, greater childhood adversity, less positive support from family, more negative support from friends and a higher frequency of financial problems. Homosexuals reported greater childhood adversity and less positive support from family.Conclusions: The bisexual group had the worst mental health, although homosexual participants also tended to report more distress. [ABSTRACT FROM AUTHOR]
Keywords: Psychiatry; Psychological stress; Sexual orientation; Mental health; Psychotherapy; Mental health services; Mental health of older people; Risk management in business; Syndromes; Therapeutics

CAROUSEL: ERWIN, ELVIRA, ARMIN, FASSBINDER, AND ALL THE OTHERS' AUTO/BIOGRAPHIES. - Pribisic, Milan (Biography: An Interdisciplinary Quarterly, 2006)
The article analyzes the motion picture "In a Year of Thirteen Moons," directed by Rainer Werner Fassbinder. The film is about a German transsexual who comes to terms with his sexuality and his country's Nazi past in a postwar, divided Germany. The storyline of the film seems to be based on the life Armin Meier, Fassbinder's lover of four years, who had committed suicide. Fassbinder positioning Armin as a victim of society's animosity toward the outsider. Fassbinder's direction underlines the narrative of regression and isolation.
Keywords: LGBTQ+ people; Suicide; Exploitation of humans; Motion pictures; Fassbinder, Rainer Werner, 1945-1982; In a Year of 13 Moons (Film)

Risk of Psychiatric Disorders Among Individuals Reporting Same-Sex Sexual Partners in the National Comorbidity Survey. - Gilman, Stephen E.; Cochran, Susan D.; Mays, Vickie M.; Hughes, Michael; Ostrow, David; Kessler, Ronald C. (American Journal of Public Health, 2001)
Conclusions. Homosexual orientation, defined as having same-sex sexual partners, is associated with a general elevation of risk for anxiety, mood, and substance use disorders and for suicidal thoughts and plans. Further research is needed to replicate and explore the causal mechanisms underlying this association. (Am J Public Health. 2001; 91:933-939) [ABSTRACT FROM AUTHOR]
Keywords: PSYCHIATRY; MENTAL illness; SAME-sex relationships; INTERPERSONAL relations; ANXIETY; SUBSTANCE abuse

Backlash. - Riley, Michael (American Journalism Review, 2001)
; Deals with `Living Gay,' a series of articles published by `Roanoke Times' newspaper about the gay and lesbian community of Roanoke, Virginia. Background on a shooting incident that killed gays in Roanoke; Complaints of readers on the series; Impact of the series on the circulation of `Roanoke Times.'
Keywords: VIRGINIA; ROANOKE (Va.); UNITED States

Campus Violence White Paper. - Carr, Joetta L. (Journal of American College Health, 2007)
; The article presents the American College Health Association's (ACHA) Campus Violence White Paper, which aims to examine patterns of campus violence and present methods to address and prevent campus violence. ACHA's "Health Campus 2010" seeks to decrease physical assaults, emotional and sexual abuse, rape, weapon carrying, and homicides. The article discusses campus crime statistics, consequences of campus violence, violence related to a person's religion, race, or sexual orientation, hazing, and suicide. Several practices to prevent violence are presented, including enforcing codes of conduct and creating a campus GLBT office.
Keywords: Safety measures; United States; CAMPUS violence; UNIVERSITIES & colleges; UNIVERSITIES & colleges; GLBT college students; VIOLENCE; PREVENTION; PSYCHOLOGICAL abuse; SEX crimes; HAZING; SUICIDE; CRIME & race; CRIMINAL statistics; UNITED States

Sexual violence among two populations of men at high risk of HIV infection. - Braitstein, Paula; Asselin, Jérôme J.; Schilder, Arn; Miller, Mary-Lou; Laliberté, Nancy; Schechter, Martin T.; Hogg, Robert S. (AIDS Care, 2006)
This study sought to compare the prevalence of, and relationship between, age at first experience of sexual violence and HIV and other health risk behaviors in two populations of men at high risk of HIV infection. Data were drawn from two cohorts: Vanguard, a prospective study of young men who have sex with men (MSM), and VIDUS, the Vancouver Injection Drug Users Study. Controlling for fixed sociodemographics, multivariate logistic regression was used to assess the relationship between age at first sexual violence (vs. never experiencing it) and several health risk behaviors. There were 140/498 (28%) MSM from Vanguard and 173/932 (19%) injection drug users (IDU) from VIDUS who reported having experienced sexual violence. Among VIDUS men, 130/852 (15%) IDU-only and 43/80 (54%) who were both IDU and MSM reported a history of sexual violence. The prevalence of child sexual abuse was 13% in Vanguard MSM, and 11% among VIDUS IDU-only, but 26% among VIDUS MSM/IDU. The median age of onset was significantly lower among VIDUS IDU-only compared to the two other groups. Experiencing sexual violence first in childhood was strongly related to ever being in the sex trade in both IDU and MSM. MSM in Vanguard who experienced sexual violence in childhood were more likely to have attempted suicide, and have a diagnosed mood disorder. Non-MSM IDU in VIDUS who experienced sexual violence in childhood were more likely to have a diagnosed mental illness, to binge on alcohol, and to have ever accidentally overdosed. In conclusion, men who have ever had sex with men appear to have a higher lifetime prevalence of sexual violence, compared to non-MSM injection drug users. Sexual violence is differentially associated with different health risk behaviors, depending on the age at first occurrence and the primary HIV risk factor (i.e. MSM vs. IDU). [ABSTRACT FROM AUTHOR]
Keywords: HIV infections; SEXUAL abuse victims; CHILD sexual abuse; RISK-taking (Psychology); MENTAL illness; SOCIODEMOGRAPHIC factors

Attitudes on End-of-Life Care and Advance Care Planning in the Lesbian and Gay Community. - Stein, Gary L.; Bonuck, Karen A. (Journal of Palliative Medicine, 2001)
Gay men and lesbians have special interests in documenting their preferences regarding advance care planning and end-of-life care. A 64-item survey instrument was developed to ascertain the preferences of this community regarding approaches to end-of-life care, viewpoints on physician-assisted suicide (PAS) and euthanasia, and practices regarding advance care planning. The survey was completed by 575 participants recruited through community-based health care and social service organizations serving the lesbian and gay community, primarily in the New York metropolitan area. Respondents represent a diverse group of women (36%) and men (63%) from various age, racial/ethnic, and religious/spiritual backgrounds; 10% were human immunodeficiency virus (HIV)-positive. Respondents' perspectives on end-of-life care are generally consistent with findings from other attitudinal studies of U.S. adults: a majority supported legalization of PAS and preferred a palliative approach to end-of-life care. However, the gay community sample revealed even stronger support for assisted suicide and palliative care. Although respondents completed advance directives at a higher rate than adults generally, the legal importance for gay men and lesbians to execute directives should encourage health care providers and community organizations to assume a larger educational role on advance care planning. Results confirm other reports on the need to address provider communication skills. It is speculated that the HIV epidemic was a major influence behind these results because of the overwhelming personal impact of the epidemic on most gay men and lesbians during the past two decades. [ABSTRACT FROM AUTHOR]
Keywords: Gay people; HIV infections; Medical care; Medical care of lesbians; Assisted suicide; Euthanasia

Social Dichotomy Versus Gender Dichotomy: A Case Report of Gender Identity Disorder. - Kumar, Kuldip; Gupta, Manushree (Indian Journal of Psychological Medicine, 2012)
Gender identity disorder is one of the most controversial diagnoses of DSM-IV and almost incomparable in the complexity of its social, ethical and political considerations to any other diagnosis. We present a case of 30 year-old male who presented with complaints of suggestive of depressive disorder with a recent suicidal attempt. Careful history taking reveals underlying conflicts with prominent gender dysphoria and social complexities. The patient is managed primarily by pharmacotherapy and harm reduction model. Our case reflects a unique coping strategy against the present sociocultural values and ambiguity of law in this part of the world. [ABSTRACT FROM AUTHOR]
Keywords: Gender dysphoria; Suicidal behavior; Drug therapy; Psychological adaptation; Mental depression; Harm reduction; Gender identity; gender role; socio-cultural

Health Care Recommendations for Lesbian Women. - Roberts, Susan Jo (JOGNN: Journal of Obstetric, Gynecologic & Neonatal Nursing, 2006)
Objective: To review research literature to provide clinicians with data-based recommendations for care of lesbians. Data Sources: Medline searches and references from selected articles with the search term “lesbian health.” Study Selection: Literature was selected whether lesbian or women who have sex with women was utilized as a category in the study and results were available on this population. Data Extraction: Data were organized according to specific health problems noted frequently in the research articles. Data Synthesis: Lesbians have previously been invisible in health services and research, but in several areas, data now exists on which to base care. Conclusions: Lesbians are now more comfortable “coming out” to providers but continue to have lower screening rates than other women. Risk is especially high in this population for cancer, heart disease, depression, and alcohol abuse. Adolescent lesbians are especially at risk for smoking and suicide/depression. JOGNN, 35, 583-591; 2006. DOI: 10.1111/J.1552-6909.2006.00081.x [ABSTRACT FROM AUTHOR]
Keywords: Lesbians; Health; Medical care; Gay & lesbian studies; Health risk assessment; Lesbian health

Bridging the Divide: Integrating Lesbian Identity and Orthodox Judaism. - Glassgold, Judith M. (Women & Therapy, 2008)
Women who consider themselves traditional or conservative in the context of religious practice often experience tremendous conflicts regarding the integration of same-sex emotional and sexual feelings with their religion and spirituality, Current religious teachings about homosexuality make this combination difficult as only heterosexual sexuality within marriage is permitted in most orthodox faiths. Further, the way that spirituality and sexuality are conceptualized as opposing dichotomous categories (e.g., body vs. soul) presents women with a framework where integration does not seem possible. Observant women who come to psychotherapy often experience tremendous distress, guilt, depression, and even suicidality due to the conflict between their sexual feelings and religious doctrine. Relieving the distress, and resolving the conflicts while honoring the emotional complexity of sexual feelings, spirituality, and religious orthodoxy can present tremendous dilemmas for the practitioner as well as the client. Using the example of psychotherapy of an Orthodox Jewish woman who integrated same-sex desire into her life, this article describes psychotherapy process and alternative ways of viewing spirituality and sexuality that permit possible resolutions for clients. [ABSTRACT FROM AUTHOR]
Keywords: Lesbians; Gender identity; Religion; Spirituality; Human sexuality; Psychotherapy; Orthodox Judaism; Judaism; Lesbian; orthodoxy; psychotherapy; spirituality

Cultural Capital and High School Bullies. - Klein, Jessie (Men & Masculinities, 2006)
This analysis of male peer hierarchies in schools argues that battles for cultural capital are a significant causal factor in the spate of school shootings across the United States between 1996 and 2002. The hallmarks of normalized masculinity--hypermasculine identification, athletics, fighting, distance from homosexuality, dominant relationships with girls, socioeconomic status, and disdain for academics--do not include alternative ways to build cultural capital when young men do not fit into rigid traditional social structures. Lacking such cultural capital, the perpetrators attempted to prove their masculinity through overwhelming violence--responses that in Michel Foucault's theoretical framework, reinforced the very power structures they seemed to want to destroy. The analysis concludes with positive directions for change including pedagogical strategies. [ABSTRACT FROM AUTHOR]
Keywords: School violence; Crime; Masculinity; Harassment; School shootings; cultural capital; delinquency; harassment; normalized masculinity; peer hierarchies; school shootings; school violence; teenage violence; violence

A Superhero for Gays?: Gay Masculinity and Green Lantern. - Palmer-Mehta, Valerie; Hay, Kellie (Journal of American Culture, 2005)
The article reports on how the United States comic book industry addressed social and political issues in its narratives through the years. The industry has provided varying approaches to issues including alcohol abuse, racism, environmental devastation, gun control and poverty. The cultural attitudes and philosophies which influenced public culture have been continually explored by industry leaders like DC and Marvel Comics, to understand the complexities of gay identity and antigay hate crimes. These leaders have introduced gay and lesbian characters in their comic books, an example is the Green Lantern hate crime story line which received attention in a wide range of media outlets in the United States.
Keywords: Alcoholism; Hate crimes; Lesbianism; Comic books, strips, etc.; Pictorial wit & humor; United States

Preventing Sexual Risk Behaviors Among Gay, Lesbian, and Bisexual Adolescents: The Benefits of Gay-Sensitive HIV Instruction in Schools. - Blake, Susan M.; Ledsky, Rebecca; Lehman, Thomas; Goodenow, Carol; Sawyer, Richard; Hack, Tim (American Journal of Public Health, 2001)
Conclusions. The findings document increased risk behaviors among GLB youths and demonstrate the potential benefits of providing gay-sensitive HI V instruction in schools. (Am d Public Health. 2001;91:940-946) [ABSTRACT FROM AUTHOR]
Keywords: HIV (Viruses); GLBT communities; GLBT youth; HIGH school students; SUBSTANCE abuse; SUICIDAL behavior

same-sex weddings, Hindu traditions and modern India. - Vanita, Ruth (Feminist Review, 2009)
The article reports on same-sex marriage and joint suicides in India. There has been an increase in the amount of same-sex unions and joint suicides among non-English speaking and low-income women in India who were mostly Hindu. Traditional Hindu ideas can be used to legitimize socially disapproved unions like same-sex relationships despite right-wing Hindu groups claiming that such things come from the U.S.
Keywords: Same-sex marriage; Suicide; Hinduism; Hindu doctrines; Hindu ethics; Hindu marriage customs & rites

YOUTH SUICIDE AND SEXUAL ORIENTATION. - Rutter, Philip A.; Soucar, Emil (Adolescence, 2002)
; Deals with a study which examined the relationship between sexual orientation and youth suicide risk. Method used in the study; Results and discussion.
Keywords: SEXUAL orientation; TEENAGERS; SUICIDE victims; Adolescent Problems and Treatment

Adolescent Homosexuality and Concerns Regarding Disclosure. - Harrison, Therese W. (Journal of School Health, 2003)
ABSTRACT: Development of sexual identity in middle childhood and early adolescence is a natural process. However, it is more stressful for homosexual adolescents. Society continues to stigmatize and marginalize homosexuality. To avoid rejection and hostility, homosexual adolescents are pressured to hide their sexual identities. This fact compounds the anticipated normal developmental concerns of adolescence, and can create unique problems for the homosexual adolescents. Homosexuality can place them at risk for social stigmatization, isolation, depression, suicide, abuse, and rejection by their families and friends. During this exceptionally stressful time, both adolescent students and their families need anticipatory guidance and support. In providing anticipatory guidance, this article discusses critical roles played by professionals who work with adolescents in community or school settings. Included are insights into development of this normal variant of sexual attraction and orientation, risks that homosexual adolescent students may face as well as their disclosure concerns, and possible reactions families may have following disclosure. Supporting homosexual adolescents and their families is emphasized with regard to sensitively providing information, disclosure decisions, coping with stigmatization, and resiliency factors. (J Sch Health. 2003;73(3): 107-112) [ABSTRACT FROM AUTHOR]
Keywords: Homosexuality; Teenagers; Families; Self-disclosure

Homophobia and the production of shame: young people and same sex attraction. - HILLIER, Lynne; Harrison, Lyn (Culture, Health & Sexuality, 2004)
Research among same-sex attracted young people in Western cultures has described a minority group of adolescents whose sexuality is negated by the significant institutions and people in their lives. Very often, there is a silence in the family and at school about same-sex sexuality and when a young person's homosexuality is suspected or disclosed s/he suffers from denial, discrimination and abuse. Not surprisingly, living in hostile environments leaves such young people at high-risk of drug abuse, depression and suicide. This paper describes some of the ways young people resist being positioned in these negative ways. Using autobiographical stories from 200 same-sex attracted young Australians, we document the discursive field of sexuality in which these young people struggle to construct positive identities. Young people were well aware of dominant discourses which characterized homosexuality as 'evil, diseased and unnatural'. Yet they use different strategies to fault, deflect and discount these negative understandings and to highlight other discourse which positions them positively. [ABSTRACT FROM AUTHOR]
Keywords: Gay men; Homosexuality; Homophobia; Drug abuse; Australians

The Health and Health Behaviors of Young Men Who Have Sex with Men. - Kipke, Michele D.; Kubicek, Katrina; Weiss, George; Wong, Carolyn; Lopez, Donna; Iverson, Ellen; Ford, Wesley (Journal of Adolescent Health, 2007)
Abstract: Purpose: To describe the range of health and mental health problems for which young men who have sex with men (YMSM) may be at risk. Methods: An audio-computer-assisted survey was administered to a large, ethnically diverse sample of 526 YMSM (aged 18–24 years) recruited from bars, clubs, and other social venues using a venue-based probability sampling method. Results: Subjects reported a range of health and mental health problems, and involvement in health-compromising behaviors, such as overweight/obesity, depression, and suicidal thoughts/attempts, and many were found to have high rates of sexually transmitted infections. Moreover, many reported not having insurance coverage and/or limited access to care. Conclusions: Many of the health concerns and risks reported by these young men are preventable and can be addressed by any number of sectors, including health care and social service providers, religious organizations, schools, and employers. [Copyright 2007 Elsevier]

Risk for Reassault in Abusive Female Same-Sex Relationships. - Glass, Nancy; Perrin, Nancy; Hanson, Ginger; Bloom, Tina; Gardner, Emily; Campbell, Jacquelyn C. (American Journal of Public Health, 2008)
Objectives. We revised the Danger Assessment to predict reassault in abusive female same-sex relationships. Methods. We used focus groups and interviews to evaluate the assessment tool and identify new risk factors and telephone interviews at baseline and at 1-month follow-up to evaluate the revised assessment. Results. The new assessment tool comprised 8 original and 10 new items. Predictors included increase in physical violence (relative risk ratio [RRR] = 1.95; 95% confidence interval [CI] = 0.84, 4.54), constant jealousy or possessiveness of abuser (RRR = 4.07; 95% CI = 0.61, 27.00), cohabitation (RRR = 1.96; 95% CI = 0.54, 7.12), threats or use of gun by abuser (RRR = 1.93; 95% CI = 0.79, 4.75), alcoholism or problem drinking of abuser (RRR = 1.47; 95% CI = 0.79, 2.71), illegal drug use or abuse of prescription medications by abuser (RRR = 1.33; 95% CI = 0.72, 2.46), stalking by abuser (RRR = 1.39; 95% CI = 0.70, 2.76), failure of individuals to take victim seriously when she sought help (RRR = 1.66; 95% CI = 0.90, 3.05), victim's fear of reinforcing negative stereotypes (RRR = 1.42; 95% CI = 0.73, 2.77), and secrecy of abuse (RRR = 1.72; 95% CI = 0.74, 3.99). Both unweighted (P<.005) and weighted (P<.004) versions of the revised assessment were significant predictors of reassault. Conclusions. The revised Danger Assessment accurately assesses risk of reassault in abusive female relationships. (Am J Public Health. 2008;98:1021-1027. doi:10.2105/AJPH.2007.117770) [ABSTRACT FROM AUTHOR]
Keywords: Same-sex relationships; Drug abuse; Alcohol drinking; Sexual orientation; Women's sexual behavior; LGBTQ+ partner abuse; Offenses against the person; Unmarried couples; Disease risk factors

SCHOOLS THAT HAVE NOT PROTECTED AND WOKED WITH GAY AND LESBIAN STUDENTS HAVE BEEN SANCTIONED BY THE COURTS. - Callahan, Connie (Education, 2000)
Three million gay and lesbian students are at risk for suicide, alcohol and substance abuse, sexual acting out, victimization, and violence. Ignoring the problems associated with this population create an enormous cost for the students, schools, and society. School districts and school personnel have been successfully sued for ignoring harassment such students face. Some school violence has been related to gay harassment in the schools. Strategies for understanding and assisting gay and lesbian students in the schools are presented. [ABSTRACT FROM AUTHOR]
Keywords: UNITED States

Crystal methamphetamine: A source of added sexual risk for Hispanic men who have sex with men? - Fernández, M. Isabel; Bowen, G. Stephen; Warren, Jacob C.; Ibañez, Gladys E.; Hernandez, Nilda; Harper, Gary W.; Prado, Guillermo (Drug & Alcohol Dependence, 2007)
Abstract: Objectives: To determine whether use of crystal methamphetamine increases HIV risk behaviors beyond the risk associated with use of other recreational drugs among Hispanic men who have sex with men (HMSM). Design: We compared the sexual behaviors and psychosocial characteristics of non-recreational drug users (non-users), recreational drug users who did not use crystal (non-crystal drug users), and recreational drug users who used crystal (crystal users). Methods: We recruited 294 HMSM from Internet and 272 from community venues. Eligible men completed an ACASI to assess socio-demographic factors, drug use, sexual behaviors and psychosocial factors and received $50. Results: In the multivariate model, crystal users were more likely than non-crystal drug users to have lower Hispanicism, higher attachment to the gay community, and history of suicide attempts. Crystal users were not significantly different from non-crystal drug users in number of sex partners; however, differences in unprotected receptive anal sex approached significance. Conclusions: The additional risk of crystal above that of other recreational drugs needs to be disentangled from those associated with poly-drug use. Our data suggest that it may depend on how one defines risky sexual behavior and is influenced by psychological, physiologic and social factors. [Copyright 2007 Elsevier]
Keywords: METHAMPHETAMINE abuse; HEALTH risk assessment; SEX; HISPANIC Americans

Homophobia and psychotic crimes of violence. - Murphy, Denis (Journal of Forensic Psychiatry & Psychology, 2006)
Irrationally negative attitudes towards homosexual people, known as homophobia, may cause assaults by mentally ill men. A qualitative study is presented in which homophobic motives are examined in detail. Five hospital in-patients were selected. All suffered from paranoid psychosis in which a homophobic theme was prominent. All had attacked with the intention to kill. Two of the victims died. The case records were studied and each patient participated in a semi-structured interview, which was audio-taped. Transcripts were made and studied using discourse analysis with an emphasis on the narrative of events leading to the crime. These cases are used as a basis for suggesting that it may be useful to categorize homophobic violence into three broad categories: non-psychotic violence, violence arising during typical psychotic illness, and violence arising during atypical or brief psychosis. The study describes and compares features of these homophobic states. Non-psychotic homophobia is an attitude often shared with others. It may lead to severe violence, often premeditated, and may influence the development of psychotic ideas. In those with typical psychotic states, abnormal ideas, often bizarre, of a homophobic nature may arise and can be described in the same way as other abnormal ideas in mental illness. In those with atypical psychosis, both the psychosis and the accompanying homophobic violence may be a reaction to a humiliating failure of gender self-esteem, which can be described as severe internalized homophobia. This may generate extreme and unbearable states of mind leading to both suicide and homicide. Inner conflicts about sexual functioning, associated with shame and rage, lead to paranoid attacks. Distinction between different forms of homophobia may be important in providing advice to courts and in planning therapy. [ABSTRACT FROM AUTHOR]
Keywords: HOMOPHOBIA; MENTALLY ill; PARANOIA; CRIMINAL behavior; MENTAL illness; homicidal assault; Homophobia; internalized homophobia

Depression Among Lesbians: An Invisible and Unresearched Phenomenon. (Journal of Gay & Lesbian Psychotherapy, 1990)
Despite the research emphasis on depression among women, there has been virtually no focus on depression among lesbians. This article reviews evidence for factors that might place lesbians at increased risk for depression as well as factors that would protect lesbians from depression. Additionally, it discusses the research on suicide attempts, alcoholism, and physical and sexual abuse of lesbians, all disorders related to depression. Homophobia, the coming out process, and the lesbian community are presented as issues not faced by heterosexual women. Depression among lesbians who are non-white, not middle class, and not young adults is discussed. Finally, the article presents evidence for the role of therapists and self-help groups in affecting depression rates among lesbians. [ABSTRACT FROM AUTHOR]
Keywords: Lesbians; Suicidal behavior; Heterosexism; Homophobia; Alcoholism; Depression in women; Homosexuality and Homosexuals; SEXUAL ATTITUDES, BEHAVIOR, AND PROBLEMS

Gay, Lesbian, and Bisexual Adolescents: A Critical Challenge to Counselors. - Coleman, Eli; Remafedi, Gary (Journal of Counseling & Development, 1989)
Meeting the health care needs of gay, lesbian, and bisexual teenagers has become a public health imperative, and mental health professionals should be prepared for the challenge. The stigma of homosexuality often gives rise to psychosocial problems for adolescents, who are in the process of sexual identity development. The stigma also may complicate delivery of appropriate, ethical, and sound mental health treatment. Suggestions are offered to support healthy development, to assist recovery from stigma, and to avert the disastrous consequences of suicide and AIDS. [ABSTRACT FROM AUTHOR]
Keywords: LESBIANS; TEENAGERS -- Health & hygiene; HOMOSEXUALITY; MENTAL health; MEDICAL care; GENDER identity

DOMESTIC VIOLENCE. (Georgetown Journal of Gender & the Law, 2009)
The article discusses the U.S. domestic violence law. It outlines the domestic violence historical treatment by which victim's rights activists fought to undo the common law that condoned domestic violence. It recounts chronologically the state's current federal domestic violence law developments from Violence Against Women Act (VAWA I) to VAWA III, concluding in the Lautenberg Amendment to the 1996 Gun Control Act showing its impact on domestic violence law. It discusses the state law by examining criminal sanctions and available civil remedies to victim. It concludes that the current advances in American criminal and civil law to protect domestic violence victims and penalize offenders has truncated proceedings and leaves limited attention on violence in heterosexual relationships.
Keywords: LGBTQ+ family violence; Heterosexuals; Crime victims; Domestic violence laws; Domestic violence -- United States; Legal status of victims of domestic violence; United States. Violence Against Women Act of 1994; Civil law; Gun laws -- United States; United States; United States. Law Enforcement Assistance Administration

Young gay men and suicide. - Macdonald, Ron; Cooper, Trudi (Youth Studies Australia, 1998)
; Presents information on a study on suicidal behavior of young gay men in the Australian city of Perth. Indication that the prevalence of homophobic attitudes and the lack of support for young gay men may be important factors in the high incidence of suicide; Reason of young gay men in giving up their suicide attempts.
Keywords: AUSTRALIA

SOME INITIAL THOUGHTS ON SEXUALITY AND GAY MEN WITH AIDS IN RELATION TO PHYSICIAN-ASSISTED SUICIDE. - Spindelman, Marc S. (Georgetown Journal of Gender & the Law, 2000)
; This article discusses sexuality and gay men in relation to physician-assisted suicide. The gay man with AIDS has played an important, though often subliminal, role in efforts to legalize physician-assisted suicide. He has been credited or burdened with helping to put the issue on the public's and policy makers' radar screens. In the cultural imagination, terminal illnesses, along with pain and suffering, are universals. They transcend sexual identity. Sexuality is thus assumed not to be a criterion, were the practice to become legal, for who would and who would not be eligible to commit physician-assisted suicide. In arguing gay men cases in courts, for example, advocates of physician-assisted suicide have relied heavily on judicial precedents involving sexual autonomy or privacy, chiefly those decisions recognizing a woman's right to abortion. Although these cases are often understood as constitutionally protecting private, consensual sexual choices, proponents of physician-assisted suicide regularly read them more broadly to hold that constitutions guarantee individuals the liberty to make certain major life decisions for themselves.
Keywords: ASSISTED suicide; SEX; GAY men; GENDER identity; SUICIDAL behavior; ABORTION

Social Alienation in Gay Youth. - Sullivan, Michael; Wodarski, John S. (Journal of Human Behavior in the Social Environment, 2002)
The focus of this article is twofold; first, to review known risk factors for gay youth including: substance abuse, depression, suicide, and HIV risks, secondly, to determine the impact of social support factors; specifically parental, peer and religious support factors for this population. Evidence suggests that gay and lesbian youth are at high risk for isolation and subsequent psychological damage that results from social alienation. Insight into the problems faced by gay youth, along with some helpful intervention strategies for professionals working with a gay adolescent population is discussed. [ABSTRACT FROM AUTHOR]
Keywords: Social alienation; Gay youth; Social conditions of LGBTQ people

Oral Sex With A Capital 'O': Sex, Violence And The Limits Of Representation. - Conway, Mary T. (Parallax, 2002)
; Provides a critique of `Eight Bullets: A One Woman's Story of Surviving Anti-Gay Violence,' by Claudia Brenner and Hannah Ashley. Narration of Brenner's survival and the demise of her lover, Rebecca Wight due to a shooting rampage in May 1988; Aim to awareness of homophobic hate crimes; Effects of the publicized account of the murders on lesbian desire and justice for the lesbian murders.

Developmental and adjustment issues of gay, lesbian, and bisexual adolescents: a review of the empirical literature. - Anhalt, Karla; Morris, Tracy L.; Anhalt, K; Morris, T L (Clinical Child & Family Psychology Review, 1998)
Various studies have reported adjustment problems experienced by gay, lesbian, and bisexual (GLB) adolescents. A primary purpose of this paper is to critically review this literature. Difficulties that have been studied include past suicide attempts, substance use and abuse, conduct problems, and academic concerns. For example, a considerable number of GLB youth report a history of suicide attempts, with prevalence rates ranging from 11 to 42%. However, among other methodological concerns, studies in this area have not used a comparison sample of heterosexual youths. Characteristics of development particular to GLB adolescents are described, the empirical research on adjustment issues is reviewed, and potential risk and protective factors for GLB youths are discussed. [ABSTRACT FROM AUTHOR]
Keywords: Psychological adaptation; Gay people; Lesbians; Bisexuals; Suicidal behavior; Substance abuse; adjustment issues; bisexual adolescents; developmental issues; Gay adolescents; lesbian adolescents

Childhood sexual abuse and sexual transmission risk behaviour among HIV-positive men who have sex with men. - O'Leary, A.; Purcell, S.; Remien, R.H.; Gomez, C. (AIDS Care, 2003)
Previous studies have indicated an association between childhood sexual abuse (CSA) and adult sexual risk behaviour among women and among men who have sex with men (MSM). However, no studies to date have tested the hypothesis that a history of CSA predicts sexual behaviour carrying risk of transmission of HIV to others, i.e. in a known HIV-positive cohort. The present study tested this hypothesis among a sample of 456 HIV-positive MSM recruited from community venues in New York and San Francisco. CSA history was found to be significantly associated with past (in the last 90 days) unprotected anal sex acts, both insertive (33% versus 20%, p < 0.05) and receptive (43% versus 27%, p < 0.02), with partners of HIV-negative or unknown serostatus. Further, several potential mediators of this effect were tested, and three found to be predicted by CSA history. Each of these potential mediators was associated with sexual risk behaviour, but differentially: anxiety and hostility were significantly associated with insertive acts, while anxiety, hostility and suicidality were associated with receptive acts. Mediation analyses supported the hypothesis that these factors significantly (albeit partially) accounted for the association of CSA with receptive anal intercourse. Nonsignificant mediation effects were found for insertive sex, suggesting the operation of unmeasured mediating variables. These results highlight the importance of mental health services for individuals who have been sexually abused, both for personal and for public health benefit, and also indicate a need for further research into mediators of CSA effects on transmission-related behaviour. [ABSTRACT FROM AUTHOR]
Keywords: CHILD sexual abuse; SEX; RISK-taking (Psychology)

Health and Social Issues of Gay, Lesbian, and Bisexual Adolescents. - Dempsey, Cleta L. (Families in Society, 1994)
Ten percent of the adolescent population in the United States is gay, lesbian, or bisexual. These teens are difficult to identify and many people are unaware of their existence, problems, and needs. The author reviews current professional and lay literature regarding social and health issues of adolescent homosexuality and presents implications for practitioners in providing comprehensive, culturally appropriate services for these individuals. [ABSTRACT FROM AUTHOR]

The courtroom and the closet in The Thin Blue Line and Capturing the Friedmans. - Druick, Zoë (Screen, 2008)
The article provides information on the epistemology of the closet seen on the films titled "The Thin Blue Line," by Errol Morris and "Capturing the Friedmans," by Andrew Jarecki. "The Thin Blue Line" tells the story of Randall Dale Adams who was wrongfully convicted for the shooting of Robert Wood in Dallas County in 1976. "Capturing the Friedmans," tells the story of Jesse Friedmans who was imprisoned for 13 years after pleading guilty to multiple counts of sexual abuse of children. These films seem to describe Eve Sedgwick's idea on the relations of the closet. Sedgwick believes that the closet becomes a shaping presence in social life for everyone including gay and straight alike.
Keywords: Human sexuality in motion pictures; Closeted LGBTQ+ people; Coming out (Sexual orientation); Sexual orientation; Film reviewing; Morris, Errol, 1948-; Jarecki, Andrew, 1963-; Thin Blue Line, The (Film); Capturing the Friedmans (Film)

Staff knowledge and attitudes towards deliberate self-harm in adolescents. - Crawford, Tanya; Geraghty, Wendy; Street, Karen; Simonoff, Emily (Journal of Adolescence, 2003)
This study investigates knowledge, attitudes and training needs concerning deliberate self-harm (DSH) in adolescents, amongst a variety of professionals involved in the assessment and management of adolescence who self-harm. A questionnaire survey was completed by 126 health professionals working with adolescents who harm themselves. The main outcome measures were a knowledge measure and three attitude measures (generated using factor analysis). The mean percentage of correctly answered knowledge questions, across all professional groups, was 60%. With regard to knowlege, over three-quarters of participants were unaware that homosexual young men and those who had been sexually abused are at greater risk of DSH, whilst one third of staff were unaware that adolescents who self-harm are at increased risk of suicide. Staff who felt more effective felt less negative towards this group of patients (B=−0.21, p=0.03). Forty-two per cent of the participants wanted further training in DSH amongst adolescents. [Copyright 2003 Elsevier]

Mental Health Problems and Use of Services of Lesbians: Results of the Boston Lesbian Health Project II. (cover story) - Roberts, Susan Jo; Grindel, Cecelia Gatson; Patsdaughter, Carol A.; Reardon, Kathleen; Tarmina, M. Suzanne (Journal of Gay & Lesbian Social Services, 2004)
The Boston Health Project II, replicating a national survey of lesbians completed in 1987, found few differences from previous data regarding mental health problems and service use among lesbians. Respondents expressed positive feelings about being lesbian but reported money and work to be major problems. Surveyed lesbians used therapy at high rates, with depression and relationship problems being common reasons for seeking care. Most respondents were satisfied with their therapy experiences; female and lesbian therapists received the highest ratings. Depression, anxiety/panic disorders, and alcohol use continued to be concerns, along with suicide attempts and eating disorders among adolescents. findings confirm that mental health needs exist for lesbians and challenge social service workers to make these services available. [ABSTRACT FROM AUTHOR]
Keywords: Psychology of lesbians; Psychotherapy; Health of LGBTQ+ people; Social surveys; Mental health services use; Women's health -- Sociological aspects; American women; Boston (Mass.); Massachusetts; alcohol use; lesbians; mental health; mental health services; women

A TRANSSEXUAL'S NIGHTMARE: THE DETERMINATION OF SEXUAL IDENTITY IN ENGLISH LAW. - Taitz, Jerold (International Journal of Law & the Family, 1988)
Transsexualism or the Gender Dysphoria Syndrome is a psychological disorder recognized by the medical profession. Transsexuals are normal biological males or females who believe that they are members of their opposite sex 'trapped in the wrong body'. The disorder manifests itself in various neurotic or psychotic forms, leading even to suicide in extreme cases. Most medical specialists believe that the only relief for transsexuals is to bring their bodies into alignment with their psychological sex. This is done by 'sex-change' surgery and hormonal treatment. After surgery the transsexual takes on the appearance of his/her opposite sex. The surgery, which has a high danger ratio, is irreversible. The essential legal consequence of a 'sex-change' is the determination of the transsexual's post-operative sex. Some countries have resolved this matter by legislation, while others, including the United Kingdom, have left the subject of determination to ad hoc decisions of the courts. The English courts, fettered by long established biological definitions of sex, have held that transsexuals, despite having the irreversible appearance of their post-operative sex, remain members of their initial biological sex. After examining the views of the principal interest groups towards 'sex-change' surgery and the leading English cases, the writer recommends that the subject of a 'sex-change' and its legal consequences be referred to the Law Commission, in collaboration with the General Medical Council, to seek acceptable resolutions for the anomalous, and indeed bizarre, legal situation in which post-operative transsexuals find themselves. [ABSTRACT FROM AUTHOR]
Keywords: Transsexualism; Legal status of transsexuals; Gender dysphoria; Sex reassignment surgery; Psychology

Letters. - Starke, Peter R.; Chowdhury, Badrul A.; Dolor, Rowena J.; Williams, John W.; Simel, David L.; Califf, Robert M.; Oserman, Stuart; Watnick, Suzanne; Griffith, Todd F.; Coladonato, Joseph A.; Owen, William F.; Vassalotti, Joseph A.; et al. (JAMA: Journal of the American Medical Association, 2002)
; Presents letters to the editor pertaining to medical topics and research as of March 13, 2002. Efficacy of intranasal corticosteroids for acute sinusitis; Time of day of hemodialysis and effect on survival; Inappropriate prescribing for elderly patients; Sexual orientation and suicide risk among teenagers; Circadian variability in hemorrhagic stroke.

Lesbians in New Zealand: their mental health and satisfaction with mental health services. - Welch, Sarah; Collings, Sunny C.D.; Howden-Chapman, Phillippa; Welch, Sarah (Australian & New Zealand Journal of Psychiatry, 2000)
Objectives: To describe the mental health of lesbians in New Zealand, and to document their accounts of their experience of mental health services. Method: This is a descriptive cross-sectional study. A postal questionnaire, the Lesbian Mental Health Survey, was distributed via lesbian newsletters to 1222 women throughout New Zealand. Mental health measures included the General Health Questionnaire (GHQ-28), Interview Schedule for Social Interaction (ISSI), and respondents’ histories of sexual abuse and psychiatric histories. Experiences of mental health services were sought. Results: The estimated response rate was 50.8%. The respondent group were predominantly New Zealand European, highly educated, urban women between 25 and 50 years of age. Three-quarters had identified as lesbian for more than 5 years. Recent self-identification as lesbian was associated with higher GHQ score, as was being younger than 35, having a history of sexual abuse, and not living with a partner. Eighty percent of respondents had used mental health services sometime in their lives and nearly 30 percent of users had received ‘lesbian-unfriendly’ treatment at some point. One-sixth of respondents had experienced discrimination from service providers in the previous 5 years. Conclusion: While the mental health of lesbians is influenced by factors similar to those influencing women’s mental health in general, because of social factors, such as stigma and isolation, lesbians may be more vulnerable to common mental illnesses. Health professionals, mental health professionals in particular, need to raise their awareness of the issues lesbians face in dealing with their sexuality, therapeutic relationships and mental health services. Increased training about sexuality for health professionals, as well as further research into areas such as stress and stigma, sexual abuse and attempted suicide among lesbian women, is recommended. [ABSTRACT FROM AUTHOR]
Keywords: LESBIANS; MENTAL health services; MENTAL health; NEW Zealand; lesbian; mental health; service satisfaction; women

Challenging heterosexism in college health service delivery. - McKee, Michael B.; Hayes, Stuart F. (Journal of American College Health, 1994)
; Explores how human immunodeficiency virus and acquired immune deficiency syndrome, substance abuse, violence and hate-related crimes, suicide and heterosexism adversely affect the physical and emotional health of nonheterosexual college students. Overview of relevant healthcare issues for lesbians, bisexuals and gays; Examples of heterosexism in college health services; Authors' recommendations.
Keywords: UNITED States; HETEROSEXISM

Gay Youth: More Visible But Fewer Problems? - Alexander, Christopher J. (Journal of Gay & Lesbian Social Services, 2000)
In recent years there has been a growing awareness among parents and social service professionals of the complex sexual identity development of adolescents. Despite this, adolescents continue to struggle to define their sexual identity. Gay and lesbian adolescents in particular are at risk for a host of problems, including substance abuse and suicide. In this context it is important for social service researchers to study adolescent sexual identity and to report their findings in such a way as to be accessible to professionals and to the public. [ABSTRACT FROM AUTHOR]
Keywords: Lesbian youth; Gay youth; Teenagers' sexual behavior; Substance abuse; Gender identity; adolescent sexuality; Gay & lesbian youth; sexual identity development

Use of anabolic steroids and associated health risks among gay men attending London gyms. - Bolding, Graham; Sherr, Lorraine; Elford, Jonathan (Addiction, 2002)
; Examines the use of steroids among HIV-positive gays in London, England. Effects of steroids on physical and mental health; Association of steroid use with depression and suicidal thoughts; Injecting behavior of steroids.
Keywords: ENGLAND; LONDON (England)

Adolescent Masculinity, Homophobia, and Violence. - Kimmel, Michael S.; Mahler, Matthew (American Behavioral Scientist, 2003)
Since 1982, there have been 28 cases of random school shootings in American high schools and middle schools. The authors find (a) that the shootings were not a national problem but a series of local problems that occurred in "red states" or counties (places that voted Republican in the 2000 election); (b) that most of the boys who opened fire were mercilessly and routinely teased and bullied and that their violence was retaliatory against the threats to manhood; (c) that White boys in particular might be more likely than African American boys to randomly open fire; and (d) that the specific content of the teasing and bullying is homophobia. A link between adolescent masculinity, homophobia, and violence is proposed. Finally, the authors offer a few possible explanations as to how most boys who are teased and bullied achieve the psychological resilience that enables them to weather adolescence without recourse to random school violence. [ABSTRACT FROM AUTHOR]
Keywords: Homophobia; School violence; Masculinity; Adolescence; School shootings

Democratic Misalliances. - Ross, Benjamin (Dissent (00123846), 2003)
; Discusses the alliances of Democratic Leadership Council of the U.S. and strategies adopted by it to win votes. Measures taken by New Democrats to draw votes from upscale suburban constituency including favor for gay rights and raising abortion issue; Approach of gun control followed by New Democrats to retain votes of Blacks; Maintenance of Democratic support by relying on Republican racism and xenophobia by democrats.
Keywords: UNITED States

Spivak's 'Echo': theorizing otherness and the space of response. - Hiddleston, Jane (Textual Practice, 2007)
This article uses Spivak's engagement with the myth of Echo and Narcissus to theorize the position of the voice of the other within her work. In the essay ‘Echo’, Spivak describes Echo's voice as an imitation without intention, a mimetic form within which the agency of the subject lies hidden. This concept of an imitation without intention can, moreover, be deployed in a reading of ‘Can the subaltern speak?’, since widow suicide or ‘sati’ is also conceived as an act of imitation in which the women's intention is inaccessible both to colonial officials and to native historians. Spivak's account of ‘sati’ can for this reason be seen to propose an alternative theory of response in its opening up of the ambivalence of the women's intentionality. In addition, Spivak's own ‘Narcissus’ or theorizing persona is self-doubting and continually mutating, so that she never sets herself up as the holder of a clear subject position. Despite critics' vilification of her self-consciousness then, this article suggests that her exploration of Echo and, the hesitancy of her Narcissus, provide a highly informative example of how to theorize alterity without obfuscating or speaking in the place of the other. [ABSTRACT FROM AUTHOR]
Keywords: IMITATION; INFLUENCE (Psychology); ORIGINALITY (Aesthetics); IDENTIFICATION (Psychology); STYLE, Literary; FICTION -- Technique; CONTENT analysis (Communication); QUANTITATIVE research; LITERATURE; SOCIAL influence; alterity; Echo; Gayatri Chakravorty Spivak; mimesis; Narcissus; subaltern

Counseling Satisfaction of Gay, Lesbian, and Bisexual College Students. - Sweet, Michael J. (Journal of Gay & Lesbian Social Services, 1996)
This paper investigates the satisfaction of gay male, lesbian, and bisexual college students with their counseling experiences. The sample of 31 research participants was interviewed using the Gay/Bisexual Counseling Satisfaction Survey, a demographic questionnaire, and the Beck Depression Inventory (BDI). Results indicated strong satisfaction with current counseling and counselors. Sexual orientation issues and loneliness were the most frequent presenting problems; these were positively associcated with counseling satisfaction, as was reporting barriers to counseling. BDI scores were copmarable to nonclinical samples, although there was frequent reporting of suicidal ideation. Implications for service delivery to this population are discussed. [ABSTRACT FROM PUBLISHER]

TURNCOAT BODIES: Sexuality and Sex Work under Militarization in Sri Lanka. - Tambiah, Yasmin (Gender & Society, 2005)
In Sri Lanka's armed conflict, gender,sexuality, and sex work are intermeshed with militarized nationalism. Militarization entrenches gender performances and heteronormative schemes while enabling women to transgress these-whether as combatants or as sex workers. Familiarly, in this nationalist encounter, women are expected to safeguard culture, notably through proper dress and sexual conduct. Sexual activity that challenges containment arouses anxiety because loyalty to military group or communal boundary can be compromised. Drawing on three examples-a dress code call by a Liberation Tigers of Tamil Eelam women's wing, consequences for a woman alleged to be a sex worker, and the public stripping of an alleged suicide bomber at a military checkpoint-this article explores how gendered behaviors and sexualities marked as culture are constructed and controlled in the interests of militarized, nationalist projects; how women can be both agents and objects of these controls; and the implications for women who refuse to comply. [ABSTRACT FROM AUTHOR]
Keywords: SRI Lanka; culture; mulitarization; nationalism; sex work; sexuality; Sri Lanka

Issue Evolution, Political Parties, and the Culture Wars. - Lindaman, Kara; Haider-Markel, Donald P. (Political Research Quarterly, 2002)
; Examines partisan polarization on several culture war issues using the issue evolution framework. Inclusion of pornography, environment, gun control, and gay civil rights; Evidence of partisan polarization among political elites; Assessment of the top-down versus bottom-up paths of influence among Republicans and Democrats.

Social alienation in gay youth. - Sullivan M; Wodarski JS (Journal of Human Behavior in the Social Environment, 2002)
The focus of this article is twofold; first, to review known risk factors for gay youth including: substance abuse, depression, suicide, and HIV risks, secondly, to determine the impact of social support factors; specifically parental, peer and religious support factors for this population. Evidence suggests that gay and lesbian youth are at high risk for isolation and subsequent psychological damage that results from social alienation. Insight into the problems faced by gay youth, along with some helpful intervention strategies for professionals working with a gay adolescent population is discussed. [ABSTRACT FROM AUTHOR]

EMOTIONAL, BEHAVIORAL, AND HIV RISKS ASSOCIATED WITH SEXUAL ABUSE AMONG ADULT HOMOSEXUAL AND BISEXUAL MEN. - Bartholow, Bradford N.; Doll, Lynda S.; Joy, Dan; Douglas Jr., John M.; Bolan, Gail; Harrison, Janet S.; Moss, Patricia M.; McKirnan, David (Child Abuse & Neglect, 1994)
From May 1989 through April 1990, 1,001 adult homosexual and bisexual men attending urban sexually transmitted disease clinics were interviewed regarding abusive sexual contacts during childhood and adolescence. Sexual abuse was found to be significantly associated with mental health counseling and hospitalization, psychoactive substance use, depression, suicidal thought or actions, social support, sexual identity development, HIV risk behavior including unprotected anal intercourse and injecting drug use, and risk of sexually transmitted diseases including HIV infection. Data suggest that sexual abuse may have a wide-ranging influence on the quality of life and health risk behavior of homosexual men. Increased awareness as to the potential outcomes of male sexual abuse is critically important to the design and implementation of medical and psychological services for sexually abused men. (English) [ABSTRACT FROM AUTHOR]
Keywords: Sex crimes; Homosexuality; Bisexual men; Gender identity; HIV; AIDS; Quality of life; Health counseling; Adult outcome; Males; Sexual abuse; Sexual identity

Lifetime Prevalence of Mental Disorders and Suicide Attempts in Diverse Lesbian, Gay, and Bisexual Populations. - Meyer, Ilan H.; Dietrich, Jessica; Schwartz, Sharon (American Journal of Public Health, 2008)
Past studies have reported little about variability in mental disorders among lesbians, gay men, and bisexual individuals. We assessed the prevalence of psychiatric disorders in 388 lesbian, gay, and bisexual Black, Latino, and White individuals. Black lesbians, gay men, and bisexual individuals had lower prevalence of all disorders than did Latino and White individuals; younger cohorts had fewer mood disorders than did older cohorts; bisexual persons had more substance use disorders than did gay men and lesbians; and Latino respondents attempted suicide more often than did White respondents. (Am J Public Health. 2008;98:1004-1006. doi: 10.2105/AJPH.2006.096826) [ABSTRACT FROM AUTHOR]
Keywords: Mental illness; Suicidal behavior; Homosexuality; Lesbians; Gay men; Bisexuals; Hispanic American LGBTQ people; Psychiatry; Sexual health

Risk Factors for Shooting Gallery Use and Cessation among Intravenous Drug Users. - Celentano, David D.; Vlahov, David; Cohn, Sylvia; Anthony, James C.; Solomon, Liza; Nelson, Kenrad E. (American Journal of Public Health, 1991)
Background. Shooting galleries, locations where intravenous drug users (IVDUs) can rent or borrow needles and syringes, are a high-risk environment for HIV-1 transmission. This study investigates risk factors for lifetime attendance at shooting galleries and differentiates characteristics of those who continue to frequent shooting galleries and those who have stopped. Methods. We interviewed 2615 active IVDUs in Baltimore in 1988 and 1989 and determined patterns of IV drug use, sociodemographics, and HIV-1 serostatus as related to persistence vs cessation of shooting gallery use. Results. Over half (52%) of active IVDUs reported ever using a shooting gallery, with 33% reporting use within the prior 3 months. In multivariate analysis, lifetime shooting gallery use was associated with male gender, homosexuality/bisexuality, low socioeconomic status, Black race, and heavier drug involvement. Persistent shooting gallery users were more frequently male, homosexual/bisexual, homeless, less educated, and started IV drug use more recently compared with those who ceased going to shooting galleries. Conclusions. Shooting gallery attendance may be pragmatic from a sociological and economic perspective, but it carries with it a heightened risk of acquiring HIV-1 infection. [ABSTRACT FROM AUTHOR]
Keywords: Intravenous drug abusers; HIV infections; Hypodermic needles; Syringes; Infectious disease transmission; Baltimore (Md.); Maryland

Lesbian, gay, and bisexual youth in community settings: Personal challenges and mental health... - D'Augelli, Anthony R.; Hershberger, Scott L. (American Journal of Community Psychology, 1993)
; Studies 194 lesbian, gay and bisexual youth who attended programs in 14 community centers to determine the personal challenges they face due to their sexual orientation and their responses to these stresses. Awareness of sexual orientation; Suicide attempts.
Keywords: UNITED States

WHAT SCHOOLS CAN DO TO HELP GAY/LESBIAN/BISEXUAL YOUTH: A HARM REDUCTION APPROACH. - van Wormer, Katherine; McKinney, Robin (Adolescence, 2003)
In recognition of the fact that heterosexism is one of the most significant realities of adolescents' day-to-day experiences in school, this paper examines the school environment in terms of disempowering and empowering aspects. It is argued that failure to take a proactive stance to help youth with gender identity issues is a major cause of psychological problems, leading in some cases to suicide, alcohol and other drug abuse, and homelessness. [ABSTRACT FROM AUTHOR]
Keywords: GENDER identity; SCHOOL environment; GLBT people; HUMAN behavior; DRUGS -- Overdose; SUBSTANCE abuse; Preventive Intervention

Suicide Among Homosexual Adolescents. - Kourany, Ronald F.C. (Journal of Homosexuality, 1987)
Investigates suicide among homosexual adolescents. Suggestion that many experts are not working with homosexual adolescents; Indication that majority of the experts treating homosexual adolescents considered them to be at higher risk for suicide; Increasing number of adolescents who are trying to kill themselves.
Keywords: Suicide; Gay teenagers; Homosexuality; Teenagers' sexual behavior; Sexual orientation

A Review of Lesbian Depression and Anxiety. - Kerr, Shelly K.; Emerson, Alice M. (Journal of Psychology & Human Sexuality, 2003)
The Surgeon General's first report on mental health identified depression and anxiety as significant mental health issues that disproportionately affect women. Research indicates that lesbians experience depression at rates that parallel those of the general female population, suggesting that depression is an important mental health issue for lesbians. Given the high rate of comorbidity between depression and anxiety disorders, it is likely that many depressed lesbians have struggled with problems related to anxiety as well. This paper reviews literature pertaining to lesbians and depression including incidence rates, risk factors, suicidality and treatment approaches, and stress and anxiety that may also contribute to the experience of depression among lesbians. [ABSTRACT FROM AUTHOR]
Keywords: Mental health; Anxiety; Lesbians; Mental depression; Psychology of women; anxiety; depression; lesbian; Review

The impact of victimization on the mental health and suicidality of... - Hershberger, Scott L.; D'Augelli, Anthony R. (Developmental Psychology, 1995)
; Studies lesbian, gay and bisexual youths to determine the impact of verbal abuse, threat of attacks and assault on their mental health, including suicide. Participants and procedure; Measures; Structural equation modeling; Multiple regression analyses.

Perceptions of life and death among suicidal gay adolescents. - Ben-Ari, Adital Tirosh; Gil, Sharon (Omega: Journal of Death & Dying, 1998)
Attempts to learn about perceptions of life and death among suicidal gay youth. Association of these perceptions with the suicide attempt; Three categories of Orbach's model.
Keywords: Gay youth; Suicidal behavior; Youth & death

Sexual Orientation and Risk Factors for Suicidal Ideation and Suicide Attempts Among Adolescents and Young Adults. - Silenzio, Vincent M. B.; Pena, Juan B.; Duberstein, Paul R.; Cerel, Julie; Knox, Kerry L (American Journal of Public Health, 2007)
Same-gender sexual orientation has been repeatedly shown to exert an independent influence on suicidal ideation and suicide attempts, suggesting that risk factors and markers may differ in relative importance between lesbian, gay, and bisexual individuals and others. Analyses of recent data from the National Longitudinal Study of Adolescent Health revealed that lesbian, gay, and bisexual respondents reported higher rates of suicidal ideation and suicide attempts than did heterosexual respondents and that drug use and depression were associated with adverse outcomes among heterosexual respondents but not among lesbian, gay, and bisexual respondents. (Am J Public Health. 2007;97:2017-2019. doi:10. 2105/AJPH.2006.095943) [ABSTRACT FROM AUTHOR]
Keywords: Sexual orientation; Psychology of lesbians; Bisexuals; PSYCHOLOGY; Adolescent psychology; Psychology; Risk factors in suicidal behavior; Gay men; Young adult psychology

Growing Up with a “Spoiled Identity”. - Grossman, Arnold H. (Journal of Gay & Lesbian Social Services, 1997)
Being a lesbian, gay or bisexual youth means having the stigma of homosexuality or bisexuality. A stigma is anything that discredits an individual and leads to one being assigned a “spoiled identity.” With reference to lesbian, gay and bisexual youth, the stigma is considered a blemish on one's character that often leads to stereotyping and stigmatisation. This homophobia puts many lesbian, gay and bisexual youth at risk for suicide, chemical abuse, dropping out of school, verbal and physical abuse, homelessness, prostitution, HIV infection, and psychosocial developmental delays. Approaches and strategies for working with lesbian, gay and bisexual youth are suggested and trends and issues about homosexuality in the United States, with a potential impact on lesbian, gay and bisexual youth, are discussed. [ABSTRACT FROM PUBLISHER]

Post-traumatic stress disorder among recently diagnosed patients with HIV/AIDS in South Africa. - Olley, B. O.; Zeier, M. D.; Seedat, S.; Stein, D. J. (AIDS Care, 2005)
This study examined the prevalence of and factors associated with post-traumatic stress disorder in recently diagnosed HIV/AIDS patients in South Africa. One hundred and forty-nine (44 male, 105 female) recently diagnosed HIV/AIDS patients (mean duration since diagnosis =5.8 months, SD =4.1) were evaluated. Subjects were assessed using the MINI International Neuropsychiatric Interview (MINI), the Carver Brief COPE coping scale and the Sheehan Disability Scale. In addition, previous exposures to trauma and past risk behaviours were assessed. Twenty-two patients (14.8%) met criteria for PTSD. Current psychiatric conditions more likely to be associated with PTSD included major depressive disorder (29% in PTSD patients versus 7% in non-PTSD patients, p = 0.004), suicidality (54% versus 11%, p =0.001) and social anxiety disorder (40% versus 13%, p = 0.04). Further patients with PTSD reported significantly more work impairment and demonstrated a trend towards higher usage of alcohol as a means of coping. Discriminant function analysis indicated that female gender and a history of sexual violation in the past year were significantly associated with a diagnosis of PTSD. Patients whose PTSD was a direct result of an HIV/AIDS diagnosis (8/22) did not differ from other patients with PTSD on demographic or clinical features. In the South African context, PTSD is not an uncommon disorder in patients with HIV/AIDS. In some cases, PTSD is secondary to the diagnosis of HIV/AIDS but in most cases it is seen after other traumas, with sexual violation and intimate partner violence in women being particularly important. [ABSTRACT FROM AUTHOR]
Keywords: POST-traumatic stress disorder; HIV-positive persons; AIDS (Disease) -- Patients; DEPRESSION, Mental; DEMOGRAPHIC surveys; SOUTH Africa

Development and Health Care Needs of Lesbians. - Lehmann, Joan B.; Lehmann, Christoph U.; Kelly, Patricia J. (Journal of Women's Health, 1998)
Lesbians have complained about the lack of awareness and sensitivity of their health care providers, resulting in unnecessary examinations and inappropriate focus on reproductive issues. This study attempted to identify psychosocial and health care needs of lesbians, to assess relationships with primary care providers and disclosure of sexual orientation, and to describe the chronologic features of a sexual identity and lifestyle. An anonymous, self-administered, written questionnaire was distributed through a campus lesbian organization. Fifty-three women (median age 23 years) completed the questionnaire Whereas 60% had disclosed their sexual orientation to their parents, only 31% had "come out" to their health care provider. Of participants who had disclosed their sexual preference to a provider, 27% reported a negative effect on their health care, 57% of participants who never had penile intercourse had annual Papanicolaou smears, and 16% felt pressured in the past to accept birth control from a physician. Lesbian sexuality was associated with several risk factors, such as childhood abuse (20%), alcohol or drug problems (39%), suicide attempts (27%), depression (49%), and physical or verbal abuse at school (34%). Average age of awareness of sexual orientation was 15 years, and average age of first homosexual activity was 17 years. Lesbians are at risk for depression, substance abuse, and suicide attempts Although most would like to confide in their physician, few do because of fears of negative reactions. Communication must be improved to better address their specific health care needs. [ABSTRACT FROM AUTHOR]
Keywords: Lesbians; Medical care; Lifestyles; Sexual orientation; Psychosocial factors; Questionnaires

Identifying risk factors for gay and lesbian suicidal behavior: Implications for mental health... - McBee, Sandra M.; Rogers, James R. (Journal of Mental Health Counseling, 1997)
Examines risk factors for gay and lesbian suicidal behavior. Previous attempts; Substance abuse; Family dysfunction; Identity confusion; Social ties; Social inequity; Implications for mental health counselors.
Keywords: Gay people; Suicidal behavior

Better dead than gay? - Nicholas, Jonathan; Howard, John (Youth Studies Australia, 1998)
Presents information on a study on suicide ideation and attempt among a sample of gay and straight-identified males aged 18 to 24 in Australia. Methodology of the study; Discussion on the results of the study.
Keywords: Suicidal behavior; Psychology; Suicidal behavior in young adults; Australia

National Lesbian Health Care Survey: Implications for Mental Health Care. - Bradford, Judith; Ryan, Caitlin; Rothblum, Esther D. (Journal of Lesbian Studies, 1997)
This article presents demographic, lifestyle, and mental health information about 1,925 lesbians from all 50 states who participated as respondents in the National Lesbian Health Care Survey (1984-1985), the most comprehensive study on U.S. lesbians to date. Over half the sample had thoughts about suicide at some time, and 18% had attempted suicide. Thirty-seven percent had been physically abused as a child or adult, 32% had been raped or sexually attacked, and 19% had been involved in incestuous relationships while growing up. Almost one third used tobacco on a daily basis, and about 30% drank alcohol more than once a week, 6% daily. About three fourths had received counseling at some time, and half had done so for reasons of sadness and depression. Lesbians in the survey also were socially connected and had a variety of social supports, mostly within the lesbian community. However, few had come out to all family members and coworkers. Level of openness about lesbianism was associated with less fear of exposure and with more choices about mental health counseling. [ABSTRACT FROM AUTHOR]
Keywords: Lesbian health; Lifestyles; Lesbian community; Mental health services; Suicidal behavior; Medical care surveys

Correlates of same-sex sexual behavior in a random sample of Massachusetts high school students. - Faulkner, Anne H.; Cranston, Kevin (American Journal of Public Health, 1998)
Objectives. This study documented risk behaviors among homosexually and bisexually experienced adolescents. Methods. Data were obtained from a random sample of high school students in Massachusetts. Violence, substance use, and suicide behaviors were compared between students with same-sex experience and those reporting only heterosexual contact. Differences in prevalence and standard errors of the differences were calculated. Results. Students reporting same-sex contact were more likely to report fighting and victimization, frequent use of alcohol, other drug use, and recent suicidal behaviors. Conclusions. Students with same-sex experience may be at elevated risk of injury, disease, and death resulting from violence, substance abuse, and suicidal behaviors. [ABSTRACT FROM AUTHOR]
Keywords: GAYS -- Sexual behavior; BISEXUALS -- Sexual behavior; HIGH school students -- Sexual behavior; STUDENTS -- Sexual behavior; MASSACHUSETTS

Euthanasia and physician-assisted suicide in homosexual men with AIDS. (cover story) - Bindels, Patrick J.E.; Krol, Anneke (Lancet, 1996)
; Presents an investigation into the incidence of medical decisions concerning the end of life (MDEL) among homosexual men diagnosed with AIDS in the Netherlands. Euthanasia as a palliative effect; Methods of study; Findings and interpretation; Discussion.
Keywords: NETHERLANDS

A Comparison of Three Psychological Testings of a Transsexual. - Hill, Evelyn F. (Journal of Personality Assessment, 1980)
This case illustrates the use of psychological testing in assessing change over a period of eight years. Evaluations were done six years before transsexual surgery, after surgery, and at the completion of psychotherapy. The initial tests were rife with morbid suicidal and pathological content. Psychotherapy in a residential setting was recommended and accepted. Psychological testing after surgery revealed identity conflicts, guilt, and underlying depression. The final evaluation revealed remarkable changes. Her ego was good. She was not handicapped by defenses. She was using her intelligence for systematic thinking. Her anxiety level was within normal limits. and concerns were realistic to her situation. [ABSTRACT FROM AUTHOR]
Keywords: Transsexuals; Psychological tests

I Will Survive. - Jordan, Karen M.; Vaughan, Jill S.; Woodworth, Katharine J. (Journal of Gay & Lesbian Social Services, 1998)
Much has been written about gay, lesbian, and bisexual students' negative experience, such as harassment and hate crimes, in high school. This study was undertaken to further explore these issues, as well as to elucidate the positive coping skills, traits, and experiences of the students. Thirty-four current high school students completed a questionnaire containing both original items and previously-developed scales. The majority of the students (73.5%) reported receiving support regarding sexual orientation issues from someone at school, and 41.2% reported that information regarding gay, lesbian, and bisexual issues was available from school staff. However, 35.3% reported a previous suicide attempt, a figure consistent with previous literature. Additional positive and negative high school experiences, as well as their interrelationships, are discussed. [ABSTRACT FROM PUBLISHER]

Asian/Pacific Islander Adolescent Sexual Orientation and Suicide Risk in Guam. - Pinhey, Thomas K.; Millman, Sara R. (American Journal of Public Health, 2004)
Objectives. We examined the effects of same-sex orientation on suicide risks for Guam's Asian/Pacific Islander adolescents. Methods. We used a probability sample and logistic regression analysis to identify suicide risk factors. Results. Same-sex orientation was associated with a greater risk of suicide attempt, especially for boys. Adolescents who reported suffering physical abuse in the context of a romantic relationship, engaging in binge drinking, and experiencing feelings of hopelessness were at greater risk for suicidal ideation and attempts. Race/ethnicity was associated with suicide risk for both boys and girls, and patterns suggest that membership in the same racial/ethnic group decreased suicide risk for girls and increased risk of suicide for boys. Conclusions. Gay, lesbian, and bisexual Asian/Pacific Islander adolescents in Guam deserve intervention and counseling programs to reduce suicide risk. (Am J Public Health. 2004;94:1204-1206). [ABSTRACT FROM AUTHOR]
Keywords: Suicidal behavior; Adolescent psychology; Suicide risk factors; Pacific Islanders; Asians; Guam

Plans to hasten death among gay men with HIV/AIDS: relationship to psychological adjustment. - Goggin, K.; Sewel, M.; Ferrando, S.; Evans, S.; Fishman, B.; Rabkin, J. (AIDS Care, 2000)
This study assessed the prevalence and nature of thoughts and future plans to end one’s life in a group of gay men with HIV/AIDS over an 18-month period. HIV-positive men ( n = 167) participated in a series of clinical interviews which measured current health status, current and past psychiatric disorders, current levels of distress, and thoughts and plans about ending their lives currently or at some future point. A small number of HIV-positive men (17%) reported serious thoughts or plans to end their lives at some point in the future which were stable over an 18-month period. No differences in psychiatric or medical measures were observed among men with and without thoughts/plans at either assessment point. In the absence of current psychiatric disorders, such thoughts or plans about the future may represent one way to maintain control and independence in the face of the uncertainty of life with HIV illness. [ABSTRACT FROM AUTHOR]
Keywords: GAY men -- Attitudes; HIV-positive persons; SUICIDAL behavior; ATTITUDE (Psychology)

Poem 754 Workshop Discussion. - Ringler-Henderson, Ellin; Dobson, Joanne; Faderman, Lillian (Women's Studies, 1989)
; Discusses the meaning of Emily Dickinson's poem 754. Comparison of life with a loaded gun; Dickinson's view of heterosexual marriage; Expression of pain.
Keywords: DICKINSON, Emily, 1830-1886; LIFE in literature; FIREARMS in literature

Constructing Genograms With Lesbian Clients. - Magnuson, Sandy; Norem, Ken; Skinner, Christopher H. (Family Journal, 1995)
; The article focuses on the use of genogram construction as a technique for increasing levels of differentiation in clients with a lesbian obsession. Researchers have shown that a higher percentage of lesbians obtain mental health services than their heterosexual counterparts. A national survey conducted in 1987 showed that 73% of the 1,917 lesbians contacted were in therapy or had been prior to the study. Treatment issues addressed with lesbian clients are representative of those presented by heterosexual clients. In therapy with lesbian clients, issues such as domestic violence, unresolved trauma from abuses suffered during childhood, and confusion regarding spirituality have been reported. Lesbian clients have presented elevated levels of anxiety, fear, loneliness, and career problems. Lesbians often seek counseling for depression resulting from ended or unsatisfactory relationships, non-events, estrangement from family, secrecy, shame, fear of disclosure, and guilt. The myriad psychosocial stressors place the lesbian population at a greater risk of contemplating suicide. Thoughts of suicide are often responses to the pressures of living in a homophobic society.

Suicide Risk among People Living with AIDS. - Mancoske, Ronald J.; Wadsworth, Cynthia Martin; Dugas, Darlene S.; Hasney, Joseph A. (Social Work, 1995)
Using data from Louisiana vital statistics records, the authors found an increased suicide risk for people with AIDS. Between 1987 and 1991 the suicide rate for people with AIDS (175 per 10,000) was 134.6 rimes that of the general population (1.3 per 10,000). The suicide rate of people with AIDS in the metropolitan New Orleans area (126 per 10,000) was half that of the state's nonmetropolitan areas (249 per 10,000). This article explores the implications of this astounding suicide rate for social work practice. [ABSTRACT FROM AUTHOR]
Keywords: LOUISIANA; gay men; HIV/AIDS; rural areas; stressors; suicide rate

Chapter 1: AIDS and Homophobia/Heterosexism. - Appleby, George A. (Journal of Gay & Lesbian Social Services, 1995)
Homophobia and heterosexism are complementary social processes that shaped the social construction and the public health response to AIDS. Both concepts view gay and lesbian oppression from different vantage points. Homophobia is a weapon of sexism and is manifested in fear and hatred. Heterosexism is an ideological system that denigrates non-heterosexual behavior. Both processes are well served by the social institutions of family, religion, law, and the ideologies of sexuality and gender. The consequences have been societal and personal: inadequate HIV medical and social services; lack of a national AIDS policy; widespread discrimination and prejudice against gay men, lesbians, and persons living with AIDS; stress, violence, and suicide; substance abuse; and HIV risk behavior and relapse. Mental health and social services, social supports, education and prevention programs, community development, and social action to broaden civil rights and to challenge institutional oppression are required to counter the ravages of hate and discrimination. [ABSTRACT FROM PUBLISHER]

THE PINK TRIANGLE THE PERSECUTION OF HOMOSEXUAL MALES IN CONCENTRATION CAMPS IN NAZI GERMANY. - Lautmann, Rüdiger (Journal of Homosexuality, 1980)
Having analyzed the fragmentary records of Nazi concentration camps, the author reports on the number and treatment of male homosexual prisoners. The total number of inmates officially defined as homosexual is estimated at about 10,000 although the number incarcerated varied greatly from camp to camp and as the war progressed. Pink-triangle prisoners had low social status, often were isolated from other inmates, and, as compared to political prisoners and Jehovah's Witnesses, more frequently were given the most difficult work assignments and less frequently were assigned to light duties. They had a higher death rate and a lower survival rate upon release. Suicide rates were not significantly different from those of the other inmate groups studied. Pink-triangle prisoners were not subjected to exceptionally cruel treatment in all camps and at all times, however, and were not the only group of prisoners subjected to extreme abuse.
Keywords: Prisoners' sexual behavior; Gay men; Homosexuality; Concentration camps; Detention of persons; Political prisoners; Germany

Homosexuality, Suicide, and Parasuicide in Australia. - Buhrich, Neil; Loke, Carlson (Journal of Homosexuality, 1988)
Discusses homosexuality, suicide, and parasuicide in Australia. Epidemiology of suicide; Terminology and epidemiology of parasuicide; Relationship between parasuicide and male homosexuality.
Keywords: Homosexuality; Suicide; Parasuicide; Men's sexual behavior; Male homosexuality; Australia

Lesbian Youth Support Information Service (LYSIS): Developing a Distance Support Agency for Young Lesbians. - Bridget, Jan; Lucille, Sandra (Journal of Community & Applied Social Psychology, 1996)
The Lesbian Youth Support Information Service (LYSIS) was established in 1991 as a result of research conducted into the needs and experiences of young lesbians. This research found that young lesbians are vulnerable to mental health problems, including depression, attempted suicide, self-harming behaviours and alcohol misuse, as well as isolation and social rejection. There were also strong indications that young lesbians are most vulnerable when they are coming to terms with their sexual orientation. LYSIS offers support to young lesbians in four main ways: correspondence counselling; telephone counselling; peer support; and information. LYSIS is part of an umbrella organization, the Lesbian Information Service (LIS), which provides indirect support for young lesbians including publishing, education and training, projects and campaigning. [ABSTRACT FROM AUTHOR]
Keywords: Lesbian youth; Lesbians; Mental health; Mental health services; Medical care; Lesbian health; Associations, institutions, etc.; counselling; information; lesbian; mental health; peer support; support; young women

Comparison of Stress and Stress Management Between Lesbian and Heterosexual Women. - Bernhard, Linda A.; Applegate, Julia M. (Health Care for Women International, 1999)
; Presents information on a study that compared the experiences of stress and the methods of stress management used by lesbian and heterosexual women. Factors responsible; Alcohol use; Violence; Suicide; Method; Results; Discussion.

I Never Felt Like Myself. - Winden, Jordan (Transgender Tapestry, 2004)
Recounts the experiences of the author as a transsexual. Thoughts on suicide; Discovery of a fellow transsexual; Research done by the author on transsexualism.
Keywords: Transsexuals; Transgender people; Suicide; Transsexualism; Persons

Choosing Sides in the Cultural War. - Tucker, Scott (Humanist, 1993)
; Confronts the responses and criticisms to two articles on gays in the military by Leo N. Miletich and Scott Tucker in the May/June 1993 issue of The Humanist. Military ban on gays; High suicide rate among gay youth; Secular humanists' and religious conservatives' common patriarchal culture; Acquired Immunodeficiency Syndrome (AIDS) scare in the military; Senator Nunn's `compromise solution'; `Don't Ask, Don't Tell' policy.

Sodomy in Enlightenment Prussia: From Execution to Suicide. - Steakley, James D. (Journal of Homosexuality, 1988)
Traces the history of sodomy in Germany during the Enlightenment period. Statute against sodomy; Association between guilt and homosexuality; Existence of homosexuality in classical antiquity.
Keywords: Sodomy; Homosexuality; Sex crimes; History; Enlightenment; Germany

The Pink Triangle. - Lautmann, Rüdiger (Journal of Homosexuality, 1981)
Having analyzed the fragmentary records of Nazi concentration camps, the author reports on the number and treatment of male homosexual prisoners. The total number of inmates officially defined as homosexual is estimated as about 10,000, although the number incarcerated varied greatly from camp to camp and as the war progressed. Pink-triangle prisoners had low social status, often were isolated for other inmates, and, as compared to political and JehovahÆs Witnesses, more frequently were given the most difficult work assignments and less frequently were assigned to light duties. They had a higher death rate and a lower survival rate upon release. Suicide rates were not significantly different from those of the other inmate groupÆs studies. Pink-triangle prisoners were not subjected to exceptionally cruel treatment in all camps and at all times, however, and were not the only group of prisoner subject to extreme abuse. [ABSTRACT FROM PUBLISHER]

VITALITY AND GROWTH IN HI V-INFECTED GAY MEN. - Schwartzberg, Steven S. (Social Science & Medicine, 1994)
The emphasis in the psychosocial literature on Human Immunodeficiency Virus (HIV) has been placed, correctly, on the traumatic impact of AIDS in terms of mortality, bereavement, suicide, psychopathology, and coping with life amid enormous multiple stressors. However, an important aspect of the HIV epidemic has been paid only minimal attention: many HIV-positive gay men have experienced beneficial, or even life-transforming, aspects of their situation. Seven }HV-positive gay men are described here who have successfully integrated HIV into a framework of world- and self-beliefs that allows for coherence, stability, emotional vitality, and positive self-regard. Eight general characteristics of these men are presented. These men represent a subgroup from a sample of 19 subjects in a qualitative clinical interview study exploring how HIV-positive gay men ascribe meaning to AIDS and their own HIV infection [1]. [ABSTRACT FROM AUTHOR]
Keywords: Health of gay men; HIV infections; AIDS patients; Mortality; Medical care; Epidemics; AIDS; HIV; meaning; resilience

The Confessions of Frankenstein (GIRL). - Hignutt, Diana (Transgender Tapestry, 2005)
Relates the story of a brother with a secret illness. Efforts to find information about the illness; Challenges encountered in dealing with the illness; Health problems suffered by the man; Decision to commit suicide.
Keywords: Diseases; Suicide; Brothers; Secrecy; Struggle

Goodbye Note to My Lover (Poem). - Gibson, Michelle (Journal of Lesbian Studies, 2004)
Presents the poem "Goodbye Note to My Lover," by Michelle Gibson.
Keywords: Lesbian relationships; Same-sex relationships; Lesbians; Depression; Lesbian; Lovers; Sadness; Suicide; Gibson, Michelle; Goodbye Note to My Lover (Poem)

Adolescent Homosexuality: Preface. - Deisher, Robert W. (Journal of Homosexuality, 1989)
Discusses studies on cross-cultural view of adolescent homosexuality. Assumptions about the surface behaviors and social patterns of gay teenagers; Limitations in Alfred Kinsey and Evelyn Hooker's studies on adult homosexuality; Association between adolescent homosexuality and suicide.
Keywords: Gay teenagers; Teenagers' sexual behavior; Sexual orientation; Homosexuality; Kinsey, Alfred C., 1894-1956; Hooker, Evelyn, 1907-1996

In memory. - Jeffreys, J.E. (TDR: The Drama Review (MIT Press), 1991)
Presents a tribute to Ethyl Eichelberger who was found dead in his Staten Island home August 12, 1990. Grande Dame of Queer Theatre, playwright, actor, performance artist and East Village drag queen. Diagnosed with AIDS; Suicide; Born James Roy Eichelberger in Pekin, Ill.; Background; Career.
Keywords: Eichelberger, Ethel

IOM: Data on Health of Lesbian, Gay, Bisexual, and Transgender Persons Needed. - Kuehn, Bridget M. (JAMA: Journal of the American Medical Association, 2011)
The article emphasizes the need to ask patients about their sexual orientation in order to improve the health status of lesbian, gay, bisexual and transgender (LGBT) people based on a report from the Institute of Medicine (IOM) released in the U.S. in March 2011. Family medicine professor Robert Graham noted the importance of gathering data on sexual orientation in medical records, demographic surveys and research. The increased risk of depression, suicidal thoughts and substance abuse among LGBT people is discussed.
Keywords: Sexual orientation; LGBTQ+ people; Substance abuse; Medical records; Demographic surveys; Institute of Medicine (U.S.); Graham, Robert

Suicidality and HIV status. - McKegney, F.P.; O'Dowd, M.A. (American Journal of Psychiatry, 1992)
; Presents a study in which the authors undertook a study of suicidality and HIV status to examine the relationship between suicidality and HIV infection in its various stages. Method; Results; Discussion.

Suicidal behaviour in gay, lesbian, and bisexual youth. - Bagley, Christopher; D'Augelli, Anthony R (BMJ: British Medical Journal, 2000)
; Debates over the repeal of Section 28 of the Local Government Act of 1998 in Great Britain which forbids the promotion of homosexuality in the country.
Keywords: GREAT Britain

Preventing Suicide Risk Among Sexual Minority Youth. - Russell, Stephen T.; Marks, Steven R. (Prevention Researcher, 2006)
The article addresses issues related to sexual minority youth sucidality risk. Coming into one's sexual identity is a developmental task that often happens within a challenging context. While a minority of heterosexual and sexual minority youth experience suicidality, it often occurs among sexual minority youth. Those who work with sexual minority youth can provide support at the family and individual levels as well as through policy change at the institution, community, and state levels.
Keywords: Sexual minority youth; Suicidal behavior; Suicide; Teenage suicide; Minority youth

ODDS RATIOS FOR SUICIDE ATTEMPTS AMONG GAY AND BISEXUAL MEN. - Paul, Jay P. (American Journal of Public Health, 2003)
; The response of the author to a letter to the editor about his article "Suicide Attempts Among Gay and Bisexual Men: Lifetime Prevalence and Antecedents," published in a previous issue of the "American Journal of Public Health," is presented.
Keywords: LETTERS to the editor; SUICIDAL behavior

Sexual Orientation and Youth Suicide. - Remafedi, Gary (JAMA: Journal of the American Medical Association, 1999)
; Discusses studies that have been done on youth suicide. Impact of sexual orientation on suicide rates; The United States government `Report of the Secretary's Task Force on Youth Suicide'; Research on homosexuality that identified a high prevalence of suicide attempts among young men; Higher rates of attempted suicide among homosexual youths than heterosexual ones.

Homosexuality, Psychopathology, and Suicidality. - Friedman, Richard C. (Archives of General Psychiatry, 1999)
; Comments on the research by Herrell et al and Fergusson et al from the October 1999 issue of the 'Archives of General Psychiatry' about the suicidal behavior and psychopathology of homosexuals. Overview of methodology and findings; Limitations of the studies; Need for additional research on homophobia, depression and suicidality.

P01-540 - The view of Iranian counseling psychologist toward working with transsexual and homosexuals clients - Koolaee, A. Khodabakhshi (European Psychiatry, 2011)
Introduction: Homosexuality is forbidden in Islamic countries. In Iran people who homosexual captures with police and in Islamic Law they are accuse and they transfer to prison. But Transsexual is accepted. So, people who are homosexual encourage changing their sexuality and identity with plastic surgery, and gaining new sexuality. Then government gets them Identification Card. Amis: The aim of this study examines the view of Iranian counselors to working with Transsexual and Homosexuals clients. Method: For gathering data, use a questionnaire. A questionnaire was about the view of counselors to Transsexual and Homosexuals clients. For analysis data, use the descriptive statistical methods. Results: The results indicate that 60 percent of counselors disagree to working to homosexual people, 25 percent answered no Idea and 15 rest of them said they were accepted the homosexual clients. Conclusion: To conclude, counselors did not interest in to working with homosexual clients, but when they are changed their sex with surgical operation and gain new Identity, counselors tend to working with them. But the reality is people who changed their Identity with surgical operation, after few months regretful and 35 percent of them attempts to suicide. [ABSTRACT FROM AUTHOR]
Keywords: Transsexuals; Gay people; Human sexuality; Plastic surgery; Suicidal behavior; Gender identity; Counseling psychologists; Iranians; Islamic law

29. The Relationship Between Parental Support and Depression and Suicidality in Transgender Adolescents - Simons, Lisa; Olson, Johanna; Belzer, Marvin; Clark, Leslie; Schrager, Sheree (Journal of Adolescent Health, 2012)
Keywords: Social support; Suicidal ideation; Transgender people; Psychology; Mental depression; Psychology of parents

Sexuality. - Colman, Adrian (Youth Studies Australia, 1999)
; Presents information on data related to sexual behavior of youth in Australia. Details on a research by the National Center in HIV Social Research on the sexual behavior of first-year behavioral science students at Macquarie University; Details on a survey about violence, abuse and discrimination suffered by homosexual and bisexual youths; Findings of a study on suicide among youth gays in Tasmania.
Keywords: AUSTRALIA

Patient suicide (physician unassisted). - Philips, Michael (BMJ: British Medical Journal, 1995)
; Presents the story of a gay patient with suicidal tendencies. Introduction with the author; Observations on the patients' fluctuating physical and emotional well-being; Realization of suicidal threats.

Health needs of women who have sex with women. - Hughes, Clare; Evans, Amy (BMJ: British Medical Journal (International Edition), 2003)
Discusses the gynecological health risks for women who have sex with women. Risk of acquiring human papillomavirus, chlamydia and gonorrhoea regardless of heterosexual contact as an indication for regular cervical smears; Uncommon transmission of human immunodeficiency virus (HIV); Increased incidence of mental health problems which include depression, anxiety and suicide attempt; Decreased childbearing and associated issues; Recommendations for medical screening and counseling.
Keywords: LGBTQ+ people; Sexually transmitted diseases; Mental health; Lesbians; Health risk assessment; Medical screening; Preventive medicine; Diagnostic services; Periodic health examinations

Subject of John/Joan twins case dies. (Contemporary Sexuality, 2004)
; This article reports that David Reimer, one of the subjects in sexologist John Money's John/Joan twins case, died on May 4 of an apparent suicide. As a baby, Reimer was the victim of a botched circumcision, which severed his penis. Doctors in his hometown of Winnipeg recommended to his parents that they take the infant to Money, an AASECT member and leading sex researcher at Johns Hopkins University in Baltimore. Money advised Reimer's parents to raise him as a girl. They agreed to sexual reassignment surgery, changed his name to Brenda and dressed him in skirts, among other things. The case became well-known to academics in the 1960s and 1970s and to a greater public in 2000 after the publication of journalist John Colapinto's book, "As Nature Made Him: The Boy Who Was Raised a Girl." Reimer later married and took a job working in a slaughterhouse. His mother Janet Reimer said that David was struggling with depression after the breakup of his marriage and the death of his twin brother two years earlier.
Keywords: REIMER, David; GENDER transition; PENIS -- Surgery; SEXOLOGISTS; MONEY, John; SEX differences; SEX reassignment surgery; GENERATIVE organs, Male

Transsexualism. Effect on rate and density-pattern of change of residence. - Akesson, Hans Olof; Walinder, Jan; Akesson, H O; Wålinder, J (British Journal of Psychiatry, 1969)
The article discusses the study on transsexualism, which attempts to demonstrate that it has another direct social consequence besides the large risk of suicide. It examines 43 transsexuals, 30 men and 13 women, assembled between April 1963 and December 31, 1965, in which all were over 15 years old and none showed any signs of psychosis. Based from observations, their movement before the age of 15 might have been due to more family circumstances than their transsexualism. Nevertheless, it is stated that the direct result of transsexualism is the difference in their migratory pattern after the age of 15 to the large strain in which their anomaly put upon their relationships in the communities in which they lived.
Keywords: Transsexualism; Gender dysphoria; Sexual orientation; Transsexuals; Emigration & immigration; Family relations; Psychoses; Community relations; Social impact

Now, He's Not Alive. - Teman, Eric D. (Qualitative Inquiry, 2010)
Through a mini-educational ethnography of a queer cultural center at a midsized, Western U.S. university, I explored the center's cultural importance on the college campus and in its surrounding community. During the course of this study, one of my gay male participants, an undergraduate student leader of the center, committed suicide. While interviewing several participants (three gay males and one lesbian), I inquired into their feelings about suicide in the gay community in general and into the suicide of the center's leader in particular. The words of four of my participants are captured in this poem. [ABSTRACT FROM AUTHOR]
Keywords: Ethnology; LGBTQ+ people; Suicide; Cultural centers; College campuses; cultural center; educational ethnography; gay; GLBT; research poetry; suicide; university

Book Corner. (American Journal of Public Health, 1998)
; Presents a listing of books in the field of public health, published as of September 1998. Includes `Miles to Go: Aging in Rural Virginia,' by Susan Garrett, `Gay and Lesbian Issues and HIV/AIDS: Final Report,' by John Fisher and `Suicide Prevention: The Global Context,' by Robert Kosky et al.
Keywords: PUBLIC health

Dog and Cat Ownership among Suicides and Matched Controls. - Helsing, Kund J.; Monk, Mary (American Journal of Public Health, 1985)
Abstract: In Washington County, Maryland, ownership of cats and/or dogs was compared among 48 residents who committed suicide in the years 1975-83 and 96 living controls matched to the suicides by race, sex, and date of birth. Another comparison used as controls persons of same race, sex, and age who died of causes other than suicide in the same year as the suicide. No material association between pet ownership and suicide was observed. (Am J Public Health 1985:75:1223-1224.) [ABSTRACT FROM AUTHOR]
Keywords: SUICIDE; DOGS; CATS; PETS; DEATH -- Causes; RACE; SEX; AGE; WASHINGTON County (Md.); MARYLAND

Letters. - Bidwell, Roberta J.; ertzel, Catherine; ucas, James A.; Synor, J. Paul; Daldin, Herman (Social Work, 1986)
Presents several letters to the editor concerning issues related to social services. Distinctive needs of special groups like lesbian alcoholics; Critical analysis of the article titled "Identifying Potential Suicides Among High-Risk Women"; Analysis of the article on medical dominance.
Keywords: Alcoholics; Human services; Lesbianism; Social services; Letters to the editor; Newspaper sections, columns, etc.

Suicide and Homosexual Youth. (Harvard Mental Health Letter, 1998)
; Presents information on a survey conducted in Minnesota to determine the relationship of sexual orientation with suicidal tendency among youth population. Statistics on the number bisexual and homosexual with suicidal tendency; Comparison of suicidal intent and attempts between homosexual girls and boys; Other findings of the survey.
Keywords: MINNESOTA; UNITED States

Issues of sexuality. - Clarke, Dave (Paediatric Nursing, 2008)
The article reports on the release of "Real Stories, Real Lives: LGBT People and the NHS," a series of web video recordings, in behalf of the British Department of Health. It reminds health care organizations not to discriminate lesbian, gay, bisexual and transgender (LGBT) people based on their sexuality under the Equality Act. It portrays their lives and addresses their needs. The agency says that LGBT youth are at risk to depression, suicide, smoking, illicit drug and alcohol use, violence and sexually transmitted diseases due to health inequalities.
Keywords: Health of LGBTQ+ people; LGBTQ+ youth; Internet videos; Sex discrimination in medicine; Great Britain; Great Britain. Dept. of Health; Great Britain. National Health Service

Study reports that sex ed in schools helps GLBT students. (Contemporary Sexuality, 2001)
; The article provides information on a report about the significance of Acquired immune deficiency syndrome (AIDS) and sex education to gay, lesbian, bisexual and transgendered (GLBT) students. According to a survey published in the June issue of the "American Journal of Public Health," GLBT students who were educated about AIDS and sex are less likely to abuse drugs as well as to engage in risky behavior or be harassed in schools. However, in schools where there is no training, more GLBT students report having attempted suicide, more than three times as many as heterosexual students. In schools with broad sexuality education, the number of GLBT students who reported contemplating a suicide attempt fell to 27.7 percent.
Keywords: SEX instruction; AIDS (Disease); GLBT students; STUDENTS -- Sexual behavior; EDUCATIONAL psychology; RISK-taking (Psychology); HOMOSEXUALITY; IMMUNOLOGICAL deficiency syndromes; DRUG abuse

ODDS RATIOS FOR SUICIDE ATTEMPTS AMONG GAY AND BISEXUAL MEN. - Pierce, Brandon (American Journal of Public Health, 2003)
; A letter to the editor is presented in response to the article "Suicide Attempts Among Gay and Bisexual Men: Lifetime Prevalence and Antecedents," by J. P. Paul and colleagues, published in a previous issue of the "American Journal of Public Health."
Keywords: LETTERS to the editor; SUICIDAL behavior

ON RELIABILITY AND CULTURAL COMPETENCE IN STUDIES OF SEXUAL MINORITY SUICIDALITY. - Mathy, Robin M. (American Journal of Public Health, 2002)
; A response by Paul et al. to a letter to the editor about their article on sexual orientation and suicide risks in the August 2002 issue is presented.
Keywords: LETTERS to the editor; SUICIDE

Suicide. - Headley, Susan (Youth Studies Australia, 1998)
; Presents an abstract entitled `Predictors of Suicide Attempts Among Gay, Lesbian, and Bisexual Youth,' by S.L. Hershberger, N.W. Pilkington et al published in the `Journal of Adolescent Research.'

Suicide. - Clymo, Philippa (Youth Studies Australia, 1995)
; Presents an abstract of the article `Suicidal behaviour and gay-related stress among gay and bisexual male adolescents,' by M. Rotheram-Borus, J. Hunter and M. Rosario originally published in the `Journal of Adolescent Research.'

Mother Calls for More Outreach. - Sadasivan, Leslie Powell (Journal of School Health, 2000)
; Deals with the appeal of a suicide victim mother regarding homophobic harassment. Details on her son's harassment experience; Failure of some schools to address the homophobic harassment of gay students; Ways to make educators become aware of the experiences of gay youths.

Dole in the doldrums over US lifestyle issues. - Greenberg, Daniel S. (Lancet, 1996)
; Asserts that American presidential candidate Bob Dole has stumbled politically on various issues involving lifestyle. Dole's problems regarding abortion and guns; Question of gay marriage, which may turn out not to be a problem due to actions by President Bill Clinton.